The ordinary life of exceptional justice : procedural law in transition - Muñoz, Anamaria (Institut d'études politiques de Paris - Sciences Po, 2026)
This dissertation interrogates the extraordinary character of transitional justice as a legal project. My central claim is that treating procedure as dispensable in pursuit of expansive transformative goals is a disservice to the project itself. The prevailing assumption among scholars and practitioners has been that the existential battles of a transition are fought and won at the macro level: in the text of peace agreements, in constitutional amendments, or in grand normative commitments to truth, justice, and reparation. I show that some of the most consequential distributions of power take place elsewhere: in the granular procedural rules that govern how tribunals operate in practice. Procedural analysis serves here as both method and argument, disaggregating legal rules to reveal who bears costs and who captures benefits, and exposing how procedural opacity creates space for alternative sources of law to emerge. I contend that the exception in exceptional justice should not extend to procedural rigor, and that holding transitional tribunals to the same standards as any other apex court is not a limitation on what transitional justice can achieve, but the condition under which its achievements can be considered legitimate. Taken together, these moves advance a broader theoretical claim: that transitional justice sustains and reinforces the very same distributive arrangements as ordinary justice, rather than disrupting them. I develop these arguments by examining transitional justice in the Colombian 2016 peace process - one of the few ongoing transitional justice processes in the world, and therefore an important site for observing the legal project of transition in motion rather than in retrospect. I engage with Colombia as a matter of epistemic justice: my political commitment is that Latin America is not merely a recipient of international legal frameworks developed elsewhere but an important site in their production. I do not take Colombia as my object because it is exceptional. I take it because the claim that it is, and what that claim conceals, is precisely what this dissertation contests. Cette thèse interroge le caractère extraordinaire de la justice transitionnelle en tant que projet juridique. Mon argument central est que traiter la procédure comme accessoire, au nom d'objectifs transformateurs ambitieux, dessert le projet lui-même. L'hypothèse dominante a été que les batailles décisives d'une transition se gagnent au niveau macro : dans les accords de paix, les réformes constitutionnelles, les grands engagements normatifs en faveur de la vérité et de la réparation. Je montre que certaines des distributions de pouvoir les plus importantes se jouent ailleurs : dans les règles procédurales qui gouvernent le fonctionnement concret des tribunaux. L'analyse procédurale est ici à la fois méthode et argument : elle désagrège les règles juridiques pour révéler qui supporte les coûts et qui capte les bénéfices, et met en évidence comment l'opacité procédurale crée un espace pour l'émergence de sources alternatives du droit. Je soutiens que l'exception dans la justice exceptionnelle ne devrait pas s'étendre à la rigueur procédurale, et que soumettre les tribunaux transitionnels aux mêmes exigences que tout autre tribunal de rang supérieur n'est pas une limite à ce que la justice transitionnelle peut accomplir, mais la condition sous laquelle ses accomplissements peuvent être considérés comme légitimes. Ces arguments avancent une thèse théorique plus large : la justice transitionnelle maintient et renforce les mêmes distributions que la justice ordinaire, plutôt que de les remettre en cause. Je les développe en examinant le processus de paix colombien de 2016 - terrain privilégié pour observer la transition en train de se faire. J'aborde la Colombie comme une question de justice épistémique : l'Amérique latine n'est pas simplement destinataire de cadres juridiques élaborés ailleurs, mais un lieu important de leur production.
Issue: 2026IEPP0015
Keywords: Courts; Criminal law; Droit procédural; Droit pénal; Justice transitionnelle; Procedural law; Transitional justice; Tribunaux

Access to social rights for temporary labour migrant women in the EU : an intersectional perspective on seasonal and posted workers in France and Spain - Deverson, Audrey (Université de Strasbourg, 2026)
Temporary labour migration constitutes both a historical phenomenon and an enduring central issue within the European Union. This thesis adopts a socio-legal approach to analyse the cases of France and Spain, focusing on seasonal work and posting of workers in the agricultural sector. It examines the experiences of temporary migrant women workers at the intersection of migration law and labour and social security law, in particular with regard to social security. Drawing on an intersectional perspective articulated around the concept of vulnerability, this research highlights the structuring role of law in these women’s experiences. This thesis demonstrates that the applicable legal framework contributes to reinforcing their vulnerability by establishing a system of exclusion and invisibilisation based on migration status, employment status and a gendered and racialised labour division, thereby limiting these women’s effective access to rights linked to their participation in the labour market, such as unemployment benefits, as well as to those relating to their reproductive lives. La migration temporaire de travail constitue à la fois un phénomène historique et un enjeu toujours central au sein de l’Union européenne. Cette thèse analyse, dans une perspective sociojuridique, les cas de la France et de l’Espagne, en se concentrant sur le travail saisonnier et le travail détaché dans le secteur agricole. Elle examine l’expérience des travailleuses migrantes temporaires à l’intersection du droit des migrations et du droit social, notamment en matière de sécurité sociale. Mobilisant une perspective intersectionnelle articulée au concept de vulnérabilité, cette recherche met en lumière le rôle structurant du droit dans l’expérience de ces femmes. La thèse démontre que le cadre juridique applicable contribue à renforcer leur situation de vulnérabilité en instaurant un système d’exclusion et d’invisibilisation fondé sur le statut migratoire, le statut d’emploi, et une division du travail genrée et racialisée, limitant ainsi l’accès effectif de ces femmes aux droits liés à leur participation au marché du travail, tels que le droit au chômage, ainsi qu’à ceux relatifs à leur vie reproductive.
Keywords: Agriculture; Approches sociojuridiques; Droit au chômage; Droit de l’UE; Droits économiques et sociaux; Espagne; European Union law; France; Intersectionality; Intersectionnalité; Justice reproductive; Migration temporaire de travail; Pays de l'Union européenne; Posting of workers; Protection sociale; Reproductive justice; Seasonal work; Social protection; Socio-Legal studies; Spain; Statut juridique; Temporary labour migration; Travail détché; Travail saisonnier; Travailleuses étrangères; Unemployment benefits; Vulnerability; Vulnérabilité; Émigration et immigration

Artificial Intelligence of Everything (AIoE) in energy sectors : cybersecurity, data protection, and data localization - Mohaghegh Montazeri, Leila (Université de Montréal, 2026)
L'Internet est devenu une partie essentielle de la vie moderne. Un développement important est «l'Internet des objets» (IoT), qui connecte des dispositifs physiques à Internet. Plus récemment, un concept plus large est apparu: «l'Internet de tout» (IoE), intégrant quatre composantes, les personnes, les processus, les données et les objets. L'ajout de l'intelligence artificielle (IA) à l'IoE a donné naissance à «l'Intelligence Artificielle de Tout» (IAdT). Cette combinaison offre des avantages significatifs pour le secteur de l'énergie en optimisant la production, la distribution et la consommation d'énergie. Cependant, elle soulève également des défis critiques en matière de protection des données, de cybersécurité et de localisation des données. Dans cette thèse, j'explore comment les gouvernements et les entreprises énergétiques peuvent collaborer pour répondre aux risques liés à la confidentialité et à la cybersécurité des technologies IAdT. J'analyse également les exigences de localisation des données et j'examine les cadres réglementaires pertinents, en particulier au sein de l'Union européenne (avec un accent sur l'Irlande) et au Canada (y compris la province de l'Ontario). The Internet has become an essential part of modern life. One significant development is the “Internet of Things” (IoT), which connects physical devices to the Internet. More recently, a broader concept has emerged: the “Internet of Everything” (IoE), which integrates four key components: people, processes, data, and things. The addition of artificial intelligence (AI) to IoE has given rise to the "Artificial Intelligence of Everything" (AIoE). This combination offers significant benefits to the energy sector by optimizing energy production, distribution, and consumption. However, it also introduces critical challenges related to data protection, cybersecurity, and data localization. In this thesis, I explore how governments and energy companies can collaborate to address privacy and cybersecurity risks associated with AIoE technologies. I also analyze data localization requirements and review relevant regulatory frameworks, particularly within the European Union (with a focus on Ireland) and Canada (including the province of Ontario).
Intelligence Artificielle du Tout (AIoE) dans les secteurs de l’énergie : Cybersécurité, protection des données et localisation des données
Keywords: Artificial Intelligence; Artificial Internet of Everything (AIoE); Cybersecurity; Cybersécurité; Data Localization; Data Protection; Energy Industry; Intelligence artificielle; Internet artificiel de tout; Internet des objets; Internet of Things (IoT); Localisation des données; Protection des données; Secteur de l’énergie

Social media and structural injustice : a critical analysis of EU platform regulation - Griffin, Rachel (Institut d'études politiques de Paris - Sciences Po, 2025)
Cette thèse examine le traitement par la régulation européenne de la problématique des injustices structurelles sociales liées aux grands réseaux sociaux. Pour ce faire, elle opère une synthèse de nombreuses recherches empiriques qui mettent en évidence les inégalités dans la gouvernance des contenus, et s'appuie sur des perspectives théoriques tirées de la philosophie politique, de la théorie juridique féministe, et des recherches en droit et économie politique. Elle présente trois lignes d'argumentation principales. Premièrement, le droit européen n'empêche pas les injustices telles que la discrimination dans la modération, les violences en ligne, ou la visibilité inégale des différents groupes sociaux, parce qu'il conceptualise ces inégalités d'une manière individualiste et formaliste, visant à protéger les droits d'individus particuliers et à assurer l'application des règles prédéfinies, tout en ignorant la nature systémique des inégalitésDeuxièmement, le droit contribue souvent activement aux injustices : par exemple, en permettant aux agences policières de demander la suppression des contenus pour des raisons politiques. Troisièmement, les aspects du cadre réglementaire qui sont perçus comme les plus à même de combattre les inégalités systémiques, à savoir les obligations autour de la gestion des risques et les principes des droits de l'homme, se révèlent en réalité peu capables d'empêcher les injustices structurelles. Ces deux éléments restent en effet inscrits dans un paradigme de régulation technocratique, dépolitisée, et favorable au marché, et excluent toute contestation réelle du pouvoir ou des pratiques commerciales des plateformes de « big tech ». This thesis analyses EU regulation of social media content governance, focusing on how the law addresses the impacts of the largest platforms on structural social injustice. To do so, it draws on theoretical perspectives from political philosophy, feminist and queer legal theory, and law and political economy, and synthesises a wide range of empirical scholarship that illuminates the unjust impacts of social media platforms' content governance. It makes three main arguments.First, EU law cannot effectively address unjust impacts - such as discriminatory content moderation, online violence, or the unequal visibility of different social groups - because it regulates them in a highly individualistic and formalistic way, focused on protecting individual rights and consistently applying predefined rules, which overlooks systemic inequalities and their connections to underlying political-economic structures. Second, moreover, the law often actively contributes to injustice: for example, by excluding minority perspectives from platform governance, or by making it easier for state institutions to target politically disfavoured content for removal. Third, the two aspects of the legal framework which are widely seen by experts as the most promising levers to address systemic inequalities and power disparities - risk management obligations, and human rights principles - are also incapable of counteracting these problems. They remain limited by a technocratic, depoliticised and marketised regulatory paradigm, which excludes genuine political contestation of the power of 'big tech' platforms to organise online content in line with their own commercial interests.
Issue: 2025IEPP0034
Keywords: Digital law; Droit des technologies de l'information et de la communication; Droit européen; Droit numérique; Eu law; Feminism; Féminisme; Platform regulation; Régulation des plateformes; Réseaux sociaux

An evaluation of China’s securitization regulatory system - Cao, Lei (Université de Montréal, 2025)
Since its innovation as a modern financial product in the 1970s, securitization has swept the global financial market. In 2000s, in order to ease China’s concentrated debt risks in the banking system and to improve the country’s imbalanced financial system, the Chinese government started to promote a trial program of securitization. An associated regulatory system was then created to facilitate the development of the Chinese securitization markets. Unlike regulations drafted and applied in North America, where an ex-ante regulatory analysis procedure and an ex-post evaluation system are installed, the current Chinese securitization regulation system is built mainly upon a basis of trial and interim rules. In other words, Chinese regulations regarding securitization were not comprehensively assessed before their adoption and there has been no systemic ex-post evaluation of the current securitization regulatory system in the past 20 years. This raises the question of whether the Chinese securitization regulation system facilitates the achievement of its regulatory objectives. The author purports to answer this question using three tools: The theory of regulation, legal historical analysis of law, and comparative law. To begin the analysis, the author designs an analytical framework based on the theory of regulation to evaluate Chinese regulations on securitization. In this evaluative framework, perspectives and criteria are stipulated to guide and draw the boundary of the evaluation. While applying the analytical framework, the author reviews the development of the Chinese securitization regulatory system over the past 20 years. The author studies the historical context of regulations established and regulatory modifications adopted in order to assess whether the logic embedded in the current Chinese securitization regulatory system is still valid. To better evaluate the Chinese securitization regulatory system, the author also applies a micro comparison of certain Chinese securitization regulations with their counterparts in North America. The purpose of this comparison is also to understand whether the Chinese characteristics in Chinese securitization regulations facilitate the achievement of its regulatory objectives. At the end of this assessment, the author provides a report to find the merits and disadvantages of Chinese securitization regulatory system. Due to the evaluative nature of this research, no demonstrated solutions are proposed in this report. Depuis sa création dans les années 1970, la titrisation s’est répandue à travers le marché financier mondial. Dans les années 2000, le gouvernement chinois a commencé à promouvoir le programme de titrisation afin d'atténuer les risques liés à la concentration de la dette dans le système bancaire et d'améliorer un système financier déséquilibré. La règlementation associée a été mise en place pour faciliter le développement du marché chinois de la titrisation. Contrairement aux régles créées et appliquées en Amérique du Nord, qui suivent une analyse ex ante —c’est-à-dire avant leur adoption — et une évaluation ex post — soit après leur application pendant une certaine période, le système de réglementation de la titrisation actuellement en vigueur en Chine a été élaboré sur la base d’essais et de mesures provisoires. Autrement dit, la Chine ne s’est pas fondée sur une analyse ex ante approfondie, et n’a mené aucune évaluation systémique ex post de ses réglementations de la titrisation au cours des vingt dernières années. Ce système chinois de réglementation de la titrisation facilite-t-il ou non la réalisation de ses objectifs réglementaires ? L'auteur tente de répondre à cette question à partir de trois outils : la théorie de la réglementation, l’analyse historique du droit et le droit comparé. Pour commencer, l’auteur conçoit un cadre analytique basé sur la théorie de la réglementation pour évaluer les dispositions chinoises en matière de titrisation. Dans ce cadre d’évaluation, des perspectives et des critères sont proposés pour guider et délimiter l’évaluation. À la lumière de ce cadre analytique, l’auteur replace la réglementation chinoise de la titrisation dans son contexte historique et retrace les modifications apportées au cours de deux dernières décennies. Il s’agit ainsi d’évaluer si la logique qui a présidé à l’adoption de ces règles reste valide dans le contexte actuel. Mais pour mieux saisir les caractéristiques de la réglementation chinoise de la titrisation, l’auteur ajoute à cette analyse historique interne à la Chine des micro-comparaisons de la titrisation chinoise et de ses règles avec leurs homologues nord-américains dans différentes sections de cette thèse. C’est ainsi qu’il sera possible de voir si les caractéristiques chinoises de la réglementation en matière de titrisation facilitent ou non la réalisation de ses objectifs. Au terme de cette recherche évaluative, l’on proposera un rapport qui mettra en lumière les avantages et les inconvénients du système chinois. En raison de sa nature évaluative, cette thèse ne proposera aucune solution aux inconvénients repérés.
Keywords: China; Chine; Evaluation of Chinese; Financial Regulation; Marchés chinois; Réglementation financière; Securitization; Securitization Markets; Securitization Regulation; Titrisation; Titrisation (réglementation)

Predictive Artificial Intelligence Tools in the U.S. Criminal Trial : Reflections on Technology and Justice - Ilhan, Mina Ayşe (Université Côte d'Azur, 2025)
Under the aegis of efficiency and neutrality, algorithmic risk-assessment tools have been rapidly inserted into the realm of pretrial justice, promising scientific and objective prediction where presumption of innocence and scarce resources are pitted against each other. Their sprawl has been uneven and confined to looser pretrial rules than would govern similar proof at trial. These systems translate miscellaneous data into scores of “risk,” inviting courts to act on what might happen rather than on what has been proven, within a process already plagued by plea bargaining, racial disparity, and institutional asymmetry. This thesis argues that such tools do not merely constitute information about the defendant; they reorder what counts as usable knowledge and who is treated as a credible knower at the weakest stage of a criminal process. The thesis lays out how scores interact with judicial decision-making; how ostensibly neutral inputs (criminal history, prior contacts, residence, employment) can re-encode social disadvantage; and how opacity and trade-secret claims frustrate fundamental rights such as due process. The doctrinal analysis clarifies the boundary between regulation and punishment under United States v. Salerno, the demands of proportionality, and the significance of the presumption of innocence when decisions are predictive. A brief technical account explains why claims of “explainability” often exceed what such models can reliably demonstrate for legal purposes, but the core argument is juridical: claims of legitimacy must be substantiated by enforceable safeguards; falling short of that, systems described as ‘explainable' or ‘fair' remain as fancy adjectives. The thesis contends that the safeguards that govern the trial must be applied earlier in the criminal process, where liberty is already fragile. Accordingly, the thesis argues for invoking evidentiary rules early on: demonstrating reliability of the tools; reasoned judicial decisions that explain how any score was weighed against case-specific facts; meaningful opportunities for defence challenge; and, where appropriate, access to independent expertise to translate model outputs without displacing judicial authorship. The researcher is of the opinion that these emphases are necessary so that pretrial decisions remain individualised and proportionate and detention retains its status as an exceptional, non-punitive measure. Finally, it defends doubt as a juridical virtue, a disciplined moment of pause that reins in the allure of algorithmic certainty and reasserts judicial responsibility, so that the presumption of innocence and liberty remains the rule even in a predictive age. Sous l'égide de l'efficacité et de la neutralité, les outils algorithmiques d'évaluation du risque ont été rapidement introduits dans le domaine de la justice pré-procès, promettant une prédiction scientifique et objective là où la présomption d'innocence et la rareté des ressources se trouvent mises en tension. Leur déploiement a été inégal et s'est inscrit dans des règles pré-procès plus souples que celles qui régiraient des éléments de preuve similaires au stade du procès. Ces systèmes traduisent des données hétérogènes en scores de « risque », invitant les juridictions à agir en fonction de ce qui pourrait advenir plutôt que de ce qui a été prouvé, au sein d'un processus déjà marqué par le plaider-coupable, les disparités raciales et les asymétries institutionnelles. La présente thèse soutient que de tels outils ne constituent pas seulement une information relative au prévenu ; ils réorganisent ce qui compte comme connaissance mobilisable et déterminent qui est traité comme un sujet crédible de savoir au stade le plus fragile de la procédure pénale. Elle expose la manière dont les scores interagissent avec la prise de décision judiciaire ; comment des variables présentées comme neutres (antécédents judiciaires, contacts antérieurs avec la police, résidence, emploi) peuvent réencoder des désavantages sociaux ; et comment l'opacité ainsi que les revendications de secret commercial entravent des droits fondamentaux tels que le droit à une procédure régulière. L'analyse doctrinale précise la frontière entre régulation et punition au regard de l'arrêt United States v. Salerno, les exigences de proportionnalité et la portée de la présomption d'innocence lorsque les décisions sont de nature prédictive. Un bref exposé technique explique pourquoi les prétentions à « l'explicabilité » excèdent souvent ce que ces modèles peuvent démontrer de manière fiable à des fins juridiques, mais l'argument central demeure juridique : les revendications de légitimité doivent être étayées par des garanties effectives ; à défaut, les systèmes qualifiés d'« explicables » ou d'« équitables » ne demeurent que des adjectifs séduisants. La thèse soutient que les garanties gouvernant le procès doivent être appliquées plus en amont dans le processus pénal, là où la liberté est déjà fragile. En conséquence, elle plaide pour une mobilisation précoce des règles de preuve : démonstration de la fiabilité des outils ; décisions judiciaires motivées expliquant la manière dont tout score a été mis en balance avec les faits propres à l'affaire ; possibilités effectives de contestation par la défense ; et, le cas échéant, accès à une expertise indépendante permettant de traduire les résultats des modèles sans se substituer à l'autorité judiciaire. La chercheuse estime que ces exigences sont nécessaires afin que les décisions pré-procès demeurent individualisées et proportionnées, et que la détention conserve son caractère exceptionnel et non punitif. Enfin, la thèse défend le doute comme une vertu juridique, moment discipliné de suspension qui tempère l'attrait de la certitude algorithmique et réaffirme la responsabilité judiciaire, afin que la présomption d'innocence et la liberté demeurent la règle, y compris à l'ère prédictive.
Issue: 2025COAZ0023
Keywords: Algorithmes; Algorithmes predictifs; Algorithms; Criminal Justice; Intelligence artificielle en droit; Justice criminelle; Justice prédictive; Procès; Risk assessment tools; États-Unis

A framework for bank resolution in Namibia - Eiseb, Bryan Karl Gunther (University of Pretoria, 2025)
Banks are regarded as special financial institutions because, apart from the various critical intermediary and other functions they fulfil in a financial system, the hallmark of their business models is receiving deposits from the public and using such deposits for extending loans against interest from which they make profit. Unlike other companies, banks are however vulnerable to loss of public confidence and remain exposed to various risks and failure. Banks are thus critically important actors in domestic and global financial systems, - thus their safety is critical to the maintenance of financial stability. As a result, banks are subject to stringent regulation and supervision to ensure their safety. Despite prudential regulation, the failure of banks remains a reality. If the risk of bank failure is not adequately addressed through appropriate regulation and supervision, , it may result in a financial crisis like the 2008 Global Financial Crisis (2008 GFC). Because banks play a special role in an economy and their failure may have an adverse impact on financial stability and depositors, this thesis aligns with the view expressed by academics and international organisations that there is a need for a special regime (lex specialis) to deal with the failure of banks since normal insolvency procedures are not suitable for this purpose. f. This is because bank failures require swift, timely intervention by a supervisor to resolve failing banks in an orderly and optimal manner to ensure the maintenance of financial stability, depositor protection and relegating bailouts with taxpayers’ money as a last resort. A very notable lesson that emanated from the 2008 GFC is the criticality of special resolution frameworks for banks; the need to balance the interests of shareholders, creditors, and depositors, while promoting financial stability objectives. As a result, the need for special resolution frameworks for banks which empowers Resolution Authorities with adequate resolution tools and powers to resolve a failing bank timeous and orderly , has become a legislative imperative in contemporary financial systems. To deal with bank failures in Namibia, the Banking Institutions Act, 2 of 1998 (the BIA 1998) contained provisions that allowed for the assumption of control and liquidation of a failed bank. However, the newly enacted Banking Institution Act 13 of 2023 (the BIA 2023 which repealed the BIA 1998) has changed that position and introduced a single provision in section 70 that provides for bank resolution. Until now, prior to the introduction of this very new statutory provision, all bank failures in Namibia were dealt with under the limited supervisory tools of the BIA 1998. This study seeks to determine whether section 70 of the BIA 2023, is sufficiently aligned with international best practice as captured in the Financial Stability Board’s Key Attributes of Effective Resolution Regimes for Financial Institutions (FSB KAs), issued in 2011, as updated in 2014 and 2024. Alternatively, if the regime introduced by the BIA 2023 does not adequately align with the FSB KAs it is then considered whether the new Namibian bank resolution framework requires to be strengthened further to better align it with the FSB KAs. To consider possible further reforms to the new Namibian bank resolution regime, this thesis considers the resolution frameworks in Germany and Nigeria by way of comparative studies to observe best practices.
Keywords: Bank; Financial stability; Key Attributes; Namibia; Resolution

A comparative statutory analysis of the causes of bank failures in Zimbabwe - Tsaura, Oscar (North-West University, 2025)
Zimbabwean financial sector has experienced significant periods of financial distress as depicted by numerous bank failures since 1980. Bank failure occurs when a financial institution experiences significant financial distress, rendering it incapable of fulfilling its obligations to depositors, shareholders and other stakeholders. In other words, bank failure is when a financial institution undergoes substantial financial distress rendering it unable to meet its obligations as they become due. In this thesis, the researcher adopted the definition of bank failure which refers to a situation where a bank is in financial distress and is recapitalised either by the central bank or a strategic investor, acquired by another institution, surrenders its license or the license is suspended, or it closes its operations altogether. This thesis reveals that in Zimbabwe bank failures can be attributed to various factors including the failure of regulatory and supervisory systems to detect irregularities in the operations of banking institutions. In addition, poor corporate governance practices such as inadequate oversight, inexperienced management, undue influence by dominant shareholders, nonperforming loans, excessive risk-taking, abusive related party transactions and noncompliance with laws are commonly cited as causes of bank failures in Zimbabwe. Bank failures often pose negative implications to the banking sector and banking stakeholders such as depositors and investors. This owes to the fact that banks serve as intermediaries that facilitate the avenues for deposits and extend credit services to individuals and the production sector of the economy. It is submitted that the proper functioning of banks requires effective and adequate regulatory supervision. Failure to provide robust and effective regulation of banks could lead to bank failures. This thesis presents a comparative analysis of the banking statutory framework of Zimbabwe and those of the UK and South Africa to determine if the banking laws in Zimbabwe are robust enough to prevent bank failures. The thesis reveals that the banking statutory framework in Zimbabwe is not robust enough to curb bank failures in times of stress because it lacks effective regulatory oversight. This thesis further reveals that poor banking regulation, inconsistent enforcement, weak regulatory insolvency procedures, and inadequate supervision framework are some of the weaknesses in the current banking statutory framework which needs to be rectified in order to combat bank failures effectively in Zimbabwe. The Banking Act does not fully incorporate the international best standards on bank supervision to prevent bank failures. Consequently, the banking statutory framework in Zimbabwe does not comprehensively and effectively provide for the prevention of bank failures like those of the UK and South Africa. The robustness of the banking statutory framework is in providing adequate and effective regulatory provisions and enforcement mechanisms that curb bank failures in Zimbabwe. The researcher proposes the adoption of a new model, the Zimbabwean twin peaks model, comprising the Zimbabwean Prudential Regulatory Authority and the Zimbabwean Financial Sector Conduct Authority. It is argued that if the adoption of the twin peaks model is considered and robustly implemented, it can prevent the causes of bank failures in Zimbabwe.
Keywords: Bank failure; Banking legislation; Banking statutory framework; Banks; Curatorship; Financial regulations; Financial stability; Fraud; Money laundering; Political instability; Zimbabwe

From trustworthy AI to technical standards : The distinctive European approach to artificial intelligence regulation - Gornet, Mélanie (Institut polytechnique de Paris, 2025)
L'Europe a été à l'avant-garde de l'éthique de l'intelligence artificielle (IA), en élaborant des chartes et des principes non contraignants sur l'IA « digne de confiance ». Le terme « digne de confiance » est utilisé par l'Europe pour désigner les systèmes d'IA qui sont « éthiques », « légaux » et « techniquement robustes ». L'Europe a complété ces principes non contraignants par un texte de loi sur l'IA, connu sous le nom de règlement sur l'IA, ou AI Act. Le règlement sur l'IA est l'un des premiers cadres légaux au monde à réglementer les systèmes d'IA dans différents secteurs et cas d'utilisation, en mettant l'accent sur la sécurité et la protection des droits fondamentaux. Pour les questions opérationnelles, le règlement sur l'IA s'appuie principalement sur des normes techniques en cours d'élaboration. L'approche européenne combine donc trois niveaux d'instruments réglementaires : les chartes éthiques de l'IA, le règlement sur l'IA et les normes techniques.L'approche par la normalisation est traditionnelle dans le domaine de la sécurité des produits, mais dans le règlement sur l'IA, les normes sont également censées répondre aux préoccupations en matière de droits fondamentaux. Pour éviter de faire des choix normatifs difficiles, les organismes de normalisation jouent la carte de la sécurité en élaborant des normes qui restent à un niveau élevé. De plus, dans le cadre du règlement sur l'IA, la responsabilité de l'élaboration des normes techniques est déléguée à des organismes de normalisation privés, où les grandes entreprises multinationales sont surreprésentées et exercent une influence considérable. Ces normes sont également généralement payantes, bien que la situation puisse évoluer dans les années à venir après une récente jurisprudence de la Cour de justice de l'Union européenne. Les experts en normalisation sont donc sous pression pour fournir des normes à temps et de bonne qualité. Europe has been at the forefront of Artificial Intelligence (AI) ethics, developing non-binding charters and principles on "trustworthy'' AI. The term "trustworthiness'' is used by Europe to designate AI systems that are "ethical'', "legal'' and "technically robust''. Europe has supplemented these non-binding principles with a binding regulation on AI, known as the AI Act. The AI Act is one of the world's first comprehensive frameworks for regulating AI systems across different industries and use cases, focusing on safety and protection of fundamental rights. The AI Act relies, for operational questions, mostly on technical standards that are in the course of development. The European approach thus combines three layers of regulatory instruments: AI ethics charters, the AI Act and technical standards.The standardisation approach is traditional in product safety, but under the AI Act, standards are also expected to address fundamental rights concerns. To avoid making hard normative choices, standardisation organisations are playing it safe, developing standards which remain at a high-level. Moreover, under the AI Act, the responsibility for developing technical standards is delegated to private standardisation bodies, where large multinational companies are over-represented and hold significant influence. These standards are also often locked behind paywalls, although the situation may evolve in the coming years after a recent case law from the Court of Justice of the European Union. Standardisation experts therefore face pressures to deliver standards on time and of good quality.
Keywords: AI Act; Apprentissage machine; Artificial Intelligence; Ethics; Inteligência artificial; Intelligence Artificielle; Intelligence artificielle; Machine learning; Normes techniques; Regulation; Règlement IA; Régulation; Technical standards; Éthique

Essays on banking and society - Heyert, Axelle (Université de Strasbourg, 2025)
This dissertation examines the relationship between banking and society. It contributes to a better understanding of how banking affects society and, in turn on how society shapes banking practices. The first chapter studies the impact of inflation on trust in banks. Chapter two deals with the effect of trust in banks on financial inclusion. The third chapter investigates whether financial inclusion influences life satisfaction. Chapter four delves into how female bank leadership affects firm credit. The final chapter focuses on the influence of bank leaders’ age on sustainable lending. Overall, this dissertation highlights the important role of banks in societal development and the major influence of society in shaping banking practices.
Keywords: ACCESS TO CREDIT; Accès au crédit; Banking; Banks; Banques; Bonheur; Confiance; Financial inclusion; Gender; Genre; Inclusion financière; Inflation; Life satisfaction; Prêts durables; Sustainable lending; Trust in banks

A trans-border African crypto asset licence to promote economic growth and deepen financial inclusion - Van der Lith, Johann Daniel (University of Pretoria, 2025)
Financial technology (Fintech) is a rapidly growing industry, both locally and globally. In various ways, Fintech is undeniably transforming financial services and products in every possible part of the financial sector by changing how people access and use financial services. By using innovative technologies, such as distributed ledger technology and cloud technology, and combining large data sets, including alternative data sets, better products can be provided that can be hyper-personalised for market segments and improve access and participation in respect of financial services. Fintech is solving issues that touch the consumer, through a bottom-up approach, considering the retail consumer as a starting point, in contrast to the common traditional finance evolution from the institutional investors to the retail consumer in a top-to-bottom approach. What is exciting about what Fintech can do for Africa, is that it can move inefficiencies in services and product life cycles to become efficiencies and move the frontiers for already efficient products and services. Fintech, therefore, provides an opportunity to improve the archaic and pave the way for the future. This study focuses mainly on crypto assets to limit its scope. It first examines the Fintech landscape in Africa, more specifically, the activity level in each selected comparative country, namely Mauritius, Kenya, Zambia, Namibia and South Africa, and how the activity benefits or can potentially benefit the economy in the host country and lead to the deepening of financial inclusion. It further examines the regulatory frameworks in those countries. The study examines the regulatory approach taken and the local activity, exploring some of the risks identified in each country, and considers the requirements that regulators chose to implement to mitigate these risks, as well as the current state of regulatory frameworks. Consideration is given as to whether similarities in both the risks and the mitigation requirements exist and how this can be aligned across jurisdictions. Recently, international standard-setting bodies have increased their focus on ensuring the alignment and cooperation of regulatory approaches globally. In light of the call for alignment and increased collaboration through policy recommendations and guidance, and or regulators to provide comprehensive and effective regulatory approaches without stifling innovation, this study considers the theoretical possibility of allowing certain Fintech companies, specifically crypto asset service providers (subject to specified conditions) to operate across jurisdictions with a trans-border licence. This study examines Europe’s Markets in Crypto Assets Regulation, as it was the first of its kind continental-wide framework for crypto assets, offering numerous lessons to be learned from this framework. The Commonwealth Model Law on Virtual Assets is also considered, as it is intended to assist member countries in implementing Virtual Asset and Virtual Asset Service Provider regimes in their respective jurisdictions, as they deem appropriate. Lastly, the study will explore what a theoretical trans-border regulatory framework containing prudential and market conduct requirements could look like and what embedded supervision tools, for instance, through forensic nodes or zero-knowledge proofs, could be utilised to ensure that all the regulators participating as part of a licencing panel receive real-time data and have a full view of the level of compliance with the requirements imposed by the joint framework and can proactively and intrusively act, when needed. The proposed trans-border regulatory framework aims to support crypto asset service providers with multi-jurisdictional strategies in Africa in scaling their operations, with a focus on building Africa as a global Fintech hub. The proposed framework aims to achieve this through a harmonised regulatory framework that simplifies compliance, increases efficiencies, enhances innovation, allows for scalability, and better risk management. In addition to the goal of positioning Africa as a globally recognised Fintech hub, the harmonised framework aims to realise the purported benefits of the technologies utilised by crypto asset service providers, thereby deepening financial inclusion and promoting inclusive economic growth through increased access and participation, as well as lower costs.
Keywords: Crypto assets; Embedded supervision; Financial inclusion; Financial technology; Regulatory frameworks

The future of a prohibition on indirect unfair discrimination as part of South African anti-discrimination employment law : a comparative reflection - Huysamen, Elsabe (Stellenbosch University, 2025)
ENGLISH ABSTRACT: The Constitution of the Republic of South Africa, 1996 (“Constitution”) enshrines the right to equality, emphasising “the full and equal enjoyment of all rights and freedoms”. This commitment embodies the principle of substantive equality, which extends beyond mere formal equality by addressing systemic inequities and striving for transformative change. The pursuit of transformative equality is underpinned by two constitutionally mandated mechanisms: affirmative action and the prohibition of unfair discrimination, both direct and indirect. Within this framework, the prohibition of unfair discrimination serves a dual purpose: It establishes a foundation for defending formal equality while simultaneously acting as a transformative tool, particularly in safeguarding against indirect discrimination. In a transformative context, the concept of protection against indirect discrimination specifically is significant as it acknowledges that equal treatment can still perpetuate inequality. The concept has the unique ability to identify hidden barriers and protect against more subtle forms of unfair discrimination, rendering it instrumental in advancing substantive equality and promoting long-term, systemic change. Yet, despite its transformative potential, the application of protection against indirect unfair discrimination in South African employment jurisprudence remains underdeveloped. And even in jurisdictions where the concept has received greater attention (for purposes of this study, the United States of America, Canada and the United Kingdom), it has not significantly advanced substantive workplace transformation. The reasons for this limited success are partly shared across these jurisdictions and partly unique to South Africa. Given the above, the primary objectives of this study are threefold: (i) to explore the protection against indirect discrimination in advancing transformative equality within the South African constitutional framework; (ii) to investigate the reasons for the limited development and application of this concept in South African employment law; and (iii) to assess whether the prohibition of indirect discrimination should be upheld as a distinct legal concept in employment law. These objectives were anchored by the fundamental question guiding the study: what role does the concept stand to play in employment law in SA in future and, if any, to what extent and in what form? The study begins by examining the broader concept of equality – a notion that is both complex and continually evolving. Key questions that are addressed include: What does equality mean? What are the objectives inherent to equality? What values underpin the concept? Following this exploration, the focus shifts to the role of equality within the South African Constitution, specifically the content of the right to equality as provided for in section 9 of the Constitution. This includes an overview of the constitutionally mandated mechanisms for enforcing equality, namely affirmative action and the prohibition of unfair discrimination, with particular attention to protection against indirect forms of unfair discrimination. The study thereafter narrows its focus to the application of the latter concept within South African employment law. It highlights the challenges that have hindered the effective development of the concept, which can be broadly categorised as conceptual and practical obstacles. The South African experience is compared to the development and application of the concept in the United States, Canada, and the United Kingdom, offering a comparative perspective on the concept’s evolution in the aforesaid jurisdictions. The study concludes by presenting suggestions and recommendations on the future role of indirect discrimination within South African anti-discrimination employment law. It also recommends strategies for more effective implementation of the concept.
Keywords: Affirmative action programs; Discrimination in employment; Employment; Labor laws and legislation; Law reform; South Africa; Unfair labor practices

Social justice at the Commission for Conciliation Mediation and Arbitration (CCMA) and the critical role of the commissioner - Letlonkane, Katlego (Stellenbosch University, 2025)
ENGLISH ABSTRACT: This study provides exploratory insight into the social justice mandate of the Commission for Conciliation Mediation and Arbitration (“CCMA”) in the context of labour relations in South Africa. As a vehicle for the advancement of social justice through the efficient resolution of labour disputes, the CCMA is a compelling actor in the pursuit of social justice in South Africa’s labour environment. Social justice as a legislative and policy imperative requires an investment in understanding its conceptual ideals and demands in order to empower those acting in its pursuit with the knowledge they need to fulfil its demands. The CCMA’s most critical functionary, its commissioner, holds the key to unlocking labour justice for many members of the public. One wonders, given the criticality of advancing social justice in labour relations, whether social justice is appropriately understood in order to enable the kind of decision-making that efficiently and consistently addresses the workings of power and inequality as they manifest in employment relationships. This study’s main provocation is to transform the pursuit of social justice (in the South African labour context, at least) from an elusive endeavour to a more tangible, realistic one. It attempts to offer a way of thinking about and applying social justice in the practice of labour dispute resolution in South Africa and the CCMA context. It critically explores the interwoven mechanisms of power, prejudice, and injustice and how these mechanisms work to sustain unequal labour relations. The commissioner’s role is thus a critical one, that involves a deliberate pursuit to recognise, understand and interrupt these movements of power and mitigate the effect of inequality. Any movement towards social justice that does not pay close attention to this matrix of power and prejudice threatens to dilute the transformative potency of social justice. This study identifies and discusses the decisions of commissioners that fall short of the kind of conscientious decision-making required by a mandate of social justice. Discussions in this study also point out significant achievements in centralising social justice principles in decision-making processes at the CCMA, where arbitrators, in reducing injustice and advancing justice in labour relations, show a conscientious consideration and appreciation of historical contexts, power, privilege and disadvantage. Living up to the constitutional imperative to transform society in the way of equality, commissioners ought to develop their agency and be empowered by the Constitution of the Republic of South Africa, 1996, to disrupt inequality. This study contributes to the understanding and clarification of social justice and its implications for the South African labour environment. It also posits ubuntu as an important consideration in the balancing exercise required to achieve justice.
Keywords: Arbitration; CCMA; Commission for Conciliation; Mediation; and Arbitration; Dispute resolution (Law); Mediation; Mediation and conciliation; Industrial; Officials and employees; Social justice

Implementation of safeguard measures in digital trade to protect African domestic industries and platforms - Rotich, Nelly Chepngetich (University of Pretoria, 2025)
As technology continues to advance, more trade is moving online. The increase in digital trade brings with it both opportunities and challenges in the international trade field. The increase in digital trade could for instance result in a spike in digital trade imports which may subsequently cause or threaten to cause serious injury to domestic industries and platforms dealing in like or directly substitutable digital data/content and services. This would necessitate the application of safeguard measures to avert any such serious injury or threat to serious injury caused to the domestic industries and platforms. The procedure for applying safeguard measures to digital trade currently is unclear. The current legal framework on safeguard measures does not apply to digital trade despite increased digital trade over the years. Thus, this study explores the prospects and practical challenges relating to safeguard measures’ application to digital trade with a specific focus on African domestic industries and platforms. While domestic industries and platforms in any part of the world could be affected by surges in digital trade imports, Africa is in a precarious position. Intra-Africa digital trade volumes could be increased and disadvantages of African domestic industries and platforms by surges in digital trade imports could be prevented through regulation and judicious use of safeguard measures. This study established the need to regulate to tap into the potential of digital trade and prevent African industries and platforms from falling behind and from the disadvantage of market dominance by big techs from outside Africa. In conclusion, the study noted legal and institutional gaps in the application of safeguard measures to digital trade. The study has recommended that specific institutions at the global, continental and national levels take necessary actions to build a clear and robust framework for safeguard measures in digital trade.
Keywords: Digital trade; International Trade

International investment regime reform : integrating sustainable development into Uganda’s bilateral investment treaty system – a new model bit - Asiimwe, Esther Muchwa (University of Pretoria, 2025)
This thesis critically analyses Uganda’s bilateral investment treaty (BIT) system to determine its compatibility with sustainable development imperatives and proposes a new model BIT that aligns with Uganda’s evolving development priorities. Recognising the country’s reliance on foreign direct investment (FDI) for economic growth, this study interrogates the extent to which Uganda’s current BITs—many of which were concluded during earlier policymaking eras—expose the country to legal, economic, and regulatory risks. These include susceptibility to investor–state dispute settlement (ISDS) claims, constraints on the host state’s right to regulate, and a lack of provisions promoting environmental, social, and developmental objectives. Through doctrinal and comparative legal analysis, the study traces the historical evolution of international investment law (IIL), critiques the limitations of Uganda’s domestic and treaty-based FDI frameworks, and identifies substantive and structural weaknesses in Uganda’s in-force and model BITs. The analysis also considers international reform efforts and best practices from new-generation investment agreements, including the AfCFTA Protocol on Investment, the Investment Facilitation for Development (IFD) Agreement, and the SADC and EAC Model BITs. Particular attention is paid to the South African BIT reform experience as a comparator for Uganda’s reform journey. The study finds that Uganda’s BIT system is outdated, overly protective of investors, and poorly aligned with its sustainable development goals (SDGs). It recommends terminating unratified and problematic BITs, renegotiating existing ones, and adopting a new model BIT that balances investor protection with Uganda’s regulatory autonomy and sustainable development objectives. To this end, a draft model BIT is proposed as an annex to guide future treaty negotiations and reform Uganda’s investment regime in line with contemporary global standards and regional aspirations.
Keywords: Bilateral Investment Treaties (BITs); ISDS; Investissements; Investment law reform; Investments; Investor-State Dispute Settlement; Uganda

Impact of the basel accords on small indigenous banks in developing countries : the case of Zambia - Rolls II, Douglas Walter (University of Pretoria, 2025)
The purpose of this thesis is to evaluate the impact of the Basel Accords on small indigenous banks in developing countries, with particular concentration on small Zambian banks. The problem statement intends to investigate whether implementing the three Basel Accords is conducive to the growth of small banks in Zambia. The study further aims to determine whether the present approach to legal regulation of small banks in Zambia is appropriate. The methodology is based on desk-bound research and examination of both primary sources and secondary sources of material such as books, journals, and relevant articles. The study is impacted by the dearth of secondary research work and the difficulty of getting information from sources like the Zambian central bank and other information centres. While Basel I and II seem to have stabilised the Zambian financial sector, the Basel III Accord appears to have impacted negatively on many small banks to the extent that they have been forced into merger and acquisition arrangements with larger foreign banks to fund their undercapitalised positions to survive. It also emerges that the Zambian financial system is strongly linked to the international global economy; regionalisation with organisations like SADC and COMESA being the first stages in the process. This situation is likely to introduce increased instability in the Zambian financial sector by making banks more vulnerable to the vagaries of the international financial markets. It is thus recommended that the Zambian central bank should be more proactive in lobbying for better conditions for small banks from the Basel Committee for Banking Supervision and other international financial regulatory bodies; it should also avoid “cutting and pasting” rules from other jurisdictions to avoid possible distortions in the banking sector. It should also encourage further development of primary and secondary markets in low-cost paper and provide small banks with long-term, low-interest loans to support their growth. The Bank of Zambia, the Zambian central bank, should consider establishing a separate Act financial services Act for small banks to better regulate them. The central bank should also seek out non-Basel Accord solutions for small banks including re-examining the positive aspects of the infant-industry argument. Lastly, it should introduce a formal system for classifying banks in Zambia. At the international level, it is suggested that the global standard-setting bodies should undergo radical reforms to ensure that they are in tandem with the problems that banks in developing countries face as well as allow them to have a say in global standard setting. It is recommended that global standard-setting bodies apply simpler rules for smaller banks. The impact of the Basel Accords on small indigenous banks in developing countries and Zambia, in particular, is important because of the role that small banks play in developing economies in growing small and medium-sized businesses that are often ignored by large foreign banks. It is also important that small banks are allowed to grow into large and medium-sized banks to effectively compete against foreign multinational banks. Institutions based on neoliberal ideals appear to only serve Western businesses’ interests despite their call for all countries to create a level playing field. Due to the dearth of empirical research, there are several gaps in the work that may provide opportunities for further research in this important area of the law.
Keywords: Banking supervision; Basel accords; Basel committee; Developing countries; Financial regulatory framework; Small banks

From Divergent Paths to the Same Trap: The Legitimacy Crisis of the Investor-State Dispute Settlement System - Sönmez, Esma Yağmur (Middle East Technical University, 2024)
This thesis critically examines a much-debated issue in international law: the legitimacy of the Investor-State Dispute Settlement system (ISDS). The system was initially conceived to provide an alternate dispute resolution mechanism for the protection and promotion of foreign investment. In time, this objective has incited a discussion on the legitimacy of the system as the developed world has started to experience the role of host states. Since then, they have taken the lead in the reform process to achieve a balance between host state's and foreign investors' rights. To this effect, both the European Union (EU) and the Third Way Approaches to International Law (TWAIL) are for centralization of the system arguing its current problems emanate from its ad hoc and decentralized nature. Although both are aimed at system centralization, the paths they take to achieve it clearly differ. The EU seeks a permanent investment court by which ad hoc arbitration would give way to a more centralized framework. However, TWAIL advocates for a return to the pre-ISDS era, where national courts resolve investment disputes between foreign investors and states. The effectiveness of these two reform ideas in addressing the purported legitimacy concerns of the ISDS is critically examined in this thesis using Martti Koskenniemi's legal approach. Ultimately, it asserts that neither proposal is adequate to resolve the legitimacy issue of the system, as legitimacy can only be achieved by strengthening the principle of justice, which is feasible alone through a more decentralized structure.
Keywords: ADR; Alternative dispute resolution; Foreign investment; Foreign investors; ISDS; Investment Dispute; Investments; Investor-State Dispute Settlement

Essays on Corporate Finance and Corporate Governance - Ding, Zijun (McMaster University, 2024)
This thesis includes three essays that examine the effects of firm policies on labor costs, corporate culture, and stock markets. The first essay studies the impact of major customers on supplier firms’ performance, and I find that supplier firms are willing to collaborate with their major customers while keeping low financial leverages. The cooperation with major customers results in higher productivity and strategic alliance, which could explain the reduction in the labor share of supplier firms. In my study, labor share is defined as the ratio of labor costs to total revenue. Compared to firms without major customers, supplier firms with at least one major customer would reduce labor shares on average by 33% in absolute terms. The findings contribute to the growing literature on the global trend of labor share reduction. The second essay examines the effect of market competition on corporate openness, which is a particular aspect of corporate culture. Corporate openness reflects how open firms are when facing new ideas and experiences, and measures firms’ willingness to innovate and cooperate. I conclude that market competition improves firms’ corporate openness through good corporate governance. Furthermore, corporate social responsibility activities are seen as a positive social outcome of corporate openness. As to economic consequences, less open firms would experience stock return reductions when the market competition is high. The third essay studies the firms listed on Chinese stock exchanges that established an internal whistleblowing mechanism. The results show that the employee whistleblowing system prevents firms from misconducting and leads to reduced stock price crash risk. Furthermore, a cooperative corporate culture helps the internal whistleblowing system decrease crash risk, while an unfair organizational climate exerts the opposite influence. Overall, this study contributes to the emerging literature on the governance role of whistleblowing.

Product Liability in a More Circular Economy : A Study of Liability for Alternative Methods of Distributing and Producing Consumer Goods - Van Gool, Elias (Université de Lille, 2024)
Specific, more strict theories of product liability, which have now largely been maximally harmonised in the EU, have developed on the basis of a linear economic model. By using doctrinal and economic legal research, this thesis examines the state of EU product liability law and how it is tested by alternative, circular economic methods of distributing and producing consumer goods, like product reuse, repurposing, resales and other retransfers, repairs, refurbishments and remanufacturing. Besides direct relevance to circular economy in the consumer goods sector, this study of so-far overlooked questions offers new theoretical insights about product liability with broader academic and practical relevance. After a general introduction to the domains of product liability and circular economy, a normative framework is developed that blends distributive justice in terms of economic efficiency with corrective justice. Subsequently, it is argued that also in a more circular economic setting a more strict product liability rule like the EU harmonisation is preferable in light of this normative framework, while the added value of product liability increases compared to its main regulatory alternatives. The thesis then studies the application to the aforementioned circular strategies of current EU product liability law based on the 1985 Directive and its almost finally adopted 2024 successor. Overall, EU product liability law turns out to be quite versatile and its relevance in a more circular consumption sector is improved by several of the new proposed rules. Nevertheless, some limitations remain and also some interpretative issues are identified in the proposed new Directive, for which amendments are proposed. Les théories spécifiques et plus strictes de la responsabilité du fait des produits, qui ont maintenant été largement harmonisées au maximum dans l'UE, se sont développées sur la base d'un modèle économique linéaire. En utilisant la recherche doctrinale et économique en droit, cette thèse examine l'état du droit européen en matière de responsabilité du fait des produits et comment il est mis à l'épreuve par des méthodes économiques alternatives et circulaires de distribution et de production de biens de consommation, comme la réutilisation des produits, le réemploi, la revente et autres retransferts, les réparations, les reconditionnements et la refabrication. Outre une pertinence directe pour l'économie circulaire dans le secteur des biens de consommation, cette étude des questions jusqu'à présent négligées offre de nouvelles perspectives théoriques sur la responsabilité du fait des produits avec une pertinence académique et pratique plus large. Après une introduction générale aux domaines de la responsabilité du fait des produits et de l'économie circulaire, un cadre normatif est développé qui mélange la justice distributive en termes d'efficacité économique avec la justice corrective. Ensuite, il est soutenu que, même dans un cadre économique plus circulaire, une règle de responsabilité du fait des produits plus stricte comme l'harmonisation de l'UE est préférable à la lumière de ce cadre normatif, tandis que la valeur ajoutée de la responsabilité du fait des produits augmente par rapport à ses principales alternatives réglementaires. La thèse étudie ensuite l'application aux stratégies circulaires susmentionnées du droit actuel de l'UE en matière de responsabilité du fait des produits basé sur la Directive de 1985 et son successeur de 2024 presque adopté. Dans l'ensemble, le droit européen en matière de responsabilité du fait des produits se révèle assez polyvalent et sa pertinence dans un secteur de consommation plus circulaire est améliorée par plusieurs des nouvelles règles proposées. Néanmoins, certaines limitations subsistent et des questions d'interprétation sont également identifiées dans la nouvelle directive proposée, pour lesquelles des amendements sont proposés.
Keywords: Accidents; Accidents de biens de consommation; Biens d'occasion; Biens de consommation; Circular economy; Commerce d'occasion; Consommateur (protection); Consumer product accidents; Product liability; Produits d'occasion; Repair; Responsabilité (droit); Responsabilité du fait des produits; Responsabilité du fait des produits (droit européen); Responsabilité du fait des services; Reuse; Réparation; Réutilisation; Second-Hand; Économie circulaire

Product Liability in a More Circular Economy : A Study of Liability for Alternative Methods of Distributing and Producing Consumer Goods - Gool, Elias van (Université de Lille ; Katholieke Universiteit Leuven, 2024)
Specific, more strict theories of product liability, which have now largely been maximally harmonised in the EU, have developed on the basis of a linear economic model. By using doctrinal and economic legal research, this thesis examines the state of EU product liability law and how it is tested by alternative, circular economic methods of distributing and producing consumer goods, like product reuse, repurposing, resales and other retransfers, repairs, refurbishments and remanufacturing. Besides direct relevance to circular economy in the consumer goods sector, this study of so-far overlooked questions offers new theoretical insights about product liability with broader academic and practical relevance. After a general introduction to the domains of product liability and circular economy, a normative framework is developed that blends distributive justice in terms of economic efficiency with corrective justice. Subsequently, it is argued that also in a more circular economic setting a more strict product liability rule like the EU harmonisation is preferable in light of this normative framework, while the added value of product liability increases compared to its main regulatory alternatives. The thesis then studies the application to the aforementioned circular strategies of current EU product liability law based on the 1985 Directive and its almost finally adopted 2024 successor. Overall, EU product liability law turns out to be quite versatile and its relevance in a more circular consumption sector is improved by several of the new proposed rules. Nevertheless, some limitations remain and also some interpretative issues are identified in the proposed new Directive, for which amendments are proposed. Les théories spécifiques et plus strictes de la responsabilité du fait des produits, qui ont maintenant été largement harmonisées au maximum dans l'UE, se sont développées sur la base d'un modèle économique linéaire. En utilisant la recherche doctrinale et économique en droit, cette thèse examine l'état du droit européen en matière de responsabilité du fait des produits et comment il est mis à l'épreuve par des méthodes économiques alternatives et circulaires de distribution et de production de biens de consommation, comme la réutilisation des produits, le réemploi, la revente et autres retransferts, les réparations, les reconditionnements et la refabrication. Outre une pertinence directe pour l'économie circulaire dans le secteur des biens de consommation, cette étude des questions jusqu'à présent négligées offre de nouvelles perspectives théoriques sur la responsabilité du fait des produits avec une pertinence académique et pratique plus large. Après une introduction générale aux domaines de la responsabilité du fait des produits et de l'économie circulaire, un cadre normatif est développé qui mélange la justice distributive en termes d'efficacité économique avec la justice corrective. Ensuite, il est soutenu que, même dans un cadre économique plus circulaire, une règle de responsabilité du fait des produits plus stricte comme l'harmonisation de l'UE est préférable à la lumière de ce cadre normatif, tandis que la valeur ajoutée de la responsabilité du fait des produits augmente par rapport à ses principales alternatives réglementaires. La thèse étudie ensuite l'application aux stratégies circulaires susmentionnées du droit actuel de l'UE en matière de responsabilité du fait des produits basé sur la Directive de 1985 et son successeur de 2024 presque adopté. Dans l'ensemble, le droit européen en matière de responsabilité du fait des produits se révèle assez polyvalent et sa pertinence dans un secteur de consommation plus circulaire est améliorée par plusieurs des nouvelles règles proposées. Néanmoins, certaines limitations subsistent et des questions d'interprétation sont également identifiées dans la nouvelle directive proposée, pour lesquelles des amendements sont proposés.
Issue: 2024ULILD015
Keywords: Accidents de biens de consommation; Biens d'occasion; Circular economy; Consumer product accidents; Product liability; Repair; Responsabilité du fait des produits et du fait des services; Reuse; Réparation; Réutilisation; Second-Hand; Économie circulaire

The role and liability of internet service providers in South Africa : a critical and comparative appraisal - Nameka, Celeste Zara (University of South Africa, 2024)
This research uses a comparative approach to explore the role and liability of internet service providers in South Africa. The research aims to analyse and compare the role and liability of internet service providers for crimes and civil infractions committed by content providers and/or internet users. Against this aim, the researcher argues that internet service providers, as intermediaries, are ideally placed to monitor and control illicit content provision and/or internet use by the end user. The research focuses on South Africa, China, Ireland, and Nigeria. The research interrogated legislative control and queried the fitness for purpose of these mechanisms for internet service providers and the lacunae created by a rapidly expanding digital world comparatively. The research points out recurrent controversial and problematic concerns that affect both the internet service provider and the consumer. The researcher further explores challenges in applying legal imperatives to internet service providers that affect their end users. The comparative analysis assists in indicating how internet service providers operate in practice and their control (or lack thereof) by various legal frameworks. The researcher makes recommendations and offers solutions to assist with the future role and development of internet service providers and their impact on the end-user and criminal justice system.

Selected legal aspects of money-laundering control in trade-finance instruments - Makuyana, Tsanangurai (University of South Africa, 2024)
The traditional perception that trade-finance instruments are less susceptible to the risk of money laundering has changed due to the increasing threat of trade-based money laundering (TBML). In the process of facilitating trade-finance transactions, financial institutions may be entrapped in the dangers of TBML and be abused for criminal gains. In this regard, the institutions play a significant role in ensuring that only legitimate trade is facilitated through trade finance without being tainted by TBML. Despite that, vulnerabilities for the vice have been discovered in the trade-finance sector. This study employs a macro-comparative approach in examining how selected jurisdictions respond to the problem of TBML in trade-finance instruments. It analyses the vulnerabilities of documentary credits, documentary collections, demand guarantees and standby letters of credit to the potential risk of TBML. The thesis compares the response of the South African AML regime with that of the English, the US and Singapore AML regimes to the threat of TBML in the selected trade-finance instruments. The study reveals, inter alia, that there is not much difference between the South African AML regime and the AML regimes of the comparative jurisdictions in terms of the legislative response to the challenge of TBML in trade-finance transactions. However, the difference is apparent when it comes to the varied institutional responses to the problem within the jurisdictions considered in this thesis. While South African AML authorities have not made any official pronouncement against TBML in trade finance, those from other comparative jurisdictions have done so. The latter have also gone a step further to produce best practice reports on TBML for banks and other financial institutions involved in trade-finance transactions to enable the institutions to prepare for the challenge. However, similar to the South African position, there has not been any legislative change in the comparative jurisdictions to provide for TBML in specific terms. This means that these jurisdictions also deal with TBML using current AML legislation, which was designed originally for cash-based money-laundering operations. Therefore, the institutions and laws under the South African AML regime are relevant in the combatting of TBML. However, they may require some modifications to appropriately counter the challenge. The study makes various policy and best practice recommendations to strengthen the South African AML regime against TBML in trade-finance transactions.
Keywords: AML Regime; Bankers Association for Finance and Trade; Black Market Peso Exchange; Customer Due Diligence; Demand Guarantees; Documentary Collections; Documentary Credits; English AML Regime; FinCEN; Financial Action Task Force; Financial Intelligence Centre Act 38 of 2001; Financial Intelligence Unit; International Best Practices; International Chamber of Commerce; International Trade; Money Laundering; Money-Laundering Control; Prevention of Organised Crime Act 121 of 1998; RBA; Red-Flag Indicators; SAMLIT; Singapore AML Regime; South African AML Regime; Standby-Letters of Credits; TBML; Trade Finance; Trade-Based Money Laundering; Trade-Finance Instruments; Trade-Finance Principles; Trade-Finance Transactions; US AML Regime; World Customs Organisation; the Wolfsberg Group

Compliance with decent work standards by multinational enterprises - Maluleke, Tirhani Foster (University of Pretoria, 2024)
In contemporary times, the issue of human and labour rights violations has gained significant momentum, rendering it imperative for international organisations, states, and businesses to address this critical concern. It is widely acknowledged that while multinational enterprises can aid in achieving economic growth by investing directly overseas and raising the standard of living for the residents of host nations, their business operations may also result in abuse of human and labour rights. The United Nations (UN) Charter was drafted to set forth obligations for individual states, yet businesses do not bear international legal obligations. The Universal Declaration on Human Rights was adopted to implement the substantive contents of human rights referred to in the UN Charter in the general way. The preamble of the Universal Declaration refers to all organs of society, but, at the time of its adoption, businesses were not considered among such organs. It was inconceivable that business organisations would become so economically powerful within a few decades that they would pose a significant risk to human and labour rights, which would not be easily regulated under the national law of their host nations. It is the hypothesis of this study that numerous multinational enterprises (MNEs) violate core human and core labour rights, and that the existing regulatory framework does not adequately regulate them. To prove this hypothesis, this thesis will adopt a two phased approach. Firstly, a careful case law and literature review will reveal the inadequate regulation of MNEs. Evidence suggests that MNEs are guilty of flagrant labour standards and human rights violations. As a result of globalisation, MNEs have gained stronger international influence, and they are able to move their businesses to countries with low cost of labour and less regulations. This phenomenon weakens the governments of host nations as they are keen to promote foreign direct investment in order to reduce unemployment and to ensure economic growth. As a result, the host nations are encouraged to set laws that will attract MNEs at the expense of human and core labour rights. As result, MNEs are not held accountable in respect of their violation of human and labour rights. Secondly, this thesis will assess the efficacy of the regulatory instruments developed by the international community in response to the mentioned problem. This aspect is covered in Chapter 3 to 7 of this thesis. The strategies include the public and private hard law and soft law mechanisms developed at international level as well as campaigns by Non-Governmental Organisations (NGOs). Based on evidence, this thesis will conclude that a soft law approach is not fully effective. As such, Chapter 8 of this thesis proposes the introduction of some hard law measures to improve the existing soft law instruments to augment the existing legislative frameworks of the host countries. In particular, the thesis recommends regulatory reforms, which will empower the International Labour Organisation to intervene to prevent the labour rights violations by MNEs and where such violations occur, to at least provide effective remedies to vulnerable employees. This thesis constitutes a theoretical study, which attempts to provide suggestions regarding the implementation of realistic measures, which if implemented, may contribute to the attainment of decent work for all men and women who are engaged in work for MNEs.
Keywords: Codes of conduct; Decent work; Hard law; Human rights; Human rights due diligence; ILO MNE declaration; International Labour Organisation; International framework agreements; Labour rights; Multinational enterprises; OECD guidelines; Regional free trade agreements; Soft law

Corporate Social Responsibility Practices in the Nigerian Public Sector - Mohammed, Abbas (University of Plymouth, 2024)
This study examines Corporate Social Responsibility (CSR) practices in Nigerian public sector organisations using a comprehensive mixed-methods approach. The data collection process involved analysing 185 organisation-year observations from annual reports spanning 2011–2020, as well as questionnaires distributed to key stakeholders and interviews with senior executives from various organisations.The analysis utilised a multi-pronged strategy, including quantitative techniques such as regression analysis to explore the relationship between CSR practices and corporate governance mechanisms and qualitative methods such as narrative analysis and thematic coding to gain insights from survey responses and interviews.The findings indicate that CSR practices in the Nigerian public sector are moving in a positive direction. Organisations demonstrated commitment to CSR activities, including community development, education, environmental conservation, and philanthropy. Survey results showed that 83% of organisations engaged in CSR, driven by community acceptance and moral obligation. Additionally, 84% of organisations complied with regulatory frameworks, and 79% aligned their CSR policies with national or international standards. The analysis also found a significant positive relationship between CSR practices and factors such as larger board sizes, greater board independence, the presence of women on the board, and CEOs with longer tenures, higher educational qualifications, and international exposure.By triangulating these findings, it is clear that organisations have a strong commitment to giving back through various CSR initiatives, such as humanitarian assistance, youth empowerment, and educational programmes. Despite challenges such as budgetary constraints and weak accountability frameworks, organisations recognise the perceived benefits of CSR, including increased public confidence, improved stakeholder perceptions, enhanced organisational reputation, trust-building, community engagement, and empowering marginalised communities through education.The insights gained from this study conducted in an emerging economy namely, Nigeria, provide a new understanding of CSR practices in public-sector organisations. They also highlight the proactive approach of public sector organisations towards responsible practices. Consequently, the implications of this research extend beyond national boundaries, encouraging diverse and dedicated leadership to enhance CSR efforts and create lasting social impact. Future studies could explore comparative analysis between the public and private sectors or different countries, as well as sector-specific impact assessments.
Keywords: CSR; Corporate Social Responsibility; ESG; Sustainability

The use of blockchain for collecting value-added tax on online cross-border trade in digital goods - Kabwe, Ruddy Kapasula (University of Pretoria, 2024)
The collection of value-added tax from the cross-border supply of digital goods remains a challenge for tax authorities around the world. South Africa is no different. The traditional methods of collecting VAT from the supply of digital goods relies on the honesty of the consumer and on the supplier to account for and remit VAT to the tax authorities in the jurisdiction where the goods are consumed. The traditional collection models are often unreliable, inefficient, burdensome, and expensive for the consumers and the suppliers. The adoption of blockchain technology as a model to collect VAT on the cross-border supply of digital goods has the potential to alleviate the compliance burden on consumers and suppliers of digital goods, improve the efficiency of tax administration, and reduce VAT fraud. Importantly, blockchain technology can create trust between tax authorities, suppliers of digital goods, and consumers. This thesis critically discusses the advantages and disadvantages of implementing blockchain technology for the collection of VAT on the cross-border supply of digital goods in South Africa. This thesis unpacks the consideration factors for policymakers in the implementation of blockchain technology for the collection of VAT on cross-border trade in digital goods. The thesis makes recommendations for the South African VAT Act to be amended to make provision for the collection of VAT by utilising blockchain technology.
URI: https://repository.up.ac.za/handle/2263/97005
Keywords: Anonymisation; Blockchain technology; Decentralisation; Digital goods; Private blockchain; Smart contracts; Taxpayer privacy; Value-added tax

"Non erit innocens malus". Looking for Justice over maritime Crimes of International Concern. A tale of dichotomies - Guizzardi Righetti, Giampaolo (Université Côte d'Azur ; Università degli studi di Milano, 2024)
This dissertation is about dualities or dichotomies. In particular it investigates the interrelationships between two couple of dichotomies, the dichotomy between international and transnational crimes and the duality of land and sea as geographical and jurisdictional spaces in the attempt to answer the question of who does or should exercise its jus puniendi in case of maritime crimes of international concern. This dissertation is about dualities or dichotomies. In particular it investigates the interrelationships between two couple of dichotomies, the dichotomy between international and transnational crimes and the duality of land and sea as geographical and jurisdictional spaces in the attempt to answer the question of who does or should exercise its jus puniendi in case of maritime crimes of international concern.
Keywords: Compétence; Droit de l'homme; Droit de la mer; Justice maritime; Responsabilité (droit international); Violation des droits de l'homme; État

A comparative appraisal of creditor protection mechanisms under South African company law - Sibanda, Mandhlaenkosi (University of South Africa, 2024)
The study comparatively scrutinised creditor protection mechanisms entrenched in South African Corporate law to determine their effectiveness in advancing creditor interests in company affairs. The enquiry was triggered by the need for corporate laws to adapt to and align with the pace of global economic changes in open and democratic societies. The 2004 DTI Policy document on South African Corporate Law Reform (SACLR) proposed a shift from the traditional shareholder-centric view, which espouses shareholder importance in corporate governance, to a model that retains the supremacy of shareholder interests while simultaneously catering to the interests of other stakeholders (the enlightened shareholder value approach). In light of the DTI policy proposal, the parliament, in enacting the South African Companies Act 71 of 2008 (the Companies Act), reflected on the need to provide appropriate redress to investors' and third parties (creditors`) rights in the preamble to this piece of legislation. It was based on the forgoing expositions that this research work sought to establish whether the South African Corporate law had been adequately modelled to protect creditors and to look beyond the traditional company’s goal of profit maximisation for the shareholder at the expense of other stakeholders, such as the creditors, who equally have stakes in the success and continuation of the company. Thus, a comparative doctrinal and critical analysis of creditor protection laws from selected cognate jurisdictions was undertaken to determine the efficacy of the protection mechanisms accorded to creditors under the South African corporate jurisprudence. It is thus the researcher's findings that the South African provisions on mechanisms to protect creditors are set in motion and are, therefore, effective to a greater extent, subject to legislature dealing with some discrepancies as per lessons drawn from comparator jurisdictions and recommendations. Conclusively, the Companies Act should clearly include the creditor’s interests in those of the company and thus give a secondary duty to directors to ensure creditor interests, among other non-member stakeholders, are assertively safeguarded.
Keywords: Company controllers; Company law; Corporate entity; Corporate law; Corporate veil; Credit systems; Creditor interests; Creditor protection mechanisms; Creditors; Directors; Employees; Investors; Shareholders; Stakeholder constituencies; Stakeholder interests; Stakeholders; Third parties

A comparative legal analysis of the accommodation of neurodiversity in the workplace : towards a universal right to reasonable accommodation - Conradie, Riana (Stellenbosch University, 2024)
Workforces are made up of individuals with differences in personal characteristics, differences that may be traced back to unique personality types and traits and – sometimes – neurodivergence. Due to the inherent subjectivity of the interpersonal relationships that form the foundation of a work environment, these differences in personal characteristics inevitably lead to tension. In addition, as part of managing a work environment employers frequently take decisions that may be influenced by views and perceptions regarding employees’ personal characteristics. This study starts with a descriptive examination of the meaning of personality and the influence that personality traits and types may have on employment. This is followed by a descriptive examination of neurodivergence, the various forms of neurodivergence, and the impact of these conditions on the work environment. Building on these descriptive and conceptual underpinnings, the legal implications of neurodiversity in the workplace are investigated by identifying which principles of the existing South African employment law framework may be utilised to provide protection and promote respect for neurodiversity and the neurodiverse differences between employees. This encompasses a discussion of the South African employment law rules relating to recruitment and selection of employees, some of the rules applicable to the day-to-day management of employees, and the rules relating to termination of employment that may be (in)directly influenced by considerations of neurodiversity. The focus thereafter shifts to consider the legal principles of employment discrimination law, where it is found that the listed ground of disability and an unlisted arbitrary ground may potentially be used as the applicable grounds of discrimination by employees if they are prejudiced due to their neurodiverse characteristics. In addition, the possibility that the rules on reasonable accommodation may be utilised as primary mechanism to properly regulate neurodiversity in the work environment and protect against prejudicial treatment of employees due to their inherent personal neurodiverse characteristics is also considered. The South African position and potential employment law rules that may apply to the management of neurodiversity in the work environment is compared to the position in the United Kingdom by focusing on the meaning of disability, the right to reasonable adjustments, and the right to request flexible working arrangements. Finally, the conclusions that may be drawn from this study are emphasised and are followed by some recommendations on how (reasonable) accommodation of neurodiversity in the work environment may appropriately be used as primary mechanism to provide employees with sufficient and appropriate protection of differences in neurodiverse characteristics. Even though this study focuses on neurodiversity and neurological differences between employees, the principles and recommendations from this study may be of value in relation to the appropriate management and regulation of all inherent differences between employees.
Keywords: Discrimination in employment; Diversity in the workplace; Employment; Labor laws and legislation; Neurodivergent people; Neurodiversity; People with disabilities

Corporate law, governance, and sustainability : the public turn in the global socio-ecological transition - Junqueira, Gabriela de Oliveira (Universidade de São Paulo, 2024)
The overlap of financial, economic, ecological, and political crises has pushed the consensus on the need to promote a socio-ecological transformation, or, in short, a green transition. The discontent with the corporate world for its contributions to those crises has taken a central stage, with calls for greater corporate responsibility being articulated under a sustainability imperative. In the context of a new round of debates on the purpose of companies, this thesis examines the turning of corporate law and governance into a site for advancing a new capitalism. More specifically, the research investigates institutional changes occurring under the label of the public turn in corporate law, addressing the following questions: what constitutes the so-called public turn? What are its drivers and the perspectives on it? Which structural features led to targeting corporate law and governance to push for responsible corporate conduct? How does the public turn in corporate law relates to the broader set of actors and norms that shape corporate governance? Guided by critical approaches to the green transition and by political theories of corporate governance, the thesis resorts to different scholarships to examine the current wave of public oriented corporate governance mechanisms from within and from without corporate law. On the one side, the thesis offers a taxonomy of corporate law strategies being employed as well as a rich account on the multiple dimensions assumed by the new tools, placed at the intersection of human rights and environmental protection, corporate social responsibility, and global value chains. On the other, the thesis embeds corporate laws public turn within the unfolding of global capitalism, as the field evolves from corporate law to corporate governance to sustainable corporate governance. The thesis argues that the public turn in corporate law, caught in between the global and the local, enables the investigation of changing roles of states, businesses, and civil society within the political and epistemic terrain of the transition to a more just and sustainable economy. A sobreposição de crises financeiras, econômicas, ecológicas e políticas impulsiona o consenso sobre a necessidade de uma transformação socioecológica, ou, em resumo, uma transição verde. O descontentamento com o mundo corporativo assume centralidade, motivando demandas por mais responsabilidade corporativa, articuladas em torno de um imperativo de sustentabilidade. No contexto de uma nova rodada de debates sobre o interesse social, esta tese examina a transformação do direito societário e da governança corporativa em um locus de promoção de um 'novo capitalismo'. Mais especificamente, a pesquisa investiga as mudanças institucionais ocorrendo sob "a virada pública no direito societário", abordando as seguintes perguntas: o que constitui a esta virada? Quais são seus impulsionadores e perspectivas? Quais características estruturais levaram a mirar o direito societário e a governança para promover conduta corporativa responsável? Como a virada pública no direito societário se relaciona com o conjunto mais amplo de atores e normas que moldam a governança corporativa? Guiada por abordagens críticas da transição verde e por teorias políticas da governança corporativa, a tese recorre a diferentes correntes acadêmicas para examinar a atual onda de mecanismos de governança corporativa orientados para o público, de dentro e de fora do direito corporativo. Por um lado, a tese oferece uma taxonomia das estratégias do direito societário utilizadas, bem como um relato abrangente sobre as múltiplas dimensões assumidas pelas novas ferramentas, na interseção de direitos humanos, proteção ambiental, responsabilidade social corporativa e cadeias de valor globais. Por outro lado, a tese contextualiza a virada pública do direito societário nos desdobramentos do capitalismo global, à medida que o campo evolui do direito societário para a governança corporativa para a governança corporativa sustentável. A tese argumenta que a virada pública no direito corporativo, situada entre o global e o local, permite a investigação das mudanças nos papéis dos estados, empresas e sociedade civil no terreno político e epistêmico da transição para uma economia mais justa e sustentável.
Keywords: Corporate governance; Corporate law; Corporate sustainability; Direito societário; Economia política; Governança corporativa; Political economy; Private regulation; Regulação privada; Sustentabilidade corporativa

The legitimacy of dismissals for off-duty misconduct in South African labour law - Phulu, Thandekile (University of Pretoria, 2024)
The main aim of this thesis is to solve the uncertainties brought about by dismissals for off-duty misconduct. First, it should be acknowledged that the world as we know it has changed and continues to evolve. Dismissals have been significantly impacted by the use of social media outside the workplace. The legalisation of the use of cannabis by an adult person has also brought uncertainties in the way dismissals are handled, especially in cases where an employee consumes cannabis off-duty. These two aspects have significantly influenced dismissals for off-duty misconduct in South Africa, with employees alleging that their rights to privacy, dignity and freedom of expression are infringed. The thesis reveals that regardless of these modern changes, off-duty misconduct dismissal is still governed by the generic provisions of the Labour Relations Act 1995 and its Code of Good Practice: Dismissal. The thesis underscores the lack of clarity regarding the regulation of dismissals for off-duty misconduct in South Africa. Furthermore, despite the judiciary’s establishment of tests (the nexus test and the breakdown of the employment relationship), challenges in adjudicating off-duty misconduct cases persist. This thesis analyses the South African legal framework governing dismissals for off-duty misconduct. The research investigates the evolution of South African dismissal law, tracing its development from the pre-democratic era to the post-democratic era. This investigation scrutinises the shifts in the legal landscape regarding dismissals for off-duty misconduct. The analysis encompasses a range of legal instruments pertinent to South Africa, including legislation, international law, common law, and judicial precedent. The current need for a Code of Good Practice for off-duty misconduct dismissal is highlighted. This rationale is prompted by a comparative examination of other countries where, despite the absence of specific codes addressing off-duty misconduct, a proactive stance has been adopted to safeguard employees’ off-duty rights by enacting relevant legislation. These chosen states have statutes regulating employees’ off-duty conduct and clarifying which conduct is protected and in which circumstances. Consequently, the thesis proposes a Code of Good Practice: Dismissal for Off-duty Misconduct. This Code would assist in the uniformity of application of relevant aspects in determining the fairness of dismissals for off-duty misconduct, thus alleviating labour suits concerning this type of dismissal. The Code would also provide employers with guidelines on how to draft off-duty misconduct policies without infringing employees’ constitutional rights.
URI: https://repository.up.ac.za/handle/2263/97021
Keywords: Cannabis use; Dismissal; Labour law; Misconduct; Off-duty; Social media; South Africa

Procedural Justice in Online Dispute Resolution: An Empirical Enquiry - Beretta, Rachele (University of Antwerp, 2024)
The surge in online interactions has led to a parallel rise in civil and commercial disputes that transcend geographical boundaries. As traditional dispute resolution mechanisms face challenges adapting to this evolving paradigm, conflicts increasingly migrate to online platforms. Within this proliferating landscape, it is crucial to recognize the scarcity of research devoted to Online Dispute Resolution (ODR) providers and the myriad types of services they currently offer to users worldwide. Despite the ongoing geographical expansion of ODR, the inquiry into how procedural justice principles manifest in these digital dispute resolution systems remains notably under-explored. A growing body of literature underscores that procedural justice is critical for building users’ trust, enhancing the legitimacy of organizations among communities, and fostering compliance with outcomes. The ability of ODR providers to meet users' expectations in terms of procedural justice can significantly shape users' perception of ODR institutions as trustworthy and dependable. This bears paramount implications for the ongoing development of ODR, whose acceptance varies widely across jurisdictions. This doctoral thesis delves into the intricate intersections of procedural justice within the realm of international civil and commercial ODR, examining the nuanced dynamics that emerge in virtual spaces. Ultimately, it seeks to understand how procedural justice principles, rooted in the notion of fairness, manifest and evolve in the context of ODR, exploring the impact of digital interventions on the perceived fairness of dispute resolution processes. Understanding procedural justice in ODR is not merely an academic pursuit; it holds profound implications for legal practitioners, policymakers, and society at large. This research aims to contribute valuable insights that can inform the design of fairer and more effective ODR systems.
Keywords: Dispute Settlement; Justice; ODR; Online Dispute Resolution; Procedure (Law); UNCITRAL Arbitration Rules

Antitrust policy and EU labour markets : lessons from the US and comparative prospects - Langlois D'estaintot, Isaure (European University Institute, 2024)
Recent empirical evidence suggests that labour markets are not as competitive as previously thought. In that context, mobilizing antitrust policy has been discussed as a possible solution. The proposition sounds counterintuitive, however. If workers are paid below the competitive level, doesn’t this promote consumers’ outcomes by reducing downstream prices? Given that antitrust policy promotes consumer welfare, why would antitrust authorities intervene against such a state of affairs? Besides, why would stepping up on antitrust enforcement improve workers’ outcomes? Their interests have traditionally been protected through their exclusion from the scope of antitrust enforcement, not by the enforcement of antitrust rules to their benefit. This thesis demonstrates that those spontaneous assumptions do not hold. Consumer welfare does not speak against the defence of workers’ interests. First, the focus on consumers is a by product of methods: it does not prevent consideration of other types of market participants. Moreover, consumers benefit from competitive labour markets. The welfare effects of monopsony power simultaneously worsen workers and consumers’ outcomes. As for the promotion of workers’ interests, it can be achieved through both positive and negative enforcement of antitrust. So far, the EU Commission has been less proactive than the American DOJ and FTC on the issue of antitrust enforcement in labour markets ( although the state of affairs is evolving). While this difference may stem from EU workers benefitting from higher levels of social protection than US workers, those higher levels of protection may not negate the usefulness of antitrust ’s intervention. The low levels of antitrust enforcement in EU labour markets may result from legal uncertainty and case law inconsistency more than an absence of harm. Just like the merger control apparatus, Article 101 and 102 TFEU can be used to scrutinize labour markets. While doing so involves some practical complexities, they can be overcome.
Accepted: 2024-04-08T07:03:10Z
Keywords: Antitrust law; European Union countries; Labor laws and legislation; Unfair competition

Global Common: The Rights and Responsibilities of the State and the Investor in Renewable Energy Foreign Investment - Pang, Hui (UNSW Sydney, 2024)
States poured millions of dollars to attract foreign renewable energy investments for climate change mitigation, however, when it becomes too hefty for some states, they have modified regulations to reduce the level of support. These regulation changes have led to dozens of investors filing arbitrations against the host states, alleging breaches of investment treaty obligations. This thesis examines whether the current investor-state dispute settlement (‘ISDS’) regime adequately addresses environmental concerns when adjudicating renewable energy investment cases. While renewable energy investments can help protect a global common (the atmosphere) and mitigate climate change, the regulation changes also seek to protect a domestic public good (financial stability of the host state). Therefore, when the protection of a global common conflicts with a domestic public interest in renewable energy ISDS cases, what are the rights and obligations of the host state and the investor? Are the existing approaches of the ISDS regime toward environmental concerns and other public interests fair and adequate, and if not, what interventions can be made? This thesis explores these questions by conducting doctrinal analysis on more than 60 renewable energy cases and the arbitral jurisprudence regarding international environmental obligations. It uses the constitutionalisation of international law to break the self-contained regime of international investment law and argues that common values should be regarded as equally important as investment protection goals in ISDS. This thesis finds that the ISDS regime considers international environmental obligations to be insignificant in supporting the host state’s defences in non-compliance of bilateral investment treaties or the investor’s claims for investment protection. This thesis shows that the current approach furthers discrepancies between climate change mitigation and international investment law. Not only does this approach fail to acknowledge the environmental connections of renewable energy investment, but it also creates opportunities for fossil fuel investors to seek compensation against environmental regulation changes using the same arguments. As an intervention against the current approach, this thesis proposes to reconstrue the concept of legitimate expectations to place common values on equal grounds with investment protection incentives. This thesis makes two significant contributions to knowledge. Firstly, it extends existing analyses of the conflicts and synergies between international investment law and environmental protection and contributes to the growing body of scholarship on this topic. Research on this topic has mainly focused on how the state safeguards environmental interests against investor protection claims. While this narrative comprises many cases, it does not capture the full picture and overlooks the possible contributions of private parties in protecting global commons. Instead, this thesis examines whether international environmental obligations can serve as a ‘shield’ for the state’s non-compliance in investment protection, or as a ‘sword’ for investors to compel the state to fulfil its international obligations. Secondly, this thesis makes an intervention to reconstrue ‘legitimate expectations’, where common values are reinforced and not only the interests of investors are protected but also the ‘legitimate expectations of a responsible investor’ from the state and local communities are taken into account.

Measuring the Effects of Post-Convention Activities at the HCCH - Zhang, Ke (McGill University, 2024)
https://escholarship.mcgill.ca/concern/theses/cn69m944k
Keywords: HCCH; Hague Conference on Private International Law

A comparative evaluation of the South African income tax regime for investments using trusts - Herbst, Hendri (Stellenbosch University, 2023)
This study evaluates the South African income tax regime for investments using trusts. It considers whether reforms are required, and if so, how can this be done to create a tax framework that will encourage investment, limit tax avoidance and curb capital outflows, while considering South Africa’s unique context and challenges.
Keywords: Income tax; Investments; Taxation; Trusts and trustees

Legal protection of the individual's image against unauthorised commercial exploitation in South Africa : a critical evaluation of existing law and suggestions for law reform - Van Gensen, Layckan Inge (Stellenbosch University, 2023)
URI: https://scholar.sun.ac.za/handle/10019.1/128896
Keywords: Commercial exploitation; Human rights; Image rights; Intangible property; Intellectual property; Personality; Right of privacy

Developing a legal framework for determining forum choices in transnational intellectual property litigation - Ho, Vannessa May Ha (Macquarie University, 2023)
As communication technologies have assisted in the rapid transfer of information and goods across borders, there has been a commensurate rise in transnational intellectual property litigation. In particular, use of the Internet for trade and consumption of information has led to simultaneous infringement of parallel intellectual property rights in multiple States. The chosen forum to resolve such a dispute is perceived to have significant effect upon the outcome of litigation. There is a need to closely evaluate current jurisdiction rules and recent reform proposals to determine the extent to which they facilitate or prevent litigants from making forum choices that can promote efficiency and fairness in the dispute resolution process. However, there is currently no formal international treaty that regulates how litigants may make forum choices during transnational intellectual property litigation. As a result, the range of forum choices available to litigants are determined by divergent domestic rules, meaning that litigants must enforce their intellectual property rights in forums within every State where the rights exist and have been infringed upon. In such as context, a critical issue is to consider is whether an international regulatory framework could be developed to facilitate appropriate forum choices which advances and calibrates efficiency and fairness in transnational intellectual property litigation. As most conceptions of appropriate forums are from a doctrinal perspective, it is necessary to create a theoretical framework to determine what constitutes an appropriate forum choice during a transnational intellectual property dispute. This theoretical framework can then be used to evaluate the merits of current rules on jurisdiction and determine whether they define a suitable range of available forums that allow litigants to make appropriate choices. The forum non conveniens doctrine also needs to be evaluated as it has the most developed case law that considers appropriate forums for civil disputes. Finally, the risks and benefits of developing an international regulatory framework needs to be examined to assess which method would be the most suitable way to facilitate appropriate forum choices. It is hoped that this research will assist courts and legal practitioners when making decisions about complicated jurisdiction issues during transnational intellectual property disputes, as well as enable policy makers to promote reform that facilitates more efficient and fair forum choices.
Keywords: Forum choice; Forum non conveniens; Forum shopping; Intellectual property litigation; International regulatory framework; Kyoto Guidelines; Lucasfilm v Ainsworth; Private international law; Rational choice; Subject matter jurisdiction

Party autonomy and judicial participation in commercial arbitration: recalibrating the role of Nigerian courts. - Aduloju, Bamikole Martins (Robert Gordon University, 2023)
Courts and arbitration tribunals aim to resolve disputes and make enforceable decisions in their distinctive way. However, unlike courts, tribunals lack state enforcement power to function independently. Consequently, arbitrating parties have had to approach the courts for various supports. However, while supporting arbitration, the Nigerian courts have been criticised for overwhelmingly undermining party autonomy. Thus, the determination of the extent to which Nigerian courts should participate in arbitration remains topical. This research reviewed the current regime governing the scope and limits to the court's roles in arbitration in Nigeria, aiming to find out the problematic areas where the court's roles have been a leeway to undermine party autonomy. The research found that the current practice in Nigeria generally observes party autonomy as an affirmative stance by the Nigerian courts and laws. It further found the areas where the Nigerian system has, nevertheless, created some leeway for the courts to undermine party autonomy. These include (i) the narrow phrasing and interpretation of Section 34 of the Act and some specific provisions, and their failure to set out a definite limit to courts' roles in arbitration, (ii) the application of the concept of constitutional supremacy which has been interpreted to allow Nigerian courts to participate in all cases including arbitration and override parties' agreement, (iii) absence of Institutionalised tracking and periodic recalibration of the relationship between the courts and arbitration, and (iv) judicialisation of administrative roles of the courts in arbitration. To this end, a legal and analytical review of these problematic issues was conducted, particularly using some elements of the legal comparative approach to analyse the problems in the light of the related practices in some similar or advanced jurisdictions such as the United Kingdom, Ghana and Malaysia. Lessons were drawn from the analysis. Short- and long-term recommendations were, therefore, made for law reforms in Nigeria, particularly towards recalibrating the court's roles in arbitration such as to wedge the loopholes in the system without which recalcitrant parties and jurists could take advantage to undermine party autonomy.
Keywords: Arbitrage; Arbitragem; Arbitration; Autonomy; Court systems; Judiciary; Tribunals

Prospects for an African continental model multilateral tax agreement for the co-ordination of cross-border corporate tax challenges - Fehun Aren, Marie-Louise (University of Pretoria, 2023)
This study explores the creation of an African Continental Model Multilateral Tax Agreement (MMTA) to address the limitations of current bilateral tax treaties and enhance existing African Regional Economic Community (REC) frameworks for more effective taxation of cross-border business profits. Focusing on critical international taxation framework issues such as taxing rights allocation, Permanent Establishment criteria, and tax dispute resolution, it compares African REC MMTA provisions with those in non-African agreements to identify key weaknesses and propose improvements. The proposed MMTA aims to ensure equitable taxing rights, update nexus rules to capture both physical and digital businesses, and provide robust dispute resolution mechanisms to foster investment. It advocates for harmonized tax policies and tax agreements across African RECs to minimize tax competition, promote intra-African trade, and support regional economic integration under the African Continental Free Trade Area (AfCFTA). By aligning with the Abuja Treaty’s objectives, the framework seeks to enhance revenue mobilization and sustainable economic development in Africa. This research provides a roadmap for creating a tailored multilateral tax treaty that balances diverse regional interests, addressing Africa’s development financing needs while promoting cross-border taxation efficiency.
Keywords: AfCFTA; African Continental Free Trade Area; Continental model; International taxation frameworks; Multilateral tax agreement; Revenue mobilisation; Tax treaties

An analysis of merger and amalgamation transactions under the Companies Act 71 of 2008 and the Income Tax Act 58 of 1962 - Meyer, Carolina (University of Pretoria, 2023)
In law it is common to encounter two separate pieces of legislation which govern a single matter or transaction, for example, the Companies Act 71 of 2008 (the Companies Act) and the Securities Transfer Act 25 of 2007 both of which address the sale of shares. Similarly, the Income Tax Act 58 of 1962 (the Income Tax Act) and the Companies Act both have regulations which govern, respectively, tax law and company law matters in South Africa. These two Acts overlap in various business and commercial fields as tax is frequently an important component of any business transaction undertaken by a company. Issues, however, arise when the regulations in these two Acts, are inconsistent. This can be observed if one compares the current South African Income Tax and Companies Act, specifically as regards the sections involving merger and amalgamation transactions. Section 44 of the Income Tax Act governs merger and amalgamation transactions from a tax perspective and provides for tax rollover relief if certain requirements are met. The regulations governing mergers and amalgamations under the Companies Act are contained in sections 113, 115 and 116 of the Act. Although these sections in both Acts address the same transaction – a merger or amalgamation between two or more companies – there are several discrepancies between the regulations in the two Acts which appear to operate entirely independently of one another. In practice, one often sees that other sections in the Companies Act and Income Tax Act are used to achieve a merger due, in the main, to the uncertainties in the application of the relevant merger sections in the two Acts and the limited interaction between them. This study identifies and assesses the impact of the discrepancies identified in these two Acts in relation to merger and amalgamation transactions. The study makes recommendations to address these discrepancies and to align the South African Companies Act and Income Tax Act as regards merger/amalgamation transactions.
URI: https://repository.up.ac.za/handle/2263/94064
Keywords: Amalgamation; Companies Act; Income Tax Act; Merger; Taxation

Earnings Management and Default Risk - Nguyen, Loan (Victoria University of Wellington, 2023)
This thesis comprehensively investigates the relationship between default risk (DR) and earnings management (EM) by addressing inconsistencies in prior research regarding the level and direction of EM in response to varying levels of DR. The thesis extends beyond severe financial distress to include firms with low and medium levels of distress. It examines the non-monotonic relationship between DR and EM, considering accrual earnings management (AEM), real earnings management (REM), and total earnings management (TEM). The thesis also examines the impact of DR on the relative use of REM versus AEM. The moderating effect of the global financial crisis (GFC) on the relationship between DR and EM is also explored.Using a sample of 29,228 firm-year observations from 4,514 US-listed firms during 2001-2019, the study employs both the traditional two-step and the more recent one-step approaches to identify EM. Sensitivity analysis is conducted, including and excluding mining firms.The findings reveal a non-monotonic relationship between DR and REM, with a concave pattern observed for all measures of REM. Initially, REM increases as DR rises, but it subsequently declines with further increases in DR. AEM, on the other hand, shows a convex or monotonically decreasing relationship with DR, although statistical significance is not consistently observed. The results for TEM align with those of REM, indicating the dominance of REM in TEM. These findings remain consistent when excluding mining industry observations and using different measures for EM and DR.The implications of these findings are significant for managers, firms, regulators, lenders, investors, and other stakeholders. The non-monotonic relationship between DR and REM offers insights for decision-making and determining appropriate levels of EM during varying levels of DR. Regulators can utilise this relationship to identify potential risk areas and develop effective regulations. Lenders can assess financial statements more vigilantly, and investors can make more accurate risk assessments and informed investment decisions. The robustness of the results and the inclusion of different EM measures provide valuable insights to auditors, analysts, and government professionals, enhancing their understanding of the complexities and risks associated with EM during varying levels of DR.The study also uncovers that the relative use of AEM and REM is complimentary, but the impact of DR dampens the increase in REM for a given increase in AEM. This result holds across primary and alternative measures of DR and is of significant interest to managers, firms, regulators, and other stakeholders. It provides insights into the interplay between AEM and REM, enabling informed decisions about EM strategies under different levels of DR. Regulators can leverage this information to identify potential risk areas and develop effective regulations to mitigate EM practices that could lead to financial instability. Lenders and investors benefit from understanding how DR affects the relative use of AEM and REM, enabling them to assess financial statements and manage investment risk more accurately. The study’s findings contribute to a deeper understanding of EM dynamics and have practical implications for various stakeholders in the financial ecosystem.Furthermore, the thesis investigates EM measures during the GFC and the moderating effect of the GFC on the relationship between DR and EM. The inclusion of REM and TEM, in addition to AEM, provides a comprehensive understanding of how firms managed their earnings during the GFC, offering insights into the effectiveness and implications of different EM strategies during a financial crisis. It confirms the decline of AEM during the GFC, reinforcing existing knowledge about the impact of the crisis on EM practices. Additionally, it identifies a negative impact of the GFC on REM and TEM, providing further evidence of the challenges and changes in EM strategies faced by firms during the economic crisis. The study also finds an insignificant moderating effect of the GFC on the relationship between DR and REM, as well as DR and TEM, shedding light on EM variation across different economic stages.Overall, this thesis contributes to the EM literature by examining the non-monotonic impact of DR on EM measures, comparing different approaches to identify EM, exploring the moderating effect of DR on the relative use of AEM and REM, and investigating EM measures during the GFC. The insights from this research assist managers in decision-making, firms in adapting financial management strategies, regulators in developing policies, lenders in risk assessment, and investors in understanding the complexities and risks associated with EM. The findings have practical implications for various stakeholders in the financial realm, guiding decision-making, regulatory efforts, risk assessment, and investment strategies.Keywords: earnings management, accruals earnings management, real earnings management, default risk, global financial crisis, one-step approach, two-step approach.

The Law of the Sea and Nigeria's Marine Policy: A Critical Evaluation - Tagowa, Wonotanzokan Nzeda (Ahmadu Bello University, 2023)
Keywords: Droit maritime; Marine policy; Nigeria; Sea

Fishing for Rights ! The Protection of the Individual in Fisheries - Longo, Andrea (Università degli studi di Milano, 2023)
La pêche est une activité humaine ayant un impact considérable sur l'environnement. Une mauvaise gouvernance, des mécanismes d'application faibles ou inexistants et des subventions excessives et non réglementées ont entraîné la surexploitation des stocks de poissons dans le monde entier, en produisant des conséquences potentiellement désastreuses sur l'écosystème marin et la sécurité alimentaire. Cependant, les pratiques de pêche non durables sont également liées à des abus à bord des navires de pêche : les organisations internationales et non gouvernementales attirent progressivement l'attention sur les pratiques répandues de violations des droits de l'homme et de crimes en mer, en appelant à repenser le régime international pour la conservation et la gestion des pêches en vue de concilier la sécurité économique et environnementale avec la dimension sociale de la pêche durable.Dans ce contexte, la présente thèse de doctorat aborde les problèmes conceptuels et pratiques qui se rattachent à la protection des individus impliqués dans ou autrement affectés par l'activité de pêche, en se concentrant particulièrement sur les victimes à bord des navires de pêche. La thèse s'appuie sur les études relatives à l'interaction des régimes en vue de favoriser le dialogue entre le droit international des droits de l'homme et le droit de la mer, deux régimes relevant du système plus large du droit international public. Après avoir exploré la portée de la question de recherche et fourni le contexte théorique et factuel, le premier chapitre se penche sur le régime du droit des droits de l'homme et examine la notion de juridiction telle qu'elle s'applique aux violations des droits de l'homme en mer, en étudiant en particulier l'utilisation potentielle de la norme sur la juridiction de l'État du pavillon comme critère pour attirer une violation des droits de l'homme à bord de navires de pêche relevant de la juridiction de l'État du pavillon. Le chapitre explore également le contenu et la portée des obligations en matière de droits de l'homme, en se concentrant notamment sur un ensemble de six droits prétendument violés à bord des navires de pêche, à savoir le droit à la vie, l'interdiction de la torture et des traitements inhumains et dégradants, l'interdiction de l'esclavage et des formes modernes d'esclavage, l'interdiction de la privation arbitraire de liberté, le droit à un travail décent et le droit à la santé. Ensuite, le deuxième chapitre se concentre sur le droit de la mer, en retraçant spécifiquement le développement historique qui a conduit à la consolidation du régime actuel de la pêche et en explorant la portée de la notion de pêche illégale, non déclarée et non réglementée et du phénomène de la criminalité dans le domaine de la pêche. Enfin, le dernier chapitre traite de la notion de juridiction telle qu'elle est utilisée dans le droit de la mer, en étudiant spécifiquement son contenu en ce qui concerne tous les acteurs étatiques de ce régime, à savoir l'État côtier, l'État du pavillon, l'État du port et l'État du marché. En particulier, ce chapitre examine de plus près les obligations de chaque État en ce qui concerne la protection de la personne à bord des navires de pêche, en accordant une attention particulière aux pouvoirs d'exécution de l'État côtier et à l'exercice par l'État du pavillon du contrôle des ses navires. Enfin, et surtout, il apporte un éclairage sur la contribution potentielle que les États du port et les États du marché pourraient apporter à la protection des personnes à bord des navires de pêche.
Cotutelle : Université Côte d'Azur
Keywords: Droit de la mer; Droits de l'homme; Fisheries regime; Fisheries resources; Fishing vessels; Human Rights; Law of the Sea; Navires de pêche; Pêches; Ressources halieutiques; Régime de pêche

Confidentiality in International Commercial Arbitration: Is it an Accepted Principle, and if so, Should the Model Law Regulate it? - Kenny, Caroline Majella (Monash University, 2023)
This thesis examines two research questions: first, whether confidentiality in international commercial arbitration (‘ICA’) is an ‘accepted principle’, and second, if the answer to the first question is positive, whether confidentiality should be regulated by the United Nations Commission on International Trade Law (‘UNCITRAL’) Model Law on International Commercial Arbitration (1985), with amendments adopted in 2006 (‘Model Law’) and how such a provision would be framed. To place the questions in context, there is empirical evidence that confidentiality is expected by users of ICA but despite this expectation there appears to be no uniform approach on confidentiality in national laws and institutional rules.
Keywords: Arbitrage; Arbitragem; Arbitration; Confidentiality; UNCITRAL Arbitration Rules; UNCITRAL Model Law

Liability in the atmosphere of groups of companies - Motassim, Sofia (Universitat de Barcelona, 2023)
Groups of companies are a complex corporate structure, whose regulation can be problematic, especially when it comes to liability. Indeed, liability within corporate groups draws forth a series of issues principally due to the principles of separate corporate personality and limited liability. In the context of limited liability, which is based on the notion of separate legal personality, the main issue waxes the protection of the creditors, in particular the creditors of the subsidiaries. One can find three regulatory templates for handling corporate groups and their liability: policing via general company and/or civil law (such as the English model); policing via special group legislation (such as the German model); and policing via branches of law such as insolvency law, antitrust law, and contract law, among others (which is the case in numerous jurisdictions, either coupled with the first or the second model). Lifting the corporate veil has come as an answer to corporate separateness, by permitting to ignore the shareholders’ limited liability and hold them personally liable for the debts of their companies in specific circumstances. However, one can hardly find cases in which the corporate veil has been successfully lifted, due to many factors. Other important questions that are posed in the scope of corporate groups liability are the parent company’s liability for the payment of its daughter companies’ debts when insolvency strikes and other respects, besides the matter of group liability. Furthermore, liability is as well a key player in terms of tort law, and corporate social responsibility has therefore found a place in the sun in the present climate.
Alternate link : https://diposit.ub.edu/bitstreams/83cde66e-b943-45b6-830b-831df41cb73f/download
Keywords: Ciències Jurídiques; Commercial law; Conglomerate corporations; Corporations; Derecho mercantil; Dret mercantil; Econòmiques i Socials; Grupos de empresas; Grups d'empreses; Liability (Law); Responsabilidad (Derecho); Responsabilitat (Dret); Sociedades; Societats

Developing a regulatory framework for electronic commerce in the Southern African Development Community: the prospects and challenges - Chimeri, Vongai (University of Fort Hare; Faculty of Law, 2023)
Keywords: Community law; E-commerce; Electronic Commerce; Electronic Transactions; Intra-regional trade; Regional integration; SADC; SADC Model Law

The interface between competition and intellectual property law : finding common ground and resolving the tensions between these areas of law from a South African perspective - Dercksen, Juletha-Marie (Stellenbosch University, 2023)
Competition law and intellectual property law share the objective of incentivising innovation. However, this objective is achieved in different ways, which, at times, can create tension between the two areas of law. It is imperative that this tension at the interface of competition law and intellectual property law is resolved in a manner that encourages innovation. Issues regarding the licensing of intellectual property, Standard Essential Patents, pay-for-delay agreements and no-challenge clauses are instances where the tension between competition law and intellectual property law is especially prevalent. These instances will be discussed in detail, and what is learnt from how the European Union and Australia handles it, will be applied to South Africa. The European Union, Australia and South Africa have different ways of dealing with situations where the exercise of intellectual property rights has an effect on competition. The European Union has block exemptions, which contains “safe havens” for conduct in specific circumstances. The block exemptions are often accompanied by guidelines, providing firms and individuals with greater detail in order to self-assess their compliance with the exemption. Australia has authorisation, notification and class exemption procedures. Firms can apply to the Australian Competition and Consumer Commission to authorise conduct that might potentially breach the Competition and Consumer Act 2010. Exemptions may also be granted more broadly by the Australian Competition and Consumer Commission in terms of the class exemption procedures. In South Africa, the law concerning the interface between competition law and intellectual property is still in its infancy, and a lot can be learned from jurisdictions like the European Union and Australia regarding the most efficient way to handle this tension. Currently, the Competition Act 89 of 1998 in South Africa contains Section 10(4), the intellectual property exemption clause. A firm can apply to the Competition Commission for an intellectual property exemption from the application of Chapter 2 of the Competition Act “to an agreement or practice, or a category of agreements or practices” which pertains to the exercise of intellectual property rights. However, it is submitted that Section 10(4), by itself, is not the most efficient mechanism to resolve the tension that arises at the interface of competition law and intellectual property law in a way that incentivises innovation. It is proposed that the exemption provision can be made more effective if it is properly applied in conjunction with class exemptions and guidelines.
URI: http://hdl.handle.net/10019.1/127343
Keywords: Antitrust law; Australia; Competencia; Competition Act; 1998; Competition law; Conflict of laws; Intellectual property; South Africa; Trade regulation

The legal regulation of trade union recognition in South Africa in historical and comparative context - Germishuys-Burchell, Wilhelmina (Stellenbosch University, 2023)
This study investigates the impact and importance of the legal regulation of trade union recognition and associated challenges in South Africa. It evaluates the current regulation of trade union recognition, including legislation and judicial attitudes apparent from the interpretation, application, and enforcement of such legislation, to ascertain its continued appropriateness in the current South African industrial relations environment. The study considers the policy choices of both voluntarism and majoritarianism underlying the Labour Relations Act 66 of 1995 (“LRA”) and the “workplace” constituency to which it applies as factors that might be contributing to challenges experienced in the current regulation of collective bargaining in South Africa. It evaluates the current model of trade union recognition and representativeness as it applies to the acquisition by trade unions of organisational rights, collective bargaining rights and trade union recognition for purposes of retrenchment consultation. It recognises that the specific model chosen to regulate the representative status of trade unions has a significant effect on the ability of trade unions to organise and conclude collective agreements and, as such, on the distributive effects of such agreements in the labour market and broader society. The study commences with an historical overview of the regulation of trade union recognition under the 1956 LRA and thereafter considers the 1995 LRA as a product of criticism against the 1956 LRA. Specific issues considered, largely based on the analysis of the relevant decisions by the Constitutional Court, include the following: the impact of Constitutional Court jurisprudence relating to trade union recognition on the process of collective bargaining and on the legal regulation of the right to strike; the role of representativeness and its link with the workplace as the constituency for recognition and acquisition of organisational rights; the often winner-takes-all effect of the current model on collective bargaining as a major cause of labour unrest; the reactive role the legislature has played over the past, almost three decades to address challenges; the extent to which intervention should take place to safeguard the institution of collective bargaining from being undermined as well as the regulation of collective agreements as the product of collective bargaining and as the primary source of terms and conditions of employment. The comparative review of Canadian law focuses on a number of issues selected specifically for their potential to provide insights into how the weaknesses in South African regulation may be remedied. This includes insights into the accommodation of special or significant minority interests and how to address recognition in the context of multi-location employers. The thesis concludes with remarks on the insights gained from the Canadian model and the 1956 LRA. Where appropriate, suggestions are made on the way forward for South Africa as to the appropriate regulation of trade union recognition and representativeness.
URI: http://hdl.handle.net/10019.1/127125
Keywords: Collective bargaining; Collective labor agreements; Dismissal of employees; Employee rights; Industrial laws and legislation; Labor disputes; Labor unions; South Africa

Mandatory Environmental, Social and Governance (ESG) Regulations: ESG Performance, Corporate Finance, and Investment - Michael, Emmanuel (Victoria University of Wellington, 2023)
This thesis investigates the relationship between cross-country mandatory environmental, social and governance (ESG) regulations and firm-level outcomes, such as ESG performance, corporate finance, and investment, for both developing and developed countries. ESG performance is initially examined to determine whether mandatory ESG regulations affect it and to what extent. Second, the study investigates the impact of mandatory ESG on corporate finance and investment. Lastly, the study explores whether mandatory ESG regulations affect firm-level outcomes based on countries' governance and economic systems, and industries. The study uses a large sample of 69,010 firm-years across 73 countries, over the period 2005 – 2020 to address the foregoing issues. In addressing the impact of mandatory ESG regulations on ESG performance, the study employs a difference-in-differences (DiD) design. The DiD technique can isolate the effect of regulatory shocks to firm-level outcomes. According to the DiD analysis conducted, cross-country mandatory ESG improves firm-level ESG performance in developed countries, but not in developing countries. The study also concludes that mandatory ESG regulations have a positive impact only on ESG components in developed countries and have a more dominant impact on environmental (E) component. The findings are robust to a range of checks and test cases, including a triple DiD design set-up and propensity score-matched sample. The study employs an investment Euler equation framework and generalised method of moments (GMM) estimators to explore how mandatory ESG impacts corporate finance and investment. Euler frameworks account for the dynamic nature of investment, whereas GMMs account for endogenous dynamics in dynamic models. The study demonstrates that mandatory ESG increases corporate investment by increasing firms' access to external funds. The findings are robust to a battery of tests, including a triple DiD design set-up, propensity score-matched sample and the parallel trends assumption. Using an investment Euler equation framework and the GMM estimators, the study explores whether the impact of mandatory ESG on corporate finance and investment is dependent on a country's governance and economic system. When mandatory ESG is affected by country factors such as governance systems and economic well-being, the effect of mandatory ESG on investment via internal finance channel persists, according to the study. However, while consistent results are found in developed countries, inconsistent results are found in developing countries. According to the study, oil, gas, and mining firms are likely to respond effectively to mandatory ESG regulations because of increased scrutiny and pressure. Overall, the findings from the study imply that cross-country mandatory ESG has had a positive impact on corporate ESG performance, finance, and investment. For firms located in developed countries, these findings hold consistently, while for those located in developing countries, the opposite holds true. Also, the study reveals that firms in the oil, gas, and mining industries effectively respond to regulatory requirements. As a result, this study provides policy makers and accountants with an understanding of how mandatory ESG impacts firm ESG activities and performance, which is crucial for regulatory reforms.
Keywords: Corporate Finance; Cross-Sectional Analysis; Developed countries; Developing countries; Economic Models and Forecasting; Finance; Financial Economics; Investment; Investment Euler equation; Mandatory ESG disclosure regulations; Panel Data Analysis; Sustainability Accounting and Reporting; Time-Series Analysis

The Double Life of State-Owned Enterprises in International Economic Law: States, Corporations or Both? - Kikarea, Eirini (University of Cambridge, 2023)
State-owned enterprises (SOEs) have recently gained prominence in global markets and feature among the world’s most influential enterprises. The aim of this research project is to analyse the international norms in force regulating whether SOEs are considered state or non- state actors, and their conduct state or non-state conduct, the interpretation and application of these norms by adjudicators in different international regimes, and to provide alternative prisms through which these rules and decisions can be assessed and re-thought by political actors. I show that, in relation to SOEs, the concepts ‘state and ‘act of state’ have been ascribed diverse meanings by adjudicators and other international actors, who have employed legal standards with divergent wording and thresholds when dealing with similar questions. I argue that the fragmented meaning of these terms should be understood, in part, as a result of the inherent malleability of these terms and the different expert vocabularies employed across regimes. It is exhibited that adjudicators in the international trade and investment regimes are more inclined towards piercing the corporate veil of SOEs, potentially evidencing the existence of biases against SOEs, which are perceived as inherently economically inefficient and politically motivated actors in an indiscriminatory manner. In the last chapter, I introduce alternative lines of thought regarding the regulation of SOEs in international law. I suggest that, instead of engaging in theoretical discussions on the proper delineation between the public and the private sector, it is more useful to focus on the distributional impact of international rules on various actors, especially on developing and emerging economies where the presence of SOEs is very high. Such alternative prisms of analysis open paths for future research and practice, with the goal of designing an international economic order that incentivises institutional experimentation in the pursuit of economic development and distributional equity.
Keywords: International Economic Law; International Investment Law; International law; International trade law; Public enterprises; State capitalism; State-owned enterprises

The adoption of international financial reporting standards and foreign direct investment inflows: the moderating effect of the institutional environment in Africa - Simbi, Chipo (Rhodes University; Faculty of Commerce, Accounting, 2023)
Globalisation has created a need for an international accounting language to facilitate the smooth flow of trade across countries. In 2003, in an effort to establish a global financial reporting language, the International Accounting Standards Board (IASB) developed a single set of high-quality accounting principles known as the International Financial Reporting Standards (IFRS). Over the last decade, several African countries have adopted IFRS, and Africa has become the second-largest adopting continent after Europe. IFRS promotes improved quality of disclosure of accounting transactions, reduces information asymmetry between preparers and users of financial information, lowers the cost of investing, and breaks down information barriers to cross-border investment. Researchers suggest many benefits of IFRS adoption for macroeconomic indicators such as Foreign Direct Investment (FDI). The reduction in information acquisition and processing costs which translates into the reduction in investment costs, has been cited by most researchers. Researchers have argued, however, that the economic benefits of IFRS in Africa depend on the strength of the institutional environment. They also argue that the Western environment in which the IFRS was developed differs from the African environment. Thus, the universal approach of the IASB may not be appropriate due to the historical, social, economic and political context of African countries. The impact of the adoption of IFRS by African countries requires further examination, particularly as a weak institutional environment confronts many African countries. Three research questions are designed for this study; (1) Is there a significant change in FDI inflows for IFRS adopters in selected African countries after the adoption? (2) Is there a significant change in FDI inflows due to the institutional environment? (3) Does the institutional environment in IFRS-adopting countries moderate the effect of IFRS on FDI in selected African countries? The present study is underpinned by the new institutional theory, the information asymmetry theory, the eclectic theory and the signalling theory, each of which provide reasons why African countries have adopted IFRS. Nine hypotheses are developed, based on the research questions, and tested using the Systems General Method of Moments and the Difference-in-Difference method. The study uses data from 26 African countries, 15 adopting and 11 non-adopting countries, over the period 1996 - 2018. First, the study establishes that the adoption of IFRS positively and significantly affects FDI inflows into the selected sample of African countries. Second, the study concludes that legal enforcement, accounting and auditing standards enforcement, and language origin positively and significantly impact FDI inflows into these countries. Legal origin, however, has a positive but insignificant association with FDI inflows. Third, legal enforcement, historical ties, accounting and auditing enforcement and the quality of the institutional environment are found to moderate the effect of IFRS adoption on FDI inflows. These results indicate that IFRS is a crucial determinant of FDI inflows into African countries, but a supportive institutional environment is needed for African countries to attract FDI inflows after adoption. The results contribute to the accounting and finance literature on FDI into African countries, and may assist the investment community to assess the institutional risk associated with investing in IFRS adopting African countries.
http://hdl.handle.net/10962/419230
Keywords: Accounting; Auditing; Difference in differences; FDI; Foreign direct investment; Generalized method of moments; IFRS adoption; Institutional infrastructure; International Financial Reporting Standards; Investments

Legal harmonisation of non-tariff barriers of regional economic communities as a catalyst to the realisation of the African continental free trade area - Achancho Etagha Epse Abia, Elisabeth (University of KwaZulu-Natal, 2023)
Legal harmonisation is an integral aspect of regional integration and the desire to promote regional and sub-regional economic integration in Africa is exemplified by the establishment of the African Continental Free Trade Area (AfCFTA) in 2018. The 2012 decision of the AU to create the CFTA by 2017 was reiterated in Aspiration two of Agenda 2063. The legal harmonisation of non-tariff barriers has been a vital instrument in the achievement of EU economic integration and the Organisation for the Harmonisation of Business Laws in Africa (OHADA). The study seeks to critically examine the theoretical and conceptual underpinnings of regional integration and legal harmonisation of non-tariff barriers by the AU and RECs. It also analyses the current political, economic, and legal reinforcements to regionalism in Africa and practices needed to advance intra-regional trade within the framework of Agenda 2063. This was done by evaluating the key legal frameworks of the AU (the Abuja Treaty, the Constitutive Act of AU, 2007 Protocol on relations between AU and RECs and Agenda 2063) with the aim of identifying best practices, gaps and impediments pertinent to strengthening Agenda 2063 CFTA. At the end of the study, the abilities of three selected RECs (SADC, COMESA and EAC) were assessed to drive home the AfCFTA. This was done by identifying flaws in existing treaties of RECs, while advancing a model of legal harmonisation of NTBs between them. It was found out that the AU and RECs have not vigorously considered the significance of legal harmonisation in their integration agendas. This resulted in the lack of unambiguous and concrete provisions for the legal harmonisation of NTBs in their guiding policies. Where some attempts are evident, such as in the EAC, they have been implemented unsatisfactorily with lack of a compliance mechanism. This study contended that if legal barriers to free trade are not eliminated, even if all other barriers were to be removed, the effective realisation of the AfCFTA would still be hindered. Hence, this study recommends the principles of direct applicability and direct effects of regional laws to addressing the legal harmonisation challenge underscored. Iqoqa Ukuvumelanisa okusemthethweni kwezithiyo ezingakhokhiswa intela kuyisici esibalulekile sokudidiyelwa kwesifunda kanye nesifiso sokugqugquzela ukuhlanganiswa komnotho wesifunda kanye nesifunda esincane e-Afrikha sibonakala ngokusungulwa kweNdawo Yezwekazi Lase-Afrikha Yokuhweba Ngokukhululekile (i-AfCFTA) ngowezi-2018. Isinqumo sowezi-2012 se-AU sokwakha i-CFTA ngowezi-2017 saphindwa Esifisweni Sesibili soHlelo- 2063. I-CFTA iphinde ibe wuhlelo olubalulekile oHlelweni-2063 futhi impumelelo yayo ibalulekile. Ucwaningo luhlose ukuhlola ngokujulile izisekelo zethiyori nezomqondo zokuhlanganiswa kwesifunda kanye nokuvunyelaniswa kwezomthetho kwezithiyo ezingakhokhisi yi-AU kanye nama-REC. Iphinde ihlaziye ukuqiniswa kwamanje kwezepolitiki, ezomnotho, kanye nezomthetho kuzwelonke e-Afrikha kanye nezinqubo ezidingekayo ukuze kuthuthukiswe ukuhwebelana kwangaphakathi kwesifunda ngaphakathi kohlaka loHlelo-2063. Lokhu kwenziwa ngokuhlola izinhlaka zomthetho ezibalulekile ze-AU (iSivumelwano sase-Abuja, UMthetho-sisekelo we-AU, 2007 Protocol on relationship between AU and RECs and Agenda 2063) ngenhloso yokuhlonza izindlela ezingcono kakhulu, amagebe kanye nezithiyo ezihambisana nokuqinisa uHlelo-2063 CFTA. Ekupheleni kocwaningo, amakhono ama-REC amathathu akhethiwe (i-SADC, i-COMESA kanye ne-EAC) ahlolwa ukuze aqhubekisele phambili i-AfCFTA. Lokhu kwenziwa ngokuhlonza amaphutha ezivumelwaneni ezikhona zama-RECs, ngenkathi kuthuthukiswa imodeli yokuvumelana okusemthethweni kwama-NTB phakathi kwawo. Kwatholakala ukuthi osopolitiki base-Afrikha abazange bayicabange indlela eqinile yokuhlanganisa umnotho wesifunda, nakuba indlela enjalo yaphakanyiswa abasunguli besifunda sase-Afrikha. I-AU kanye nama-REC awazange acabangele ngamandla ukubaluleka kokuvumelana kwezomthetho ezinhlelweni zawo zokuhlanganisa. Lokhu kuholele ekuntulekeni kwezinhlinzeko ezicacile nezibambekayo zokuvumelana ngokusemthethweni kwama-NTB kuzinqubomgomo eziqondisayo. Lolu cwaningo lwagomela ngokuthi uma izithiyo ezingokomthetho zokuhwebelana ngokukhululeka zingaqedwa, ngisho noma zonke ezinye izithiyo zizosuswa, ukufezeka ngempumelelo kwe-AfCFTA kusazothikamezwa. Ngaphakathi kwalokhu kwangemuva, lolu cwaningo luncoma izimiso zokusebenziseka okuqondile kanye nemiphumela eqondile yemithetho yesifunda ukuze kubhekwane nenselele yokuvumelana kwezomthetho egcizelelwe.
Keywords: Common External Tariff; Direct Effect; Legal harmonisation

Environmental protection under national legislation and agreements between oil and gas multinational corporations and host communities - Adedipe, F. (Canterbury Christ Church University, 2023)
The exploration, production and shipment of crude oil and gas by multinational corporations (MNCs), involved in bilateral treaties in Nigeria has perpetrated environmental disasters upon host communities. This has been as a result of oil and gas leaks from MNCs facility into the air, land, water, marine habitat, and cultural life of host communities are heavily polluted. International law has attempted to regulate the activities of MNCs particularly in the protection of the environment in which they operate through four main treaties: Universal Declaration of Human Rights,1International Covenant on Economic, Social and Cultural Rights (ICESCR), 2 Declaration of the United Nations Conference on the Human Environment (Stockholm Declaration)3and Declaration of the United Nations on Environment and Development (Rio Declaration). In addition, the demand for environmental protection is foregrounded under the right to life recognized in article 6 of the International Covenant on Civil and Political Rights (ICCPR). However, a major criticism of international law is its inapplicability to non-State actors such as corporations. This creates a lacuna in the legal framework of protections which has been exploited by opportunistic MNC’s. International soft law such as the Global Compact, Organization of Economic Cooperation and Development (OECD) Guidelines for Multinational Enterprises and United Nations Guiding Principles (UNGPs) on Business and Human Rights encourages corporations to respect environmental rights and creates substantive standards for States to hold corporations accountable for environmental and human rights violations. The challenge remains that these international laws having soft law status are not binding on corporations. Also, a further problem is that several developing state governments may be complicit in the environmental abuses perpetrated by MNCs for the purpose of boosting economic development. Therefore, this research proposes the regulation of MNCs under national legislation and bilateral investment treaties. It recommends certain preventive and mitigation measures against the adverse environmental effect of their activities in the exploration of natural resources, waste disposal and other connected operations in developing communities in Nigeria. Some of these preventive measures include environmental impact assessment (EIA), mandatory reporting and disclosures, community stakeholder participation, environmental management and safety practices, with activity, temporal and spatial management as mitigation measures. Also, clean-up and compensation by MNCs are effective remedies for environmental abuses. Furthermore, fines, blacklisting, withdrawal of license and criminal charges are recommended for the enforcement of environmental protection of host communities.
Permalink: https://repository.canterbury.ac.uk/item/95yw5/environmental-protection-under-national-legislation-and-agreements-between-oil-and-gas-multinational-corporations-and-host-communities
Keywords: Agreement; Environment (protection); Host communities; Multinational corporations; Oil and Gas Industry

The regulation of Corporate phoenix activity in South Africa - Basson, André Stephan (University of Johannesburg, 2023)
Phoenix activity involves conduct whereby a failing company (the old company) is replaced by a second company (the new company) in the operation of the same or a similar business and that involves the same or similar company controllers. Transactions of this nature can be legal and even be beneficial to society, since entrepreneurs who pursue a viable business may, if the new company succeeds, benefit the economy and many other stakeholders. These transactions are referred to as legal phoenix activity. Problems arise however when phoenix activity is engaged in with the goal of evading the debt of the old company, known as illegal phoenix activity. In other cases, even well-intentioned company controllers can cause significant harm by resurrecting a fundamentally flawed business. This conduct, although not illegal, is unduly prejudicial to stakeholders and is known as problematic phoenix activity. While this thesis focuses on illegal phoenix activity, several measures identified should also curb problematic phoenix activity. This study identifies the elements and common characteristics of illegal phoenix activity. It then analyses regulation pertaining to those elements and common characteristics with the aim of finding effective solutions to the problem. This includes evaluating measures that reverse prejudicial transactions that occur during illegal phoenix activity as well as holding complicit parties, such as company controllers and the new company, accountable for their actions. Regulation aimed at preventing and investigating illegal phoenix activity is also considered. This thesis uses the comparative legal approach to analyse regulatory responses to illegal phoenix activity. Australia, the United Kingdom, and the United States of America are examined. Several reported cases in South Africa involving what appear to be illegal phoenix activity are explored, along with the existing measures that are applicable to illegal phoenix activity in South Africa. A single anti-phoenix provision is undesirable as it has the potential to unjustifiably infringe on legal phoenix activity. This thesis proposes a multi-pronged approach, which involves a combination of better enforcement of existing laws and the introduction of smaller targeted amendments to legislation aimed at reducing the incidence illegal phoenix activity.
Keywords: ABUSE OF THE CORPORATE FORM; Bankruptcy fraud; Evasion of liability; Fraud on creditors; Phoenix activity; Phoenixism; Strategic bankruptcy; Successor liability; Transactions prejudicing creditors; Transfers at an undervalue

A legal analysis on how France, Germany, the European Union and South Africa responded to the United Nations guiding principles on business and human rights - Buis, Jeanette (University of Pretoria, 2023)
Globally, companies pursue profitability; they want lower prices for the goods they buy and for the services they use. To gain profit and keep their prices low, they contribute to human rights violations and/or the devastation of the environment. The UNGP is the UN unanimously endorsed instrument that encourages states to pass legislation to compel companies to exercise human rights due diligence and to report on their efforts. The United Nations Guiding Principles (UNGP) impose a duty on companies to conduct human rights due diligence that apprises them of possible human rights or environmental risk exposure in their international operations. States have a responsibility to assist those harmed by a company’s activities to seek judicial relief. The UNGP is a soft law instrument but has had a major effect in the field of business and human rights. Though a voluntary obligation, the UNGP has become the reference document and is used by Civil Society Organisations (CSO) to pressure states into passing regulations on business and human rights. In 2016 Germany passed a National Action Plan (NAP) and the Lieferkettensorgfaltspflichtgesetz (Supply Chain Due Diligence Act) in 2021. France passed a Vigilance Law (Loi de Vigilance) in 2017. Additionally, a UN resolution has initiated a treaty-making process, which might lead to an internationally legally binding instrument that will articulate companies’ responsibilities to avoid, mitigate and remedy human rights violations that their activities cause. The South African government’s response to the UNGP has focused on negotiating a legally binding instrument at an intergovernmental level. This research examines three countries’ varying responses to the UNGP, a soft law instrument. In February 2022 the EU Commission published a proposed directive on corporate sustainability due diligence. The proposed EU legislation aims to advance respect for human rights and environmental protection. The goal is to create a level playing field within the European Union which leads to the exploration of the role China plays in a globalised world. China aims to be more than the world's factory and to become a leader in innovation and high-end manufacturing.
URI: https://repository.up.ac.za/handle/2263/93522
Keywords: CSR; Corporate Social Responsibility; Corporate governance; Human rights due diligence; Mandatory corporate due diligence; RSE; United Nations Guiding Principles; responsabilité sociale des entreprises

The commercial sexual exploitation of children perpetrated by the private sector: can international law be improved? - Hecht, Mark (Université de Sherbrooke, 2023)
International law is a robust system designed to unite world governments in an effort to, inter alia, cease human rights violations and hold those who commit them accountable. As it currently stands, and by its own design, the international human rights legal regime focuses on and applies only to state actors, meaning that violations committed by non-state actors, such as multinational corporations (MNCs), are seemingly conducted with impunity inside this space. Multinational corporations are powerful international players that have undoubtably fostered a significant role in reducing global barriers. By their very nature, they are far more mobile than states, allowing them to evade domestic power and regulatory schemes by detaching from their home state and relocating to a host state with weaker oversight and/or enforcement powers. Simply stated: even though MNCs have better financing, heightened mobility, and a disproportionate amount of influence when compared to world states, they operate with less global accountability. Commercial sexual exploitation of children (CSEC) is a fundamental violation of children’s rights. It consists of sexual abuse by the adult and remuneration in cash or kind to the child or a third person or persons. The child is treated as a sexual object and as a commercial object. Multinational corporations have been implicated in CSEC through acts of omission and commission. And despite the fact that much international law has been drafted to protect children around the world from CSEC—most notably the United Nations Convention on the Rights of the Child and its Optional Protocols—the numbers of children who have been emotionally and physically harmed by and through MNC conduct has only increased in the past decade. There have been numerous efforts by international organizations to address the challenges when regulating and monitoring human rights violations by MNCs. States, civil society organizations, and the private sector itself have also attempted to address these human rights violations through domestic law, modifying international law principles, and with civil regulation. Obstacles exist in the effectiveness of each of these approaches, leaving children at risk with no single effective strategy to combat and address rights violations by MNCs. The dissertation conducts a review of the current landscape of child law, through the lens of corporate accountability for CSEC. Then, it suggests a new alternative, putting forward an international solution to an international problem.
Keywords: Commercial sexual exploitation of children; Convention on the rights of the child; Corporate Social Responsibility; International child law

Land Reform in Sub-Saharan Africa: Exploring Interested Parties Perspectives on Cameroon's Land Tenure and Land Law Reform. - Kenfack Kenjio, Jacques Wilfried (Antioch University, 2023)
This research study seeks to understand interested parties’ perspectives on Cameroon's existing land tenure systems, the 1974 land law, and ongoing efforts to reform this land law. It identifies both concerns and specific recommendations from these parties on the formulation and implementation of future reforms. In the decades following the achievement of independence from European colonizers, most governments in sub-Saharan Africa (SSA) have adopted new national land tenure policies to meet their countries’ needs and aspirations. In some parts of SSA, however, this process of land tenure formalization has negatively impacted the land rights of people observing customary land tenure. This has been a result of government interventions such as compulsory land acquisitions, which while technically legal, are ethically questionable. In the face of this challenge, efforts to reform post-colonial land laws have become a matter of urgency. A national land reform process for Cameroon, announced in 2011 has adopted a multistakeholder approach. My study seeks to understand interested parties’ perspectives on Cameroon’s existing land tenure systems, the 1974 land law, and ongoing efforts to reform the land law. This study applied a case study methodological approach and a convergent mixed-method design. Evidence from this study shows that interested parties in Cameroon are in agreement on 1) the reform of the 1974 land law, 2) the recognition of customary land tenure, 3) the continued use of multistakeholder participation in land law reform, and 4) the promulgation of the new land law through mass sensitization and information dissemination.
URI: http://rave.ohiolink.edu/etdc/view?acc_num=antioch1684431556060359
Keywords: Government-Driven Land Dispossessions; Land Expropriations; Land Law; Land Reform; Land Tenure; Mixed Methods; Multistakeholder Participation; Sub-Saharan Africa

The Autonomy Doctrine in the Law of Letters of Credit and Demand Guarantees in Libya, Egypt and England: A Comparative Study - Mukhtar Elhouderi, Tajeldin Eissa Saleh (University of Leicester, 2023)
Letters of credit and demand guarantees play a prominent role in financing international trade. They provide assurance of payment and security for the performance of contractual obligations and have been described as the ‘lifeblood’ of international commerce. Autonomy is the central principle for the instruments of letters of credit and demand guarantees. Under the autonomy principle, the bank’s undertaking to pay for the beneficiary ought to be independent of the diversity of other relationships arising from the underlying contract. In spite of the autonomous nature of these instruments, in certain cases, the national laws will recognise some exceptions or limitations that restrict the application of the doctrine of autonomy. Exceptions such as fraud, nullity, and illegality will allow the national courts to interfere and override the autonomy doctrine by considering other matters, even those concerning the underlying contract. Furthermore, the exceptions of unconscionability or abuse of rights have an effective role in providing deep solutions, especially with regard to the problem of abusive calls for demand guarantees. The autonomy principle is recognised under Libyan commercial law but has yet to form the subject of serious academic literature covering its legal aspects. This study, in part, aims to fill that gap and will examine the extent to which legal aspects govern the principle of autonomy and its exceptions under Libyan law with reference to the new Libyan Commercial Code. A comparison of the laws in England, Libya, and Egypt will be conducted to examine how legal matters concerning autonomy and its restrictions in their laws are addressed. Furthermore, consideration will be given to the experience of Singapore, particularly with regard to the unconscionability and nullity exceptions. The results of this study will consider many different exceptions to autonomy and suggest that fraud is not the only exception to autonomy and that it is not imperative that all exceptions in letters of credit be equally applied to demand guarantees.
Keywords: Commerce international; Comparative study; Contractual obligations; Egypt; England; International Trade; International commerce; Letter of credit; Letter of guarantee; Lettre de crédit; Lettre de garantie; Libya; Obligation contractuelle

The goals of competition law for merger analysis in developing jurisdictions : a critical appraisal of merger analysis under Kenyan competition law - Njako, Priscilla Mumbua (University of Pretoria, 2023)
This thesis considers whether jurisdictional exigencies should influence competition law enforcement, with a specific focus on merger analysis. It examines various approaches and schools of thought regarding the goals of competition law and how these play out within jurisdictional parameters. The history of enforcement of American antitrust is scrutinised to establish the nature of the interplay between greater economic policy direction and the goals of competition law. The study also explores the issue of convergence and whether developing jurisdictions should align their competition law to that of developed jurisdictions with mature competition law.
URI: https://repository.up.ac.za/handle/2263/91683
Keywords: American antitrust; Competencia; Competition law; Concurrence (droit); Kenya; Merger analysis

Harmonisation in the rules governing the recognition of foreign judicial ship sales - Shao, Yingfeng (World Maritime University, 2023)
Ships, the high-value asset used in both seagoing and inland navigation, and in which various legal and natural persons have interests, must be secured against legal risks arising from any cross-border legal divergence. Legal certainty of ownership of the ship is therefore desirable but it is under challenge with regard to the judicial sale of a ship: the effects of a judicial sale may be denied in a jurisdiction other than the place where it was sold under the principles of state jurisdiction. Multiple efforts have been made to address legal uncertainty. Particularly important is a new treaty governing the international effects of judicial sales: the United Nations Convention on the International Effects of Judicial Sales of Ships (Beijing Convention). This dissertation is intended to contribute to that process by setting out two tasks; first, it seeks to identify the obstacles to the recognition of foreign judicial sales, providing additional knowledge which may aid national legal orders when deciding recognition approaches; second, it looks for a universal solution that better guarantees recognition which would benefit shipping. A comparative legal research exercise exploring similarities and dissimilarities in the municipal and international laws governing the recognition and sale procedures is undertaken. Research results are presented in this kappa and research papers, exhibiting the profuse difficulties a party seeking recognition may encounter in the current legal framework, and explains the new recognition approach under the Beijing Convention. Based on the research findings, a universal solution is proposed that avoids révision au fond, defines the finality of a judicial sale, and sets forth a fixed number of grounds for denial of recognition which may bring greater certainty. This purported optimal solution should guarantee equal treatment for all foreign sales seeking recognition before the registry while minimising the registrar’s burden of finding and examining foreign laws. In the interest of universality, this solution better accommodates disagreeing principles underlying certain aspects of the sale, viz., the ship’s location at the time of sale, the notification of sale, and the variance in the standard sale, namely, court-approved private sales, in a manner that more states may accept. This solution is largely in line with the recognition approach under the Beijing Convention. Considering the greater legal certainty the new instrument may bring, ratification is supported.

The public domain and the legal protection of Indigenous Knowledge Systems - Verhoef, Gerardus (North-West University, 2023)
IKS stakeholders often debate the divide between indigenous and other knowledge systems. IP rightsholders seek advice on how they can strengthen and secure their proprietary rights or broaden the public domain, while other interest groups such as indigenous peoples and local communities want to know how the public domain can be enclosed. One reason for this divide seems to be that the IP regime operates in a sphere where the public domain is demarcated by individual rights, as opposed to the indigenous knowledge systems regime where the public domain is demarcated by social embeddedness and connected to the land on which indigenous peoples and local communities live. This problem manifested itself over centuries of colonialism and technological development worldwide, but also because indigenous worldviews do not share the pre-appropriation narrative of the public domain than technological advanced societies. Within the context of this narrative the research question was posed, namely "what are the appropriate legal instruments for protecting Indigenous Knowledge Systems without compromising the public domain?" To answer this question, the public domain was analysed from three perspectives, namely international law instruments, human rights and IP rights. It was found that none of these perspectives lead to a narrow interpretation of the public domain – in fact, they all aim to broaden the public domain. These early findings on the public domain assisted to apply the fundamentals of the public domain to international law instruments and their application to IKS. In this regard it has been shown that the existing international law instruments, as well as the natural evolvement of these instruments over time, adequately provides for the protection and commercial exploitation of IKS worldwide. There is a proviso, though: IKS need to be viewed through the WIPO lens, which provides for the distinct delineation of categories of IKS, namely traditional knowledge, traditional cultural expressions and genetic resources. For example, the Bern Convention is founded on the three principles of droits des auteurs, droit moral, and domaine public. The boundaries of the public domain within the context of IKS can be reconciled with all three of these principles, and national legislators merely need to apply these principles to national legislation. With these insights gained on international law instruments, a few countries were analysed to ascertain how they address their local challenges pertaining to IKS. The countries that were analysed all aimed to appreciate international law instruments to which they are signatories, while they develop country specific IKS-related jurisprudence, although it cannot be said to be the same in each country. None of the findings pertaining to these countries could provide convincing arguments as to why a sui generis system for IKS can work. The research then moved to a legal analysis of South African legislation in relation to IKS. It has been shown that in general, South African legislation on IP is well aligned with international law instruments. These findings assisted with the research question at hand and was instrumental with coming to the early conclusion that IKS neatly fits into South Africa's current IP regimes and their associated public domains. Throughout the thesis, the rights and obligations of IKS rightsholders were demarcated since no right is absolute, as has been shown when the South African Constitution was discussed. In this regard, the droit moral of individuals from indigenous peoples and local communities, as well as the indigenous peoples and local communities, are to be respected. This approach led to more practical measures to ensure that matters such as prior informed consent, secrecy and sacredness, equity and access to TK, TCE and GR and benefit sharing were all understood within the boundaries of the public domain.
Keywords: Indigenous knowledge (protection); Intellectual property; Propriedade intelectual; Propriété intellectuelle; Savoirs traditionnels

The Law Applicable to Security Interests in Intermediated Securities under OHADA Law - Monsenepwo Mwakwaye, Justin (Universität Würzburg, 2022)
In recent decades, the technical handling of custody business in the OHADA region has undergone a lasting change. There has been a shift from a direct to an indirect holding system, in which the interests of an investor in respect of the underlying securities are recorded in the books of an intermediary (such as a bank or a securities firm). Under the law of all states within the OHADA region, the traditional conflict of laws rule for determining the enforceability of a securities pledge that occurs in the indirect holding system is the lex rei sitae (or the lex cartae sitae or the lex situs ) rule. However, the traditional lex rei sitae rule cannot be appropriately applied to a system where the dematerialised securities are held through multiple layers of intermediaries located in different jurisdictions. Yet, until the intermediated system and the collateralisation of intermediated securities in the OHADA region will continue to operate in somewhat legally murky waters, leading to more instability in the financial markets. Therefore, Justin Monsenepwoaims to find an appropriate and consistent approach that reflects the reality of the indirect holding system in the OHADA region. “This publication is essential reading for policy makers, academics, market participants, and legal practitioners in the OHADA region and beyond. I am convinced that its in-depth analysis of OHADA’s substantive and conflict of laws rules will go a long way in filling the gap in this area and encouraging further development in the future.” Christophe Bernasconi, Secretary General of the „Hague Conference on Private International Law“ – HCCH in the foreword
Keywords: Competencia; Competition law

Overcoming Divergence in English and French Contract Law: A Common Taxonomy of Commercial Contracts - Pedamon, Catherine (University of Westminster, 2022)
The works presented for the PhD by publication are all connected in the way they engage in a functionally comparative study of the English and French law responses to common problems pertaining to contractual performance and contractual interpretation. My comparative inquiry demonstrates that both France and England have stayed true to their historic responses in times of peace and crisis confirming different mentalités juridiques. As neither England nor France offers ideal solution, parties may be better off finding a resolution to their disputes beyond the legal realm and respond to calls for collaboration. This nevertheless shows persisting differences in Anglo-French approaches. This thesis however argues that these divergences may nevertheless lead to common results through the lens of a taxonomy of commercial contracts – professionally drafted contracts may lead to converging results given the common application and interpretation of frequently used clauses beyond a domestic legal culture; by contrast, rudimentary contracts produce diverging results as the interpretation of these agreements is marked by a distinctive domestic socio-legal culture. This taxonomy has the potential to improve the predictability of outcomes in commercial disputes in England and France.
Keywords: Commercial contracts; Contract law; England; France

Reforming investor-state dispute resolution: Focusing on the roles of domestic courts - Ma, Wanli (Erasmus University Rotterdam, 2022)
While a universally applicable multilateral agreement on investment is not yet available, a broad network of BITs and investment chapters in FTAs has been put in place to protect foreign investors and their investments. Meanwhile, investment arbitration has become a defining feature of modern international investment law over the recent decades, enabling foreign investors to launch an investment arbitration against host states, often without the need to go through local remedies before that. With the caseload of investment arbitration increasing at a rather rapid speed, such a dispute resolution method has also attracted fierce criticism. Many commentators have alleged, among other, that the decision-making of investment arbitrators has been inconsistent and unpredictable, that investment arbitration has become a threat to public interest, that investment arbitration proceedings are not transparent enough, that the arbitrators involved are not independent nor diverse enough, that the lack of an applellate mechanism compromises the quality of decision-making, and that investment arbitration has become far too costly and time-consuming. Against such a backdrop, the global community has made joint efforts to reform the investment arbitration system, not least through various initiatives developed at ICSID and UNCITRAL. Almost at the same time, national states also seem to have started to reconsider the costs and benefits of including investment arbitration in their investment agreements as a method for the resolution of disputes with foreign investors. Although the caseload of investment arbitration continues to grow and national states keep concluding IIAs containing investment arbitration clauses, at least some countries in their more recent investment treaty making practice have demonstrated a policy trend to rein in investment arbitration and ramp up the role of domestic courts in resolving investment disputes. They often do so by exiting the ICSID system, terminating their investment agreements with economic partners, excluding investment arbitration from their investment agreements, and conditioning investment arbitration upon the prior use of litigation via domestic courts. While the state practice mentioned above surely does not suggest the global society has any intention to abandon investment arbitration any time soon, it prompts us to take a step back and reconsider the role that domestic courts may play in resolving investment disputes, instead of solely focusing on the piecemeal reform of investment arbitration. When it comes to investor-state dispute resolution, domestic courts can indeed play different roles along the process. Like investment tribunals, domestic courts can also adjudicate investment disputes between foreign investors and local authorities. Such a judicial role sometimes is also confirmed in investment agreements through, for example, the exhaustion of local remedies rule, the clause demanding pursuit of local remedies prior to investment arbitration and the fork-in-the-road provision. In the context of non-ICSID arbitration, disputing parties are often entitled to applying for the review by domestic courts loci arbitri of the rulings and awards rendered by investment tribunals. Domestic courts loci arbitri would thus assume a supervisory role with regard to arbitration proceedings and arbitral outcomes, as they may set aside arbitration awards in question according to the review grounds enumerated in local arbitration laws. Moreover, domestic courts in a broader sense may be called upon to support the conduct and / or authority of investment arbitration, by recognizing and enforcing the investment awards rendered by arbitral tribunals and issuing interim measures of a judicial nature to facilitate the arbitration process. Since litigation through domestic courts and investment arbitration are two primary remedies that foreign investors often rely on for the resolution of investment disputes, this study constructs three models of institutional design with regard to the allocation of jurisdiction over investment disputes between domestic courts and investment tribunals. While the reality may turn out to be more complicated, such three models roughly represent the institutional choices facing national states. These three models are: (i) utter reliance on domestic courts as the exclusive forum for investor-state dispute resolution, (ii) investment arbitration operating as a substitute for litigation via domestic courts, and (iii) investment arbitration working as a complement to litigation via domestic courts. In order to conduct a comparative institutional analysis of the three models to reveal their respective tradeoffs, this study employs a goal based approach which is increasingly used to analyze the effectiveness of international adjudicatory mechanisms. As a result of the employment of the goal-based approach, the goals of investor-state dispute resolution are recognized as achieving fair and efficient dispute resolution, promoting state compliance with investment treaty norms, facilitating the objectives of the investment law regime, and legitimizing the underlying investment treaty regime. While the quality of the national judiciaries of many developing countries is not the same as it was decades ago largely due to the judicial reforms launched around the world, fairness and efficiency in dispute resolution still cannot be fully guaranteed in the domestic courts of those countries without a robust legal system and a good record of the rule of law. However, there are certain institutional characteristics of court litigation that may facilitate the efficiency in the resolution of investment disputes, such as the unique advantage of domestic courts that they can work as a single forum for dispute resolution and the better knowledge of court judges of the domestic legal framework at issue. Domestic courts also hold great potential in promoting the compliance by national states with investment treaty norms not least because they have more flexibility in awarding both primary and secondary remedies, but that of course depends on whether domestic courts can adjudicate investment disputes in a fair and impartial manner. Moreover, while utter reliance on litigation via domestic courts may strengthen the domestic rule of law and improve the investment climate in the long term by pressing host states to improve their legal systems and judicial institutions, it may also invite the politicization of investment disputes and the diplomatic intervention from home states in investor-state dispute resolution. Furthermore, despite the risks created for foreign investors, reliance on domestic courts as the exclusive forum may enhance the legitimacy of the investment treaty regime by reducing the sovereignty costs incurred by national states and putting domestic investors and foreign investors on the same footing. Investment arbitration operating as a substitute for domestic courts, on the other hand, demonstrates certain advantages, which are typically affiliated with international arbitration, in achieving the fair and efficient resolution of investment disputes. Unlike domestic courts, which are an integral part of the state apparatus, investment arbitrators are often immune from the influence of domestic politics and are thus believed to be independent and impartial. Meanwhile, the specialization of arbitrators in a particular area of knowledge and the procedural flexibility of arbitration proceedings, among others, are expected to improve efficiency in the resolution of investment disputes. However, empirical evidence presented in the literature sometimes suggests that, in reality, investment arbitrators may not be that unbiased and investment arbitration proceedings often drag on with a bill of a massive amount. Besides, although investment tribunals have a broad scope of jurisdiction over the behavior of different government branches, the practical difficulties they face in awarding primary remedies may damage their ability in promoting state compliance with investment treaty norms. In addition, the introduction of investment arbitration grants to foreign investors a standing in international arbitration proceedings, to a large extent reducing the need for diplomatic protection and home state intervention. However, the positive impact of investment arbitration in facilitating the development of the domestic rule of law and the maintenance and increase of foreign capital is less certain. As for the preservation of the legitimacy of the underlying investment treaty regime, investment arbitration as an alternative to domestic courts cannot be relied on to produce much positive impact. For instance, the increasing sovereignty costs and financial burden imposed on national states would probably prompt more of them to turn against the investment treaty regime. The complement model, in which domestic courts assumes primary jurisdiction and investment tribunals secondary jurisdiction over investment disputes, stands a good chance in keeping the advantages of both court litigation and investment arbitration while avoiding their disadvantages. In the complement model, domestic courts will act as the first line of defense in adjudicating investment disputes, and the institutional advantages of court litigation will be enabled to release their potential. At the same time, even if foreign investors are not satisfied with the judicial outcome or regard the court proceedings as corrupt or unfair, they may escalate the specific disputes to investment tribunals for further consideration. Since court judges are more knowledgeable and experienced in the interpretation and application of domestic law, the legal analysis of court judges will also benefit the decision-making of investment arbitrators in the subsequent arbitration proceeding. Allowing domestic courts to have a first try at investment disputes will also increase the likelihood that primary remedies could be accorded, thus the unique advantages of primary remedies in promoting state compliance with investment treaty norms are not discarded in the complement model. Moreover, the complement model is also more promising in facilitating the achievement of the objectives of the investment treaty regime, and that is because domestic courts are not marginalized in the complement model, the antagonism between foreign investors and host states may be expected to decrease, and the depolicization of investment disputes will not be lost since investment arbitration is kept as an option. Furthermore, the complement model strikes a better balance among the interests of foreign investors, host states and other stakeholders, thus it is more likely to preserve and even enhance the legitimacy of the underlying investment treaty regime than the other two institutional choices. Although the complement model serves the goals of investor-state dispute resolution the best in theory, not any casual combination of court litigation and investment arbitration will do the job; instead, only a smart mix of the two dispute resolution methods can give full play to the advantages of the complement model. Now, we switch to the supervisory role of domestic courts in investor-state dispute resolution. While a systemic appellate mechanism has not been created for investment arbitration, disputing parties may rely on setting-aside proceedings in non-ICSID arbitration to challenge arbitration awards. In other words, domestic courts loci arbitri may conduct a judicial review of the rulings and awards made by investment tribunals. However, a theoretical analysis of the judicial review mechanism supported by empirical evidence has shown that the mechanism has several flaws, which include but are not limited to the points that follow immediately. Since there is only a casual link between the seat of arbitration and the investment dispute, it is inappropriate to subject the decision-making of arbitrators to the judges from the place where the arbitration proceedings took place. The very fact that review courts have been overwhelmingly located within the developed North could raise concern that the judicial review mechanism is inherently biased against developing countries which have already shown a somewhat negative sentiment towards investment arbitration. Given that judicial review proceedings could easily go through more than one instance of court proceedings in many jurisdictions, the dispute resolution process may consume more time and generate higher costs. From this point of view, the judicial review mechanism favors the richer party in investment arbitration and could become a weapon of dilatory tactics available for such a party. Considering the higher error costs relating to investment arbitration than that relating to commercial arbitration, limited review grounds and a copious amount of deference to arbitral tribunals may not prove to be as effective in the scrutiny of investment awards. Moreover, the idiosyncrasies as to review grounds and standards across jurisdictions indicate that inconsistency would also probably permeate the judicial review practices, which would then encourage forum shopping that leads to increased costs and decreased efficiency. In addition, as both review courts and enforcement courts may exercise control over investment awards, the setting-aside decision may be merely disregarded at the enforcement stage and the overall efficiency of investor-state dispute resolution may be reduced. In order to overcome many of the flaws mentioned above, a delocalized form of review should be introduced to take place of the current judicial review mechanism.

Corporate Governance and Women on the Board of Directors : the Legal Framework towards a Minimum Harmonisation in the European Union - Lamy Martin, Joy (Université Paris-Saclay, 2022)
This thesis concerns the recent and considerable change in corporate governance legislation, specifically how boards of directors address the issue of parity and the appointment of its members in public limited companies. This research will challenge European Union law which, to date, does not propose EU harmonization.The UK, France, Germany and Norway (a non-member country but one that will be included in this research) have introduced changes to their national legislation in relation to company boards in public listed companies. This research will focus on a comparative study of parity on company boards under European Union law and its application in the UK (pre-Brexit), Germany, France and Norway. The application of corporate governance codes or soft law and the proposal for a hard law directive demonstrate a fragmentation in the EU, as the application of law by hard quotas divides member states and parliamentarians in European Union law. Corporate governance law in the member states varies considerably, but it must respect the EU's primacy law. Comparisons of legislation between member states reveal the marked differences in law.Women are significantly under-represented on the corporate boards of public limited companies in Europe. Legitimate questions need to be asked. Does the European Commission have the right to make a proposal for a directive allowing for parity on the boards of public limited companies in the EU? The reality is that the Commission does not have a solid approach in dealing with the issue of parity. As long as there is too much inconsistency between Member States, this leaves considerable room for further research. Legislation and governance law between member EU member states diverge considerably and demonstrate inconsistency with the legislation between them, resulting in little or no consensus in the interpretation of EU law. Or member states diverge with opposing interpretations of EU law, especially concerning sovereignty.National legal systems differ considerably in the way legislation allows for the appointment of board members and the notion of parity. A review of corporate governance matters concerning shareholders, the composition and appointment of board members corporate governance codes reveal the gap between member states. The research focus on parity by way of a comparison of the soft and hard laws of the member states.. The research upholds European law Article 157(3) Treaty of the Functioning on the European Union (TFEU), which is the fundamental principle of EU law and basis of gender equality and parity.The research will contribute to raising awareness of this issue through quota legislation and the question of parity on boards in public limited companies in the EU.
Issue: 2022UPASH012
Keywords: Board of directors; Comparative Law; Conseil d'administration; Corporate Governance; Droit comparé; Gender and parity; Genre et parité; Gouvernance des entreprises; Quotas; The European Union; Union européenne

The protection of the national labour force against foreign competition under labour migration laws and policies : a comparative analysis between the Democratic Republic of Congo and South Africa - Kamwimbi, Kasongo Theodore (University of South Africa, 2022)
Labour migration, which involves both labour immigration and labour emigration, refers to ‘the cross-border movement of people from a homeland to a location outside that homeland, with the purpose of taking up employment’.1 Labour migration has become an ever more important feature of the globalising world as it plays an important role and has a direct impact on African countries’ economies and societies. Recognising the significant benefits of labour migration to countries of origin and destination, the African Union urges African States to enact labour migration laws, regulations, and policies in a regular, transparent, and comprehensive manner at both continental and country levels. In this regard, many African countries have exercised their prerogative to regulate labour migration, which falls within each state’s sovereign discretion. By way of illustration, this thesis focuses on two specific countries, namely the Democratic Republic of Congo (DRC) and South Africa, which have regulated the employment of foreign-born workers. The two countries have established a legal and regulatory framework aimed at protecting the national labour force against foreign competition. The two countries have been selected for this study because they are comparable in many ways while differing as much as possible in terms of the institutional set-up of their migration systems and labour markets. In fact, this study seeks to compare the DRC’s and South Africa’s labour migration laws, regulations and policies, particularly how these legal and regulatory instruments effectively protect the national labour force against foreign competition. In this sense, the study explores the overall successes and challenges of these legislative and regulatory endeavours, while identifying the shortcomings and merits of the implementation of the laws and policies in the two countries.
Keywords: Congo (Democratic Republic); Contract of employment; Emigration and immigration law; Foreign workers; Labor laws and legislation; Labour market; Manpower policy; Migrant workers; South Africa

A comprehensive analysis of the law regulating equal pay in South Africa - Ebrahim, Shamier (University of South Africa, 2022)
The purpose of this thesis is as follows. Firstly, to identify the problems associated with the causes of action in section 6(4) of the EEA; the onus in section 11 of the EEA; the right to access pay related information; the grounds of justification in section 6(2) of the EEA and the Employment Equity Regulations; the equal pay provisions in sections 198A-198C of the LRA; and section 27 of the EEA. Secondly, to discuss and analyse the South African equal pay legal framework in order to provide answers and solutions to the research problems. Thirdly, to discuss and analyse the international legal framework regulating equal pay and the United Kingdom equal pay law in order to provide answers to the research questions to the extent and breadth called for. Fourthly, to summarise the answers to the research questions as sourced from South African law, international labour law and the United Kingdom equal pay law.
Keywords: Comparator; Equal pay claims; Equal pay for substantially the same work; Equal pay for the same work; Equal pay relating to non-standard (atypical) employees; Grounds of justification; Hypothetical comparator; Onus in section 11 of the EEA; Right to access pay-related information; Same employer; Section 27 of the EEA; Section 6(4) of the EEA; Sections 198A-198C of the LRA; Subordinate comparator; Terms and conditions of employment

Legal texts on trade facilitation: comparative analysis of the World Trade Organisation and the African Continental Free Trade Area - Shumba, Willie (University of South Africa, 2022)
Trade agreements are a common feature in international economic law as they govern trade relations between states. These agreements are anchored by a firm foundation of the requisite legal provisions to support trade. In this regard, the World Trade Organisation (WTO) and the African Continental Free Trade Area (AfCFTA) have each developed their own legal texts that acknowledge the significance of trade facilitation and would, when implemented, facilitate the movement of goods and services across international borders. The thesis was a comparative analysis of the legal texts on trade facilitation of the WTO and the AfCFTA whose aim was to identify the resemblances and divergences between the two. The WTO has a broader mandate of global trade and ensures that trade amongst its members is conducted in conformity with global rules. On the other hand, the AfCFTA is a trade agreement that has been negotiated by African member states pursuant to the political vision of the African Union (AU), and within the confines of WTO, specifically Article XXIV of GATT 1994. This research was therefore undertaken against the backdrop of these seemingly contradicting circumstances. The central research question for the study concerns the differences and similarities between the legal texts on trade facilitation of the WTO and the AfCFTA. The study was qualitative involving a desktop review of primary and secondary sources of data. Among others, the thesis finds that the AfCFTA complies with the strategic goals of the AU, and at the same time, complements the multilateral trading system of the WTO. The thesis concludes that while there are certain similarities, the legal texts on trade facilitation of the WTO and the AfCFTA are different. The inherent dissimilarities in the texts are not contrary to the principles of the WTO. The thesis contributes to scholarly literature in trade facilitation with respect to both the AfCFTA and the WTO. It also identifies new areas for further studies and provides the necessary groundwork. The study recommends some improvements that can be made to the respective legal texts on trade facilitation.
Keywords: AfCFTA; AfCFTA Agreement; African Continental Free Trade Area; Comparative analysis; Customs union; Free trade area; GATT; General Agreement on Tariffs and Trade; Global trade; International Trade; Legal texts; Multilateralism; Regional Economic Community; Regional Trade Agreements (RTAs); Regionalism; Trade Facilitation Agreement (TFA); Trade agreement; Trade facilitation; World Trade Organization

An evaluation of the strengths and weaknesses of South Africa’s corporate rescue regime as a potential benchmark for Uganda - Waiswa, Abudu Sallam (University of South Africa, 2022)
This thesis evaluates the strengths and weaknesses of the legal framework on corporate rescue in South Africa and Uganda. Although corporate rescue was initially not one of the objectives of insolvency law, it has now become the focus of modern insolvency law. South Africa became the first country to recognise the need to create a legal framework for rehabilitating financially distressed companies when it incorporated judicial management in the Companies Act of 1926. Judicial management was, however, not successful as a corporate rescue procedure. The South African policy makers however continued to explore ways through which financially distressed but viable companies could be saved from collapsing. This culminated into the introduction of business rescue in Chapter 6 of the Companies Act 71 of 2008. The study presents a detailed analysis of the strengths and weaknesses of the South African business rescue framework. It posits that unlike the Ugandan system, the South Africa legal regime reflects the principles of a modern and effective corporate rescue system. Whereas the government of Uganda attempted to embrace corporate rescue through the introduction of administration in the Insolvency Act 2011, the law is devoid of the internationally recognised features of a modern and effective business rescue framework. Administration has remained a white elephant in Uganda’s insolvency system, with liquidation continuing to be the predominant procedure used by both creditors and financially distressed companies. It is recommended that Uganda’s policy makers should benchmark the South African system to reform Uganda’s corporate rescue framework. This thesis is based on the law as at 31st of May 2022, found in the sources available in South Africa and Uganda.
Keywords: Bankruptcy; Business rescue; Corporate insolvency; Corporate insolvency law; Corporate reorganizations; Corporate rescue; Insolvency; Judicial management; Provisional administration; Rescue finance; South Africa; Uganda

Three Essays on Digital Platforms and Competition Policy - Yan, Jun (Université Toulouse 1 Capitole, 2022)
Cette thèse se compose de trois chapitres indépendants et examine différentes questions antitrust liées aux plateformes de gatekeeper. Le chapitre I explore le problème du verrouillage vertical dans les marchés bifaces. Dans le cadre des Accelerated Mobile Pages (AMP) de Google, le chapitre 2 examine la question de l'accès des plates-formes de contrôle d'accès aux données des utilisateurs professionnels. Le chapitre 3 se concentre sur le droit d'auteur numérique et étudie le comportement de Google consistant à utiliser le contenu des éditeurs pour afficher des réponses courtes sur les pages de résultats de recherche.Le premier chapitre examine comment l'intégration verticale d'une plate-forme monopolistique, qui se caractérise par des externalités de réseau bilatérales entre groupes, influe sur son incitation à s'engager dans le verrouillage en aval. Je me concentre sur un environnement où la plate-forme et les vendeurs en aval sont confrontés à l'incertitude quant aux gains du commerce au stade de la passation des marchés. Le choc aléatoire étant non contractile, la contractualisation crée des frictions qui faussent la structure tarifaire de la plateforme. En revanche, l'intégration verticale atténue ce problème en permettant à la plate-forme d'intégrer le choc aléatoire des prix à la consommation. En raison de l'interaction entre la friction des transactions et les externalités de réseau intergroupes, je trouve que l'intégration verticale pourrait réduire l'incitation de la plate-forme à la forclusion.Le deuxième chapitre est un travail conjoint avec Doh-Shin Jeon. Nous étudions comment l'adoption par les journaux d'AMP, un format de publication qui permet le chargement instantané de pages Web dans les navigateurs mobiles, modifie l'allocation des données et, par conséquent, les incitations des journaux à investir dans un journalisme de qualité. L'adoption d'AMP permet à Google d'obtenir des données sur les consommateurs à partir d'articles AMP et de les combiner avec d'autres sources de données sur les consommateurs pour améliorer le ciblage des publicités diffusées par Google sur d'autres sites Web. Même si une telle combinaison de données augmente l'efficacité statique, elle peut réduire l'efficacité dynamique lorsqu'elle diminue les revenus publicitaires par trafic de journal, réduisant ainsi la qualité du journalisme. Les journaux sont confrontés à un problème d'action collective car l'adoption de l'AMP par un journal génère des externalités négatives pour les autres journaux via le classement des recherches et la fuite de données. Google peut tirer parti de son pouvoir de marché dans la recherche et l'intermédiation publicitaire pour inciter les journaux à adopter AMP. Nous fournissons des recours politiques.Le troisième chapitre construit un modèle théorique de biens d'information divisibles pour examiner comment l'utilisation d'extraits par un moteur de recherche monopolistique impacte la consommation et la création de contenu. En affichant des extraits dans la zone de réponse sur les pages de résultats de recherche, le moteur de recherche dissocie les informations essentielles et les informations supplémentaires des articles. Elle crée donc deux effets opposés sur l'incitation des éditeurs à investir dans la qualité : l'effet de taille du marché et l'effet d'élasticité. Son impact sur le bien-être social est ambigu. D'une part, la boîte de réponse améliore l'efficacité de la recherche en offrant un accès plus large aux informations essentielles et en permettant aux consommateurs inframarginaux de substituer les informations essentielles à l'article complet. D'un autre côté, cela pourrait réduire le trafic sur le site Web, réduire les revenus publicitaires des éditeurs et les inciter à investir dans la qualité. J'examine les impacts des différentes politiques qui obligent le moteur de recherche à payer pour l'utilisation d'extraits.
Keywords: Antitrust law; Competencia; Competition Policy; Competition law; Concurrence; Concurrence (droit); Digital Platforms; Economie des médias; Google; Intellectual property; Marché biface; Media Economics; Online Advertising; Plateformes digitales; Propriedade intelectual; Propriété intellectuelle; Publicité en ligne; Technologies de l'information et de la communication – Aspect économique; Two-Sided Market

EU copyright reform : an institutional approach - Mangal, Natasha (Université de Strasbourg, 2022)
Cette thèse a pour objet d’étudier comment le dispositif institutionnel actuel pour l’adaptation du droit d’auteur dans l’Union européenne peut être reconsidéré afin de promouvoir le niveau de cohérence plus élevé dans les pratiques réglementaires des États membres, ainsi que dans l’intérêt de la promotion d’un corps de règles européennes plus dynamiques en la matière.À l’aide de l’outil normatif de l’analyse institutionnelle comparative, les dispositions institutionnelles actuelles sont examinées, en se concentrant sur la qualité de la participation des parties prenantes du droit d’auteur dans le système politique, le marché et les tribunaux. Des exemples d’institutions administratives du droit d’auteur dans certaines juridictions (États-Unis et Canada) sont analysés plus en détail, en tirant des conclusions sur leurs fonctions et leurs rôles dans leurs systèmes juridiques respectifs. Enfin, cette thèse propose plusieurs solutions politiques, y compris la possibilité d’envisager une nouvelle autorité au niveau de l’Union européenne pour le droit d’auteur. En fin de compte, la remise en question du statu quo institutionnel dans l’Union européenne peut révéler de nouvelles voies prometteuses pour développer les fonctions administratives, quasi judiciaires, d’observation et de conseil nécessaires à la gestion du droit d’auteur à l’ère du numérique.
Keywords: Analyse institutionnelle comparative; Comparative Institutional Analysis; Copyright; Digital Single Market; Droit de la propriété intellectuelle; Droit d’auteur; Droits d'auteur; Institutions; Intellectual property; Intellectual property law; Marché unique numérique; Union européenne

Performance and rarity of worker-owned firms : empirical evidence from France - Mirabel, Thibault (Université Paris 10, 2022)
This thesis compares the performance of worker-owned firms (WOFs) and conventional firms (CFs). These firms differ by their distribution of ownership rights and their mode of governance. In WOFs, the ultimate control is held by the suppliers of labor, whereas in CFs the ultimate control is held by the suppliers of capital. WOFs represent an implementation of democracy in firms and, as such, are likely to be immune to institutional harassment and socialwashing. WOFs have also been supported by citizens, politicians, and economists from across a wide ideological spectrum. Despite their attractiveness, WOFs represent a minute proportion of firms in our contemporary economies. This thesis seeks to bring new insights and stylized facts to better understand the rarity of WOFs. Chapter 1 studies how the interaction of the sunk costs of human capital and physical capital impacts the probability of WOF entry. I show that the likelihood of WOF entry is the highest when the sunk cost of human capital is dominant while the sunk cost of physical capital is negligible. Chapter 2 compares the survival patterns of WOFs and CFs. I show that WOFs survive longer than CFs regardless of whether they have different or similar entry resources, and that some entrepreneur and firm characteristics impact WOF and CF survival differently. Chapter 3 compares the survival patterns of WOFs distinguished by their entry mode (i.e., newly created, worker buyouts of sound CFs, worker buyouts of CFs in difficulty, and worker buyouts of nonprofit organizations). I show that any type of worker buyout survives longer than newly created WOFs. Overall, this thesis suggests that the rarity of WOFs is more likely to result from entry barriers specific to WOFs rather than from poor performance compared to CFs. Cette thèse compare la performance des coopératives de travailleurs (SCOPs) et des entreprises conventionnelles (ECs). Ces entreprises diffèrent par leur distribution des droits de propriété et leur mode de gouvernance. Au sein des SCOPs, les travailleurs ont le contrôle ultime de leur entreprise. Les SCOPs instituent la démocratie dans le monde économique et, à cet égard, furent et sont encore défendues par des économistes appartenant à une large palette idéologique. Malgré leur attractivité, les SCOPs représentent une fraction minuscule des entreprises dans le monde. Cette thèse entend apporter des éléments nouveaux pour comprendre la rareté des SCOPs. Le Chapitre 1 étudie comment l’interaction des coûts échoués en capital et en travail impacte la probabilité de créer une SCOP. Je montre que la probabilité de créer une SCOP est maximale lorsque le coût échoué en travail est dominant et que le coût échoué en capital négligeable. Le Chapitre 2 compare les profils de survie des SCOPs et des ECs. Je montre que les SCOPs survivent plus longtemps que les ECs indépendamment du fait que leurs ressources à l’entrée diffèrent ou non. Je montre aussi que certaines caractéristiques de l’entrepreneur différemment la survie des SCOPs et des ECs. Le Chapitre 3 compare les profils de survie des SCOPs en distinguant quatre modes d’entrée (les SCOPs nouvellement créées, les reprises d’entreprises saines, les reprises d’entreprises en difficulté et les reprises d’organisations à but non-lucratif). Je montre que les reprises en SCOPs survivent plus longtemps que les SCOPs nouvellement créées. Dans l’ensemble, cette thèse suggère que la rareté des SCOPs est due à des barrières à l’entrée spécifiques aux SCOPs plutôt qu’à leur prétendue moindre performance vis-à-vis des ECs.
Keywords: Coopératives; Coopératives ouvrières de production; Coûts échoués; Democracy; Efficacité de l'organisation; Entry mode; France; Mode de création; Participation à la gestion; Performance; Personnel; Scop; Sunk costs; Survie; Survival; Worker-owned firms; Études comparatives

An examination of the challenges posed by the internet economy for the South African income tax regime - Odhiambo, Oluoch Rodney (University of South Africa, 2022)
The way of doing business has changed significantly since the turn of this century due to the growth of internet technology and the global digital economy. This growth has reduced the importance traditionally attached to tangible assets and physical location in both commerce and taxation. This implies that any country that relies on physical presence to trigger tax liability in today’s digital economy may be forced to reconsider the relevance, effectiveness, and efficiency of its income tax legislation. This thesis postulates that South Africa’s income tax law and the international taxation principles it relies on in taxing cross-border and digital transactions have not grown in tandem with the changing landscape of today’s digital economy. The thesis contends that South Africa will not receive its fair share of tax from giant multinational enterprises such as Google, Facebook, and Amazon which operate and trade in the country, if it does not amend its income tax laws to address the challenges posed by the internet economy. In examining the challenges posed by the internet economy to South Africa’s income tax regime, the thesis commences in Chapter 2 by discussing the growth of the digital economy and its implications for South Africa’s income tax system. Chapter 3 offers a critical analysis of South Africa’s income tax laws and the international principles on which they rely in taxing the digital economy. Chapter 4 discusses the measures that South Africa’s government has taken to tax its digital economy, while Chapter 5 compares how the Organization for Economic Cooperation and Development (OECD), the European Union (EU), Kenya, India, and New Zealand have dealt with the issue of taxing the digital economy and the lessons to be learned from these jurisdictions. The thesis concludes in Chapter 6 by proposing recommendations that South Africa could consider to make its income tax regime more efficient and effective in taxing transactions that take place in today’s digitised economy.
Keywords: Cryptocurrency; Digital economy; Digital tax; E-commerce; E-signature; Electronic commerce; Formulary apportionment; Income tax; Internet industry; Signature électronique; Taxation; Virtual currency

The use of MASS in the context of International Law of the Sea - Mandrioli, Daniele (Università degli studi di Milano, 2022)
L'automatisation et la numérisation redéfinissent l'ergonomie des comportements humains. En se limitant au domaine maritime, les nouvelles technologies permettent d'automatiser entièrement l'activité traditionnelle de la navigation ; aujourd'hui, les navires peuvent être contrôlés depuis le rivage et l'intervention humaine dans la boucle de décision n'est plus nécessaire.Cette innovation disruptive offre de grandes opportunités pour l'industrie maritime. Intuitivement, les profits tirés du transport de marchandises et de personnes en mer peuvent être maximisés ; la réduction ou l'absence d'équipage à bord entraîne une réduction considérable des coûts pour les opérateurs (et pour les consommateurs), surtout en cette période historique marquée par la propagation mondiale du virus SARSCOV-2. En ce qui concerne la sécurité maritime, l'innovation que constitue le contrôle autonome réduit fortement le risque d'accidents dus à des erreurs humaines, qui sont à l'origine de la plupart des accidents maritimes. En ce qui concerne la protection de l'environnement marin, la navigation autonome peut en outre rendre le transport maritime plus durable.Pour ces raisons, les États et les entités privées financent plusieurs projets de développement de navires autonomes : au cours des dernières années, les premiers navires de surface autonomes (ci-après dénommés MASS) ont été testés et produits. En l'état actuel des connaissances, l'adoption de cette nouvelle technologie n'est plus un événement futuriste : plus d'un millier de MASS naviguent actuellement sur les océans du monde.Étant donné que l'activité humaine de la navigation est sujette à des changements, on peut se demander si les règles internationales qui la régissent sont d'une certaine manière remises en question par l'essor de l'automatisation.Habituellement, une nouvelle invention technologique s'accompagne de nombreuses questions réglementaires. D'une part, la loi est tenue de contrôler et de prévenir les conséquences involontaires découlant du recours à la nouvelle technologie. D'autre part, la loi est appelée à admettre et à autoriser son utilisation.Par conséquent, l'objectif de cette thèse est d'étudier les implications juridiques internationales découlant de l'utilisation croissante des moyens autonomes de transport maritime. En quelques mots, il s'agit ici d'aborder la question de savoir si et comment le recours à la technologie MASS a un impact sur le cadre juridique international préexistant qui régit l'exécution de la navigation et le contrôle de l'Etat sur celle-ci.Au cours des dernières années, ce sujet a suscité une attention croissante. En particulier, en 2019, le Comité de la sécurité maritime (CSM) de l'OMI a approuvé les "Directives provisoires pour les essais de navires autonomes de surface (MASS)". En outre, l'Organisation a très récemment achevé le "Regulatory Scoping Exercise on Maritime Autonomous Surface Ships" (ci-après RSE), qui avait débuté trois ans auparavant.La recherche proposée veut s'inscrire dans ce débat ouvert (et le dépasser) afin de fournir un panorama étendu des implications juridiques internationales émergeant de l'utilisation de l'automatisation et du contrôle dans le domaine maritime. Ce faisant, l'attention se concentrera sur trois blocs normatifs : les règles internationales sur la sécurité de la navigation (chapitre I), les règles internationales régissant l'attribution de la juridiction des États sur les navires (chapitre II) et les règles internationales traitant de l'assistance aux personnes trouvées en détresse en mer (chapitre III).
Keywords: Commande automatique; Droit de la mer; Droit maritime; Law of the Sea; Mass; Navires; Pilotes automatiques (navigation); Ships; Systèmes de guidage

Trade facilitation through border enforcement of Intellectual Property Rights: issues, concerns and possible remedies - Hossain, Syed Saifuddin (Macquarie University, 2022)
In the present era of rapid globalisation, countries are intrinsically integrated with each other by way of international trade to ensure optimal utilisation of their resources. Trade facilitation is now recognised as a key driving factor in determining export competitiveness of a country. Customs administrations, the frontier border agency responsible for regulating import and export of legitimate goods, are increasingly faced with the challenge of intellectual property rights (IPR) infringement. In addition to national governments, various international organisations have devised guidelines and tools to facilitate and empower Customs agencies in their fight against IPR infringement. In particular, the multilateral Agreement on Trade Related Aspects of Intellectual Property Rights (TRIPS) of the World Trade Organization (WTO) articulates a prescription for border enforcement of IPRs in Articles 51-60. In this backdrop, this thesis attempts to answer a very fundamental question: What are the implications of ‘Border Measures’, specified under the WTO TRIPS Agreement, for facilitating international trade? To this end, it critically examines the concepts of trade facilitation, TRIPS and IPR protection to highlight the links that connect them and the missing links that need to be established. Obligations to protect IPR under national and international laws are also scrutinised. Research shows that efforts by WTO, World Customs Organization (WCO) and World Intellectual Property Organization (WIPO) have been instrumental in this context. While policy planning at the national level should be the first priority, commitment by the advanced economies to support their less developed counterparts through technology transfer (TT) is of paramount importance. The thesis suggests that TRIPS-plus provisions, if implemented arbitrarily by developed countries, have the potential to undermine the interests of countries with resource constraints. In this context, the thesis analyses the effects and implications of the Trans-Pacific Partnership (TPP) and the Trans-Atlantic Trade and Investment Partnership (TTIP) agreements, and the Revised Kyoto Convention (RKC) for the border protection of IPRs. The thesis investigates the socio-economic impacts of IPR infringement and articulates strategies to be adopted and applied at individual, collective, business and government levels to stop trade and use of IPR infringed goods. Drawing on the analysis of the relevant WTO Articles, scrutiny of various border measures put in place by national governments and international bodies, and current state of play under the Doha Development Round (DDR), the thesis puts forward a set of short and long term policy recommendations for all relevant stakeholders. These inclusively include: (i) strengthening risk management procedures; (ii) cooperation and coordination at national and international levels; (iii) awareness raising initiatives; (iv) establishing advanced technologically driven border enforcement system; (v) empowering Customs with effective administrative authority; (vi) IP related technical capacity building within the Customs and business community; (vii) technology transfer to LDCs from developed countries; and (viii) LDC friendly dispute settlement process under the WTO.
Keywords: Border protection; Customs; IPR; Intellectual property; Intellectual property infringement; Intellectual property rights; Trade facilitation

The Economics of Trade, Innovation and the Technology Revolution - Tharwat, Ismaeel (Université Paris-Saclay, 2022)
Cette thèse étudie principalement l'impact du commerce international sur l'innovation, avec un accent particulier sur les pays en développement. Elle couvre également l'impact des retombées commerciales sur les inégalités de genre. Le chapitre 1 présente un aperçu de la littérature économique théorique et empirique récente traitant de l'effet de la concurrence des importations sur les résultats liés à l'innovation. Ce chapitre est divisé en quatre sections. Tout d'abord, un historique des brevets et des marques déposées en tant qu'indicateurs d'innovation est présenté. Deuxièmement, les mécanismes théoriques qui sous-tendent l'impact de la concurrence des importations sur l'innovation sont discutés. Troisièmement, une revue de la littérature des études empiriques récentes sur le commerce et l'innovation est résumée. Enfin, une analyse empirique est menée pour examiner l'impact de la concurrence des importations chinoises sur l'innovation, mesurée par l'activité de dépôt de brevet, dans les pays en développement.Le chapitre 2 est un exercice empirique qui examine l'impact de la concurrence des importations chinoises sur l'innovation, en utilisant une nouvelle mesure qui est le dépôt de brevet. L'étude utilise un ensemble de données de panel de 1995 à 2018 sur plus de 100 pays en développement. Le modèle empirique corrige l'endogénéité en utilisant une approche de variable instrumentale qui permet d'identifier la part du développement dû aux importations chinoises dans d'autres pays en développement. Les principales estimations trouvent un effet global décroissant de la concurrence des importations sur l'activité de dépôt de brevet. Les résultats de la variable instrumentale sont particulièrement robustes pour les demandes de brevet, mais pas pour les enregistrements. Cela suggère que la concurrence des importations affecte négativement les nouvelles innovations locales de produits ou de services dans les pays en développement.Enfin, le chapitre 3 aborde la question de l'impact des retombées du commerce international sur les normes d'égalité de genre. La majorité des études existantes documentent l'effet des épisodes de libéralisation sur les inégalités de genre. Celui des acteurs commerciaux, en revanche, a été largement ignoré. L'inégalité de genre au sein d'un pays est-elle affectée par ses partenaires commerciaux? Nous avons examiné cette question dans cet article en adoptant un modèle spatial du commerce entre 123 pays sur la période 1997-2013. Nous utilisons l'indice d'inégalité de genre pour capturer les tendances globales sur le genre au sein d'un pays. Nous avons ensuite désagrégé les échanges commerciaux au niveau produits afin d'identifier un canal technologique. Les résultats montrent que des normes d’égalité de genre plus élevées à l'étranger se répercutent, via les importations de produits de moyenne, haute technologie et minéraux, sur des normes d'égalité de genre plus élevées au niveau national. Ces résultats suggèrent qu'une révolution technologique affecte les entreprises, les ménages et les gouvernements en ayant un impact sur l'autonomisation des femmes.
Keywords: Brevets; Brevets d'invention; Economie du genre; Economie internationale; Gender Economics; Innovation; International Trade; Marques commerciales; Marques de commerce; Patents; Technologie; Technology; Trademarks; Économie de marché; Études sur le genre

The legal framework for multimodal transport in West Africa: the African Continental Free Trade Area in perspective - Osinuga, Damilola (World Maritime University, 2022)
This thesis examines how multimodal transport can play a role in achieving the objectives of the African Continental Free Trade Area (AfCFTA). The thesis argues that multimodal transport is cheaper compared with unimodal transportation. While there are a number of issues affecting the operationalisation of multimodal transport in Africa, this study considers, at its core, the legal regimes and other fragmented institutional and governance frameworks of multimodal transport in West Africa. The fragmentation of the legal framework governing multimodal transport leads to uncertainty and unforeseeability of the liability of parties involved in multimodal transport, consequently leading to increased legal costs. There is an undisputed view that for effective regional integration, which Africa is seeking to achieve through the establishment of the African Continental Free Trade Area, there is a need to eliminate all trade barriers. Trade barriers (tariff or non-tariff barriers) should be removed to improve competitiveness and reduce trade friction costs. In other words, to achieve the objectives of the African Continental Free Trade Area, it is essential that all unnecessary costs associated with trade are eliminated or reduced to the barest minimum. The process of doing this is called trade facilitation. This thesis looks at the impact of trade facilitation on regional integration and trade. This thesis’ original contribution to knowledge is that Africa’s regional integration process needs cost-effective transportation in order to achieve smooth market access, and multimodal transportation can provide the most cost-effective solution. However, the legal uncertainty and complexities that could potentially ensue from the use of multimodal transport make it unattractive to prospective users. Accordingly, actions must be taken to reduce legal ambiguity and create a system in which liability is foreseeable and predictable. This study reveals that the current legal framework is incomplete, unsatisfactory and, ultimately, leads to uncertainty. The thesis further contends that neither the option of freedom of contract nor improving the current system of various Economic Community of West African States (ECOWAS )member-states’ view of multimodal transport, can significantly improve the current fragmented system or deliver the needed certainty. Accordingly, the thesis proposes that a modified uniform system would help achieve the legal certainty needed for multimodal transport. The thesis finally submits that the ECOWAS should establish a legally binding, regional governance regime on multimodal transport and a majority of its member-states should ratify the instrument.

Foreign Bank Penetration, Institutional Structures and Banking Sector Stability in Sub-saharan Africa - Abeka, Mac Junior (University of Cape Coast, 2022)
Link broken
Keywords: Bank penetration; Banking sector; Sub-Saharan Africa

The rising role of China and Chinese enterprises in transnational labour law: Theoretical inquiries and case studies in the context of Chinese outward mining investment in Africa - Chen, Si (McGill University, 2022)
Transnational labour law scholarship has emerged over the past three decades. However, relatively limited scholarship has explored the role of actors from emerging market economies and the challenges and opportunities they have brought for achieving decent work in a globalized economy. This thesis addresses the research gap through an in-depth investigation into the role of actors from China in the dynamics of multi-level governance of labour rights in a globalized economy. Building on a multi-level, actor-centred and processual approach, this thesis argues that China and Chinese enterprises are playing a rising role in developing and shaping the dynamics of multi-level governance of labour rights in the global cobalt supply chain. Furthermore, the thesis suggests that actors from China have started challenging some unequal patterns of existing labour governance in the global cobalt supply chain and have demonstrated the potential to form a counterbalancing force to challenge the dominant role of actors from the global North. A multi-level governance framework has recently emerged and rapidly evolved in the global cobalt supply chain to eliminate child labour in the artisanal copper-cobalt mining sector in the Democratic Republic of the Congo. This framework is complex, pluralistic, and decentred. A wide range of state and non-state actors are developing various governance initiatives and shaping the dynamics of multi-level governance. Actors from China are playing a rising role in the global cobalt supply chain alongside a few other actors that have also provided proposals from the global South. Over the past decade, Chinese state agencies, nationwide industry associations and mining enterprises have proactively engaged in developing and shaping the multi-level governance framework to address governance deficits on decent work in the global cobalt supply chain. State agencies have developed various regulatory documents to enhance the social dimension of the Chinese regulatory framework for outward foreign direct investment. Nationwide industry associations have further conceptualized the term “corporate social responsibility” and have taken labour rights as key to the social responsibilities of Chinese enterprises operating overseas. Specifically, a Chinese nationwide industry association for the mining industry has developed comprehensive guidelines and initiatives to clarify and operationalize the labour component of social responsibilities in Chinese outward mining investment. The changing dynamics of multi-level governance have played a crucial role in shaping the private labour governance initiatives that Chinese mining enterprises are developing in the global cobalt supply chain. The contributions of this thesis are original, significant, and timely, given the notable research gaps on China and Chinese enterprises’ engagement with the dynamics of multi-level governance of labour rights in a globalized economy and the ongoing development of a multi-level governance framework in the global cobalt supply chain
Identifier: https://escholarship.mcgill.ca/concern/theses/7d2790853
Keywords: Chinese enterprise; Droit du travail; Investment in Africa; Labour law; Transnational labour law

Local Content Requirements in WTO Law: Between Free Trade and the Right to Development - De Lima Figueiredo, Natalia (Maastricht University; Universidade de São Paulo, 2022)
In the international arena, there is a strong rhetoric against a type of industrial policy measure called local content requirements (LCRs). They are often characterised, especially by developed countries, as protectionist measures. However, under certain circumstances, LCRs can have a central role in a country’s development process. Indeed, both developed and developing countries use them to boost their economies. Despite this developmental aspect of LCRs, WTO (World Trade Organization) rules restrict their use. The WTO Agreement, however, has a development dimension and WTO law is supposed to be read in light of the wider corpus of international law. The right to development, in turn, is a principle rooted in core human rights treaties, is consolidated in several instruments of soft law nature and could potentially play a role in the interpretation of WTO provisions. In this scenario, the thesis investigates if it is possible to further a development-oriented interpretation of WTO rules affecting LCRs so that those measures that incorporate genuine development goals are not considered a violation of WTO rules.
Keywords: Development; Free Trade; Human rights; Local content requirements (LCRs); WTO; World Trade Organization

Bank Bail-ins in International Investment Law - Duque-Cordero, Luciano (Universität Wien, 2022)
The global financial crisis led to the introduction of special resolution regimes for financial institutions. The most prominent innovation of these resolution regimes is the so-called bail-in tool, which allows regulators to recapitalise financial institutions by expropriating shareholders and creditors. This thesis analyses the conditions under which a hypothetical bail-in of a financial institution would constitute a compensable breach of international investment law. It identifies the issues that are most likely to be relevant if a bail-in were to be litigated before an investment arbitration tribunal. The thesis first addresses jurisdictional issues, in particular the question of whether bail-inable instruments can even be considered an investment in procedural terms. The analysis then continues to substantive standards of protection. It deals comprehensively with the question of expropriation and related issues such as compensation, the right to regulate, and causation. It concludes with possible violations of the fair and equitable treatment standard.
https://phaidra.univie.ac.at/detail/o:1417287
Keywords: Bail-in; Bank resolution; Expropriation; International Investment Law; Investments

Sanitary and phytosanitary measures as barriers to trade : a South African perspective - Joubert, Biandri (North-West University, 2022)
Sanitary and phytosanitary (SPS) measures are measures aimed at the protection of human, animal and plant life and health, within World Trade Organization (WTO) Member territories, from the risks associated with the introduction and spread of pests and diseases into such territories through trade. The WTO, through its Agreement on the Application of Sanitary and Phytosanitary Measures (WTO-SPS), guides the application of sanitary and phytosanitary measures and provides a set of guiding principles, rights and obligations applicable to Member States. Dispute resolution through the processes of the WTO is available to Members on a Member to Member level within a defined scope and on specific terms. Private parties who operate within the SPS chain at a national level, whether involved in import or export or neither, are dependent on solutions to barriers or disputes available to them through national legislation. In the absence of an enabling legal framework to facilitate aspects of trade such as certainty and continuity in standard setting, the basis of measures taken in science, transparency and legal recourse to resolving barriers or disputes arising, private parties are vulnerable to fluctuations in, for example, their country’s disease-free status. Private parties are also vulnerable to losing relevance as trading partners in periods of ongoing SPS events and to the loss of trust that trading partners have in the country’s ability to trade safely. These are matters that affect private parties who do not have legal recourse to the WTO dispute resolution procedures which are well within WTO concern as they are directly related to the purpose of SPS measures, the principles, rights and obligations on which they are based. Given the importance of agriculture and the increasing inseparability of international rights, obligations and principles in a field of WTO law such as SPS, the importance of a national legislative framework in as far as being the translator of such rights, obligations and principles into legally enforceable rights, obligations, principles, processes and procedures is significant. The rights, obligations, and principles of SPS measures apply to all products, processes and procedures that are within the scope of the agreement and may include at least 36 chapters of the harmonised tariff book. It is necessary to consider also that international trade, national trade and the associated rights, obligations, and principles of the WTO-SPS agreement interact with the social, political, and economic realities of the country within the countries to which the agreement applies. Therefore, researching some of the persistent challenges experienced by the red meat industry in South Africa prone to negative trade-related consequences during and after the outbreak of a notifiable disease, provides insight into the perception of the ability of the legislative framework to provide solutions to these consequences. This research applies a mixed methodology approach whereby qualitative research by means of semi-structured interviews was combined with doctrinal legal research and a quantitative content analysis using Rprogramming. The qualitative research focused on the role of legislation and the perspectives of selected actors in the red-meat industry, specifically in reference to the foot-and-mouth-disease (FMD) outbreaks and subsequent loss of disease-free status since 2019. The doctrinal legal analysis and content analysis focused on the SPS-related legislative framework. The combination of these methods provides a multi-perspective analysis of SPS measures as barriers to trade from a South African perspective and contributes to the mixed-methods turn in legal studies. The objective of this research is to identify and explore persistent challenges to the prevention and resolution of barriers or disputes connected to sanitary and phytosanitary (SPS) measures in the South African context. Ultimately, this research recommends potential practical solutions to the identified challenges with specific focus on SPS-related barriers or disputes that are beyond the strict terms of dispute resolution available through the World Trade Organization (WTO).
Keywords: AfCFTA; Barriers to trade; CADA; CAQDSA; Content analysis; Dispute resolution; FMD; NTB; OIE; Qualitative research; Rstudio; SADC; SPS; Sanitary and phytosanitary measures; WTO

Paradigm Shift in Investment Treaty Arbitration: Toward Stricter Control over the Qualifications and Conduct of Arbitrators - Kamalinejad, Hassan (University of Victoria, 2022)
There is a growing concern over the qualifications and social interactions of investment treaty arbitrators. The characteristics of this class of international adjudicators have significantly evolved over the past few decades. The contemporary arbitration panelist interacts within a broad and complex network of arbitration participants. Their patterns of social behavior both within the community of panelists and within the broader network of actors in arbitration proceedings have fundamentally reshaped the composition, dynamics and culture of the arbitration community. These new forms of relationships and patterns of conduct are new in the context of public international law. These have created unprecedented challenges to the investment treaty arbitration system. New manifestations of attributes and social behavior of panelists demonstrate inadequacies of the existing standards, rules and procedures that govern panelists. This study surveys problematic patterns of social behavior of investment treaty adjudicators and shows how certain instances of social behavior inevitably or potentially jeopardize the very foundations of the system. This research empirically examines the voting behavior of two distinct groups of party-appointed panelists, and the results reveal a relationship between appointments and the decision-making attitude of adjudicators. It further methodically maps the pool of ICSID panelists and answers the question ‘who are ICSID panelists?’ It reviews the evolution of the attributes of ICSID adjudicators, assesses the composition of the ICSID pool, and evaluates the social interactions of this group of investment treaty adjudicators. To address the challenges that investment treaty arbitration faces, a radical and multidimensional shift is occurring in the system. This transformation is directed towards greater control over the qualifications and conduct of adjudicators. These developments reconstruct the composition of the pool of adjudicators and influence how they interact with other actors in investment treaty arbitration proceedings. The ongoing reform progress indicates that the attributes and behavior of future investment treaty adjudicators would likely be different from the characteristics and conduct of the contemporary generation of panelists.
URI: http://hdl.handle.net/1828/14772
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitrators; Code of conduct; ICSID; Impartiality; Investment treaties; Investment treaty arbitration; Investments; Permanent court system; Qualifications; State practice

Climate change and development : the global administrative law of the UNFCCC financial mechanism - Larrea, Gonzalo (European University Institute, 2022)
This research deals with the legal responsibility of states to provide climate finance to developing countries in order to facilitate climate mitigation and adaptation. The research demonstrates that the area of climate finance has not escaped globalization, where global actors operating at a level beyond the state (the UNFCCC and several Climate Funds) have increasingly taken over some of the climate finance functions previously performed by states. Against this backdrop, the thesis also examines the role of international bodies in providing climate finance, assesses to what extent these bodies are accountable to affected local stakeholders, and puts forward recommendations to foster increased accountability. The research project employs Global Administrative Law (GAL) as a normative framework for assessing and fostering accountability. This thesis is relevant, first and foremost, as an examination of the extent to which global climate finance is adequate for addressing climate change impacts in developing countries. To this end, it engages in a detailed analysis of the international legal framework for climate change and of the relevant financial instruments. It also engages in a normative evaluation of these instruments using the standards proposed by GAL. In keeping with this, the research gives substance and a better definition to these standards. As such, the thesis has the potential to contribute not only to the literature on climate finance, but also to the literature on GAL. It also sheds light on the relationship between climate finance and GAL, a topic that has been largely neglected in the academic literature so far.
Accepted: 2022-03-02T09:10:59Z
Keywords: Climate Change; Climatic changes; Environmental Law

Letters of credit and demand guarantees : a legal study on the impact of targeted financial sanctions from a South African perspective - Lupton, Cayle Selwyn (University of Johannesburg, 2022)
The purpose of this study is to provide a legal analysis of the impact of targeted financial sanctions on letters of credit and demand guarantees. The letter of credit is an important method of payment used in international trade. The demand guarantee plays a significant role as an instrument of security in commercial transactions. In their simplest form both instruments constitute an undertaking by a bank to pay a beneficiary against delivery of certain stipulated documents. Letters of credit and demand guarantees are known to be reliable and provide a considerable measure of certainty and predictability to the underlying transaction. Consequently, they have been described as the “lifeblood of international commerce”. Targeted financial sanctions entail assets freezing and prohibitions to prevent funds or other assets from being made available, directly or indirectly, for the benefit of designated individuals and entities. Endorsed by the United Nations and implemented by the vast majority of jurisdictions around the world, targeted financial sanctions are increasingly being used to combat financial crime, including money laundering, terrorism financing and weapon proliferation financing. Banks play a critical role in financial crime prevention and detection. Hence they have been identified as institutions that must comply with targeted financial sanctions. The relationship between targeted financial sanctions and letters of credit and demand guarantees has generally not been well documented. It is hoped, therefore, that this study will make a meaningful contribution to the jurisprudence on letters of credit and demand guarantees. In investigating the impact of targeted financial sanctions, the study can be categorised into three parts. Part one investigates a bank’s compliance with domestic targeted financial sanctions. The chief findings of the study in this regard are that banks are under a legal obligation to comply with sanctions and, as a result, a bank that refuses to perform its contractual obligations under a letter of credit or demand guarantee may have a defence in law. In South African law the bank can raise the so-called defence of legal impossibility of performance to resist a claim for, or potential litigation in respect of, payment. Part two investigates a bank’s compliance with foreign targeted financial sanctions. Because compliance in this regard has no (legal) basis, the bank may conceivably be sued by the beneficiary for payment on the basis of breach of contract. Part three investigates problematic documentary practices that banks have adopted or conceivably may adopt to manage their sanctions risk exposure. In this regard, attention is given to so-called sanctions clauses and other non-documentary conditions. The issue of unjustified amendments by the beneficiary for the purposes of sanctions evasion is also considered in part three. The general conclusion arrived at is that by interfering with payment, targeted financial sanctions render letters of credit and demand guarantees unreliable, thereby having the effect of reducing their value to international trade and commerce. The author proposes certain recommendations and initiatives aimed at mitigating the impact of targeted financial sanctions on credits and guarantees. Key terms: letters of credit; demand guarantees; financial crime; sanctions evasion; targeted financial sanctions; compliance; banks; due diligence; payment; reimbursement; credits; guarantees.
Keywords: Banks; Compliance; Credits; Demand guarantees; Due diligence; Financial crime; Guarantees; Letters of credit; Payment; Reimbursement; Sanctions evasion; Targeted financial sanctions

Airport Charges Regulation: A Private Law Approach - Mei, Di (McGill University, 2022)
This thesis explores the regulation of airport charges, which is an important but marginalised topic. It particularly examines how private law instruments can play a role in the regulatory process. Airports used to be subject to traditional regulation, which operates in a command-and-control mode. As the airport industry becomes increasingly complicated, traditional regulation seems problematic. First, the method that is associated with traditional regulation to draw a line between regulated and unregulated airports has downsides. Second, the international regulatory framework on airport charges lacks binding rules. This suggests that traditional regulation is not the best niche for airport charges regulation. Third, good regulation needs independent regulatory bodies, which are hard to achieve in practice.In this context, this thesis argues that a private law approach can serve as a more flexible and effective way to regulate airport charges. There are two instruments under this overarching approach. First, contracts can be adopted to incorporate airport charges regulations. Second, robust corporate governance generates the effect of good regulation. This is an interdisciplinary work that has engaged air law, contract law, corporate law, competition law, and aviation business and management. It also employs the method of case studies. Chapter 4 examines the regulation of airport charges in the UK, Canada, and India. The three case studies demonstrate that private law instruments have been implicitly implemented to different degrees in these countries. These demonstrate the feasibility of applying private ordering in the regulatory process. I also look into the regulation of countries and regions including Australia, Ireland, the EU, and Germany throughout this thesis. This study also examines a specific sector of airport charges, namely, charges for ground-handling services. This sector possesses a unique feature in that it is between aeronautical and non-aeronautical services. A private law approach can also be adopted in the regulation of charges relating to ground-handling services. Additionally, ICAO as an important international organisation governing international air transport can also contribute to a private law approach of airport charges through its soft-law making function. This thesis aims to shed light on a private law approach, as an innovative regulatory mechanism, to airport charges. That said, regulation by this approach and traditional regulation are not contradictory but can cooperate to an extent, depending on how much power one wants to give to private ordering
Identifier: https://escholarship.mcgill.ca/concern/theses/8910k0504
Keywords: Airport; Regulation

Articulating clearer fair and equitable treatment clauses within Tanzania’s international investment agreements: correcting the disparity between host state and international investor interests - Ntangeki, Joanitha (Canterbury Christ Church University, 2022)
International Investment Agreements seek to promote foreign investment whilst protecting foreign investors. Despite the goal of International Investment Agreements being to secure parity between the interests of the host State and the foreign investor, there has been consequential disparity in the protection of the interests of both parties. Notably, the host State is susceptible to disadvantage. This research examines the extent to which International Investment Agreements in Tanzania have facilitated this disparity. In particular, the research evaluates the inclusion of fair and equitable treatment provisions in Tanzania’s International Investment Agreements and the extent to which fair and equitable treatment provisions have in some way facilitated this disparity. The research examines systematically the fair and equitable treatment provisions contained in twenty IIAs signed by Tanzania between 1965 and 2013 (eleven of which are still in force). The research takes a comparative approach in evaluating and contrasting the Tanzanian provisions with other fair and equitable treatment clauses in IIAs signed by India, Morocco and the Netherland. The Tanzanian provisions are vague and non-uniform in comparison. The research is situated in the broader context of national sovereignty and the relationship between Tanzania and its foreign investors under international law. The substance of the analysis centres on foreign investors in the mining sector in Tanzania and the extent to which these investors have sought to take advantage of the fair and equitable treatment clauses in the IIAs in order to pursue their activities to the detriment of local populations. The research evidences the negative impact of their claims that changes in government policy (often aimed at benefiting citizens) amount to unfair treatment of the foreign investor. This has a significant impact on the ability of the government to develop its policies around sustainable development, environmental protection and the guarantee of human rights of the citizens of the host State. The research demonstrates that a clearer and fuller articulation of fair and equitable treatment clauses within Tanzania’s IIAs can act as a corrective to the disparity between the host State and the international investor. This requires that IIAs are drafted to include an exhaustive and full list of the State’s obligations towards the foreign investor so as to limit foreign investor claims against the host State. The impact of not doing so has grave implications for the rights of the citizens of Tanzania and unnecessarily tips the balance of power in favour of the foreign investor and away from the host State. This undermines the ability of the host State to assert its sovereignty within its own borders.
Permalink: https://repository.canterbury.ac.uk/item/9714v/articulating-clearer-fair-and-equitable-treatment-clauses-within-tanzania-s-international-investment-agreements-correcting-the-disparity-between-host-state-and-international-investor-interests
Keywords: Foreign investment; International investment; Investor interest; Tanzania

Story of a legal codex(t) : writing law in code - Ma, Megan (Institut d'études politiques, 2021)
How is the law measured? For long, it appeared that the law cannot be measured. While there are standards and processes, the law was not regarded as quantifiable. Only in the advent of recent technological advancements in law have there been considerations for metrics. These technologies sought to tackle the legal field’s inherent protectionism fueled by deep asymmetries in information. Consequently, the rise in legal ‘metrics’ stems from an access to justice perspective. The assumption is that in making the law more quantifiable, knowledge that has been historically opaque and inaccessible outside of the legal community may be revealed.Alternatively, it may be argued that the law has always been measurable. Words, through linguistic devices, have shaped legal meaning. In effect, the law conceivably has been measured by its words. In fact, “law exists as text” (Hildebrandt, 2015). I further this line of thinking by investigating natural language as the key vessel through which the law has manifested itself. Does the law depend on natural language to do its work? Importantly, is the language sufficient at housing legal norms?This dissertation seeks to tell a narrative. Broadly, it chronicles the story of law’s intimate relationship with language. But more specifically, the thesis details the law’s recent encounter with the digital. When law met technology, its relationship with language changed, invoking skepticism around its fitness for the conveyance of legal concepts. With the introduction of an innovative player – code – the law had perceivably found its new linguistic match. As a result, code was tested for its ability to perform and accommodate for the law’s demands. Ultimately, confronted by natural language and code, the law is asked whether code can be its language. Comment mesure-t-on le droit ? Longtemps, le droit semblait résister à la mesure. Bien qu'il existe des normes et des processus, le droit n'était pas considéré comme quantifiable. Ce n'est qu'avec l'avènement des récentes avancées technologiques dans le domaine du droit que l'on a commencé à envisager une telle quantification. Ces technologies ont cherché à s'attaquer au protectionnisme inhérent au domaine juridique, alimenté par de profondes asymétries d'information. Par conséquent, l'essor de la "métrique" juridique découle d'une perspective d'accès à la justice. L'hypothèse est qu'en rendant le droit plus quantifiable, des connaissances historiquement opaques et inaccessibles en dehors de la communauté juridique peuvent être révélées.On peut également faire valoir que le droit a toujours été mesurable. Les mots, par le biais de dispositifs linguistiques, ont façonné la signification juridique. En effet, il est concevable que le droit ait été mesuré par ses mots. En effet, "le droit existe en tant que texte" (Hildebrandt, 2015). J'approfondis cette ligne de pensée en examinant le langage naturel en tant que vecteur clé à travers lequel le droit s'est manifesté. La loi dépend-elle du langage naturel pour faire son travail ? Plus important encore, le langage est-il suffisant pour abriter les normes juridiques ?Cette thèse cherche à raconter une histoire. De manière générale, elle relate l'histoire de la relation intime du droit avec le langage. Mais plus spécifiquement, la thèse détaille la rencontre récente du droit avec le numérique. Lorsque le droit a rencontré la technologie, sa relation avec le langage a changé, suscitant le scepticisme quant à son aptitude à transmettre des concepts juridiques. Avec l'introduction d'un acteur innovant - le code - le droit a visiblement trouvé sa nouvelle adéquation linguistique. En conséquence, le code a été mis à l'épreuve quant à sa capacité à fonctionner et à répondre aux exigences du droit. Finalement, confronté au langage naturel et au code, le droit se demande si le code peut être son langage.
Keywords: Connaissance du contexte; Contextual knowledge; Droit et informatique; Informatique; Langage juridique (informatique); Langages de programmation; Law and computation; Linguistics; Linguistique; Programming languages

Four Essays on Tax Transition Reform in Developing Countries - Adandohoin, Kodjo (Université Clermont Auvergne, 2021)
Ces dernières années, la plupart des pays en développement sont confrontés à la nécessité de concilier deux impératifs : d’une part, une demande sociale forte qui nécessite un besoin de ressources publiques supplémentaires, et d’autre part le désarmement tarifaire consécutif aux politiques d’ouverture commerciale, qui les prive de la majeure partie de leurs recettes budgétaires. D’où l’impérieuse nécessité pour ces pays d’assurer une transition dans la structure de leur prélèvement public c’est à dire de transférer la pression fiscale du commerce extérieur vers la fiscalité domestique. Cette thèse s’intéresse à cette problématique et vise à étudier les conditions de réussite d’un tel phénomène dans les pays en développement au travers de quatre essais empiriques. Le premier essai concerne le rôle de la TVA et des droits d’accises dans une première vague de transition. La TVA étant un impôt neutre et à très large assiette fiscale, cette dernière a été suggérée comme outil majeur pour réussir le transfert des ressources publiques du cordon douanier vers la fiscalité domestique et en complémentarité avec les droits d’accises. Nos investigations empiriques soutiennent cette assertion théorique et montrent que le couple TVA-accise joue bien ce rôle de substitut aux recettes de porte en quasi baisse suite au démantèlement tarifaire dans les pays. Néanmoins le rôle d’appui de la TVA et des droits d’accises est limité à partir d’un certain seuil de baisse des recettes de porte, qui traduit aussi le fait que le potentiel de mobilisation fiscale par la TVA dans ces pays est limité et qu’il faudra s’en préoccuper. Dans le second essai nous analysons la transition de seconde génération basée sur les impôts directs (impôts sur les revenus et impôts fonciers). Nous trouvons que les impôts directs sont des outils pauvres de transition fiscale dans les pays en développement. Pourtant, nous trouvons que le développement financier est un médiateur certain et incontestable à une politique de transition fiscale de seconde génération basée sur les impôts directs, car permettant de recouper l’information sur les revenus des contribuables et de générer des traces documentaires à l’administration fiscale, qui permettent d’envisager une mise à fiscalisation des contribuables, gage de recettes fiscales directes supplémentaires dans les pays. Dans le troisième essai, nous nous intéressons à l’effet de la mise en place d’une réforme de transition fiscale sur l’efficience dans la collecte des recettes en menant une étude de cas pour l’union économique et monétaire ouest africaine (UEMOA). Nos résultats supportent l’affirmative, en ce sens que la réforme accroit globalement une mobilisation efficiente des recettes dans la zone UEMOA. Cette efficience entrainerait par ailleurs avec elle une amélioration du climat des affaires dans la zone, suite à la mise en place de cette réforme. Enfin nous terminons cette thèse par un quatrième essai qui interroge quand à lui les impacts distributifs et de pauvreté d’une réforme de transition fiscale basée sur la TVA. Quoique les résultats montrent une incidence régressive de la réforme sur le revenu des ménages, une redistribution par la dépense aurait le mérite d’atténuer l’incidence sociale de cette stratégie de réforme sur le revenu des contribuables.
Keywords: 2SLS-IV model; Accises; Administration fiscale; Analyse des frontières stochastiques; Business climate; Climat des affaires; Computable general equilibrium; Contrôle Synthétique; Coordination fiscale; Corporate tax; Developing countries; Développement financier; Efficience; Efficiency; Effort fiscal; Excise; Exemptions; Exonérations; Financial development; Fiscalité; GMM; Harmonisation; Harmonization; Impôt foncier; Impôt sur le revenu; Impôt sur les sociétés; Income tax; Inequality; Internet; Inégalités; Micro-simulation; Modèle 2SLS-IV; Pauvreté; Pays en développement; Politique fiscale – Pays en voie de développement; Potentiel fiscal; Poverty; Probit and Logit; Probit et Logit; Propensity scores; Property tax; Réforme fiscale; Scores de Propension; Stochastic frontier analysis; Synthetic control; TVA; Tax administration; Tax coordination; Tax effort; Tax potential; Tax reform; Tax transition; Taxation; Taxes sur le commerce extérieur; Trade taxes; Transition fiscale; VAT; Équilibre général calculable

Abuse of dominance and the Internet : an assessment of the South African Regulatory Framework - Koornhof, Pieter Gerhardus Jacobus (Stellenbosch University, 2021)
While electronic commerce in South Africa is still comparatively small, it is growing rapidly. The advent of the internet has potentially fundamental impacts on business and the law both locally and internationally. It is submitted the free competition on the internet is important and will continue to be so in the future. The research in this thesis relates to the rise of so-called internet monopolies (such as Google, Facebook and Amazon) and its implications for competition law enforcement. A particularly problematic aspect of the products provided by some of these companies is that their products and services are ostensibly free to consumers. This thesis examines whether the traditional model for the regulating abuse of dominance would be effective in the instance where such an internet monopoly is charged with a contravention under South African competition law. The research and analysis in the thesis are effectively divided into three parts. The first considers whether abuse of dominance related to the internet deserves closer analysis and also assesses the purposes of competition law and how these are changing (or should change) in the light of new technology and markets. The second part deals with abuse of dominance both generally and specifically in relation to the internet. In this context, the thesis considers how harms may manifest and how dominance may be determined in the context of the internet. The final part considers specific issues that may be problematic in light of the internet. The interrelationship between intellectual property and competition law is analysed, along with aspects pertaining to the assertion of jurisdiction, the nature of competition law enforcement and the extent to which different jurisdictions may (and/or should) cooperate in dealing with abuse of dominance on the internet. The thesis submits that the South African legislative framework for regulating abuse of dominance on the internet is broadly fit for purpose, but that there is a need for developing new approaches and policy within that framework. It contributes to the existing body of knowledge and discourse by providing a comprehensive overview of the regulatory framework in South Africa, informed by comparative analysis; by applying this in a new context (hitherto under-researched in the South African context), and by offering concrete suggestions to frame policy and approach.
URI: http://hdl.handle.net/10019.1/123687
Keywords: Competencia; Competition law; E-commerce; Electronic commerce; Internet monopolies; South African competition law; South African legislative Framework

Botswana’s Anti-Money Laundering and Combating the Financing of Terrorism Regime - Tshiamo-Kgati, Kuda (University of Pretoria, 2021)
Money laundering, the financing of terrorism and proliferation financing continue to be serious threats to the stability of the international financial system. The international community therefore has prioritised the fight against these activities. For example, international bodies such as the Financial Action Task Force (FATF) and others have developed standards and recommendations against which countries and organisations are measured in this regard. Against this background, this thesis investigates to what extent Botswana’s legislative framework regarding money laundering, terrorism financing and other illicit financial flows complies with international standards, especially the FATF Recommendations. The study sets the scene by defining and describing money laundering, financing of terrorism and proliferation financing, after which the current statutory framework in Botswana is discussed in detail. After subsequently setting out the various global and regional (specifically African) initiatives in the fight against money laundering and other financial crimes, the current state of affairs in Botswana is benchmarked against both the South African framework as well as the FATF Recommendations. The investigation is limited to a technical assessment (doctrinal analysis) of Botswana law to determine the current compliance (or lack thereof) of the country’s statutory provisions and to make recommendations regarding how the framework can be improved. It is difficult for some countries, especially African countries like Botswana, to comply fully with the FATF Recommendations, since compliance can be expensive and dependent on high levels of expertise on the part of the relevant authorities. Therefore, such more vulnerable countries tend to face a higher risk of being used as conduits for money laundering and related activities. Despite these and other challenges, Botswana has gone to great lengths to re-assess and improve its anti-money laundering and combating the financing of terrorism (AML/CFT) legislation with a view to move towards full compliance with the FATF Recommendations. Nevertheless, the evaluation indicates that there are some remaining shortcomings in Botswana’s legislation. Consequently, the thesis concludes by proffering certain recommendations towards ensuring that Botswana’s AML/CFT legislation is rendered fully compliant with the FATF Recommendations.
URI: https://repository.up.ac.za/handle/2263/82675
Keywords: AML/CFT; Anti-money laundering; Botswana; Financement du terrorisme; Financial law; LBC/FT; Lutte contre blanchiment de capitaux; Money laundering

Challenges and solutions for the harmonisation of contract law within the BRICS countries. Invalidity of contracts and hardship - Veronese, Lígia Espolaor (Universidade de São Paulo, 2021)
The present thesis is concerned with a comparative study of contract law applicable in the BRICS countries Brazil, Russia, India, China and South Africa with a strong focus on the issues of invalidity of contracts and hardship. The purpose is to identify commonalities and divergences in these systems with different legal backgrounds, particularly the influence of civil law tradition in Brazil, Russia and China as opposed to common law in India, and the mixed system in South Africa. Among the identified divergences and challenges, the thesis purports to demonstrate that the obstacles are not insuperable and that there are rooms for the harmonisation and compatibility within the BRICS context with respect to the two selected topics of contract law. Even when full harmony is not reached, the research also purports to demonstrate that some countries may benefit from others divergent experiences. Detecting mutual contribution is of particular relevance to this group of countries, since they share the characteristic of being evolving systems which have undergone recent reforms in their legislation on contract law and may be more open to assess and incorporate more efficient contract practices.
Keywords: BRICS; Brazil; Common law vs. Civil law; Comparative law; Contract law; Contribuição; Contribution; Direito comparado; Direito contratual; Hardship; Harmonisation; Harmonização; Invalidade dos contratos; Invalidity of contracts; Russia; South Africa; Validade dos contratos; Validity of contracts

Firm Performance, Financial Constraints, and Dual-Class Share Structure - Ahamed, Fatematuz Tamanna (Victoria University of Wellington, 2021)
This thesis addresses two aspects of financial constraints focusing, firstly, on the impact of financial constraints on firm performance and, secondly, on the impact of dual-class share structure on financial constraints. The first issue has been addressed in a large number of research studies, but the results are mixed. This study, therefore, conducts a meta-analysis of those earlier studies to provide a summary view of the results which, in contrast to narrative reviews of the empirical literature, provides an objective overview. The second issue examines the impact of dual-class share structures on financial constraints. The period of the global financial crisis is used to test the impact of the state of the economy on that relationship. To examine the impact of financial constraints on firm performance, 26 empirical studies with 189 effect sizes representing listed firms have been analysed. The study finds that overall there is a positive relationship between financial constraints and firm performance. The study also shows that the set of market-based measures of firm performance has a significant negative impact on the relationship, compared with the set of accounting-based measures. In terms of the financial constraints measure, the set of external financial constraints measures have a positive and highly significant impact on the relationship. The meta-regression analysis suggests that the choice of measure, regional difference, journal quality and publication status all have a significant impact on the relationship, and explain the variation in the association. To examine the impact of dual-class share structures on financial constraints the study analyses a sample of non-financial US firms over the period 2002-2018. Share structure is measured by the existence of a dual-class structure and also by excess voting rights and the proximity of the superior class shareholders in such structures. The study also shows that if financial constraints are measured by the WW index, irrespective of how dual-class share structure is measured, it increases the level of financial constraints. Similar results are obtained where financial constraints are measured by the KZ and SA indexes, except where dual-class share structure is measured by the proximity of superior class shareholders. The study also finds that if financial constraints are measured by the WW index, dual-class had a reduced impact during the period of the global financial crisis, thus, providing support for the propping theory. However, if financial constraint is measured by the SA index, dual-class share structure appears to have an increased impact during the GFC years. Among the additional tests, the HM index has been used as a measure of financial constraints, and the findings show that the impact of dual-class structures on financial constraints appears to be driven by their effect on debt constraints. The study also shows that firm age moderates the impact of dual-class share structures if financial constraints are measured by the WW index. The KZ, WW, and SA indexes are based on firm characteristics and, therefore, the study also tests for an impact of dual-class structures when financial constraint is measured by a text-based index, the BLM index. However, the results do not provide evidence of an impact in that case.
Keywords: Dual-class share structure; Financial Accounting; Financial Constraints; Firm Performannce; Meta analysis

Value Relevance of Integrated Reporting using a Novel Approach: Comparative Cross Country Evidence of Mandatory and Voluntary Implementers - Mohaimen, F. J. (Victoria University of Wellington, 2021)
This thesis examines the value relevance of accounting information under integrated reporting (IR) in a comparative mandatory and voluntary setting. A meta review is conducted of all published work focusing on integrated reporting since 2011, which provides detailed insight into the gaps in the IR literature. Multiplicative log-linear model is used in measurement, which is a novel technique that mitigates the shortcomings of traditional value relevance models. The findings show that value relevance of summary accounting information increases after the implementation of IR in the mandatory setting. In the voluntary setting, market effect and the existing reporting paradigm effect the value relevance of accounting information under IR. If the market is large and existing reporting requirements are robust voluntary adoption of IR has minimal to no effect. However, in smaller markets with less rigorous reporting environment, adoption of IR does result in increased value relevance of accounting information. Compared to traditional models, the multiplicative model provides estimates that are more stable over time and shows better explanatory power. Overall, the findings of this thesis show that capital providers value the information content of IR under specific circumstances. This thesis contributes to the IR and value relevance literature by providing the first comparative cross-country evidence of the effect of IR in the change in value relevance of reported accounting information. It provides policy relevant input to the standard setters of IR by demonstrating the effect of IR in the decision usefulness of summary accounting information. The thesis further provides robust evidence of the efficacy of using the multiplicative log-linear model in measuring value relevance instead of the traditional linear additive models.

Compensation for Regulatory Expropriation in International Investment Law - Khachvani, David (Université de Genève, 2021)
The States, international organizations and interest groups are increasingly concerned with treaty claims of foreign investors, who sometimes seek compensation for the States' legitimate regulatory measures, such as tobacco plain packaging, nuclear energy phase out and environmental regulations. International investment law has yet to develop a comprehensive and predictable framework addressing some of the basis questions related to compensability of legitimate regulatory measures. The thesis carries out a comparative legal analysis to identify the key features of the prohibition of uncompensated expropriation as a general principle of law, and explores the rationale of that principle in political philosophy. Equipped with the results of this analysis, it proceeds to propose an analytical approach addressing practical questions related to the compensatory protection of foreign investments.
Keywords: Climate Change; Compensation; Expropriation; Investments; Police Powers; Regulatory Powers

A developing country's perspective on forum shopping and long arm jurisdiction in light of US and UK insolvency laws - Gatoto, Phoebe Njoki (Nottingham Trent University, 2021)
The trend for multinational companies has been a preference to forum shop rather than to open insolvency proceedings in developing countries. The US and the UK are prime venues for such bankruptcy tourism enabled by long-arm jurisdiction through extraneous connection. At the same time, there has been a pattern in developing countries of insolvency law reforms which have been circumvented when multinational companies forum shop. Using doctrinal and comparative methodologies, this thesis examines how forum shopping and long-arm jurisdiction to the US and UK affect the efforts of developing countries to reform their insolvency laws and their possible effects on local stakeholders of multinational companies in developing countries. Additionally, the thesis proposes a longer-term strategy of dealing with forum shopping and long-arm jurisdiction by using the concept of centre of main interests ('COMI') as the basis for opening main insolvency proceedings. To ensure that the proposed insolvency procedural legal law is implemented uniformly, the thesis proposes the creation of a supranational court from which national courts, insolvency practitioners and multinational companies can request clarifications on the provisions of the proposed insolvency procedural legal framework. The thesis identified that developing countries require effective insolvency laws and institutions and highlighted key principles that should be included in the reforms. The hope is that developing countries can improve their insolvency laws and institutions to a global standard. Once the proposed insolvency procedural legal framework is implemented, multinational companies will be encouraged to utilise them once jurisdiction is identified through the COMI test rather than forum shopping.
https://irep.ntu.ac.uk/id/eprint/46506/

Corporate Social Responsibility, Corporate Governance and Banking Performance in the CEMAC Region - Fondem, Divine (Liberty University, 2021)
This researcher examined the effect of corporate governance (CG) and corporate social responsibility (CSR) on banking performance in the Central African Economic and Monetary Community (CEMAC) region. The data was obtained from the Worldwide Governance and the World Bank sovereign database from 2003 to 2018. This study employs the z-score to proxy the CSR factors such as labor force participation rate, population density, and renewable energy. The results reveal that the fixed effects model is superior to the pooled ordinary least square (OLS) and the random-effects model. The findings show that CSR has a significantly positive relationship, while CG has a positive but insignificant relation with banking performance in the CEMAC region. It suggests an ineffective implementation of CG strategies in the entire CEMAC region.
Keywords: Banking Performance; CEMAC; CSR; Central Africa Economic and Monetary Community; Corporate Social Responsibility; Corporate governance; RSE

Legal Challenges in the Enforcement of Foreign Arbitral Awards in Nigeria - Kudirat, Magaji (University of Ilorin, 2021)
Businessmen have a choice in the resolution of disputes, they may elect litigation or submit to arbitration. Delays, outrageous cost and undue technicalities associated with courts, makes commercial arbitration the preferred mode of settlement in the business world. However, the recalcitrance of an award-debtor to comply with the terms of the award necessitates the intervention of the courts. Nigeria has provisions for enforcement of foreign arbitral awards within her legal system. However, reliance on courts for enforcing foreign awards frequently frustrates the gains initially made by arbitration. Enforcement of arbitral awards via the courts has numerous legal challenges. This study is therefore aimed at analysing the challenges facing enforcement of foreign awards in Nigeria. The objectives of the study were to: (i) analyse the impact of extant legal regimes on the recognition and enforcement of foreign awards in Nigeria; (ii) examine the effects of the concepts of arbitrability and public policy exceptions on the enforcement of awards in Nigeria; (iii) examine the challenges inherent in judicial review on the enforcement of foreign awards in Nigeria; and (iv) examine the adequacy of the Arbitration and Conciliation Act 1988 (ACA 1988) in the recognition and enforcement of Islamic commercial arbitral awards. The study employed doctrinal methodology of legal research where primary and secondary of legal materials were subjected to descriptive and content analysis. The primary sources used were legislations, regulations, treaties, conventions and case laws, while secondary sources used were texts books, journals, internet materials, conferences and seminars papers. The findings of the study were that: i. the provisions of the laws regulating enforcement of foreign arbitral awards in Nigeria, particularly, Sections 51 and 54 of ACA 1988 have inherent and procedural defects, thus preventing the smooth enforcement of the award; ii. the narrow interpretation by the Nigerian courts on ‘arbitrability’ based on Sections 54 and 57 of ACA 1988 which restricts disputes to contractual and commercial disputes only, prevents the enforcement of foreign awards from jurisdictions with liberal interpretation. iii. the amorphous nature of the scope of public policy creates a challenge for the courts in Nigeria in determining whether a foreign award violates the country’s public policy or not; iv. the powers of the courts to set aside foreign awards based on grounds contained in Sections 29, 30 and 48 ACA 1988 are open-ended and allow the courts to examine the merit of the disputes rather than limit themselves to the validity of the award for enforcement; v. the provisions of ACA 1988 on enforcement of foreign arbitral awards do not consider the idiosyncrasies of awards from Islamic law jurisdictions, despite growing investors’ interests in Islamic commercial transactions. The study concluded that it is obvious that the various legal challenges identified showed that the existing legal frameworks on enforcement of foreign arbitral award in Nigeria are weak and ineffective. The study therefore recommended that the Nigerian arbitral laws in particular, the provisions on enforcement of arbitral awards under ACA 1988 should be amended.
Keywords: Enforcement; Foreign Arbitral Awards; Legal Challenges; Nigeria

The legal nature of debt securities in South African law - Beer, Johan Philip de (Stellenbosch University, 2021)
The problem statement of this thesis is ascertaining the legal nature of debt securities in furtherance of a consistent and coherent legal description of the South African positive law as it relates to this class of instruments. It focuses on four core issues: the legal history, legal nature, classification, and current legal issues relating to debt securities. Historical and analytic-systemic approaches to the problem statement make up Part 1 of the study. The historical approach shows an emergent commoditisation of debt, which is an important phenomenon in the analysis of securities law. It further shows a great deal of English influence in the development of the South African legal environment, most notably in terms of company law (as the primary driver of securities law) and the financial marketplace, its institutions and its regulation. Also highlighted is a notable scarcity of debt securities relative to equities, which materially impacted legislative developments. Finally, it points to an increase in the legal importance of the “securities” concept as a legal term to describe and govern debt and equity securities. Thereafter the analytic-systemic approach is used to identify a set of private law-rooted first principles applicable to South African registered securities, and herefore to debt securities as well. It posits that these securities should be understood conceptually as comprised two interdependent but functionally separate legal objects, rather than in terms of two different kinds of ownership (i.e. beneficial and registered). The first object is the "security instrument”, a locus for (holdership of) the incidents that flow from the entitlement of determination (beskikkingsbevoegdheid) over the underlying complex of rights and competencies of registered securities. These can be understood as incidents of execution. The second is the "security asset”, a locus for (holdership of) the incidents that flow from the entitlement of enjoyment (genotsbevoegdheid) over that underlying complex, and corresponds with the proprietary, patrimonial dimension of securities. These can be understood as incidents of enjoyment. This construction enables a more coherent understanding of the sui generis relationship of agency between beneficial owner and her nominee, as well as of the dynamics of ownership and quasi-possessio. These insights are then applied to the uncertificated environment, addressing a number of difficult and uncertain problems within the system that enables uncertificated securities and their holdership. Finally the particularly difficult issue of how to classify (and therefore identify) debt securities is dealt with. Here it is concluded that a typological approach is the only viable methodology to deal with this problem, and a number of necessary and thereafter possible classificatory indicia are outlined for this purpose. The functional-policy approach makes up Part 2 of the study. It is a policy-aware application of the theoretical framework developed to a select number of themes and legal issues of the current environment. Principally it shows that the reconceptualisation of registered securities has explanatory and problem-solving value, specifically relating to transfer, the granting of limited real interests, good faith acquisition, and the protection of holdership of certificated and uncertificated securities.
URI: http://hdl.handle.net/10019.1/110018
Keywords: Beneficial ownership; Debt and equity Securities; Securities; Securities industry; South Africa; Titre de créance

The impact of multilateral trade agreements on intra-regional trade : the case of SADC and ECOWAS - Osarumwense, Uwakata Yvonne (University of South Africa, 2021)
This study examines the comparative impact of multilateral trade agreements on intra-regional trade in the Southern African Development Community (SADC) and the Economic Community of West African States (ECOWAS) regions in Africa. Annual data was gathered from 2000 to 2018 and dynamic panel data and econometric techniques were used to control for individual country characteristics, endogeneity, serial correlation, heteroscedasticity and interdependencies between the countries in each region. Two estimations were done, one using the tariff measures of multilateral agreements, the second using non-tariff measures of multilateral agreement. The results of the empirical analysis show that the SADC region has a slight edge over ECOWAS in terms of technological progress and investment, especially in trade infrastructure. However, the ECOWAS levels of employment and economic growth are higher than those in the SADC region. These differences further translate into differences that drive intra-African trade in these regions, and how they relate to the role of multilateral agreements in intra-African trade in each of these regions. While technology and investment are key drivers and enhancers of intra-African trade in SADC countries, economic growth and employment stand out as key enhancers of intra-African trade in ECOWAS, especially where multilateral agreement is represented by tariff measures. This study reports that when non-tariff measures are used to represent multilateral agreements, export trade costs, in addition to investment and technology, are the key drivers of intra-African trade in SADC countries. For ECOWAS, under non-tariff measures of multilateral agreements, only economic growth drives intra-African trade.
Keywords: Commercial treaties; Customs unions; Institutional environment; Intra-African trade; Investments; Multilateral agreement; Panel data estimation; Tariff and non-tariff trade barriers

The influence of capital structure and profitability on the solvency of nascent SMEs - Amoa-Gyarteng, Karikari (University of Johannesburg, 2021)
Even though small and medium enterprises contribute significantly to the growth of national economies, they are vulnerable in their early stages and may fail. Hence younger businesses are more likely to fail than more established ones because they face complex challenges that may limit their viability. This is a notion established in the liability of newness framework. According to the liability of newness concept, the precarious existence of emerging organisations is due to difficulties in managing relationships among strangers, not quickly assembling resources, and not coping with difficult environments, among other issues. All these elements notwithstanding, previous literature suggests that small businesses can, and sometimes do engage in techniques or approaches to help reduce the liability of newness, such as raising adequate capital. This study suggests that not only is adequate capital important but that the right mix of capital also results in higher solvency, thereby mitigating the liability of newness. Because the various funding forms have distinct advantages and disadvantages, an appropriate capital structure reduces the cost of financing while increasing the value of the firm. This study also advances the idea that profitable businesses are productive and financially strong, and thus nascent enterprises with high profitability can minimise the liability of newness. As a result, the study sought to examine the influence of capital structure and profitability on the solvency of nascent small and medium enterprises. To put the study's hypotheses to the test, 1106 nascent small and medium enterprises that are registered with the National Board for Small Scale Industries were sampled across three major cities in Ghana. Thus, data was gathered from every member of the population. Such data, gathered from the SMEs' financial statements, was submitted to preliminary screening as well as a number of statistical measurements. Operationally, the dependent variable, solvency, was defined as the solvency ratio, working capital ratio, and net worth. As a result, three distinct regression models were developed for robustness. The study's findings broadly indicate that capital structure and profitability have an influence on the solvency of nascent small and medium enterprises. The study also determined that emerging small and medium enterprises should follow the principles of the pecking order theory to reduce the liability of newness. These findings, if adopted by SME owners, can aid in the maturation of their fledgling businesses.
Keywords: Entrepreneurship; New business enterprises

Securities regulation, enforcement and market integration in the development of sub-Saharan Africa's capital markets - Aziza, Onoriode Reginald (University of Oxford, 2021)
This thesis examines securities market development in sub-Saharan Africa, focusing on securities law, securities law enforcement and securities markets integration. Adopting a primarily comparative methodology, the thesis examines the continued relevance of securities markets in sub-Saharan Africa; the way selected countries in the region regulate their markets and enforce compliance with securities law; and the potential of market integration to promote market development. This thesis advances 4 main claims. First, empirical evidence supports the link between liquid securities markets and economic growth, independent of the level of banking development. In this sense, securities markets can act as good complements to banks in providing capital to the real economy. Second, at the minimum, there is an arguable preliminary case that rules of securities regulation can hinder market development in select countries in sub-Saharan Africa, by imposing high compliance costs and eligibility requirements, without commensurate benefits in greater liquidity or reduced cost of capital. Third, enforcement of securities regulation in sub-Saharan Africa is generally weak. Whilst public regulators often have formal powers, budgets and staff; actual enforcement activity is sometimes limited by inadequate market monitoring and reliance on criminal as opposed to administrative sanctions. Poor public enforcement, in turn, reinforces poor private enforcement, leading to reduced market participation, illiquidity, and ultimately market underdevelopment. Fourth, although increased market integration can go a long way in facilitating market development in the region, integration cannot be a short/medium term solution to market underdevelopment in sub-Saharan Africa, given the significant economic, political and socio-cultural barriers to integration initiatives in the region. Ultimately, to develop their securities markets, policymakers in sub-Saharan Africa must focus their attention on making and credibly enforcing market-friendly rules of securities regulation. The thesis explores some ways this may be realistically accomplished.
Keywords: Africa; Capital Markets; Capital market; Developing countries; Fintech; Going public (Securities); Market Integration; Securities; Securities Law; Securities Law Enforcement; Sub-Saharan Africa

A constitutional analysis of a differentiated tax treatment of residents and non-residents in respect of income deriving from immovable property in South Africa - Baines, Daniel (University of Pretoria, 2021)
A constitutional analysis of a differentiated tax treatment of residents and non-residents in respect of income deriving from immovable property in South Africa', Daniel Baines explores whether South African resident taxpayers' constitutional rights to equality and property are infringed by current laws which tax residents at higher rates than non-residents on rental income and proceeds from the disposal of fixed property. He aptly sets out what the right to equality and property entails and how these relate to taxpayers. He finds that the higher effective tax rates paid by residents violates their constitutional right to equality. The thesis provides valuable insight into a resident's right to equality and property in terms of current tax rates and illustrates how current tax rates are unconstitutional. The recommendations brought forward contribute toward the discussion of how tax rates should be altered in order to ensure that residents' constitutional rights are no longer violated.
URI: https://repository.up.ac.za/handle/2263/82750
Keywords: Immovable property; Income tax; South Africa; Tax treatment

The arbitration of internal trust disputes in English law: Legal challenges and pathways - Clover Alcolea, Lucas (McGill University, 2021)
The arbitration of internal trust disputes has attracted significant attention in the arbitration and trust law communities in recent years with draft clauses and rules produced by arbitral institutions, several states undertaking legislative reform in order to provide such arbitrations with a statutory basis and numerous scholars as well as practitioners writing articles on the subject. Such enthusiasm is justified on the basis that arbitration has several advantages over litigation, such as confidentiality, international enforceability of judgments, the ability to choose one’s judge and the power to tailor the procedure. Notwithstanding these advantages, trust arbitration has failed to make any great inroad into trust disputes due to the many novel and complex points of legal practice and theory which it entails. For example, although arbitration does not typically involve minors or legally incapable parties’ trusts do, and thus trust arbitration raises numerous due process and human rights concerns. Similarly, court supervision and enforcement of trusts is sometimes considered essential to the very nature of trusts and questions therefore arise concerning the extent to which arbitral tribunals could supplant courts in that regard. Another complication is that trusts are not contracts and questions therefore arise about how to bind individuals to a trust arbitration agreement, particularly as regards beneficiaries who may be unascertained, minor or legally incompetent at the time the trust was created. The aim of this thesis is to analyse and present potential solutions to these complications from an English law perspective, although other common law legal systems will be analysed where relevant
Identifier: https://escholarship.mcgill.ca/concern/theses/x346d9718
Keywords: Arbitrage; Arbitragem; Arbitration; Internal trust disputes

Optimising regulatory responses to consumer disempowerment over personal data in the digital world - D'Amico, Alessia (European University Institute, 2021)
This thesis addresses the problem of individuals’ lack of control over personal data in the digital world. It sheds light on market and regulatory failures that lie behind the status quo and proposes a framework to improve regulatory responses. The two regulatory regimes that are at the core of this thesis are EU data protection regulation, which protects individuals’ fundamental rights over data, and EU competition law, which safeguards the sound functioning of the market and consumers’ economic interests. Despite the existence of these two regulatory regimes, individuals do not have sufficient control over personal data collected by digital firms, whose control over large datasets is a factor contributing to market monopolisation. The thesis argues that one reason for the shortcomings of today’s regulatory framework is that the market failure is composed of a combination of factors, which are currently addressed by the different regimes relatively independently. This dichotomy hinders the development of an effective strategy to tackle the market failure in its entirety. The approach taken in this thesis is that by integrating the two regimes, it might be possible to close the gaps deriving from a narrow perception of their regulatory spaces. Hence, the thesis formulates a holistic approach, encompassing data protection regulation and competition law, designed to increase the effectiveness of the regulatory framework as a whole. Different dimensions of the regimes’ interrelation are analysed, to uncover new ways to harness their complementarity and minimise their inconsistencies and overlaps. The thesis looks at how the regimes can incorporate elements from each other to inform their policies and application of their rules, as well as developing a complementary enforcement strategy. The holistic framework ultimately allows both regimes to better tailor their regulatory responses to the functioning of the digital market and take account of the diverse elements that constitute the market failure they seek to correct.
Accepted: 2021-07-07T10:12:30Z
Keywords: Data Protection; Personal data; Privacy

The conflict of jurisdiction between intra-EU BITs and European law: proposal for an EU investment court - Lewis, Krystle (Canterbury Christ Church University, 2021)
This work aims to find a practical solution to the problem that exists between intra-EU Bilateral Investment Treaties (BITs) and European Union (EU) law over conflict of jurisdiction issues. Currently, there is a problem as the EU Commission has rendered intra-EU BITs incompatible with EU law. This work argues that the current conflict of jurisdictional problems within investment agreements can be overcome by the creation of an EU investment court. The reliance on this court for the resolution of this conflict, as opposed to private law mechanisms, is important as it is the way forward in handling the conflict of jurisdiction issue at its best. This work argues that an EU investment court will be a panacea to the current problems concerning the conflict of jurisdiction. These problems will be presented through a positivist method where the law is analysed in its current form, highlighting its current weaknesses and resolving these weaknesses by proposing recommendations for such a court through a comparative examination of other international courts that fulfil a similar dispute resolution function, namely the Organisation for the Harmonisation of Business Law in Africa (OHADA) and the Unified Patent Court (UPC) and the World Trade Organisation (WTO). The purpose of this work is manifold. The work will provide an analytical examination of the relationship between EU law and international obligations within intra-EU BITs. It will further explore and assess the viability of a range of alternative solutions to intra EU BITs enforcement within the EU. It will additionally examine the operation of the OHADA, the UPC and the WTO to inform the proposal of an EU investment court. This is important as the outcome of these examinations will support the argument made in this thesis. It will also impact dispute resolution beyond academia by providing a practical solution to alleviate the current challenges with intra-EU BITs. The recommendations thus can inform changes for lex ferenda.
Permalink: https://repository.canterbury.ac.uk/item/94574/the-conflict-of-jurisdiction-between-intra-eu-bits-and-european-law-proposal-for-an-eu-investment-cour
Keywords: Bilateral Investment Treaties (BITs); Investissements; Investments

Optimising the legal regulation of circular labour migration between South Africa, Lesotho and Zimbabwe - Matete, P. (North-West University, 2021)
Circular labour migration is steadily gaining prominence the world over, primarily due to the benefits it offers to the migrants, to the sending country, and to the receiving country – the so-called "triple-win" benefits. In order to enhance the benefits of circular labour migration, both the International Labour Organisation and the International Organisation for Migration recommend that adequate instruments of governance should be utilised. From the outset, this thesis recognises bilateral labour arrangements as the ideal instruments for enhancing the potential benefits that circular labour migration offers to the stakeholders involved in the process. As far as could be established, there has been no comprehensive research that seeks to provide insights on how the selected countries in the Southern Africa Development Community (South Africa, Lesotho and Zimbabwe) could optimise the benefits of circular labour migration for all stakeholders, primarily through the use of bilateral labour arrangements. The need for these insights in Southern Africa is pertinent due to the absence of a contemporary and clear framework regulating circular labour migration in the region. Based on the foregoing, this thesis advances the proposition that the guidelines provided by international law and standards of labour migration, and the best practices in Spain and New Zealand, can provide significant insights on how South Africa, Lesotho and Zimbabwe can enhance the regulation of circular labour migration to provide optimised benefits for all stakeholders. Proceeding from the above premise, this thesis makes a number of findings. These include the affirmation that bilateral labour arrangements are indeed the key regulatory instruments for promoting the triple-win benefits that circular labour migration offers; that circular labour migration, if managed well, plays an instrumental role in development in both the sending countries and the receiving countries; and that three key areas should be addressed in bilateral labour arrangements in order to effectively promote triple-win benefits. The three key areas that need to be addressed in bilateral labour arrangements in order to enhance the benefits for all stakeholders are linking migration with development, migration governance, and the protection of the rights of migrant workers. This thesis outlines the various principles that are necessary to give effect to these three key areas. This thesis finds that, based on the guidelines provided by international law and standards, it is essential that bilateral labour arrangements, at the minimum, incorporate provisions that facilitate skills training, the return and reintegration of migrants, the transfer of remittances, and the promotion of human resources development. In this regard, this study finds that the bilateral labour arrangements between South Africa and its neighbours, Lesotho and Zimbabwe, fall short of the guidelines provided by international law and standards on labour migration and by the best practices in New Zealand and Spain. The original contribution of this study lies in it being the first study to comprehensively explore the legal measures that South Africa, Lesotho and Zimbabwe could utilise to optimise the regulation of circular labour migration to South Africa as the main receiving country in SADC. This study makes recommendations on how the labour migration legal framework between the three countries can be improved, based on lessons learned from international law and standards on labour migration and best practices from selected countries.
Keywords: Bilateral arrangements; Circular labour migration; Droit du travail; Labour law; Migrant workers; Remittances; Travailleur migrant

Challenges for Responsible Investment in the retirement benefits sector of Kenya - Mathenge, Elizabeth (Victoria University of Wellington, 2021)
Responsible investment (RI) is the investment strategy that incorporates environmental, social and governance (ESG) factors into the investment decision-making process (Hebb, Hawley, Hoepner, Neher, & Wood, 2015). RI has shifted from what was considered a niche market to become one of the fastest-growing areas of finance in many parts of the world (PRI, 2019b). However, a closer look at the development of RI and adoption rates in countries and regions reveals that RI is not commonly practised in sub-Sahara Africa (except for South Africa). This study explores the critical challenges for RI development in the retirement benefits sector of Kenya and, by engaging with a variety of key stakeholders, proposes how to overcome the identified challenges. It contributes to the literature on challenges for RI in a developing country by offering an in-depth case study of the retirement benefits sector.My study employs qualitative methods to collect and analyse data collected from semi-structured interviews with 22 participants (asset managers, regulators and capital market experts, and a council member of the Association of Retirement Benefits Schemes of Kenya) as well as a collection of published documents by government agencies in Kenya. Also, I analysed 10 annual reports to assess the kind of ESG information that is disclosed by listed companies. My study explores, in particular, how actors in the retirement benefits sector conceptualise RI. It identifies the leading ESG factors in Kenya and draws on the business-case approach to RI to explore whether the participants consider those factors as material risk factors that present both risks and opportunities to the investment decision-making process. Further, my study identifies the specific barriers for RI development and proposes how to overcome them. The findings show that participants define RI using several terminologies. This is consistent with the existing literature. My study finds that all participants consider corporate governance as a material risk factor that can impact the financial returns of a portfolio. However, most of the asset managers do not think that the environmental and social factors can present material risk factors to their investment decision-making process. Although over a third of the asset managers recognise that the environmental and social issues in Kenya present business opportunities to retirement benefits schemes, there is a shortage of well-structured assets in those areas. Further, this study identifies five specific barriers for RI development: diversification challenges; a lack of ESG data; a lack of demand/incentives; short-termism; and the demand for high financial returns and a lack of awareness and expert knowledge of RI practices. My study recommends that the National Treasury of Kenya develops RI policy for the entire finance sector. In addition, the findings support a recommendation for the Capital Markets Authority and the Retirement Benefits Authority to embark on capacity building programmes to educate the actors in the finance sector on RI strategies and to create awareness of the impact of ESG on financial returns in the long run.
Keywords: Investment and Risk Management; Kenya; Responsible investment; Retirement benefits schemes

Governance of non-bank systematically important financial institutions - Morbee, Katrien (University of Oxford, 2021)
This thesis identifies the circumstances under which corporate governance regulation can help gain traction to minimise systemic risk. Systemic risk is the risk that local losses spread through the financial system and badly affect the financial system and the real economy. Excessive risk-taking by financial institutions can contribute to such systemic risk. Prudential regulation and supervision of financial institutions leave corporate decision-makers with room for discretion to increase or decrease systemic risk. The incentives of these decision-makers are not necessarily aligned with minimising systemic risk. The thesis shows that this problem exists across different business models. More specifically, it identifies perverse incentives in the case of systemically important banks, CCPs, mutual funds, and hedge funds. The need for corporate governance regulation therefore lies in the inherent incompleteness of prudential regulation and supervision. Corporate governance regulation can help fill this gap by regulating the environment within which choices are made within these types of institutions. The analysis has three steps. First, it characterises the systemic importance of financial-sector activities carried on outside the context of ‘banks’. The governance literature so far has focused on the ‘systemic externalities’ created by banks. However, our analysis shows that other non-bank SIFIs generate similar systemic externalities with socially harmful consequences. These systemic externalities are not considered by SIFIs when taking business decisions. In a second step, the thesis shows that prudential regulation and supervision are incomplete and leave room for governance regulation to fill in the gaps. The final step shows that a corporate governance framework focused solely on the interests of shareholders will have negative consequences for systemic stability. Given such divergence between the decision-makers’ and society’s interests, corporate governance regulation can complement the traditional prudential framework.
Keywords: Asset managers; Central counterparties; Corporate governance; Finance; Non-bank financial institutions; Systemic risk

Regulatory measures to address bank failures in Zimbabwe - Nyaude, Ashley Batsirai (University of Pretoria, 2021)
The main rationale of prudential bank regulation and supervision of banks has traditionally been to ensure the safety and soundness of banks and protection of depositors. However, best practice standards in bank supervision acknowledge that it is impossible to completely prevent bank failures. Therefore, it is crucial to have regulatory measures in place to deal with banks that fail. Banks are core players in the financial system as the intermediaries between savers and users of capital. In addition, banks provide critical services to consumers, small and medium-sized businesses, large corporate entities and governments who rely on them to conduct their daily business, both at domestic and international level. Banks also fulfil a sui generis role that sets them apart from other financial institutions that are role players in the financial system because, inter alia, they hold “highly” liquid liabilities in the form of deposits that are repayable on demand; they extend long-term loans that may be difficult to sell or borrow against on short notice; they are the back-up source of liquidity to all other institutions (financial and non-financial); and, are also the transmission belt for monetary policy. Unlike other players in the financial system, banks are vulnerable to loss of public confidence and to liquidity risk. Liquidity risk being the risk that a bank will not have sufficient cash to meet short term obligations and the fact that a "run on the bank" by depositors can result in devastating liquidity drainage. Because banks play a special role in the economy and their failure may have a significant impact on financial stability, they need a special approach when they become insolvent or are likely to become insolvent. The 2008 Global Financial Crisis (“GFC”) demonstrated the importance of special resolution regimes for banks; and the need to balance the interests of shareholders, creditors and depositors, while promoting financial stability objectives. Given the critical role of banks in the economy the need is clear for a special resolution regime for banks that provides a legal framework for regulators that avails to them a suite of resolution tools which they can apply to resolve the bank in an orderly manner; to rescue those parts of the bank that may still be viable and to liquidate those parts that are not whilst avoiding a drain on public funds. In order to deal with bank failures in Zimbabwe, the Banking Act [Chapter 24:20] has provided for the mechanism of curatorship since 2000, as a rescue measure aimed at restoring failing banks to economic viability. Curatorship has over the years been applied with mixed success; consequently, Zimbabwe has undertaken a number of reforms which include the enactment of the Troubled Financial Institutions (Resolution) Act in 2005; and the introduction of the problem bank regime via the Banking Amendment Act of 2015. Throughout these reforms, Zimbabwe has elected to retain curatorship, which was once a standalone process in banking legislation to enable bank rescue; and assimilated it into a broader bank resolution framework. This study seeks to determine whether Zimbabwe’s resolution regime requires to be strengthened and if so, to recommend reforms that will align the resolution regime in Zimbabwe with international best practice. For such purpose it will draw upon the Financial Stability Board’s Key Attributes of Effective Resolution Regime as international best practice benchmark. It will further also consider guidance yielded by a comparative study of the resolution regimes in the United Kingdom and South Africa.
URI: https://repository.up.ac.za/handle/2263/80388
Keywords: Bank failure; Bank supervision; Zimbabwe

Allocating rights between nations: Legitimacy and justice in international tax policy - Ozawa Ozai, Ivan (McGill University, 2021)
Although extreme poverty has decreased in the last decades, we are a long way from eradicating global poverty. Similarly, the world has seen a considerable decrease in global inequality due to recent developments in emerging economies, but overall inequality between nations has risen in the last decades. International tax law may have a relevant role in improving or worsening global inequality. Extensive research has shown that the present international tax system was designed in a way that tends to benefit high-income economies. However, there has been no significant discussion about whether and how international tax law rules should be changed to address global inequality. The main goal of this thesis is to analyze the existing legitimacy and distributive justice issues that limit the ability of lower-income countries to raise tax revenues and consider what can be done to make the current international tax regime more aligned with global justice principles.The thesis builds on the contemporary literature in international political economy and global distributive justice and puts forth a normative framework for allocating the international tax base among states. First, it analyzes some of the legitimacy deficits of the present international tax system. In contrast to prevailing views about improving legitimacy, it demonstrates the shortcomings of focusing solely on making international tax policymaking processes more inclusive and argues for a greater focus on global distributive justice. It then analyzes the main tax theories that have defined international tax relations to date and demonstrates some of their limitations. The final part of the thesis puts forth normative principles that integrate distributive justice and considers the practical implications of the proposed normative framework for some of the most recent issues discussed in international tax policy
Identifier: https://escholarship.mcgill.ca/concern/theses/rf55zd52x
Keywords: International tax; International tax policy

Improving international investment law’s treatment of (anti-)corruption: Towards a more balanced approach - Yan, Yueming (McGill University, 2021)
In recent years, investment arbitration tribunals are increasingly confronted with allegations of corruption, mostly invoked by host States as a defense to investors’ claims. After an affirmative finding of an alleged corrupt act between the investor and a public official of the host State in the establishment or conduct of the investment, tribunals have adopted a binary approach to the issue – if they uphold allegations of corruption, they completely dismiss the investor’s submissions. This binary approach has resulted in an asymmetry of liability for the two parties to a corrupt act (i.e., investors and host States/host State officials), failing to take into account the inherent bilateralism of corruption and the fact that domestic laws and international norms have outlawed both the act of offering and of accepting bribes. In particular, public officials’ free participation in a corrupt act to advance investments is attributable to the host State and requires State responsibility under international law. Moreover, the increasingly prevalent practice of inserting anti-corruption provisions in investment treaties has reinforced this lop-sided feature, as well as offering only weak effectiveness in terms of deterring corruption. After a careful examination of the treatment of corruption issues in investment arbitration and investment treaties, this thesis proposes a paradigm shift from the current asymmetric approach to a more balanced approach. It calls on investment tribunals to take a dual-track approach that investigates both corruption and investors’ claims, and ensures that each party assumes responsibility for its own misconduct. It also proposes that treaty drafters include anti-corruption provisions that impose strong obligations of anti-corruption on both sides of corruption (i.e., investors and host States) rather than merely on a single party to it
https://escholarship.mcgill.ca/concern/theses/5q47rt984
Keywords: Anti-Corruption Law; Investment arbitration; Investment treaty; Investments

Legalization through adjudication: The case of investor-state dispute settlement - Yu, Chen (McGill University, 2021)
The reform of the Investor-State Dispute Settlement (ISDS) mechanism has provoked much debate among legal scholars and practitioners. The critiques of ISDS mainly arise from concerns regarding the legitimacy of the mechanism such as the perceived tolerance for the lack of impartiality and consistency. To allay these concerns, there have been proposals to reform ISDS by establishing investment courts with tenured judges and appellate tribunals. However, international adjudication systems like ISDS cannot be fully analogized to domestic courts in common law countries: ISDS falls into a broader international regime where there are neither hierarchical/centralized decision-making and enforcement authorities nor a multilateral investment treaty, and the rules and principles on foreign investment protection are fragmented in around three thousand Bilateral Investment Treaties (BITs). Against this backdrop, this thesis argues that, although there is a general agreement among the international community to further legalize international investment law, the process of legalization via the specific avenue of reforming the adjudication mechanism (i.e. ISDS) is subject to (1) the institutional constraint of international investment law, especially the lack of shared understanding among the international community regarding the treatment of foreign investments, and (2) the internal constraints of adjudication as a mode of social ordering. It further cautions that pursuing predictability while disregarding the low level of shared understandings regarding investment protection may cause more legitimacy problems than it solves
https://escholarship.mcgill.ca/concern/theses/2j62s986g
Keywords: Bilateral Investment Treaties (BITs); ISDS Reform; International Investment Law; Investments; Investor-State Dispute Settlement

The Development of Accounting in Africa in the Era of International Financial Reporting Standards - Agyeman, Charles Gyamf (University of Westminster, 2020)
This thesis consists of two separate, but related studies on the development of accounting in Africa in the era of International Financial Reporting Standards. The first part of this thesis presents the first empirical test of a hypothetical classification of financial reporting in Africa based on de facto or actual practices as opposed to de jure rules. Three multivariate techniques (principal component analysis, cluster analysis, and multidimensional scaling) were used to analyse the accounting policies of large, listed companies in Africa that are required by law to adopt IFRS. It was found that there is a dichotomy between the IFRS policy choices of companies in Francophone and Lusophone countries, on the one hand, and those in common law jurisdictions, on the other, thus confirming the two-group classification schemes proposed by Elad (2015) and Nobes (1983). The results of this study extend previous research by demonstrating that international differences in financial reporting in Africa have survived in the era of IFRS and that pre-IFRS regulations enshrined in national and regional charts of account appear to have influenced IFRS policy choice. Furthermore, companies in common law countries tend to provide more extensive disclosures in their IFRS financial statements than their counterparts in code law countries. These findings have important policy implications, particularly in the context of recent recommendations of the World Bank, the International Monetary Fund, and the Pan-African Federation of Accountants that large entities in Africa adopt IFRS. The systematic differences in the choice of IFRS options between companies in civil law and common law jurisdictions suggest that it would be difficult to achieve internationalcomparability and consistency in financial reporting. The second part of the study uses semi structured telephone interviews to undertake interpretive accounting research (Baker and Bettner, 1997, p.293) to assess the perception of accounting professionals in relation to IFRS adoption and its use in Ghana. It concludes that despite the problems associated with its adoption and implementation, overall, International Financial Reporting Standards are viewed as necessary for the financial reporting needs of the country.
Keywords: Accounting classifications; CFA franc zone; IFRS practices; OHADA accounting system; Plan Comptable Général; SYSCOHADA

Consumer protection in an electronic environment - Akhigbe, Iyen Joy (University of South Africa, 2020)
Consumer protection laws have not evolved on par with the development of electronic media. As a result, consumer protection laws do not address all major areas of legal concern that affect the electronic commerce (e-commerce) consumer. Furthermore, differing laws in the area of consumer protection make harmonised consumer protection neigh on impossible. Currently, there is a plethora of laws on the protection of consumers but most of these laws are within the sphere of conventional consumer protection legislation which does not adequately address the legal challenges posed by the proliferation of electronic transactions (e-transactions). Specific e-transaction laws are now to be found in certain international and regional documents emanating from organisations including: the United Nations (UN); the Council of Europe; the Organisation for Economic Cooperation and Development (OECD); the African Union (AU); the Economic Community of West African States (ECOWAS); the Southern African Development Community (SADC); the Common Market for Eastern and Southern Africa (COMESA); and the East African Community (ECA). These legal instruments have already been implemented in certain states’ national legislation, while other countries have yet to accede to them. Despite these legal instruments, e-commerce consumers are faced with inadequate or obsolete legislative provisions and are yet to enjoy full protection equivalent to that accorded to the “traditional” consumer. Furthermore, given the trans-national nature of the internet, divergent laws will inevitably prove to provide inadequate protection to e-commerce consumers. In this research, international and regional legislative instruments, as well as the national laws of selected countries such as the United States (US), the United Kingdom (UK), the Republic of South Africa (South Africa), the Federal Republic of Nigeria (Nigeria), and the Commonwealth of Australia (Australia) are examined. The strengths and gaps in each of these instruments and laws are identified with the aim of harmonising the principles they espouse in a single, cogent, and comprehensive body of rules which could take the form of an international convention. An international convention should be based on national and international best practices. The national adoption of the minimum standards espoused in the proposed Convention will ultimately, promote harmonisation.
Keywords: Borderless jurisdiction; Cooling-off; Cyberspace; E-agent; E-commerce consumer rights; Electronic transferable record; Hidden charges; Information; Keystroke error; M-commerce; Shrinkwrap; Single window facility; Terms and conditions; Transaction; Web-wrap; Wireless Application Protocol

Historical and comparative perspectives on trade union regulation with specific emphasis on the accountability of trade unions to their members - Greenhalgh, Bradley Paul (Stellenbosch University, 2020)
How do members hold their own trade unions accountable in South Africa? What legal mechanisms, if any, are available to assist union members in receiving adequate representation and service from their unions? This study approaches these questions through a comparative and historical examination of the regulation of the union member relationship in the UK, USA and the RSA. The study commences with an examination of what unions do, how they function and what benefits potentially accrue to their members, while the role played by unions in utilising collectivisation to offset the bargaining power of employers is demonstrated. The need for organised labour, by society in general, but South Africa specifically, is brought into sharp relief. This is, however, offset by the examination of 25 constitutions of broadly representative South African trade unions, where the lack of proper regulation of the union-member relationship is brought to the fore. This already means the common law and current judicial approach that is so reliant on the interpretation and implementation of trade union constitutions to address union-member disputes is unsuitable, certainly in those instances where the constitution is either silent or ambiguous, or where the nature of the relationship between the union and its member(s) mimics that of the constantly present imbalance of power and influence between employers and employees. The comparative examination of union accountability is undertaken against the backdrop of the common historical phases of proscription, acknowledgement/assimilation, and readjustment of and towards trade unions. The historical and contemporary regulation of the union-member relationship in South Africa is examined in the same way. The study demonstrates that purely statutory regulation of the union member relationship by means of punitive provisions and inter-union self-regulation measures are not feasible. A series of possible legal mechanisms – that draw from the comparative examination – are suggested, even though they are to be utilised in a collective (rather than individual) way. Even these suggestions, however, are subject to the challenges of cost-effectiveness, accessibility and efficiency of enforcement by (the) average union member(s). Three proposals are made to foster improved union member accountability: Firstly, the use of section 103A of the LRA by the Registrar so as to place unions that meet the appropriate criteria under administration, in order to restore accountable functioning and elevate the interests of the member(s) over that of the officials of the union; secondly, the introduction of a duty of fair representation – to be administered by the CCMA – to hold both union and employer accountable to members, and; thirdly, in conjunction with the first two proposals, the use of a package of further measures (and an associated information campaign), such as bolstering the financial/institutional capacity of the Registrar’s office, compelling the inclusion of accountability clauses within union constitutions, and minor amendments to the LRA with regard to balloting, reporting/transparency (and the enforcement thereof). If implemented, the expected outcomes are improved labour relations, increased accountability and professionalisation of trade union administration, a realignment of the employer-union divide and elevating the awareness of union member rights and concomitant obligations on trade unions – all of which are of critical importance in South Africa’s post-Marikana society.
URI: http://hdl.handle.net/10019.1/109343
Keywords: Labor union members; South Africa; Trade union accountability; Union security

Decompilation and copyright in ideas - the protection of non-literal elements of computer software and the idea/expression dichotomy - Jooste, Jacobus Petrus (Stellenbosch University, 2020)
The maxim, that copyright law does not protect ideas, is frequently challenged when the established principles are tested against new forms of expression or exploitation of a work. The evolution of computer programs, its unique characteristics and the increasing value of software as a commodity have resulted in a strained relationship between copyright law and the public interest regarding access to the underlying ideas in a computer program. This work examines the misalliance between copyright principles and the technical nature of computer programming, with a specific focus on the act of decompiling an existing program where it is undertaken in order to understand the underlying ideas and techniques. The impetus for this analysis is the sui generis classification of computer programs in South African copyright law and the potential this offers for development of domestic law in pursuit of national policy goals. This work conducts a normative analysis of the law and the technical reality of decompilation, from the perspective that copyright law must maintain a clear separation between the idea and the expression. The review of national and foreign copyright law is, throughout, conducted with a perspective on the effect of protection and a critical examination of the degree to which the law maintains an adequate balance between the private and public interests in the protection of software. In this respect, the current legal position is evaluated and a different, normative and prodevelopmental perspective regarding decompilation is proposed. It is submitted that are balancing of interests is justified and essential in order to establish an appropriate level of fairness and, at the same time, stimulate progress in this industry. It is argued that the act of using computer code to discover its meaning should not amount to infringement in the form of reproduction or adaptation of the work. It is found that the perception of decompilation, as a form of infringement, relies on an analogy to literary work. This view, it is argued, is ill suited to the nature of computer programs, at odds with the sui generis classification in SA copyright law, causes overbroad protection and violates the idea/expression separation. In light of the technical review of decompilation, it is found that the legal basis for prohibiting decompilation as a form of infringement is narrower than commonly assumed and that copyright law principles should be reinterpreted purposefully to permit decompilation. This work advocates that decompilation must be permissible and that an exemption, in SA copyright law, which is limited to decompilation for interoperability alone, is not appropriate in light of the national developmental agenda. Therefore, an alternative exemption is proposed which accommodates the technical reality of decompilation, the public interest in access to ideas and the commercial interests of copyright owners. This approach is supported by an analysis of international copyright law and is based on the inherent flexibilities of the three-step test. The justification for the findings of this work and the proposed departure from foreign precedent is supported by a close examination of the effect of a limited decompilation exception in foreign law and the impact of legislative measures to restrict circumvention of technological protection measures.
URI: http://hdl.handle.net/10019.1/109088
Keywords: Copyright; Copyright infringement; Decompilation; Intellectual property; International Copyright

Commercialization of Microfinance in Cameroon : How can Microfinance Institutions manage their dual social and commercial goals? - Singhe, Steffi Sandra (Université de Nantes, 2020)
La commercialisation de la microfinance a mis au premier plan la performance financière des I MF, les IMF adoptant désormais une logique commerciale de rentabilité en plus de leur logique sociale établie de lutte contre la pauvreté. Cela pose un défi de gestion crucial pour les IMF pour équilibrer l'aspect social et commercial de leur mission. Cette thèse vise à analyser comment les IMF surmontent leurs défis pour atteindre leur double objectif social et commercial. Elle s'appuie sur le concept de bricolage comme perspective théorique et sur une approche méthodologique abductive, exploratoire et qualitative. La thèse vise également à fournir une meilleure compréhension du secteur de la microfinance camerounaise, en termes de son histoire et évolution, et des défis spécifiques au secteur. L'étude identifie diverses pratiques de bricolage que les IMF utilisent pour faire avancer la réalisation de leur double mission. Les résultats suggèrent l'utilisation de ces pratiques de bricolage par les IMF pour mobiliser des ressources, renforcer la légitimité et accroître leur ou/reach, dans un contexte caractérisé par des contraintes de ressources. Ces trois résultats de bricolage se renforcent mutuellement pour faciliter la réalisation du double objectif des IMF. Cette recherche a également mis en évidence les quatre phases d'évolution du secteur de la microfinance camerounaise et les cinq principaux défis auxquels sont confrontées les IMF du secteur. Cette thèse contribue à la littérature sur la microfinance. Elle propose un nouvel regard sur la gestion de la double mission des IMF en montrant comment les IMF mobilisent les stratégies de bricolage pour faire avancer leurs objectifs sociaux et commerciaux. Elle met en lumière le lien entre la littérature sur la microfinance et le bricolage. The commercialization of microfinance has brought to the forefront the financial performance of MF!s, with MF!s now adopting a commercial logic of profitability in addition to their established social logic of poverty alleviation. This poses a crucial management challenge for the MF!s in terms of balancing the social and commercial aspect of their mission. The main aim of this thesis is to understand how MFls overcome their challenges so as to achieve their dual social and commercial goals. lt draws on the bricolage concept as a theoretical perspective and on an abductive, exploratory and qualitative research approach. The thesis also aimed to provide a better understanding of the Cameroonian microfinance sector, in terms of its history and evolution, and the challenges specific to the sector. The study identifies various bricolage practices that the MF!s use to advance the fulfilment of their dual mission. The findings suggest the use of these bricolage practices by the MF!s to mobilize resources, build legitimacy, and increase outreach, in a context characterized by resource constraints. These three bricolage outcomes reinforce each other, and they all strengthen the achievement of the MF!s' dual goals. This research also highlighted the four phases of evolution of the Cameroonian microfinance sector and the five main challenges faced by MF!s in the sector. This thesis contributes to the microfinance literature. lt offers a new perspective on MF! dual-mission management by showing how MF!s mobilize bricolage practices to advance their dual social and commercial goals. lt brings light on the link between the literature on microfinance and bricolage.
Keywords: CSR; Cameroun; Microfinance; RSE; Responsabilité sociétale; Régulation (théorie)

A review of the Libyan insolvency and restructuring laws informed by insolvency law theory and international benchmarks - Hosen, Emad-edden Rajab A. (Nottingham Trent University, 2020)
The research aims to evaluate the adequacy of the insolvency system in Libya to support the national desires and objectives identified in the country to enhance the national economy and to maintain social stability. The thesis considers the need for reform in the current business insolvency and rescue framework taking into account the country’s domestic circumstances. To conduct this evaluation, the research reviews the Libyan insolvency law by examining the theoretical approaches to corporate insolvency laws in order to understand the role that should be played, or the goal that should be reached, by the insolvency law. This is important to identify whether the insolvency and rescue laws should be concerned only about maximising economic interests or should be concerned also about wider societal interests and objectives. The study also undertakes an in depth evaluation of the current business insolvency and rescue framework by using the international benchmarks with particular reference to the UNCITRAL Legislative Guide on Insolvency Law. The thesis establishes that the current insolvency law is insufficient to promote the economic and social goals of the country because of both the deficiency of the legislative framework and inefficient institutions. The investigation reveals also that an application of the social justice theory as traditionally perceived by the Civil Code 1953 (as manifested in property law and contract law) that is primarily designed to achieve social goals (for example, the priority given to the wide-ranging category of privileged creditors over secured creditors) prevents the insolvency law from achieving the sought-after objectives leaving much to be desired for a reform. The research builds on these foundations to identify challenges and impediments to the development of the insolvency and rescue regime of Libya.
https://irep.ntu.ac.uk/id/eprint/41433/
Keywords: Company law; Corporate law; Insolvabilité; Insolvency; Libya; Procédures collectives; Restructuration; Restructuring law

The Impact of Employee Board Representation on the Firm’s CSR Engagement : evidence from the French Context - Boukadhaba, Amal (Le Mans Université, 2020)
Cette thèse propose d’examiner la relation entre la représentation des salariés dans le conseil d’administration et l’engagement RSE de l’entreprise. En particulier, nous étudions comment les investisseurs perçoivent-ils le reporting RSE et laperformance ESG lorsque les salariés sont représentés au sein du conseil d’administration. En utilisant un échantillon de sociétés françaises appartenant à l’indice SBF 120 sur deux périodesdifférentes de 2001 à 2011 et de 2007 à 2017, nos résultats montrent que la présence des administrateurs salariés modère positivement la perception du reporting RSE et négativement la perception de la performance ESG par les investisseurs. Un examin plus détaillé montre que les administrateurs élus par les salariés par leur droit de travail améliorent exclusivement la performance sociale et modèrent négativement la perception des investisseurs vis-à-vis de la performance ESG. Au contraire, les administrateurs élus par les salariés actionnaires renforcent la performance ESG globale ainsi que les performances environnementale et de gouvernance et modèrent positivement la perception de la performance ESG par les investisseurs. Nos résultats mettent en évidence un conflit d’intérêts entre les actionnaires et les administrateurs salariés, notamment avec les représentants des travailleurs. Cette thèse couvre plusieurs disciplines à savoir la comptabilité, la gouvernance d’entreprise et lagestion des ressources humaines. En conséquence, elle intérèsse vivement les législateurs, les investisseurs, les managers et les actionnaires.
Impact de la représentation des salariés au sein du conseil d’administration sur l’engagement RSE de l’entreprise : Etude du contexte français
Keywords: Actionnariat du personnel; Administrateurs salariés; CSR reporting; ESG performance; Employee board representation; Firm market value; Gouvernement d'entreprise; Performance ESG; Performance boursière; Personnel – Participation à la gestion; Relations avec les actionnaires; Reporting RSE; Responsabilité environnementale; Responsabilité sociétale; Sociétés

State aid to state owned enterprises in South Africa : the need for a comprehensive State aid policy : a competition law inquiry - Afrika, Sasha-Lee Stephanie (Stellenbosch University, 2020)
The Competition Act 89 of 1998 applies equally to all firms with regard to anti-competitive behaviour regardless whether it is privately or publicly owned. Therefore it applies to stateowned enterprises (SOEs) if their actions fall short of the Act. There is however one aspect relating to SOEs which is not covered by the application of the Competition Act but may have a significant impact on free and fair competition and can be of big concern for private competitors of SOEs. Since discriminatory policies during Apartheid have created a huge inequality gap in post-Apartheid South Africa, the government has to be actively involved in the economy to address the inequality. Therefore the government uses SOEs as vehicles to achieve its developmental goals. As a result SOEs in South Africa which are active market participants may always rely on the financial support of the state. They may do so purely because of their crucial governmental mandates regardless of financial mismanagement, poor corporate governance and deep seated corruption in almost every SOE. Even though the fundamental need for the existence of SOEs in South Africa is acknowledge, it is argued that state financial aid could qualify as a state-initiated constraint on competition in South Africa as it creates an uneven playing field between SOEs and their private competitors, which is always skewed in favour of the SOEs. It may create warped incentives and SOEs may not compete efficiently if they know that they are protected by a state sponsored safety net. This dissertation asks the question whether the time has not arrived in South Africa for state aid to SOEs to be subjected to a certain degree of scrutiny in order to bring about a level playing field between SOEs and their private competitors. It is recognised that privatisation of SOEs is not always the better option as it could threaten the delivery of basic services and goods to poorer South Africans. Hence, the dissertation investigates whether a state aid control model, based on the European Union state aid rules, is not perhaps a solution to address the potential distortion of free and fair competition by state financial aid. It proposes a customised state aid control regime for South Africa which provides for an active role by the competition authorities in state aid decisions and it presents draft legislation which could be used as a basis for the implementation in South Africa of a regulated system of state financial aid to SOEs (and even private enterprises where applicable).
URI: http://hdl.handle.net/10019.1/108193
Keywords: Government business enterprises; South Africa; State aid; State-owned enterprises; Unfair competition

The Effect of EU State Aid Law on the Future of EU Investment Policy - Finckenberg-Broman, Pamela (Griffith University, 2020)
On 1 July 2017, the Commission of the European Union (Commission) announced that investor state dispute settlement (ISDS) was dead. Apart from the fundamental public distrust of ISDS, its rejection by the European Union (EU) is a symptom of several underlying causes, the foremost of which is the need to protect the autonomy of the EU legal order and its right to regulate public policy objectives, as well as to avoid jurisdictional conflicts. With this backdrop EU state aid law, which enjoys public policy status, has emerged as a major example of the conflict between investor protection and the right to regulate. As state aid law imposes measures on the EU Member States that conflict with these states’ international obligations to foreign investors under bilateral investment treaties (BITs), they have become subject to claims and substantial liabilities. This dilemma can arise in any setting that involves the EU or one or more of its Member States. It also includes relations with non-EU countries, as the web of international investment agreements (IIAs) operates, in different forms, on an international scale. Therefore, this dilemma and the EU’s responses to it is analysed through the different forms in which EU state aid law appears, dependent on the EU investment policy aspect utilised as a platform for analysis. Utilising a doctrinal analysis by studying, discussing and analysing the impact of EU state aid law on the EU Member States’ BITs and EU Trade Agreements, this dissertation provides an insight into the function and logic behind international treaties involving the EU’s competition and investment policy. This is done by utilising the research question: How does the European Union (EU) state aid law affect the future of EU investment policy in a global context? Further, this thesis puts forward three arguments in which EU state aid law is affecting the future of EU investment policy in a global context. First, state aid law applies in the EU’s incorporation of clauses promoting fair competition and state aid policy in international trade agreements. Second, state aid law and policy has contributed to recent EU internal development, which led the EU Member States to terminate their bilateral agreements with each other (intra-EU BITs) by the end of 2019. Third, the EU has been working towards replacing the existing BITs between the EU’s Member States and third countries (extra-EU BITs) with the EU’s own trade agreements, which are aligned with EU legislation. Essentially, this thesis golden thread is a debate on who gets to decide on the scope of state aid law now and in the future. In other words, is it the EU that sets the borders and the status of state aid law and policy law regarding investment protection or the international investment tribunals by their legal practice? Hence, this thesis offers a glimpse of a conceivable future of EU investment policy in a global context. An analysis of the relevant literature, and observation of recent policy changes on its subject matter, as reflected in the Commission’s policy documents, the EU’s international agreements and declarations by the Member States, leads to the findings of this dissertation. A conflict situation that originated from legal conflicts within the EU, the EU experience of investment protection and state aid regarding intra-EU BITs, provided some lessons to learn for the EU organs. These lessons learned have found expression on a global scale. By incorporating fair competition and state aid policy in international trade the EU is reasserting that it is the EU that decides on state aid law and policy law regarding investment protection. Indeed, the EU is attempting to tame investment protection in such a way that fair competition and investment protection can peacefully coexist in international trade. Ultimately, the interplay of state aid and the EU’s investment policy within the internal market reflects on the external trade relations of both the Member States and the EU through this practice. Thus, state aid law affects and will continue to affect the future of EU investment policy in a global context.
Keywords: EU; European Union; Investment protection; Investments; Policy Law; State aid law

Corporate Social Responsibility and Organizational Performance of Oil Companies in Southern Nigeria - Daubry, Powei Martin (Walden University, 2020)
In this study, the relationship between corporate social responsibility (CSR) activities and organizational performance (OP) of international oil companies (IOCs) operating within the Niger Delta Region of Nigeria was investigated. Grounded on the stakeholder theory, the problem being investigated involved the extent to which dimensions of CSR in terms of centrality, visibility, and voluntary contributions impact measures of OP (relational capital and employees’ commitment) specifically within the oil industry in Nigeria. Data for the study were obtained through a quantitative survey instrument from a sample of a population of individuals (N=270) living in host communities who are impacted by IOC activities in Rivers, Delta, and Bayelsa States. The results of the multiple regression analysis indicated a predictive model F (1, 268) = 774, p < 0.05, and R 2 = .742, which indicated that CSR was positively and significantly correlated with OP. In addition, centrality and voluntary contributions significantly affected OP. Also, centrality and voluntary contributions significantly correlated with employees’ commitment while only voluntary contributions significantly correlated with relational capital. The results of the study corroborated the need for CSR practitioners in the oil industry within the Niger Delta to operate in a socially responsible manner. The implications for positive social change include the potential for policy makers to use the findings to create mutually beneficial relationships that could contribute to resolving persistent adverse issues involving oil exploration and production in the Niger Delta Region by improving the socioeconomic dynamics of the host population, not only in the region, but also throughout Nigeria and similar countries.
Keywords: CSR; Corporate Social Responsibility; Nigeria; Oil companies; Organizational performance

Capital market effects of adoption of IFRS - Opare, Solomon (Victoria University of Wellington, 2020)
This thesis examines the impact of adoption of IFRS (International Financial Reporting Standards) on two aspects of the operation of capital markets. Firstly, the impact of adoption of IFRS on financial reporting comparability, market liquidity, and cost of capital. Secondly, the impact of adoption of IFRS on seasoned equity offering (SEO) underperformance. To examine the impact of adoption of IFRS on financial reporting comparability, market liquidity, and cost of capital, the study used meta-analysis of empirical studies published since 2000. Meta-analysis provides an objective view of the empirical results, in contrast to narrative reviews, which offer subjective conclusions. From meta-analysis of 55 empirical studies with 1,259 effect sizes, the study finds that IFRS adoption has increased financial reporting comparability, market liquidity, and reduced cost of equity. For cost of debt, a decrease is observed only for voluntary adoption. The meta-regression analysis shows how the results differ across mandatory and voluntary adoption of IFRS and that the measurement choices, type of control variables, study design, and strength of empirical results explain the variation in the observed effect of adoption of IFRS. To examine the impact of adoption of IFRS on SEO underperformance the study analyses a large sample of SEOs from 51 countries over the period 1992-2017. Given that the empirical literature on SEOs has established that information asymmetry contributes to SEO underperformance, it is important to assess whether adoption of IFRS has reduced the uncertainties surrounding SEOs and, thus, subsequent underperformance. The study employs a control sample of non-IFRS adoption countries and applies a difference-in-difference (DiD) design to test for the incremental change for IFRS adoption countries over non-IFRS adoption countries. The study finds that SEO underperformance reduces for IFRS adopters relative to non-IFRS adopters in the post-adoption period. The reduction in SEO underperformance is influenced by increased disclosure, increased comparability, and number of accounting changes. The study also finds that the impact of adoption of IFRS on SEO underperformance exists only for firms in countries with strong enforcement, and is conditional on the implementation credibility of countries. The findings are robust to the application of a different measure of SEO underperformance. Overall, the study suggests that IFRS has had a positive impact on capital markets. However, increased disclosure, comparability, and credible implementation play important roles in realising the benefits of adoption of IFRS. Thus, policymakers of weak enforcement countries are encouraged to strengthen their institutional environment in order to reap the benefits that adoption of IFRS can provide to their capital market.
Keywords: Cost of debt; Cost of equity; Enforcement; Financial reporting comparability; IFRS adoption; Market liquidity; Meta-analysis; SEO underperformance; Seasoned equity offering

Protecting the Industrial Designs of Today and the Future - Samoylov, Vladimir (Victoria University of Wellington, 2020)
This study examines and critiques New Zealand intellectual property protection for industrial designs, taking into account that many New Zealand industrial design owners outsource manufacture of their designs to China. Industrial design, which refers to improving the aesthetics of products to increase their marketability, is evolving conceptually and practically. In New Zealand, copyright and registered design laws each protect, respectively, the visual expression and the “eye appeal” of an original design. As design practices evolve with advances in technology however, it is increasingly evident that industrial design is about more than just visual expression or “eye appeal”. Many designers are not focusing solely on product stylisation and decoration, but on the provision of a more holistic product experience for the consumer. The development process of industrial designs from concept to marketable product is also changing, with many New Zealand industrial design owners employing increasingly efficient design development strategies. The fast-paced, cost-effective infrastructure of China is often utilised by New Zealand businesses for the manufacture of industrial designs. This study therefore sought to determine how to appropriately protect New Zealand industrial designs, in light of: a. foreseeable advances in technology; and b. the fact that many New Zealand industrial designs are manufactured in China. To answer these questions, this study examined and analysed New Zealand’s copyright and registered design laws, taking into account not only existing protections, but also factors that are likely to be of significant relevance in the future, such as the impact on industrial design from developments in 3D printing and virtual reality. The Chinese intellectual property regime for industrial designs was also examined because China is a major trading partner and often, as noted, the locus of manufacture. The study included an empirical investigation, in the form of interviews with designers and design academics as well as legal practitioners specialising in intellectual property law. The input of the interviewees, together with the legal analysis, informed a series of suggestions and recommendations for New Zealand policy and its law-makers regarding how industrial design protection can be improved. A key finding of this study was that existing legal protections do not appropriately protect increasingly holistic designs, as well as new types of designs emerging from developing fields such as virtual reality. In assessing the appropriateness of protection, the interests of industrial design owners were balanced against the public interest in protecting the public domain. It is suggested that to achieve equilibrium copyright law should be expanded to protect design expressions for all senses. Moreover, new categories of copyright protected works should be introduced to accommodate emerging design. The definition of design in registered design law should also be reconceptualised in order to acknowledge new types of designs and evolving design practices. Industrial design owners who outsource manufacturing to China can protect their designs via copyright as well as design patent. However, enforcement of intellectual property protection is unsatisfactory in many areas of China. Therefore, New Zealand industrial design owners should also employ non-legal protection strategies. Interviews with successful businesses, in the course of the empirical investigation for this study, revealed that the leveraging of existing relationships of those with already established operations in China, and intentionally splitting an industrial design’s component parts for manufacture among several factories in different locations, are useful strategies to employ.
Keywords: 3D printing; Artistic Craftsmanship; China; Copyright; Doing business in China; Intellectual property; Multisensory Designs; Propriedade intelectual; Propriété intellectuelle; Registered design; Spare Parts; Virtual Designs; Virtual Reality

The Distributional Effects of Value-Added Taxes in OECD Countries - Thomas, Alastair (Victoria University of Wellington, 2020)
Most OECD countries’ value-added tax (VAT) systems apply reduced VAT rates to a selection of expenditure items in order to achieve distributional goals, and – to a lesser extent – social, cultural and employment-related goals. This thesis investigates the distributional effects of the VAT in OECD countries, and the merits of using reduced VAT rates to achieve distributional goals. The research adopts a microsimulation modelling approach that draws on household expenditure microdata from household budget surveys for an unprecedented 27 OECD countries. A consistent microsimulation methodology is adopted to ensure cross-country comparability of results. Non-behavioural VAT microsimulation models are first built to examine the overall distributional impact of the current VAT systems in each country. The research assesses the competing methodological approaches used in previous studies, highlighting the misleading effect of savings patterns on cross-sectional analysis when VAT burdens are measured relative to income. Measuring VAT burdens relative to expenditure – thereby removing the influence of savings – is found to provide a more reliable picture of the distributional impact of the VAT. On this basis, the VAT is found to be either roughly proportional or slightly progressive in most of the 27 OECD countries examined. Nevertheless, results for a small number of countries (Chile, Hungary, Latvia and New Zealand) highlight that broad-based VAT systems that have few reduced VAT rates or exemptions can produce a small degree of regressivity. Results also show that even a roughly proportional VAT can still have significant equity implications for the poor – potentially pushing some households into poverty. Behavioural VAT microsimulation models are then built for 23 OECD countries to investigate whether reduced VAT rates are an effective way to support poorer households, and whether the use of targeted cash transfers would be more effective. The behavioural microsimulation methodology follows the Linear Expenditure System based approach of Creedy and Sleeman (2006). Complementing this approach, a Quadratic Almost Ideal Demand System (QUAIDS) is estimated specifically for New Zealand, thereby providing the first estimates of a QUAIDS model based on New Zealand data. Simulation results show that, as a whole, the reduced VAT rates present in most OECD countries tend to have a small progressive impact. However, despite this progressivity, reduced VAT rates are shown to be a highly ineffective mechanism for targeting support to poorer households: not only do rich households benefit from reduced rates, but they benefit more in aggregate terms than poor households do. When looking at reduced VAT rates applied to specific products, results are found to vary considerably. Reduced VAT rates specifically introduced to support the poor (such as reduced rates on food consumed at home and domestic utilities) are generally found to have a progressive impact, though rich households still receive a larger aggregate benefit than poor households. In contrast, reduced VAT rates introduced to address non-distributional goals (such as reduced rates on restaurants, hotels, and cultural and social expenditure) often have a regressive impact. Additional simulation results show that an income-tested cash transfer will better target support to poorer households than reduced VAT rates in all countries. Furthermore, even a universal cash transfer is found to better target poorer households than reduced VAT rates. However, results also show that it is very difficult for an income-tested cash transfer to fully compensate all poor households for the removal of reduced VAT rates. This is due to the significant variation in the underlying consumption patterns across households. While a small number of poor households lose out from replacing reduced VAT rates with targeted cash transfers, those that receive support are instead determined by income and family characteristics as opposed to consumption tastes – thereby increasing horizontal equity. Furthermore, many households are lifted out of poverty as revenue previously transferred to richer households is now transferred to poorer households. These results empirically confirm the theoretical expectation that, where available, direct mechanisms (whether via the income tax or benefit system) will better achieve distributional goals than reduced VAT rates. Countries that currently employ reduced VAT rates to achieve distributional goals should therefore consider removing these reduced rates and adjusting their income tax or benefit systems to achieve these distributional goals instead. Countries should also consider removing reduced VAT rates aimed at non-distributional goals where a more effective instrument is available to achieve the particular policy goal. At a minimum, the merits of these reduced VAT rates should be reassessed in light of their negative distributional impact.

Selected legal aspects of liability insurance - Jacobs, Wenette (University of South Africa, 2020)
Liability insurance concerns an insured’s insurance of its legal liability towards a third party for the latter’s loss. This specialised type of insurance is rather neglected in South African insurance law. There is a lack of understanding of the intricacies of liability insurance and its unique challenges. This flows primarily from its complex nature as third-party insurance, which involves legal obligations between multiple parties, and a lack of statutory regulation of the distinctive contractual aspects of liability insurance. Furthermore, limited authority exists on contentious legal aspects as a result of the relatively small number of judicial decisions in this field of law. It is also evident that liability insurance constantly evolves as new grounds of liability emerge and new insurance products develop in response to the changing demands of society. The rise of consumerism and the increase in third-party claims amplify the economic significance of the law of liability insurance in South Africa. A substantial knowledge gap remains in our jurisprudence, irrespective of the recent introduction of new statutory instruments aimed at regulating insurance practice in general. These reforms have not as yet been applied critically to liability insurance, and no specialised legislation in South Africa regulates aspects of this branch of insurance as is the case with microinsurance. The focus in this thesis is on two main issues: the insurer’s duty effectively to indemnify the insured, and the insurer’s defence and settlement of third-party claims brought against the insured. As a subsidiary theme, this thesis analyses legal uncertainties that may persist during pre-contractual negotiations, the liability insurance contract lifecycle, and even after the expiry of the contract. Legal challenges can be addressed by novel and creative application of the national law. Potential solutions can be gleaned from the other progressive jurisdictions reviewed – English and Belgian law. It is evident that this research may prompt Parliament to develop specific rules and regulations for liability insurance contract law. This thesis includes a check list of some of the most important disclosure duties for procuring liability insurance cover, its operation, and claims processes.
Keywords: Claims-made policy; Duty to indemnify; Indemnity insurance; Liability insurance; Liability insurer; Third-party insurance

Investor-state arbitration and African states: a proposal for a Pan-African investment court - Ama, Obiajunwa (Canterbury Christ Church University, 2020)
This thesis proposed for the reform of Africa’s Investor-State Dispute Settlement (ISDS) landscape through the establishment of a Pan-African Investment Court (PAIC) as a mechanism for the resolution of Investor-State Disputes. This proposal is influenced by the findings of my investigation on the functioning of Investor-State Dispute Settlement (ISDS) through the deployment of Investor-State Arbitration to resolve Investor-State Disputes between African states and foreign investors. This research is motivated by the criticisms of the Arbitration mechanism by a broad spectrum of constituencies within international investment law. These criticisms are primarily anchored on the legitimacy crises of ISDS, a dissatisfactory notion that denounces the deployment of the private mechanism and privity of contract ingrained investment arbitration framework to resolve publicly-inclined investor-state disputes. Ancillary to this critical holy grail are further dissatisfactions on the practical functionality of investment arbitration in aspects of high volume of cases against developing states, lack of diversity in the appointment of arbitrators and curtailment of sovereignty of host states through the intrusion of provisions of International Investment Agreements on legitimate internal decision-making powers. Consequently, this thesis investigated the practical functioning of ISDS in African states. After the study of the experiences of Egypt, South Africa and Tanzania; it was found that the legitimacy crises of ISDS also impacts on African states, and does not support their socio-economic and sustainable developmental aspirations. As a remedy, I proposed for a reform to an Investment Court System (ICS) through the establishment of a Pan-African Investment Court (PAIC). An evaluation of this recommendation was conducted that evidenced potential challenges that may mitigate its feasibility, thus leading to the advancement of two secondary reform alternatives vis the reform and retention of the current investor-state arbitration framework and engagement in innovative treaty-making practices by African states. To the best of my knowledge, this thesis has not been previously submitted in any higher institution or published by another person. The contents of this thesis are my ideas. Where the materials of others were used, due acknowledgement and reference was provided. Acknowledgements
Permalink: https://repository.canterbury.ac.uk/item/90873/investor-state-arbitration-and-african-states-a-proposal-for-a-pan-african-investment-court
Keywords: Arbitration; Investment Court System; Investments; Investor-State Dispute Settlement; Investor-state arbitration

Rights on news : expanding copyright on the internet - Furgal, Urszula (European University Institute, 2020)
The internet and digital technologies have irreversibly changed the way we find and consume news. Legacy news organisations, publishers of newspapers, have moved to the internet. In the online news environment, however, they are no longer the exclusive suppliers of news. New digital intermediaries have emerged, search engines and news aggregators in particular. They select and display links and fragments of press publishers’ content as a part of their services, without seeking the news organisations’ prior consent. To shield themselves from exploitation by digital intermediaries, press publishers have begun to seek legal protection, and called for the introduction of a new right under the umbrella of copyright and related rights. Following these calls, the press publishers’ right was introduced into the EU copyright framework by the Directive on Copyright in the Digital Single Market in 2019.
Accepted: 2020-02-20T11:26:15Z
Keywords: Copyright; Digital media; Electronic information resources; Intellectual property; Internet; Propriedade intelectual; Propriété intellectuelle

Re-integration, rehabilitation and return-to-work of disabled workers : a comparative legal enquiry - Gresse, E. (North-West University, 2020)
There are many employment positions in the labour market that could be filled by the disabled of whom most, given the right environment, could be productive in the workplace. However, there are employers who still labour under the misconception that Persons with Disabilities (PWDs) are unqualified and unproductive although their participation in the workplace could contribute to the national economy, while restoring their dignity and social integration. The United Nations Convention on the Rights of Persons with Disabilities (CRPD) entered into force on 3 May 2008. The CRPD is the first international legally binding treaty aimed specifically at protecting the rights of PWDs. It is expected of ratifying States Parties to either amend their domestic existing laws or to enact new legislation in order to meet their obligations, as set out in the CRPD. In 2008, South Africa ratified the CRPD and the Optional Protocol, thus committing itself to the provisions relating to, inter alia, workplace integration. Article 26 of the Convention mandates States Parties to take effective and appropriate measures to enable PWDs to attain and maintain maximum independence, physical, mental, social and vocational ability, and to ensure their social inclusion. Article 27 stipulates, inter alia, that States Parties shall safeguard and promote the realisation of the right to work, including those who incur a disability during the course of employment. Legislation should make provision for, inter alia the following: • enable PWDs to have effective access to general technical and vocational guidance programmes; • placement services and continued vocational training; • promote employment opportunities and career advancement; • assistance in sourcing, obtaining, maintaining and returning to work; and • reasonable accommodation in the workplace as well as vocational and professional rehabilitation. Although the Compensation for Occupational Injuries and Diseases Act 130 of 1993 was amended recently to include rehabilitation, re-integration and return to work (RTW) as part of its objectives, it will be argued that South Africa needs to initiate targeted legislation and policies that make disability management functions mandatory. Employers’ obligations need to be set out clearly in the Act, because, as it stands, the following lacunae exist: • There is no obligation to appoint Case Managers; • Dismissal protection is not provided for; • The regulation of negative incentives to assist with RTW compliance is lacking; and • The roles of different stakeholders in the RTW process require clarification. Without South Africa having an appropriate and detailed RTW framework, ill or injured employees stand the risk of losing their jobs and becoming dependent on family members and/or disability grants. Against this background, a comparative analysis of international and regional law and the RTW practices of two foreign jurisdictions were made. This enabled the author to devise recommendations and identify the roles of the government, employers, employees and Case Managers. The primary objective of this thesis is to determine how and to what extent regional and international standards and RTW programmes in other countries could assist in developing and amending the current legislative and policy framework in South Africa to promote the RTW of disabled employees.
Keywords: Disability management; Persons with Disabilities; Re-integration; Rehabilitation; Return to work

The effectiveness of the adopted OECD transfer pricing dispute resolution mechanisms in an African context - Kekana, Nelson Doctor (University of Pretoria, 2020)
With the developments happening globally that are aimed at curbing base erosion and profit shifting by multinationals, improving the resolution of transfer pricing disputes has been identified as one of the key issues. This thesis investigates the challenges uniquely faced by African countries that militate against the use of the OECD transfer pricing dispute resolution mechanisms. The thesis starts by reflecting on the effect of transfer pricing manipulation by multinational enterprises in Africa in particular. Transfer pricing manipulation is one of the causes of the so-called tax gap, which is, the gap between anticipated and actual revenue collection. The aggression by revenue authorities against transfer pricing manipulation in order to close this gap has triggered a lot of transfer pricing adjustments. These adjustments have resulted in multiple transfer pricing disputes. In the analysis of the adopted OECD dispute resolution mechanisms, the thesis focuses on the effectiveness of the mutual agreement procedure (MAP), the advance pricing arrangement (APA) and the mandatory binding arbitration (MBA). It identifies the problems that result in the failure of or the delay in the resolution of many transfer pricing disputes by analysing the domestic frameworks that exist in four African countries namely: South Africa, Kenya, Uganda and Ghana. The thesis identifies problems such as the absence of a tax treaty network within the African continent, the use of underdeveloped double tax agreements and the lack of commitment from African countries to subscribe to and ratify multilateral conventions. These problems delay or stifle the resolution of tax treaty disputes. They also cause uncertainty for taxpayers and lead to continued tax avoidance by multinational enterprises that essentially avoid paying tax in African countries where the economic activities of these enterprises take place. The thesis also identifies the importance of other OECD supporting tools such as the exchange of tax information in the resolution of transfer pricing disputes. It focuses on tools such as country by country reports, the master file, the local file and simultaneous tax examination as covered by the Multilateral Convention on Mutual Administrative Assistance in Tax Matters. The thesis contributes to the resolution of the identified problems with transfer pricing dispute resolution in Africa by recommending certain improvements that can be effected. These recommendations entail, regarding the MAP, the expansion of tax treaty networks by African countries and the establishment of a Tax Treaty Dispute Resolution Committee by ATAF. Regarding the APA, it is recommended that African countries should sign the multilateral instrument (MLI) and make use of advance tax rulings (ATRs) as alternatives. With respect to the MBA, this thesis recommends that African countries should use optional arbitration by effectively using article 25(4) of the OECD Model tax convention (MTC). It also recommends that African countries must enhance their tax transparency by ratifying multilateral conventions that seek to address international tax co-operation and to improve compliance with transfer pricing documentation requirements in order to make the resolution of transfer pricing disputes more effective.
https://repository.up.ac.za/handle/2263/80889
Keywords: Dispute resolution; Model Tax Convention; OECD; Transfer pricing

Algeria and the African Union - between security and economic integration: a neofunctionalist and regionalist reading - Lamri, Amel (Canterbuy Christ Church University, 2020)
This thesis investigates the process of integration in the African Union (AU), and the reasons behind the slow progress of the AU to achieve the goal of deeper economic integration. In the research I explore the role of an AU member state in the process of African integration: Algeria. The research scrutinises the development of Algerian foreign policy towards the AU and highlights any changes in the Algerian FP attitudes and the reasons behind these changes. Similarly, the research unveils the reality of the decision-making process in this country, and the different agents that influence it. To achieve the main goals of the research, different theoretical choices were elaborated. This resulted in researching European integration theories; Neofunctionalism was, then, selected to study the Algerian development in the making of its foreign policy in general and towards the African Union specifically. Some concepts within the Neofunctionalist thinking were used including the principle of the shift of loyalties, the socialisation process, the spillover system, and the role of interest groups in the process of integration. Moreover, the theory of Regionalism was used to examine the process of integration in the AU discovering new reasons that led to the slow development of economic integration in Africa. Consequently, the research highlights the current obstacles and challenges that have hindered the process of economic integration in the AU, including the poverty of most of the AU member states, the limited financial budget of the Union and the instability of the majority of African countries. Furthermore, the research unveiled the lack of political will towards AU economic integration plans. Hence, this contribution extends beyond the traditional models of explanation, and discusses the situation in AU member states (in this case Algeria) and points to other factors as well such as the weakness of the lobbyist activities and business groups in Algeria specifically and Africa more generally. The thesis, then, focusses on Algeria’s supportive and active status in the AU security sector, highlighting how Algeria has been successful in pushing its own security and antiterrorism agenda to the AU level, thereby demonstrating that integration into the AU is possible, if it is backed by influential member states, and wider coalitions can be built to promote integration and cooperation.
Permalink: https://repository.canterbury.ac.uk/item/8y60y/algeria-and-the-african-union-between-security-and-economic-integration-a-neofunctionalist-and-regionalist-reading
Keywords: Africa Union; Algeria; Intégration régionale

An Empirical Analysis of Private Equity Investment Affecting Enterprise Value - Li, Jianhong (Université de Genève, 2020)
The lack of long-term and stable financial support for SMEs is the fundamental reason why enterprises cannot develop for a long time. At present, the situation of financing difficulties for SMEs is becoming more and more serious. Private equity (PE) investment has emerged as an important financing method. Private equity investment, while broadening the financing channels of SME capital markets, brings advanced management experience to enterprises, which helps enterprises to develop rapidly and effectively. According to the statistics of the Zero2IPO Research Center, the active investment institutions in China's equity market have grown from more than 200 in 2000 to more than 14,000 in 2018, with a total asset under management over RMB 9 trillion. Great progress has been realized in the scale and development of the industry. In addition, with the launch of the GEM in 2009, PE investment industry met new opportunities of development and became popular. At present, the development of China's PE investment business is still at an early stage. Neither relevant policies, laws and regulations nor supporting mechanisms are mature enough. Therefore, researches on China's PE investment business needs to be carried out. In this context, more and more scholars are beginning to focus on the field of PE investment. This paper focuses on whether PE investments can fundamentally increase the enterprise value. The basic theory is sorted out to serve as the theoretical basis for this study. Through a systematic analysis, this paper draws out 4paths of PE investment affecting enterprises, which are the influence on technological innovation, corporate governance activities, dividend distribution decision and earnings management, respectively. And through empirical analysis, it finds the empirical basis of the impact of PE investment on enterprise value, and investigates how PE investments affect enterprise value based on the difference in investment characteristics such as investment duration and whether the investment is joint or not. This paper conducts an empirical test by selecting the listed companies of the Shenzhen Stock Exchange GEM in 2015-2018 as sample. The results show that the investment of PE firm will significantly increase the value of the target enterprise. This paper makes a detailed analysis of sample data. The conclusion of the study is that private equity investment will have a significant impact on the value of target enterprises. Private equity investment plays an important role in the modern governance structure of small and medium-sized enterprises in China This paper enriches the existing literature and provides constructive suggestions for the health development of the PE investment market. 中小企业缺乏长期稳定的资金来源是企业无法长久发展的根本性原因，目前 中小企业融资难的形势越来越严峻，私募股权投资作为一种重要的融资手段应运 而生。私募股权投资在拓宽中小企业资本市场融资渠道的同时，给企业带来先进的 管理经验，有助于企业快速并有效的发展。据清科研究中心的统计数据显示，中国 股权市场活跃的投资机构已由 2000 年的 200 多家发展到 2018 年的 1.4 万多家，管 理资本量超过 9 万亿人民币，行业规模和发展实现了质的飞跃。此外，随着 2009 年创业板的推出，私募股权投资行业的发展业迎来了新的希望和契机，私募股权投 资业务开始盛行。目前，我国私募股权投资业务的发展还处于早期阶段，无论是从 政策还是法律法规再到配套机制，都还不够健全。因此，对我国私募股权投资业务 的研究亟需开展，在此背景下，越来越多的学者开始关注私募股权投资这一领域。 本文研究的重点是私募股权投资是否能够根本上提升企业价值。本文首先对 基础理论进行了梳理，以此作为研究的理论依据，而后论述了私募股权投资对被投 资企业价值影响的理论分析，。本文通过系统的理论分析得出了私募股权投资影响 企业的路径，并通过实证分析，得到私募股权投资对企业价值的影响的实证依据， 并且从投资期限和是否联合投资等投资特征的差异性，深入研究私募股权投资对 企业价值的影响方式。本文通过选取深圳证券交易所创业板 2015-2018 年的上市企 业作为样本，进行了实证检验，并得出以下研究结论:私募股权投资的参与会显著 提升目标企业的价值，同时，私募股权投资的期限越长、联合投资机构的数量越多， 目标企业的价值也会越高。 本文基于理论又结合实际，对样本数据进行了分析，研究的结论是私募股权投 资会对被投资企业的价值产生显著影响。私募股权投资对于我国中小企业的现代 化治理结构起到了完善作用。本文的研究结果丰富了现有文献，对私募股权投资市 场健康发展提出了建设性的建议。
Keywords: Enterprise Value; Investment Term; PE Investment

Corporate social responsibility and executive personality - Li, Xin (Simon Fraser University, 2020)
My dissertation investigates two streams of managerial accounting literature; specifically, corporate social responsibility (CSR) and executive personality. Paper 1 focuses on whether companies strategically engage in CSR practices to retain employees. Using a difference-in-differences design, I find that an increase in the enforcement of non compete agreements (which enhances a firm’s ability to retain employees) deteriorates CSR performance. Paper 2 extends prior literature and links managerial risk tolerance and firms’ CSR performance. The empirical result of Paper 2 shows that pilot CEOs are less likely to exhibit better CSR performance. Paper 3 examines the spillover effect of managerial risk tolerance along the supply chain. Specifically, I follow Paper 2 to use the pilot status of CEOs to proxy for the customers’ risk tolerance level. Overall, the results support a negative association between customer risk tolerance and supplier investment efficiency, and customer companies ran by pilot CEOs leads to supplier investment inefficiency. Each chapter is designed to be self-contained and provides a more detailed discussion of the research question and contribution.
Keywords: CEO; CSR performance; Corporate Social Responsibility; Non-compete enforceability; Pilot; RSE; Risk tolerance; Supplier investment efficiency

The regulation of international commercial arbitrators - Loreto Ilhao Moreira, João (University of Oxford, 2020)
International commercial arbitration has established itself as the main dispute resolution mechanism for international commercial disputes. This increased visibility has drawn attention to arbitrators’ public role, leading to a well-established general perception that arbitrators are bound to special obligations, such as the duty to be independent and impartial or the obligation to assure that arbitral proceedings are not abused to achieve nefarious goals. Despite this general acknowledgement, little attention has been paid to the mechanisms that ensure that arbitrators adhere to these obligations. In particular, there has been limited analysis of the underlying mechanisms that incentivise the production and enforcement of professional norms in this field. This thesis argues that the particulars of the arbitration market largely explains why the evolution of the regulation of international arbitrators has not matched those of other professions. At the same time, it will argue that those same particularities create incentives for several actors, most notably the arbitral community itself, to step in and occupy this regulatory vacuum. In particular, it explores the notion that the market strategies employed by arbitrators, arbitral institutions and other members of the arbitral community have the production of professional norms as a by-product. It further explores how the arbitral market tends to create an environment where compliance with professional norms is rewarded, leading, at the same time, the arbitral community to work as a network that promotes adherence to professional norms through mostly informal sanctions.
https://ora.ox.ac.uk/objects/uuid:c2dd717f-e53b-4ab6-b848-c089b70adec2
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration (international law); Arbitration market; Dispute Resolution; International commercial arbitrators; Regulation

Portability of social security benefits of circular migrant workers in selected SADC member states - Masoebe, P. (North-West University, 2020)
The issue of portability of social security benefits is a daunting issue facing migrant workers in both Southern Africa and the world in general. In the Southern African Development Community region migration seems to be driven mainly by the need to attain economic freedom. The fact of the matter is that migrant workers from Lesotho and Swaziland who work and have worked in South Africa do play a major role in boosting these countries’ economies. Another issue that cannot be ignored is the fact that circular migration as a phenomenon is unlikely to come to an end any time soon in this part of the world. This means that social security benefits of migrant workers and its portability should be an issue that is dealt with cautiously and speedily, especially in terms of looking at the millions of unclaimed social security benefits reported each year by social security funds and schemes in South Africa. While examining the extent to which selected SADC member states, namely Lesotho, Swaziland and South Africa, have undertaken to combat this issue, international and regional instruments that have a bearing on social security rights are analysed and the realisation is that in as much as these do provide for social security rights and portability of benefits thereof, a lack of ratification and implementation play a vital role in achieving efficient portability of these rights. Although South Africa, as the largest migrant-receiving country in the SADC region, does provide for the right to social security in its Constitution, the fragmented nature of its social security framework, together with other factors such lack of information, exploitation by employers, distances travelled to lay claims and a non-existent social security adjudication system means that migrant workers are normally left with lack of redress when their contracts of employment reach an end. On the other hand, Swaziland and Lesotho, as migrant-sending countries, do not even have provisions in their constitutions that specifically deal with the right to social security. This means that citizens who work abroad do not have sufficient social security coverage in either country, as well as in South Africa as a host country. Consequently, multilateral and bilateral agreements on social security are pivotal in addressing this issue of unclaimed social security benefits as they go a long way in making sure that migrant workers are provided with adequate social security protection and coverage as a whole. Migrant sending countries also need to undertake unilateral initiatives to guarantee that their citizens are adequately protected in this specific sphere of social security. Examples are further drawn from the best practices of different regions in the world, namely the Southeast Asian Nations Region, Caribbean Community and Common Market and the Southern Common Market. The above-mentioned regions have established multilateral social security agreements that seek social security protection for migrant workers who play an undeniable role in their economies. Bilateral social security agreements between Zambia and Malawi, together with the one between Sweden and Philippines, are taken into consideration as best practices that Lesotho, Swaziland and South Africa may draw examples from when drawing up and concluding their own bilateral social security agreements. The Philippines’ unilateral initiatives are also discussed and hailed as the best practices that migrant-sending countries such as Lesotho and Swaziland may further draw examples from. The Philippines has developed strategies aimed at guaranteeing social protection for its migrant workers abroad and further makes sure that it enters into bilateral agreements with any country that receives services from its citizens. While the need to conclude multilateral and bilateral agreements on social security cannot be denied, there is also a need for migrant-sending countries to come up with unilateral initiatives to lessen the burden on migrant-receiving countries in this social security domain. Sectors such as the mining sector should also have mining-specific agreements that specifically deal with issues related to migrant mine workers. Lack of statistics of migrant workers moving in and out of South Africa has also been labelled as one of the reasons halting access and portability of social security benefits; hence there is a need to develop a data-base aimed at keeping track of all migrant workers, retired and otherwise. Migrant workers who seek redress regarding access of their unclaimed or unpaid social security benefits also have to be provided with comprehensive protection from the courts of law. This therefore means that an adjudication system should be established to deal with social security woes so that those seeking redress have adequate legal support.
Keywords: Labour and social protection; Migrant workers; Multilateral agreements; SADC; SADEC; Social protection; Social security; Sécurité sociale; Travailleur migrant

The liquidation process and unsecured creditors: using the resulting trust to restore the balance - Stubbins, Matthew (Canterbury Christ Church University, 2020)
Ever since the formation of limited companies became permissible, unsecured creditors have faced a Sisyphean struggle to regularly recover substantial levels of the debts owed to them should corporate creditors enter insolvency. These low recovery rates result in many issues for lenders, including large losses, and in some cases, the insolvency of the lender themselves. The causes of these low return rates are long established and clearly demarcated. They consist of the existence and widespread use of security interests - which remove the majority of the company’s assets upon insolvency occurring - and the statutory priority of distribution, which ensures that parties other than the unsecured creditors have their debts discharged first by the liquidator from the already insufficiently resourced asset pool. English insolvency law has sought to provide some protection to the unsecured creditors through the anti-deprivation and personal liability provisions of the Insolvency Act 1986, which are intended to protect the integrity of the insolvent company’s asset pool. However, as concluded by this thesis, these provisions fail to afford adequate protection as a consequence of their substantive, evidential and remedial limitations, potentially resulting in the distributable assets being misappropriated and out of the reach of unsecured creditors. This thesis therefore analyses the limitations of the existing anti-deprivation and personal liability provisions before concluding as to how and why they fail to adequately protect unsecured creditors. This is done through a doctrinal and theoretical analysis of the provisions, before these conclusions are then tested empirically in two case studies. Given the inadequate protection provided by the Insolvency Act, this thesis then analyses the resulting trust – on which little analysis has been conducted in the context of insolvency – to determine whether it is capable of assisting unsecured creditors to increase their liquidation return rates. This increase is achieved through returning assets beneficially owned by the company to the company, or by preventing parties from becoming unsecured creditors in the first place by removing assets beneficially owned by them from the company. This analysis too will adopt a doctrinal and theoretical methodology, and it is concluded that the resulting trust is able to assist should the requisite factual matrices occur.
Permalink: https://repository.canterbury.ac.uk/item/8z4x2/the-liquidation-process-and-unsecured-creditors-using-the-resulting-trust-to-restore-the-balance
Keywords: Insolvabilité; Insolvency; Insolvência; Liquidation

Promoting financial inclusion through mobile money while introducing regulatory solutions to reduce and control money laundering in Lesotho - Taole, T. E. (North-West University, 2020)
Mobile money services have considerable potential in modern economies. They have the potential to increase financial inclusion for poor people and people excluded from formal financial services. This is because mobile money services can be accessed simply using a mobile cellular phone and the majority of people nowadays own mobile phones, including people living in the rural areas. Mobile money can therefore solve the problem of financial exclusion because even the people who live in the rural areas without access to formal financial services can now access financial services thorough mobile money services. Financial inclusion, on the other hand, is simply defined as a situation where every member of the society has access to and is able to use financial services offered by formal financial services institutions, such as banks and insurance companies. Financial inclusion has many benefits, the main benefit being the stimulation of the economy of a country. For mobile money services to operate smoothly and financial inclusion to be achieved, there must be enabling regulation. Regulation must not be so strict as to prevent mobile money service providers from operating. Regulation must allow for innovation and at the same time maintain financial integrity and stability by ensuring that financial crimes, such as money laundering, do not affect mobile money services. Although mobile money services can increase financial inclusion, regulators must be vigilant to ensure that they stop criminals from using mobile money services to commit money laundering offences. This research focuses mainly on mobile money services in the Kingdom of Lesotho. The aim is to find out how regulation can be improved to ensure that mobile money services can help to increase financial inclusion. The aim is also to find out how regulation can help to ensure that mobile money services operate smoothly, and that the crime of money laundering is prevented from affecting mobile money services. To achieve this aim, the research is divided into different chapters and in each chapter the aim is to find ways in which the main aim can be achieved. In the research, mobile money and financial inclusion will be defined and their importance in modern economies will be demonstrated in greater detail. Furthermore, the issues of money laundering will be discussed. The threat of the crime of money laundering will be highlighted. An analysis of the legal regulatory framework of mobile money services and money laundering in Lesotho will be undertaken to determine the extent to which these regulatory frameworks can help realise financial inclusion and promote mobile money services in Lesotho. The same discussion is made in respect of other African countries. The legal regulatory framework of Lesotho will be compared to the framework of other African countries to ascertain how mobile money services and money laundering and financial inclusion issues are regulated in those countries. The countries discussed in this research are South Africa, Malawi, Kenya, Nigeria, Uganda, Tanzania, and Ghana. Based on these discussions, some shortcomings in the legal regulatory framework of mobile money services and money laundering in Lesotho will be identified and the conclusion will be drawn that the two frameworks have to be revisited to ensure that mobile money services will operate smoothly in the Kingdom of Lesotho. Furthermore, recommendations will be made to address the legal shortcomings identified in the framework.
Keywords: Financial inclusion; Lesotho; Mobile money services; Regulatory framework

The adaptation of China’s maritime arbitration system to international legal norms and practice - Xuan, Yan (The University of Queensland, 2020)
Maritime transport is essential to the world’s economy and maritime arbitration plays a crucial role in maritime dispute resolution. Nowadays, many coastal jurisdictions have set up their own maritime arbitration institutions such as those in the US, the UK, Germany, Australia, China, Japan, Hong Kong, and Singapore. Building a national world-advanced maritime arbitration system as soon as possible to suit China’s rapid developments in shipping and international trading does not permit of any delay. How should China improve her laws, rules and institutions, including those for the enforcement of maritime arbitration awards, having regard to leading international maritime arbitration systems? It is posited that selective adaptation from the successful experience of other maritime arbitration systems is the most convenient and effective way to achieve such a goal. This adaptation will follow from a comprehensive and comparative study of the maritime arbitration laws, rules and the maritime arbitration institutions, including the laws relating to the enforcement of maritime arbitration awards, from these main global maritime arbitration centres in order to make China’s maritime arbitration more competitive at the international level. This thesis does not purport to cover every research field relating to maritime arbitration. Instead, as previously stated, it will focus only on the comparative study of some selected key issues of international commercial arbitration among the selected jurisdictions. A comprehensive study of international commercial arbitration or international maritime law is not the subject of this thesis. It should be noted further that this research basically concentrates on the practical problems of maritime arbitration practices, rather than taking an overly theoretical approach. The thesis selects the UK, the US, Singapore and Hong Kong as the target jurisdictions for comparison. Through selective comparative analysis of the key issues of maritime arbitration systems in the selected jurisdictions, which are internationally recognised as significant by many arbitration scholars, this thesis proposes that all these issues could conveniently be categorised into four key criteria; namely, fairness, confidentiality, efficiency and enforceability. It follows that the adaptations of the Chinese maritime arbitration system should mainly focus on these four criteria, as these are the most critical factors for the development of Chinese maritime arbitration system. Moreover, these four criteria should also have significance for other underdeveloped maritime arbitration systems. Also, based on these four key criteria, the thesis provides some specific suggestions on how the Chinese maritime arbitration system can be adapted to reflect other selected jurisdictions in the respects of some key issues of international commercial arbitration.
Keywords: Arbitrage; Arbitragem; Arbitration; Confidentiality; Droit maritime; Efficiency; Enforceability; Fairness; Maritime arbitration

What drives individual decision-making of Foreign Direct Investments (FDI) to Sub-Saharan Africa - Yusuf, Mukhtar Abubakar (Case Western Reserve University, 2020)
This dissertation examines a multiplicity of factors that influence at the microeconomic level the level of Foreign Direct Investment (FDI). The main objective of the dissertation is to empirically explore and validate the effect of a select set of individual-level perceptual factors on FDI decisions. Given the paucity of research on the topic in comparison to macroeconomic studies of investment inflows between regions and countries, we conduct the study as a mixed-method study. The study consists of three interconnected empirical studies. The first seeks to identify the presence of factors that shape an individual’s decisions on FDI inflows. The two following ones seek to validate the effects of these factors on the individual decision maker's propensity to invest in a specific country. The first study belongs to a qualitative strand and answers the following research question: What are the investor’s critical perceptual factors and experiences that influence their FDI decisions? The study participants consisted of 30 foreign investors, the government’s Ministries, Departments, and Agencies (MDAs), and the Nigerian investors in the diaspora. The paper finds that on the supply side, several key FDI perception factors influence decision-making. On the demand side, there are four attractors and four repellents that influence potential investors' decisions. In the quantitative strand of the study, we offer the following questions: (1) To what extent do investment decision perception impact foreign direct investment (FDI) inflows? And (2) To what extent do the investors from Europe and North America and investors from Asia and Africa (the West and the East) influence what factors matter in foreign direct investment (FDI) decisions? The samples consist of 269 individuals from the private sector, both in Nigeria and in the diaspora that participated in the survey. I use structural equation modeling to find that Return on Investment (ROI), Security/Personal Safety, and Investment Facilitation Services have a significant direct effect on the FDI decisions. A post hoc exploratory analysis indicates positive relationships between Ease of Doing Business and Investment Promotion and FDI are significant for investors from the investors from Europe and North America as well as the negative impact of Corruption. In contrast, the positive relationship between Return-On-Investment and FDI is more substantial for investors from East Asia and Africa. The next part of the quantitative strand investigates (1) to what extent investment promotion services and Investment Facilitation effects in the receiving country shape positive investment decision outcomes, and (2) to what extent investment perceptions and related decisions vary across industry groups facing different investment horizons and risk levels. The analysis indicates that the Investment Promotion services significantly mediate Corruption Perceptions and Investment Facilitation services. And Investment Facilitation does moderate the effect of Investment Promotion. The exploratory industry-level analysis reveals that the effects of Return On Investment to FDI decisions and Security to FDI decisions significantly differ across Infrastructure-Mining/Services, Services/Agriculture-Manufacturing, and Agriculture-Manufacturing/Infrastructure-Mining industries suggesting significant Industry-level effects. Generally, these findings reveal much more refined and complex dynamics of FDI inflows and how individual investor’s perceptions shape them. Specifically, the results provide deeper insights into the investor’s risk perceptions that arise in a particular country. This depends on holistic perceptions of the country’s economic, political, and social environment, and also the investor’s time horizon and risk preferences signaling significant individual and situational differences in how decision-makers approach FDI.
Keywords: Corruption; Ease-of-doing-business; FDI; FDI attractors; Foreign direct investment; Investment decision-making; Investments; Nigerian Investment Promotion Commission; Perception; ROI; Return on investment; Security

The enforceability of interim measures granted by an emergency arbitrator in international commercial arbitration - Zhang, Junmin (ProefschriftMaken, 2020)
The emergency arbitrator mechanism makes interim measures possible for parties involved in international commercial arbitration before the constitution of arbitral tribunals under urgent situations. However, with the development of the emergency arbitrator mechanism, the enforceability of interim measures made by an emergency arbitrator is questioned. This uncertainty leads to the hesitation of legal practitioners to apply the emergency arbitrator mechanism in practice. The research conducted two comparisons between different arbitration rules and between arbitration laws in jurisdictions. After discussing the legal status of an emergency arbitrator, the legal criteria to render interim measures, the potential barriers for the enforceability, and possible harmonization, it concluded that the interim measures granted by an emergency arbitrator in international commercial arbitration should be enforced and even harmonized through mandatory and non-mandatory methods.
Keywords: Arbitrage; Arbitragem; Arbitral Tribunal; Arbitration; Arbitration Law; Arbitrator; Commercial Arbitration; Emergency arbitrator; Enforceability; Interim measures; International commercial arbitration

The Impact of Economic Institutions on Small Firms in Developing Countries - Pouliquen, Victor (Ecole des Hautes Etudes en Sciences Sociales, 2019)
In many developing countries, economic institutions are failing. This translates into structural problems such as widespread informality, rampant corruption and the impossibility for governments to raise taxes. This thesis study how economic policies affect economic institutions in developing countries. It focuses on two broad questions: (1) What are the effects of policies to reduce informality? and (2) how are new technologies reshaping the way governments collect taxes?The first chapter uses a randomized experiment to study the introduction of a new legal status in Benin, created to make it easier for small firms to become formal. To make this new status attractive, the government added supplementary incentives designed to enhance the presumed benefits of formalizing. We find that few firms register when just given information about the new regime, but our full package of supplementary efforts boosts formalization by 16.3 percentage points. However, this formalization does not bring firms higher sales, profits or access to credit, and the cost of formalizing these firms exceeds the added taxation they will pay over the next decade. We show how better targeting of these policies towards firms that look more like formal firms to begin with can increase the formalization rate and improve cost-effectiveness. The second chapter studies the impact of formalization on intra-household relationships, still in Benin. The idea behind this chapter is that formalization changes effective property rights by clarifying who in the household is the legal owner of the business and who will keep it in case of divorce. The causal effect of formalization is identified using the same random experiment used for the first chapter. We find first that formalization increases entrepreneurs' (both male and female) control over household revenue. They contribute proportionally less to household expenditures and to the personal expenses of their partner. Second, using a behavioral game, we find strong gender differential effects of formalization on the probability that entrepreneurs pay to hide a windfall transfer from their spouse. Female entrepreneurs are much more likely to pay to hide, while male entrepreneurs are much less likely to do so. Using a theoretical model, we show that this result is compatible with the idea that women entrepreneurs are constrained and cannot invest as much as they would like in their own business. Women who became formal hide the windfall transfer more because they have more property rights and want to invest more in their business. Our conclusion is that formalization has important effects on intra-household dynamics.The third and final chapter of this thesis deals with the second question and examines how internet is changing the way taxes are collected. Specifically, we study the impact of electronic tax filing (e-filing) for small firms to replace in-person submission of paper-based forms to tax officials. We examine the impact of e-filing on compliance costs, tax payments, and bribes payments using experimental variation and data from Tajikistan firms. We find that firms that e-file have lower compliance costs, spending five fewer hours each month on fulfilling tax obligations. There are no significant average effects of e-filing on tax or bribe payments, but significant heterogeneity exists across firms by their baseline likelihood of tax evasion. Among firms previously more likely to evade, e-filing doubles tax payments, likely by disrupting collusion with officials. Conversely, among firms less likely to have been evading, e-filing reduces tax payments, suggesting that officials had previously required them to pay more. These firms also pay fewer bribes, as e-filing reduces opportunity for extortion. Our conclusion is that e-filing reduces compliance costs and makes the distribution of tax payments across firms arguably more equitable. Dans les pays en développement, les institutions économiques sont souvent défaillantes. Cela se traduit par des problèmes structurels tels que l’omniprésence du secteur informel, la corruption généralisée et l’incapacité des États à collecter les impôts. Cette thèse porte sur les politiques publiques permettant d’améliorer le fonctionnement des institutions économiques. Elle se focalise sur deux questions : (1) Quels sont les effets des politiques de réduction de l’informalité ? et (2) Comment les nouvelles technologies affectent la collecte des taxes ? Le premier chapitre étudie à l’aide d’une expérimentation aléatoire l’introduction d’un statut légal facilitant la formalisation des petites entreprises au Bénin. Afin de rendre ce statut attractif le gouvernement l’a accompagné d’incitations supplémentaires créés pour amplifier les bénéfices potentiels de la formalisation. Nous trouvons que très peu d’entreprises se formalisent lorsqu’elles reçoivent uniquement de l’information sur le nouveau statut. Cependant, lorsque l’information est combinée aux incitations, la formalisation augmente de 16,3 points de pourcentage. En revanche, les effets sur les performances des entreprises sont limités, et le coût des incitations est supérieur au total des impôts qu’elles paieront pendant les 10 prochaines années. Enfin, nous montrons comment un ciblage sur les entreprises ayant des caractéristiques proches des entreprises déjà formelles améliorerait l’efficacité de ce type de programme. Le second chapitre étudie l’impact de la formalisation sur les relations intra-ménages, toujours au Bénin. Dans ce contexte, la formalisation renforce les droits de propriété et clarifie au sein des ménages qui est le propriétaire légal de l’entreprise, et qui la gardera en cas de divorce. L’effet causal de la formalisation est identifié à l’aide de l’expérimentation aléatoire déjà utilisée pour le premier chapitre. Nous trouvons que les entrepreneurs s’étant formalisés ont plus de contrôle les ressources de leur ménage. Ils ou elles contribuent proportionnellement moins aux dépenses du ménage et transfèrent moins d’argent à leur partenaire. Deuxièmement, en utilisant un jeu comportemental dans lequel les entrepreneurs peuvent cacher un transfert monétaire à leur partenaire, nous trouvons que les femmes qui se sont formalisées cachent davantage à leur mari. A l’aide d’un modèle théorique, nous montrons que ce résultat est compatible avec l’idée que les femmes ne sont pas libres d’investir comme elles le souhaiteraient dans leur entreprise et doivent le faire secrètement. Notre conclusion est que la formalisation a des effets importants sur les dynamiques intra-ménage. Le troisième chapitre utilise une expérimentation aléatoire conduite au Tadjikistan pour étudier l’impact d’un système permettant aux entreprises de déclarer leurs taxes en ligne plutôt que de soumettre un formulaire en personne. Nous trouvons que ce système réduit le temps passé par les entreprises pour remplir leurs obligations fiscales de 5 heures par mois. Nous ne trouvons pas d’effets sur le montant des impôts payés ni sur le versement de pots-de-vin. En revanche, l’absence d’effets moyens masque une importante hétérogénéité. Les entreprises le plus susceptibles de faire de l’évasion fiscale dans le système précédent payent davantage d’impôts quand elles déclarent en ligne, probablement car elles ne peuvent plus entrer en collusion avec les agents des impôts. À l'inverse, les entreprises qui étaient les moins susceptibles de faire de l’évasion, payent moins des taxes quand elles déclarent en ligne, suggérant qu’elles étaient forcées de payer plus d’impôts avant. Ces entreprises paient également moins de pots-de-vin, ce qui suggère que déclarer en ligne offre une protection contre le risque d'extorsion de la part des agents du fisc. Notre conclusion est que permettre la déclaration des taxes en ligne a rendu l’appareil fiscal à la fois plus efficace et plus juste.
Keywords: Droits de Propriétés; Electronic Tax Filing; Impôt; Impôt (recouvrement); Informality; Informalité; Innovation; Intra-Household Relationships; New Technologies; Nouvelles Technologies; Paiement en ligne des Taxes; Petites Entreprises; Petites et moyennes entreprises; Property Rights; Propriété; Relations Intra-Ménage; Small Firms; Taxation; Économie souterraine

The contribution mediation can make in addressing economic crime in corporate and commercial relationships in South Africa - Hoffman, Cornelia Hendrina (Stellenbosch University, 2019)
Economic crime is complex and costly. It is costly because it harms victims, both directly and indirectly, as well as the broader economy. The cost is not only financial, but also to confidence and trust in corporate and commercial relationships in South Africa. Economic crime is complex because it includes offences from common-law fraud to statutory contraventions such as incorrect bookkeeping. There are several mechanisms in the South African legal justice system to address economic crime. The conventional legal models include adversarial criminal prosecution of the offender and civil compensation claims, the model of inquisitorial administrative investigations and sanctions like penalties and compensation orders. In 2001 section 105A of the Criminal Procedure Act, namely plea and sentencing agreements, was added as a model of negotiated justice. This mechanism allows the prosecution and the offender to negotiate and enter into an agreement regarding the charges and the sanctions, subject to approval of the court that the plea of guilty is proper and that the proposed sanction is a just sentence. This dissertation proposes that mediation be added to the existing alternative models to help combat economic crime. Mediation involves negotiated justice, as well as restorative justice. More specifically, mediation as a restorative justice process, constitutes a practical alternative to standard litigation as the affected parties themselves, with the facilitation of a third person, resolve the disputes between them. Mediation, a facilitative and flexible procedure, allows the voices of both the victim and the offender to be heard securely and meaningfully. Mediation is rehabilitative and allows for agreed restorative provisions for both the perpetrator and the victims of economic crime. The outcome is a proposed amendment to the Criminal Procedure Act 51 of 1977, namely the insertion of section 105B, “Mediated Settlement Agreements”, that will provide for mediation and a mediated settlement agreement to be incorporated into and form part of the criminal justice processes. It is envisaged that an accredited mediator will mediate between the parties, including the public prosecutor, the perpetrator, the victim and possibly members of the community. The mediated settlement agreement will include both compensation for the victims and a proposed sentence for the perpetrator. This mediated settlement agreement will then be tabled before the court for adjudication and approval to serve as an effective court order. The proposal is a logical legal development of section 105A of the Criminal Procedure Act on plea and sentencing agreements, as the process of mediation builds on the process of negotiation established in it. To put it bluntly, if a plea and sentence agreement can be negotiated between the prosecutor and the offender, a plea and sentence agreement can be mediated between the prosecutor, the offender and the victim. Mediation can integrate and expand the constitutional principles of reparation and ubuntu and curb economic crime by providing an effective restorative and just response to it.
URI: http://hdl.handle.net/10019.1/107281
Keywords: Alternatives to prosecution; Commercial law; Dispute resolution; MARD; Mediación; Mediation; Mediação; Médiation; South Africa

A comparative appraisal of debt relief measures for no income no assets (NINA) debtors in Nigeria - Osunlaja, Tobi Titilayo (University of Pretoria, 2019)
Nigeria currently has a non-functioning insolvency system; it is yet to record a successful insolvency case. This failure principally is attributable to the weak laws and enforcement policies in existence. The problem is exacerbated by burgeoning consumer debt in the formal sector. The causal factors for this increase in debt are negative economic growth indices such as rising inflation, interest rates and unemployment. With these indices predicted to worsen, a new Bankruptcy and Insolvency Act (BIA) was proposed in 2016. The BIA seeks to regulate individual insolvency proceedings in Nigeria. However, the BIA (as currently conceptualized) does not make provision for debtors with neither income nor assets, often referred to as No Income No Assets (NINA) debtors who, it can be argued, are in the majority in the Nigerian state. The aim in this thesis is to propose debt relief measures that cater for NINA debtors in Nigeria. This proposal aims to prevent further discrimination against these debtors in terms of the current law and the proposed BIA. It envisages that catering for NINA debtors in Nigeria will boost the Nigerian government’s drive to encourage entrepreneurship. In providing for NINA debtors it will provide a safe landing for poor debtors in the event of entrepreneurial failure. The thesis achieves its stated aim by studying international principles and guidelines as espoused by leading bodies. Furthermore, the thesis performs a comparative analysis of relevant NINA provisions in South Africa, Sweden, France, Ireland and Canada. The thesis proposes amendments to the proposed BIA in light of the aforementioned analysis and posits that procedures that are formal and extra-judicial, which have no financial requirements and are easily accessible to debtors should be incorporated.
https://repository.up.ac.za/handle/2263/92927
Keywords: Debt relief measures; Insolvency; Insolvency system; Laws and enforcement policies; No Income No Assets (NINA)

What Process is Due – Sanctions Regimes of Multilateral Development Banks - Madir, Jelena (University of Westminster, 2019)
Much has been written about the consequences for companies of criminal convictions for bribery and other corrupt practices. However, less attention has been paid to the sanctions regimes that have been developed by multilateral development banks in order to combat fraud and corruption in their operations. This is likely to change in view of the fact that on 9 April 2010, the heads of five leading multilateral development banks (MDBs) – the African Development Bank, the Asian Development Bank, the European Bank for Reconstruction and Development, the Inter-American Development Bank and the World Bank Group – signed the Agreement for Mutual Enforcement of Debarment Decisions, which provides for mutual and reciprocal enforcement of debarment decisions taken by any one of them against parties that engage in fraud, corruption, coercion or collusion in connection with MDB-financed projects. For parties that are seeking financing form an MDB or are competing for contracts funded by an MDB, this means that a sanctionable practice committed in a single country could result in global sanctions. Against this background, this thesis examines the type of due process rights that should characterise MDBs’ sanctions procedures. More particularly, the thesis analyses the extent to which MDBs’ sanctions regimes should be bound by the rules of law, analogous to those of national judicial bodies, and the level of due process and transparency that should be required from these ever-evolving regimes. In other words, (how) can the tension between the administrative and business considerations of MDBs’ sanctions regimes (coupled with their immunity from judicial review) be reconciled with due process considerations and principles of fairness that underpin a national judicial model?

The Legal Regime of Real Estate Investment Financing by Musharaka Contract - Morjane, Hicham (Université Hassan 1er, 2019)
Islamic banking is marked by its use of overly generous terms that are likely to apply to multiple factual situations forming more disputes than the law is supposed to settle, these terms are chosen in the style of Islamic Shariah and are considered as statements of Islamic principles rather than as the enactment of legal rules directly applicable to the facts and therefore able to propose solutions. Wishing to gain a better understanding of this young institution, the Musharakah contract in real estate financing. And as a result of our study and final arguments: this thesis will be a legal theory describing with legal simplicity the complex concept of the Musharakah contract in Islamic real estate financing in comparative law. In addition to the fact that the law must be normative, intelligible, in other words readable, clear and precise. Thus, our thesis is a research of analysis and demonstration, making the Musharakah contract in real estate financing go beyond the purely Islamic context and explicitly position it in a universal legal field as: "a legal regime of a contractual structure combining the company contract and the trust contract".
Il s'agit de la traduction d'une thèse déjà présente dans référencée sur notre sité
Keywords: Banque islamique; Financement immobilier; Investissement immobilier; Islamic banking; Moucharaka; Musharakah; Real estate financing; Real estate investments

Adoption, compliance, and consequences of International Financial Reporting Standards in Africa - Tawiah, Vincent K. (Griffith University, 2019)
This thesis investigates the adoption, compliance and consequences of International Financial Reporting Standards (IFRS) in Africa, a continent which has mostly been ignored in prior studies due to the use of generic proxies. Drawing on DiMaggio and Powell (1983), this thesis examines the institutional pressures of IFRS adoption in Africa. Stakeholder salience theory, developed by Mitchell, Agle and Wood (1997), is employed to analyse the determinants of IFRS compliance outside the traditional capital market settings. As regards to the consequences of IFRS in Africa, this thesis analyses the impact of IFRS on audit fees, audit reporting lags and auditor switch. The study used panel data from 54 countries and 205 firms covering the financial years 2003-2016. Secondary data was sourced from reputable database and annual reports of sample companies. Different analytical tools such as ordinary least squares, logit and multinomial regressions were used based on their suitability to address the research questions. The study found that only 18 out of the 54 countries required all listed and large companies to report per IFRS, while 25 did not permit IFRS. The results supported the theoretical prediction that coercive, mimetic, and normative isomorphism influenced IFRS adoption in Africa. Specifically, the World Bank (WB) and International Monetary Fund’s (IMF) influence on African countries in adopting IFRS was not through foreign aid and grants; instead, their recommendations made in the Report on Observance of Standard and Codes (Accounting and Auditing) initiatives. The finding(s) also demonstrated that the presence of global audit firms and the number of years of IFAC membership had a strong association with a country’s decision to adopt IFRS. Moreover, countries with strong professional accounting organisations (PAO) were more likely to adopt IFRS. On IFRS compliance, the study found that the average compliance score among the companies over the period was 70.94%, with a minimum score of 58.59% and a maximum of 83.55%. The findings reported a significant positive association between audit committee competence (ACC) and compliance, and between chartered accountants on board (AOB) and compliance. The thesis also documented that compliance has been increasing over the years. Regarding the impact of IFRS on the audit market, the findings suggested IFRS was positively and significantly associated with an increase in audit fees regardless of early or late adoption. Also, on average, ARL increased by 26% across all samples, with late adopters experiencing 28% and earlier adopters 22% during the adoption year. Contrary to the late adopters, early adopters experienced a significant increase in audit fees during the pre-IFRS period due to the set-up and implementation at the time. In addition, IFRS adoption was likely to cause companies to switch from small audit firms to the Big 4. The findings on adoption suggest that global accounting agencies such as IFAC and IASB should focus on building vibrant national level accounting institutions such as PAOs to facilitate the adoption of IFRS in Africa. The thesis, therefore, adds to the adoption literature the finding that the isomorphic pressures in Africa are different from those suggested in prior studies. The results on compliance imply that companies that appoint more professional accountants to their boards are more likely to comply with the requirement of IFRS. Therefore, it is suggested that companies should engage more chartered accountants in their governance. Also, corporate boards must strive to strengthen their audit committees by appointing more NEDs and CAs to the committee. The findings also provide valuable information for professional accounting organisations on the role of its members (professional accountants) in the effectiveness of IFRS compliance. The findings of the consequences of IFRS on the audit market alert small and medium practitioners (SMPs) in non-IFRS countries of the possible loss of clients to the Big4 due to the adoption of IFRS. To mitigate this effect, the national PAO should build the capacity of their local accountants through training and education to handle the complexities and continuous upgrading of IFRS. Such training is seen as being crucial for SMPs in OHADA countries, Ethiopia, Djibouti and other countries which are in the process of implementing IFRS.
Keywords: Adoption; Africa; Audit market; Compliance; Consequences; IFRS; Institutional pressures; International Financial Reporting Standards; Stakeholder salience

Abuse of legal personality to avoid tax : piercing the corporate veil as remedy in case of the abuse of legal personality for tax purposes - Marais, Albertus Johannes (Stellenbosch University, 2019)
Companies are legal persons and as much part of commercial traffic as the natural persons owning and controlling them. Compared to one another, companies and natural persons nevertheless have very different legal abilities and characteristics. It is therefore not unexpected that they are treated differently for purposes of the law of taxation. As a result it may often be more beneficial to have the profits generated by a business enterprise taxed in a company rather than in the hands of a natural person, especially in instances where a shareholder would be commercially indifferent to whether those profits are generated in a company or not. By using the separate legal personality of a company shareholders may often perpetrate an abuse of that separate legal personality. Such abuse of legal personality can also take place when legal personality is employed primarily for tax reasons. While a limited form of abuse of the corporate veil is tolerated, whether the use of separate legal personality for tax reasons amounts to an abuse thereof beyond what is permitted in South Africa can be determined in terms of three tests. These tests are the traditional “piercing of the corporate veil” judgments forming part of the common law, section 20(9) of the Companies Act 71 of 2008 and the General Anti-Avoidance Rules (“GAARs”) (and other specific provisions) in the Income Tax Act 58 of 1962. This dissertation considers when any of these various tests will dictate that the separate personality of a company be ignored (or “pierced”) for purposes of taxes levied in terms of the Income Tax Act. Through critical analysis of both the South African rules on piercing as applied for tax purposes as well as the circumstances under which selected other jurisdictions provide for piercing for tax reasons the dissertation formulates what best practice and desired policy for piercing for tax reasons are.
URI: http://hdl.handle.net/10019.1/106096
Keywords: Close Corporations Act; 1984; Companies Act; 2008; Corporate veil; Corporations; Income Tax Act; 1962; South Africa; Tax evasion; Taxation; Unconscionable abuse

Regulation of takeovers and mergers with an emphasis on the mandatory offer rule: a comparative and critical analysis of the law and the institutions that have been set up to enforce the law - Phakeng, Madimetja A. L. (Stellenbosch University, 2019)
ENGLISH ABSTRACT :This dissertation assesses the regulation of takeovers and mergers and the institutions created to enforce the law, from a comparative perspective. It uses South Africa as its point of departure and takes the laws of Delaware in the United States, the United Kingdom and Australia into account. The dissertation indicates that numerous takeover provisions in South Africa are poorly formulated, making them difficult to interpret and apply. Accordingly, the dissertation recommends amendment and improvement of certain Takeover Provisions. Special emphasis is placed on the mandatory offer requirement. The dissertation critically and comparatively analyses this requirement and especially its impacts on the market for corporate control, efficient usage of capital, corporate governance and (in South Africa) Broad Based Black Economic Empowerment. It appears from the literature explored that the mandatory offer requirement originated from the Perlman case in the United States as an expression of the equal opportunity rule. According to the equal opportunity rule, the controlling stake of a company is enriched with a premium of control, which must be shared with other shareholders when there is a change of the controlling shareholder. Shareholders must be given an equal opportunity to share in this control premium. Hence, a mandatory offer must be made to the remaining shareholders of the company by the new controlling shareholder at a price at which control was bought. Perlman case was decided in the United States of America during 1955. It is contended in the dissertation, that the mandatory offer requirement in section 123 of the Companies Act 71 of 2008 (“the Act”), can ultimately be traced back to this case. Researchers have criticised the mandatory offer requirement in a number of respects. It has been pointed out that the rationale for the decision in the Perlman case was not clear and applied in limited circumstances. Other scholars point out that the case was not a final decider on the sharing of the control premium due to later judicial pronouncements that differed with that case. Despite these commentaries, it appears that the case became a basis for imposing and enforcing this most debated rule in takeover and merger law. The dissertation concludes that the sharing of a premium of control, as envisaged by the mandatory offer requirement, is not enforced in the state of Delaware. It further concludes that in the UK, the mandatory offer rule forms the cornerstone of enforcement of the equal opportunity rule, but that widely dispersed shareholding ameliorates it negative consequences in that jurisdiction. The dissertation favours the Australian approach. That jurisdiction does not require a mandatory offer similar to that in section 123 of the Act, but, Australian Takeover Provisions, unlike their South African equivalent, have been tailor-made for Australian market conditions. The dissertation accordingly concludes that the mandatory offer requirement in section 123 of the Act in its current form is not appropriate for South Africa.
URI: http://hdl.handle.net/10019.1/105995
Keywords: Consolidation of corporations; Delaware; Great Britain; Merger of corporations; Regulation; South Africa

The definitions of ‘inside information’ and ‘insider’ in the Financial Markets Act 19 of 2012 - Van Der Walt, Johann Nico (Stellenbosch University, 2019)
The definitions of ‘insider’ and ‘inside information’ in the Financial Markets Act 19 of 2012 are, as is the case with their international counterparts, central to the Act’s regulation of insider trading. It has long been recognised, however, that those definitions, inherited from repealed companies and market abuse legislation, are cumbersome and counter-intuitive. This state of affairs obtains as the South African legislature has failed to undertake the most fundamental enquiry in formulating a coherent regulatory scheme aimed at prohibiting supposedly wrongful conduct: identifying a single theory of wrongfulness upon which to base its prohibitions. Instead, the definitions include elements of all possible regulatory bases for insider trading, including those having as their object the protection of proprietary rights in information and born out of the fiduciary doctrine. It is argued that the definitions, part of legislation aimed at addressing a financial market wrong, should be formulated with reference to the rights and obligations at play in those markets and the legislature’s objectives for those markets. A proposal is made in that regard.
URI: http://hdl.handle.net/10019.1/105745
Keywords: Finance; Financial Markets Act; 2012; Insider trading in securities; Markets; South Africa

The China-OHADA BIT, a step in the right direction : a new model of China-Africa BIT at a regional or sub-regional level - Sun, Sisi (Université de Montréal, 2019)
L’Afrique jouit non seulement de ressources naturelles, mais aussi d’un grand potentiel de marché. Ces dernières années, il y a une injection croissante d'investissements privés en provenance de Chine vers l’Afrique. La Chine souhaite exploiter le potentiel de l’Afrique en tant que marché émergent grâce aux investissements considérables réalisés par des entreprises privées. Parallèlement, les pays africains ont besoin d'investissements chinois dans divers domaines pour stimuler chaque aspect de leurs économies. L'investissement privé axé sur le marché nécessite un environnement d'investissement ouvert, stable, sécurisé et prévisible. Or, les traités bilatéraux d'investissement (TBI) existants entre la Chine et l'Afrique adoptent le modèle post-établissement axé sur la protection. La plupart de ces traités prévoient simplement des obligations générales de protection des investissements, laissant toutes les autres questions à la discrétion de l’État hôte. Les régimes juridiques instaurés par les TBI conclus entre la Chine et les États africains manquent de lisibilité, de prévisibilité et de cohérence. La conclusion de l'accord économique et commercial global entre l'UE et le Canada (AECG) suggère l’idée que la Chine pourrait s’inspirer de ce modèle pour conclure un accord bilatéral autonome avec les pays africains au niveau régional ou sous régional afin d’attirer des investissements chinois vers l’Afrique. Cet accord pourrait intervenir dans le cadre de l’Organisation pour l’Harmonisation en Afrique du Droit des Affaires (OHADA) étant donné son niveau d’intégration et son autorité en matière de commerce et d’investissement sur le continent. Ce TBI modèle comportera des normes uniformes en matière d’accès aux marchés et de protection des investissements, ce qui limitera les risques d’interprétation divergente et partant, contribuera à l’instauration d’un climat d'investissement stable, sûr, prévisible et plus ouvert. Africa enjoys not only natural resources, but also market potential. There has been a growing injection of private investment inflows from China to Africa recently. China needs to exploit Africa’s potential as an emerging market for its tremendous investments by private enterprises. Moreover, the African countries need Chinese investments in various areas to boost aspects of their economies. Private, market-oriented investment calls for an open, stable, secure and predicable investment environment. However, existing bilateral investment treaties (BIT) between China and Africa adopt the protection-oriented, post-establishment model. The treaties merely provide for some general obligations of investment protection, leaving all other matters to the policy discretion of the host state. The China-Africa BIT regime is sporadic, uninformed and incoherent. The conclusion of the Comprehensive Economic and Trade Agreement between the EU and Canada (CETA) develops the idea that China might conclude a standalone BIT with the African countries at a regional or sub-regional level to attract Chinese investment inflows into Africa through an open, coherent and uniformed investment scheme. Given the integration of Organisation pour l’harmonisation en Afrique du droit des affaires (OHADA) to be one single jurisdiction over trade and investment, the China-OHADA BIT is the one most likely to be expected. This standalone BIT regime inherently calls for an absolute standard for market access and investment protection, and uniformity to limit the discretion of interpretation, and as such, contribute to a more open, stable, secure and predictable investment climate.
Keywords: BIT regime; China-OHADA BIT; Chine-OHADA TBI; Climat d'investissement; Discrétion politique; Investment climate; Investments; Policy discretion; TBI modèle

The copyright protection of musical works : a historical and contextual analysis - Baloyi, Jele Joel (University of South Africa, 2019)
This work is concerned with an analysis of the copyright protection of musical works. Musical works form part of the categories of works protected under copyright law. It would be easy to dismiss musical works as not warranting a serious study, as would for example, be warranted for “industrial property” rights such as patents and geographical indicators, or more “serious” copyrights such as architectural works and computer software. Such a perspective would however, not be cognisant of the significant contribution that the music industry, as part of the broader cultural and creative industries makes to the global economy. It has, for example, been shown that in 2013, the global cultural and creative industries contributed some US$2,250b, employing some 29,5 million people, with the music industry being one of the top three employers and with its revenues exceeding those of radio.1 A single successful musician can earn in excess of US$100m per annum,2 making the industry ripe for litigious claims. For this reason therefore a consideration of the legal rules that apply to the protection of musical works is crucial. There is currently no clear exposition and systematic analysis of the legal principles applicable to the field of music copyright and no work devoted to the in-depth delineation of the rights and sub-rights relating to musical copyright protection. This study seeks to address this research and knowledge gap by providing a historical and contextual analysis of the protection of musical works. The aim is to provide a complete picture of the milieu of music copyright protection to enable the reader to feel empowered in dealing with the subject-matter. This the writer does by mapping the historical development of music copyright protection in particular from eighteenth century England when the first copyright legislation was enacted, until the enactment of the British Copyright Act of 1911, which signalled the emergence of the “common law” copyright system. The writer then shows how this enactment shaped the development of modern music copyright law, and concludes by presenting a contextual consideration of the current South African law of music copyright and highlighting the challenges it is faced with.
Keywords: Copyright; Copyright protection; Dramatico-musical works; Imperial Copyright Act; Intellectual property; Intellectual property rights; Music; Music trade; Musical compositions; Musical works

Third Party’s Intellectual Property Rights And The Seller’s Liability Under The United Nations Convention On International Sale Of Goods (CISG) And The Sale Of Goods Act (SGA) - Kiraz, Serife E. (University of Leicester, 2019)
This thesis is a comparative analysis of the provisions on the seller’s duty to deliver the goods free from any third-party intellectual property rights (IPRs) under the United Nations Conventions on the International Sale of Goods (CISG) and the UK Sale of Goods Act 1979 (SGA). As a consequence of technological advancement, there has been an increased observance of the interaction between intellectual property rights (IPRs), which are intangible property rights, and tangible goods. As a result of this interaction, growing numbers of goods, which are either subject to IPRs as a whole or that possess an IP-protected component, have become subject to sales agreements. The circulation of the goods around the world increases the likelihood that third-party IPRs over the goods will be infringed. This risk of infringement also raises the possibility that the application of IP law remedies will prevent the buyer from reselling or using the goods in question. This study is concerned with the question of how the sale of goods is affected by third-party IPRs, and it proposes to undertake a comparative analysis of the provisions that determine the seller’s liability when third-party IPRs arise in relation to goods that are sold under the CISG and the SGA. It seeks to determine which instrument offers sufficient protection that will benefit the buyer. In attempting to reveal the sufficient protection, it also undertakes a comparative analysis of the remedies that are available to the buyer under the CISG and the SGA when third-party IPRs over the goods are raised. With regard to the widely acceptance of the CISG by 89 states, and the dominant role of English law in commercial law and its preference as a governing law to most contracts, it is aimed to determine the differences and similarities between the CISG and the SGA, and the practical consequences of their application to the contracts when third-party IPRs over the goods arise. The thesis will seek to determine if the text of the relevant CISG articles can be improved and will accordingly formulate proposals that work towards this outcome.

Shareholder activism, corporate social responsibility and financial performance - Yang, Yi (Victoria University of Wellington, 2019)
The thesis examines the influence of shareholder activism on corporate social responsibility (CSR) disclosure of targeted firms and its spillover effects on CSR disclosure, corporate social performance (CSP) and financial performance (FP) respectively in peer firms. The research is motivated by filling the research gaps in prior literature and providing insights to shareholders, the management and regulatory bodies in practice. The thesis consists of three parts. Firstly, this thesis reviews the literature surrounding shareholder activism by conducting narrative reviews of 92 working papers and publications and meta-analysis on 55 working papers and publications, published during 2000-2017 period. Theories from prior literature, namely agency theory, stakeholder theory and stakeholder salience theory are analysed through narrative review analysis at the beginning of the chapter. Then, the analysis of narrative review also documents mixed findings of the associations among shareholder activism and FP and CG and CSP, including spillover effects. That is, the associations could be positive, negative and not significant in prior literature. The results of meta-analysis indicate that shareholder activism improves FP and CSP respectively. In addition, the thesis also examines the major types of shareholder activists and main forms of shareholder activism. Overall, through the analysis, the thesis identifies the research gaps of prior literature, thereby pointing out future research directions. Secondly, by employing shareholder proposals from Standard & Poor's 1,500 (S&P 1,500, hereafter) companies in the United States as a proxy of shareholder activism during 2006-2014 period with 13,572 separate observations, this thesis examines whether the whole sample of shareholder activism, institutional shareholder activism and coordinated shareholder activism could influence CSR disclosure level respectively. Simultaneously, this thesis also investigates whether shareholder activism affects CSR disclosure level given the other corporate governance mechanisms, namely board size, the presence of female directors, outside directors and CEO incentives. The results typically demonstrate that: (1) while shareholder activism negatively relates to CSR disclosure level, larger board size or the presence of female directors combined with shareholder activism directly relates to maintaining better CSR transparency; (2) coordinated shareholder activism could decrease social disclosure level. The findings also indicate that CSR disclosure provides an approach to strategically manage risks. Thirdly, the thesis explores spillover effects from different types of shareholder activism on CSR disclosure level, CSP and financial performance by using data gathered from S&P 1,500 companies during 2007-2014 period. The findings show that shareholder activism increases social disclosure level and environmental disclosure level in peer firms. It also shows that there is a weak positive association between shareholder activism and CSP. It therefore demonstrates the weak influences of shareholder activism in changing firms’ CSP. It also illustrates that institutional shareholder activism has an advantage over coordinated shareholder activism in terms of increasing corporate transparency. In this manner, it indicates that the collective action problem among coordinated shareholders could also attenuate the impact of shareholder activism in peer firms. The thesis contributes to the literature on shareholder activism practically and theoretically. The findings provide useful insights to shareholders, management teams and regulatory bodies for their policy-making. Beyond the practical contribution, the thesis also provides empirical evidence to stakeholder salience theory and analyses the collective action problem.
Keywords: CSR disclosure; Corporate Social Responsibility; Corporate governance; Corporate social performance; Financial performance; Shareholder activism

The tax trade interface : an investigation of the influence of the Nigerian income tax incentives on taxpayer behaviour - Aniyie, Ifeanyichukwu Azuka (University of Pretoria, 2019)
The Companies Income Tax Act provides the architecture for corporate income taxation (CIT) in Nigeria. It specifies the rate, the tax base and contains the bulk of the incentives to which qualified corporate taxpayers are entitled. This thesis investigates the influence of incentives on the compliance behaviour of micro and small companies (MSCs) in Nigeria. By Nigeria’s standard, these are companies which: (1) employ between 1 to 49 persons and/or own assets (excluding land and building) valued at less than NGN 100million; or (2) are either private limited companies or one-man businesses. In the context of the Nigerian tax system, MSCs are corporate taxpayers with turnover of less than NGN 200 million. This choice of research population is a consequence of the globally acknowledged niche occupied by MSCs vis-à-vis the of the socio-economic objectives of any state. In the course of the study, the formulated research questions were resolved using a multi-stage mixed methods framework which allowed for the fusion of qualitative and quantitative epistemology as well as facilitated the introduction of pragmaticism into the research process. The thesis, inter alia, identified gaps in the administrative regime of CIT incentives in Nigeria and highlighted the fact that they have the potential to introduce uncertainty into the tax system. In addition, it revealed that the regulatory regime for the role and services of tax intermediaries within the tax system, in terms of current standards and reality, is sub-optimal. On the basis of a survey of a small sample of MSCs, it was concluded that the influence of tax intermediaries with regard to the compliance behaviour of MSCs was marginal. Reason for this was traced to the fact that the role and services of the latter vis-à-vis clients who are MSCs are actuated by variables which are within the psycho-social space of the tax intermediairies and the desires/requests of the MSC. This dismisses, in the context of Nigeria, the notion that the tax intermediary is the initator of every tax dodge. Based on the findings, the thesis, inter alia, recommended a re-orientation in the conceptualisation of tax compliance as the prevailing theoretical premise for the extant tax law and policy does not contemplate that non-economic factors and referents outside the realm of taxation are capable of influencing tax compliance behaviour. In addition, recommendations with the capacity to change the law, policy and administrative regime relating to CIT incentives as well as the role and services provided by tax intermediaries were made after an examination of the situation in Kenya and South Africa.
URI: https://repository.up.ac.za/handle/2263/72637
Keywords: Companies Income Tax Act; Corporate income taxation; Income tax; Nigeria; Tax trade; Taxpayer

Copyright as a constraint on creating technological value - Drążewski, Kasper (European University Institute, 2019)
How do we legislate for the unknown? This work tackles the question from the perspective of copyright, analysing the judicial practice emerging from case law on new uses of intellectual property resulting from technological change. Starting off by comparing results of actual innovation-related cases decided in jurisdictions with and without the fair use defence available, it delves deeper into the pathways of judicial reasoning and doctrinal debate arising in the two copyright realities, describing the dark sides of legal flexibility, the attempts to ‘bring order into chaos’ on one side and, on the other, the effort of judges actively looking for ways not to close the door on valuable innovation where inflexible legislation was about to become an impassable choke point. The analysis then moves away from the high-budget, large-scale innovation projects financed by the giants of the Internet era. Instead, building upon the findings of Yochai Benkler on the subject of networked creativity, it brings forth a type of innovation that brings together networked individuals, sharing and building upon each other’s results instead of competing, while often working for non-economic motivations. It is seemingly the same type of innovation, deeply rooted in the so-called ‘nerd culture’, that powered the early years of the 20th century digital revolution. As this culture was put on trial when Oracle famously sued Google for reuse of Java in the Android mobile operating system, the commentary emerging from the surrounding debate allowed to draw more general conclusions about what powers the digital evolution in a networked environment. Lastly, analysing the current trends in European cases, the analysis concludes by offering a rationale as to why a transformative use exception would allow courts to openly engage in the types of reasoning that seem to have become a necessity in cases on the fringes of copyright.
Accepted: 2019-01-14T15:17:37Z
Keywords: Copyright; Fair use (Copyright); Intellectual property

The challenge of three-dimensional printing : questioning established concepts in intellectual property law - Elam, Viola (European University Institute, 2019)
Over the last years, academics, practitioners and policy makers have focused their attention on an emerging technology: three-dimensional printing (“3DP”). 3DP is often portrayed as a game changer, showing the potential to disrupt established socioeconomic paradigms and exert profound implications in disparate areas of law. 3DP not only is well integrated in the manufacturing industry, but also increasingly adopted at consumer level. Recent developments have made it possible for ordinary people to take an active role in the production, customization and distribution of goods, and likewise paved the way for the proliferation of new market entrants, such as 3DP online platforms. Against this background, this thesis aims to shed some light on the implications that 3DP may have for Intellectual Property Law. In particular, this work attempts to predict and grasp the consequences that the digitization of real world things may carry in the area of IP law, both from the side of protection and infringement. This contribution is intended to create general awareness about the current state of the art and likewise delineate possible future scenarios in the 3DP ecosystem. The research question at the core of the analysis is whether the current legal framework of different IPRs already offers suitable means for regulating the thin dividing line between the digital and the analogue world, or rather needs to be amended, in order to cope with such a fascinating reality. To this end, the analysis contributes insights to the best legal treatment that CAD files shall receive, in case such files embed products protected by copyright, designs, patents and trademarks. Hence, it addresses right owners’ concern that the online transmission of CAD files, combined with the ease of converting such files into the final printout, will facilitate mass-scale and worldwide infringement of all IPRs.
Accepted: 2019-01-15T14:09:48Z
Keywords: 3D; Copyright; Intellectual property; Three-dimensional printing

Expanding access to justice: an exploration of large firm pro bono practice across Europe - Khadar, Lamin (European University Institute, 2019)
This PhD thesis explores pro bono practice among large, international law firms in Europe. The central question addressed by the thesis is: does “Big Law Pro Bono” contribute to access to justice in Europe? The thesis commences with a review of the literature which both contextualizes and situates the thesis. This review also identifies gaps in the existing literature particularly related to the globalization and localization of law firm pro bono and its practice beyond the United States (i.e. its practice in other parts of the world such as Europe, Asia, Africa and Latin America). After identifying issues with the current definition of access to justice, used throughout much of the existing literature, the thesis proposes a new definition which is then used throughout the thesis to evaluate pro bono practice in Europe. Towards this end, the thesis first provides historical context to law firm pro bono practice by exploring the history of pro bono, legal aid and other models of progressive lawyering across Europe. Following this, the thesis closely explores the process by which large firm pro bono practice arrived in Europe (i.e. globalization), the contemporary practice and the process by which it adapted to the European legal, social and political ecosystem (i.e. localization). Ultimately, it is suggested that large firm pro bono does not contribute to access to justice in Europe insofar as access to justice is defined narrowly - in the way that it has been conceived of in much of the existing literature. However, by embracing a broader definition of access to justice, it is possible to perceive the actual (and possible) social and political impact of large firm pro bono practice in Europe.
Accepted: 2019-05-28T07:38:42Z
Keywords: Justice; Legal assistance to the poor; Legal services

Modernisation of customs regulations and practices to combat customs offences in France, South Africa and Cameroon - Kouamo, Juliette Armelle (North-West University, 2019)
The modernisation of customs regulations and practices involves a process of transformation aimed at boosting the capacity of customs agencies so that they can respond more efficiently to the ever-changing trade environment. In the context of this study, the transformation referred to is changes and adaptations of the institutional, structural, legal, practical, and managerial aspects of revenue collectors’ work. Several global changes in international trade prompted the World Customs Organization (WCO), an international customs body, to pilot projects for the modernisation of customs in order to adapt the approach of this administration to the various changes occurring in the field. These changes relate to the increasing volume of world trade, technological advances, the transformation of businesses models and the steady rise in criminal activities and security threats. The modernisation of customs with the WCO's guidance and support entails inviting and empowering member states of the WCO to align their customs regulations and practices with international standards. Customs modernisation became a topic of interest and started gaining worldwide attention when international trade experienced unprecedented changes coupled with technological advances. This has opened debates around issues relating to globalisation, such as the lowering and removal of trade barriers. There is also a necessity to ensure that customs authorities have sufficient strategic controlover imported and exported commodities. It has become imperative for all states to improve their competitiveness in customs through the revision of regulations which give rise to burdensome practices and procedures. The removal of cumbersome legislative provisions and practices will ensure an increment of efficiency in customs processes.Customs modernisation differs in developed, developing or under-developed states. Hence, the approach to customs modernisation differs from one jurisdiction to another. While some states embrace customs modernisation, others are unable, unwilling or merely reluctant to do so. There are different reasons for the variation in states’ attitudes towards customs modernisation. These attitudes are reflective of the political and economic realities prevailing in each state. Some states are open to customs modernisation but lack the financial and structural resources necessary to be vii able to engage in such modernisation. Others are plagued by corrupt syndicates which employ all the means at their disposal to defend their manipulation of customs authorities.This study analyses the modernisation of customs regulations and practices in France, South Africa and Cameroon. These jurisdictions have different economic powers, are located in different geo-economic zones, and differ in their capacity to implement customs modernisation. The study examines how the respective states incorporate modernisation into their daily customs operations, as recommended by the WCO, of which they are all member states. The study further analyses the impact of customs modernisation on the fight against customs offences in the three jurisdictions.Changes in international trade have both positive and negative impacts on customs. The negative impacts include changes in the forms and increases in the frequency of customs offences. Customs offences are breaches or attempted breaches of customs laws. States suffer financial loss, and these illegal activities threaten their security. The benefits that accrue to businesses and the quality of their products are also challenged by these unlawful behaviours. In addition, the health and safety of citizens are imperilled by customs offences such as the illicit import of counterfeit, sub-standard and dangerous goods and substances. Irrespective of their nature, customs offences have negative impacts on society.To limit and mitigate the adverse effects of customs offences on society and revenue collection, there is a need for strategic customs administrations that embrace technology and modernisation in general. France, South Africa and Cameroon have modernised their customs administrations. While these countries have incorporated the WCO conventions and tools in their respective environments, the impact of the incorporation on customs offences, in general, can be inferred from the simple implementation of these instruments and tools. vii able to engage in such modernisation. Others are plagued by corrupt syndicates which employ all the means at their disposal to defend their manipulation of customs authorities.This study analyses the modernisation of customs regulations and practices in France, South Africa and Cameroon. These jurisdictions have different economic powers, are located in different geo-economic zones, and differ in their capacity to implement customs modernisation. The study examines how the respective states incorporate modernisation into their daily customs operations, as recommended by the WCO, of which they are all member states. The study further analyses the impact of customs modernisation on the fight against customs offences in the three jurisdictions.Changes in international trade have both positive and negative impacts on customs. The negative impacts include changes in the forms and increases in the frequency of customs offences. Customs offences are breaches or attempted breaches of customs laws. States suffer financial loss, and these illegal activities threaten their security. The benefits that accrue to businesses and the quality of their products are also challenged by these unlawful behaviours. In addition, the health and safety of citizens are imperilled by customs offences such as the illicit import of counterfeit, sub-standard and dangerous goods and substances. Irrespective of their nature, customs offences have negative impacts on society.To limit and mitigate the adverse effects of customs offences on society and revenue collection, there is a need for strategic customs administrations that embrace technology and modernisation in general. France, South Africa and Cameroon have modernised their customs administrations. While these countries have incorporated the WCO conventions and tools in their respective environments, the impact of the incorporation on customs offences, in general, can be inferred from the simple implementation of these instruments and tools.
Keywords: Customs modernisation; Customs offences; Customs regulations

Rationality and legality of non-market economy treatment in Antidumping law: novel perspectives on the changed legal environment - Long, Shao (Universität Wien, 2019)
AD Recht ermöglicht die Anwendung des Instruments nichtmarktwirtschaftlicher Behandlung (NME) zwecks Bestimmung des normalen Ausfuhrpreises von importierten Waren aus Ländern deren Märkte als weitgehen von Regierungen beeinflusst und deren Preise und Kosten für diese Berechnung als unverlässlich angesehen werden. Stattdessen sollten diese Berechnungen auf der Basis von Preisen in einem Vergleichsland mit funktionierender Marktwirtschaft ( „surrogate country‟ ) erfolgen. Die vorliegende Dissertation legt dar, dass die Anwendung der NME Behandlung zum Schutz gegen unfairen Importwettbewerb nicht auf rechtlich gesicherter Grundlage erfolgt, sondern als willkürlich eingeseztes protektionistisches Instrument gehandhabt wird. Besonders die Anwendung dieser Methode auf Chinesische Exporte nach 2016 ist rechtlich fragwürdig. Die Dissertation untersucht die Rechtmäßigkeit und Zweckmäßigkeit diese Methode, erstens durch die Analyse der wirtschaftlichen Begründung des AD Rechts und der geschichtlichen Entwicklung seit seinen protektionistisch motivierten Anfängen. Sie untersucht sowohl die relevanten Regeln und Praktiken aus der Zeit vor der Gründung der WTO als auch solche die danach zur Anwendung kamen und kommt zum Schluss, dass sie angesichts des grundlegend geänderten globalen rechtlichen Umfelds nicht mehr tragbar sind. Die Autorin empfiehlt daher, dass die auf NME Behandlung bezogenen Regeln und Praktiken vollständig aufgegeben werden und im Rahmen der gegenwärtigen Bemühungen um eine Modernisierung des gesamten WTO Regelwerks durch angemessene andere Regeln ersetzt werden sollten.
https://phaidra.univie.ac.at/detail/o:1354372
Keywords: Antidumpingrecht; Nichtmarktwirtschaftlichen Behandlung; Non-market economy

Curbing transfer pricing manipulation in South Africa : lessons from selected jurisdictions - Mboweni, Abel Mabawuzeni (University of Pretoria, 2019)
Transfer pricing manipulation is a worldwide problem which results in a massive loss of revenue which is meant to finance government socio-economic programmes. South Africa is not immune to this problem. South Africa is losing billions of Rands in tax revenue due to this scourge. This research is an attempt to find ways and means which can be employed to combat or control the problem. In order to find the envisaged solutions, this research investigates the causes of the problem by analysing the weaknesses and the strong points of the arm’s length principle which is the basis of transfer pricing practice in South Africa and elsewhere. The research also investigates and analyses the corporate reasons for Multinational Enterprises (MNEs) to engage in transfer pricing with a view to demonstrating that transfer pricing is a neutral tax avoidance concept if it is applied for genuine business considerations. The investigation also entails analysing the legal framework of transfer pricing in South Africa which is embodied in section 31 of the Income Tax Act 58 of 1962. The research analyses the efficacy of section 31 in dealing with the sophisticated transfer pricing manipulation schemes. In addition, an extensive reference to the Organisation for Economic Co-operation and Development (OECD) Transfer Pricing Guidelines is made as South Africa relies heavily on the guidelines. A comparative analysis of selected topics is also conducted with the United States (US) and India with a view to drawing lessons from those jurisdictions. Based on the outcome of the analysis and the lessons drawn from the comparative analysis, findings are presented followed by legislative proposals or recommendations which will help to eradicate the problem. It is hoped that implementation of the recommendations taking into account the socio-economic conditions of South Africa will help to deal with the problem.
URI: https://repository.up.ac.za/handle/2263/69915
Keywords: Loss of revenue; South Africa; Tax Revenue; Transfert pricing

Sustainable tourism development in transfrontier conservation areas : a legal perspective - Mugadza, Amanda Tapiwa (North-West University, 2019)
Transfrontier conservation areas (TFCAs) originate from the idea of conservation across international boundaries. Within the SADC region, they are defined as areas or components of large ecological regions that straddle the boundaries of two or more countries, encompassing one or more protected areas, as well as multiple resource use areas. While the objectives of TFCAs are manifold, key among these are biodiversity conservation, improvement of livelihoods - poverty alleviation and economic development. Within SADC, tourism is identified as a key driver of these objectives. To explore this further, the study embarks on a case study of the Great Limpopo Transfrontier Conservation Area (GLTFCA), the oldest and second largest TFCA in the region, involving South Africa, Mozambique and Zimbabwe. From the GLTFCA, it is established that challenges exist with the manner in which tourism development is undertaken. However, it is further established that these challenges do not necessarily stem from the tourism development itself but from the weaknesses in the governance structures of this TFCA. In particular, the exclusion of local communities as key governance actors in the GLTFCA is seen to be detrimental to conservation and perpetuates poverty. Superimposed on these weaknesses, the tourism development therefore fails to adequately promote biodiversity conservation, improvement of livelihoods - poverty alleviation and economic development in the GLTFCA. To resolve these challenges, the study explores the concept of sustainable tourism development from a legal perspective guided by the question: what is the legal framework necessary, at domestic level – in TFCA participating countries to ensure that sustainable tourism development promotes the key SADC TFCA objectives? Through the aims or policy implications of sustainable tourism development, the study determines a legal framework comprising of the relevant TFCA governance actors as well as the governance-based tools that are necessary to promote the TFCA objectives. The domestic legal frameworks of the GLTFCA participating countries are measured against this legal framework to establish whether they promote sustainable toruism development. It is established that the domestic legal frameworks of South Africa, Mozambique and Zimbabwe, individually and as a whole, neither provide effectively for all relevant TFCA governance actors, especially local communities; nor for the tools that promote biodiversity conservation, the improvement of livelihoods-alleviation of poverty and economic development in the GLTFCA. Thus, the legal framework of the GLTFCA does not provide for sustainable tourism development as it should. For this reason, the study’s principal recommendation is the adoption, by all SADC TFCA participating countries, of a domestic legal framework for sustainable tourism development with specific elements which provides for the key TFCA governance actors as well as the relevant governance-based tools.
Keywords: Biodiversity conservation; Domestic legal framework; Economic Development; GLTFCA; Governance actors; Governance-based tools; Improvement of livelihoods; Sustainable tourism development; TFCAs; Tourism

Interrogation proceedings in insolvency law: a comparative study - Mwelase, Musamuni Barrah (North-West University, 2019)
Interrogation proceedings in insolvency circumstances have always been a thorny issue in South Africa, even prior to the advent of the new constitutional democracy. After the adoption of the new Constitution in 1993, a number of court cases seeking adjudication on constitutional compliance came before our courts. The insolvency of both natural and juristic persons necessitates the employment of specified proceedings such as insolvency interrogations. The latter is done to enable an efficient and effective collection and collation of information that would assist in the administration, sequestration and winding-up of the affairs of the affected person. These proceedings are intended to benefit creditors of an insolvent (natural and juristic). The matters of Ferreira v Levin; Vryenhoek v Powell 1996 (1) SA 984 (CC) (1996) (1); Bernstein and Others v Bester 1996 (2) SA 751 (CC); Harksen v Lane 1998 (1) SA 300 (CC; De Lange v Smuts 1998 (1) SA 736 (C) are still leading cases in relation to the constitutionality of interrogations in insolvency circumstances. The Constitutional Court has on a number of occasions, declared the interrogation proceedings in insolvency matters constitutional, with minor amendments on a case-by-case basis. The effect of these judgements is that, in every case in which an insolvent debtor has to undergo an interrogation process, the presiding officer must ensure that compliance with the constitutional requirements are in place. The current position in which the sequestration of insolvent estates and the winding-up of insolvent companies are respectively regulated by two statutes, is a matter for concern. This situation has led to duplication and contradictions in the two statutes. Further, the absence of specialist tribunals or officers dedicated to the administration of insolvency related matters is a further hurdle to the effective and efficient finalisation of the affairs of insolvent estates or insolvent companies’ affairs. The matter of Leong comes to mind. In this case, the Master of the High Court issued a warrant of arrest for a witness who was subpoenaed to appear at the meeting of creditors in his insolvent estate. This was the case, despite the fact that Leong had previously submitted a medical certificate to the effect that he was unable to attend the meeting due to illness. This case is a clear indication of a lack of proper guidelines to deal with insolvency related matters - for non-judicial officers (such as the Master of the High Court). This incident took place in 2016, long after the decision in De Lange v Smuts 1998 (1) SA 736 (CC). Interrogation processes in insolvency circumstances in Namibia and Botswana are almost similar to South Africa’s processes. Divergent provisions in Namibia and Botswana exist, but not to a great extent. Like South Africa, the above-mentioned jurisdictions adopted a constitutional democracy long before South Africa. One would have expected that interrogation proceedings in insolvency circumstances would be in line with human rights. Further, as is the case in South Africa, insolvency of natural persons and of juristic persons are regulated by two separate statutes in these jurisdictions. This thesis investigates issues relating to the interrogation process in insolvency proceedings in the three SADC countries, namely South Africa, Namibia and Botswana. It compares the position to two foreign jurisdictions, namely England and Canada – as leading jurisdictions in human rights. Thereafter, suggestions on processes and methods of information gathering in line with human rights and in specialist tribunals will be made. In addition, recommendations for inclusion in a unified statute regulating insolvencies of both natural and juristic persons will be made. This will be done taking into consideration the economical and socio-political circumstances of South Africa and the SADC countries forming part of this thesis.
Keywords: Insolvency; Private enquiries; Public enquiries; Subpoena; Summons; UNCITRAL Model Law; World Bank

An appraisal of the provision of "benefits" as an unfair labour practice in South African labour law - Newaj, Kamalesh (University of Pretoria, 2019)
This thesis seeks to resolve the ambiguities surrounding the use of the unfair labour practice relating to the provision of “benefits” as a dispute resolution mechanism in South African labour law. This mechanism has been plagued with uncertainty, primar-ily because of the lack of a statutory definition of benefits. Evidently, the interpretation and application of benefits have been left to the courts, resulting in two diverse ap-proaches being endorsed. The first one sought to confer a narrow connotation on ben-efits, the rationale being to separate benefits from the definition of “remuneration”. It further sought to limit the use of this unfair labour practice to instances where the benefit claimed was exclusively provided for ex contractu or ex lege. The primary ob-jective was to protect the divide between disputes of right and disputes of interest, a distinction that is recognised and encouraged in our law. The second approach was one that fostered an expansive interpretation of the term, deeming it to be part of re-muneration. Needless to say it resulted in countless items being subject to determina-tion as benefit disputes. Furthermore, it extended benefits beyond those rooted in con-tract or legislation, including those granted or offered subject to the exercise of mana-gerial discretion. The supplementary challenges firstly relate to the absence of statutory direction on the standards of fairness to be applied in evaluating employer conduct. Secondly, the judiciary has provided opportunities for employees to utilise recourse other than the unfair labour practice provisions to address benefit disputes. Such leeway comes in the form of contractual recourse as well as the ability to institute strike action. In search of solutions to the problems identified above, the study explores and anal-yses the history of the unfair labour practice concept. Thereafter, an extensive exam-ination of the developments in this area of the law is undertaken. This includes a com-prehensive analysis of legislation, case law and academic writings. Having docu-mented and analysed the South African position both pre- and post-democracy, the study critically evaluates these sources of law. The study further involves a diagnostic assessment of international legal instruments and foreign law in order to extract best practices. The conclusions reached are, firstly, that an expansive interpretation of benefits is warranted. This is in line with a purposive interpretation of the LRA, which promotes the constitutional right to fair labour practices and international law. This study there-fore proposes a wide-ranging definition of the term benefits. Secondly, standards of substantive and procedural fairness have been found to be applicable in evaluating employer conduct. As such, fairness guidelines based on these standards have been developed. Thirdly, in respect of the alternate avenues available to resolve benefit disputes, it has been found that although there are strong indicators that point to a conclusion that contractual recourse has been supplanted by statutory recourse, such a finding cannot be definitively made. Furthermore, section 64(4) as it stands provides for the right to strike over unilateral changes to terms and conditions of employment, which includes unilateral changes to pre-existing benefits. However, the judiciary can limit the use of this section in benefit disputes by prioritising the substance of the dis-pute over its form. This thesis ultimately proposes the incorporation of a Code of Good Practice into the LRA. The Code of Good Practice: Benefits adopts the principal research findings of this study. It encourages the enforcement of benefit disputes through the dispute res-olution institutions set up by the LRA. The adoption of this Code (The Code of Good Practice: Benefits) will bring certitude to this field of labour law.
URI: https://repository.up.ac.za/handle/2263/72658
Keywords: Labour law; Labour practice; South Africa

Article 6.8 and Annex II of the WTO agreement on antidumping - Persoz, Dimitri (European University Institute, 2019)
Article 6.8 of the Antidumping Agreement (AD) allows domestic investigating authorities to make determinations on the basis of the best information available (BIA) when any interested party does not cooperate during an antidumping investigation under the discipline of Annex II of the AD. Since its introduction, this provision has been the source of extensive and neverending litigation in front of both domestic investigating authorities and the Dispute Settlement Body. In this thesis, we research to what extent the findings of the Panels and the Appellate Body regarding Article 6.8 AD are consistent with the mandate set out in Articles 3.2, 11 DSU and 17.6 AD and to what extent they are reasonable from an economic perspective. To answer the first question, we first discuss Articles 3.2, 11 DSU and 17.6 AD to establish what is the mandate of the Panels and the Appellate Body under the Dispute Settlement Body. We then examine the findings of the Panels and the Appellate Body in the interpretation of the seven terms of Article 6.8 AD under the previously established mandate. To answer the second question, we summarize the latest developments in the economic theory of adjudication and litigation. We then discuss the findings of the Panels and the Appellate Body using this economic standard. In the conclusion, we compare the results of our analysis with current negotiations on Article 6.8 AD in the Doha Round framework and further discuss the opportunity to create a single united international investigating authority.
Accepted: 2019-07-10T10:52:46Z

Resale price maintenance in consumer good markets: an economic justification for the prohibition of RPM - Schwaderer, Melanie Ariane (European University Institute, 2019)
The thesis contributes to the debate on the EU’s approach to the business practice of resale price maintenance (RPM), which is widely criticized as too strict and in conflict with what is considered to be the consensus in the economic literature. The thesis critically dissects the economic consensus, on which the critique against the EU’s approach is based, by analyzing the empirical evidence that is cited to support the claim that RPM can frequently be explained by the service-based RPM models and shows that there is no convincing evidence that would support the significance of these positive RPM models that predict positive effects on welfare. To support this finding the thesis collects new evidence by surveying the marketing literature and shows that not only is there no convincing evidence that the positive RPM models frequently apply, but to the contrary there is evidence that these models are inconsistent with the real world phenomenon of RPM. Having refuted the service-based models the thesis takes up the scientific challenge that “it takes a theory to beat a theory” and proposes to fill the gap with three price-based models. The thesis offers an analysis of the three price-based RPM models, first from the perspective of welfare effects and then from a broader economic perspective in an attempt to ultimately show that the EU approach to RPM can be justified based on these economic models. All three models explain the situation in which RPM is used by a branded good manufacturer to create the perception of high quality, which is used either as a credible quality signal, becomes a component of the product or is used to bias the consumer decision; they thus enter the difficult terrain of consumer preference formation and of markets for the intangible components of a product.
Keywords: Competencia; Competition law; European Union countries; Marketing; Price maintenance

Entry of Foreign Investments: Convergence of International Trade and Investment Law? - Lubambo de Melo, Murilo Otávio (University College London, 2018)
The thesis analyses how public international law regulates the entry of foreign investors and investments into states. It explores the various legal concepts and techniques to limit the freedom of states to accept investments and regulate their access, employed in different regimes of international law. These are: international trade law – mainly illustrated by the WTO (World Trade Organisation) agreements, in particular, the General Agreement on Trade in Services (GATS), and preferential trade agreements (PTAs) – and international investment law (IIL) – scattered through a network of bilateral investment treaties (BITs). The thesis concludes that there are signs that the international rules regulating the entry of investments in services are converging in several levels of alignment and treaty making. Convergence means a reduction of non-shared legal and systemic characteristics or an increase in shared characteristics. Several factors support this conclusion: the progressive incorporation in treaties of establishment rights for investors, that is, commitments by states to allow foreign investments under certain conditions; the narrowing-down of investor-state dispute settlement clauses dealing with entry, which makes IIL systemically closer to international trade law regarding dispute settlement; the hidden liberalising power that flows from the broad interaction of the most-favoured-nation (MFN) clauses in the GATS and IIL with entry provisions; and, the incorporation of concepts and techniques from the international trade law world into investment chapters of larger international economic agreements, such as the GATS absolute standard of market access and its system of exceptions and justifications. These converging signs are considered a natural evolution of the rules given that trade and investment sometimes represent complementary market access strategies in the context of global value chains. The thesis suggests that this move towards convergence may bring about more effectiveness to the rules by attaining the goal of investment liberalisation balanced with the safeguard of regulatory space.
Keywords: Domestic investor; Foreign investment; GATS MFN clause; International Economic Law; International Trade; Investment Law; Investments; Remedies; State-State Investment Arbitration; WTO regulation

The defence of illegality in international investment arbitration : a hybrid model to address criminal conduct by the investor, at the crossroads between the culpability standard of criminal law and the separability doctrine of international commercial arbitration - Busco, Paolo (Sant'Anna School of Advanced Studies ; Université Paris 1, 2018)
Cette thèse analyse la question relative au cas où, dans l'arbitrage international en matière d'investissements, dont le but principal est l'application des normes visées à la protection des investisseurs, l’État défendeur soutient que l'investissement pour lequel la protection est demandée a été obtenu au moyen d'une forme de criminalité. Dans ce contexte, la défense de l'illégalité soulevée par les État dans les contentieux d'investissement est de plus en plus courante. Cette défense fonctionne selon le schéma suivant : un État hôte enfreint les dispositions de fond que le droit international accorde aux investissements effectués dans un pays étranger, par exemple en expropriant un investisseur étranger de son investissement sans indemnité. Dans le différend qui s'ensuit devant un tribunal arbitral d'investissement, l'État défendeur invoque l'illégalité commise par l'investisseur lors de la réalisation de l'investissement pour se défendre contre la procédure arbitrale intenté contre lui. Le but principal de cette étude est celui de démontrer que des considérations systématiques de nature strictement juridique, aussi bien que de politique juridique, exigent que la défense d'illégalité dans l'arbitrage d'investissement soit strictement restreinte et qu'un tribunal ne puisse décliner d'exercer sa compétence / juridiction que dans des cas exceptionnels. Cette étude aboutit à la conclusion d'après laquelle les tribunaux d'arbitrage devraient plutôt examiner au cas par cas au stade du fond l'ensemble des circonstances soumises devant lui et procéder à une mise en balance appropriée entre les comportements de l'investisseur et ceux de l'État hôte. This thesis addresses the question as to how an investment Tribunal is to react if, in the context of a case brought before it for breach of standards of protection of an investment, the respondent argues that the investment for which protection is sought has been secured by resorting to some form of criminality. Against this background, a defence by the Host State that has become increasingly common is the so-called Defence of Illegality. It operates on the basis of the following scheme : a Host State breaches the substantive provision that international law accord to investments made in a foreign Country, for instance by means of expropriating without compensation the investor's investment. In the ensuing dispute before an investment Tribunal, the defendant Host State raises the illegality committed by the investor in the making of the investment as defence against the breach of the substantive provisions on the protection of the investment, of which it is accused, to avoid responsibility. This thesis intends to demonstrate that both legal and policy consideration dictate that the Defence of Illegality in investment arbitration should be strictly curtailed and that a Tribunal should only decline to exercise its jurisdiction in exceptional cases. Rather, Tribunals should look at the entire set of circumstances at the merits stage and perform a proper balancing test between the conduct of the investor and the Host State.
Keywords: Admissibility and jurisdiction; Admissibilité; Approche comparée; Arbitrage; Arbitrage commercial; Arbitrage d'investissement; Arbitrage et crime; Arbitrage international; Arbitragem; Arbitration; Arbitration and crime; Clause de légalité; Clean hands doctrine; Commercial Arbitration; Comparative law; Compétence; Compétence juridictionnelle; Corruption; Defence of Illegality; Doctrine des mains propres; Défense d'illégalité; Investment arbitration; Investments

The regulation of non-standard employment in Southern Africa : the case of South Africa with reference to several other SADC countries - Mokofe, William Manga (University of South Africa, 2018)
This doctoral thesis deals with the regulation of non-standard employment in Southern Africa: the case of South Africa with reference to several other SADC countries. The growth and presence of non-standard employment since the 1970s has revealed an important concern in a number of countries, both at the global and national levels. The overall significance of non-standard employment has increased in recent decades in both developed and developing states, as its use has grown exponentially across economic sectors and employment. Non-standard employment is the opposite of the standard employment relationship, which is work that is full time and indefinite. Non-standard employment includes an unequal employment relationship between an employee and an employer. Some workers choose to work in non-standard employment, and the choice has positive results. Nonetheless, for the majority of workers, non-standard employment is associated with job insecurity, exploitation, and the absence of trade unions and collective bargaining. Non-standard employment can also create challenges for firms, the labour market and the economy, including society at large. Backing decent work for all entails a comprehensive understanding of non-standard employment and its ramifications. This study explores the regulation and protection of non-standard employment in Southern Africa with focus on South Africa. The study draws on international and regional labour standards, the South African Constitution of 1996, and the national experience to make policy recommendations that will ensure workers are protected, firms are sustainable and labour markets operate well. Social justice and the democratisation of the workplace cannot be achieved if workers in non-standard employment are excluded from the labour relations system.
Keywords: Collective bargaining; Labor laws and legislation; Non-standard employment; Part-time employment; South Africa; Standard employment; Temporary employment; Temporary workers; Vulnerable workers

Business combinations and group of companies : perspectives from accounting, law and corporate finance - Coda, Stefano (Université Paris 1, 2018)
Dans le cadre général des regroupements d'entreprises et des groupes de sociétés, cette thèse porte sur des questions d'intérêt à la croisée de la comptabilité, du droit (notamment les dispositions légales et la réglementation comptable) et de la finance d'entreprise. En ce qui concerne la théorie comptable, le chapitre 2 étudie comment les chercheurs en économie d'entreprise ont compris les groupes d'entreprises, les comptes de groupe et le processus de leur préparation, en particulier par rapport aux juristes italiens. Ensuite, le chapitre 3 reconstruit le processus politique et législatif qui a engendré la naissance du concept de groupe de sociétés dans le corpus juridique italien.Concernant le droit et la politique comptable, une analyse comparative est effectuée au chapitre 4qui montre clairement l'évolution de la notion de contrôle et de son utilisation dans les comptes consolidés (comptes de groupe) et les regroupements d'entreprises (I) en droit européen, (II) selon les normes comptables internationales publiées par l'IASB (International Accounting Standards Board) et (III) par rapport aux principes comptables généralement admis aux États-Unis («USGAAP»). De plus, les chapitres 5 et 6 étudient les effets du lobbying sur les normes comptables concernant les états financiers consolidés et les regroupements d'entreprises publiés par l'IASB. Fait intéressant, les résultats concordent avec une forme de capture du normalisateur comptable international par une catégorie d'institutions financières. En effet, confrontées à un modèle de consolidation prétendument basé sur le contrôle, ces dernières ont plaidé en faveur d'une exception de consolidation fondée sur un modèle de propriété et documentée comme ayant été proposée par les sociétés d'audit américaines dans ce contexte au moins depuis 1995. Ce modèle s’avère avoir trouvé un terrain fertile au sein de l'IASB. En conséquence, d'autres catégories d'institutions financières,telles que les fonds d'investissement à long terme et ceux gérés par une famille tout en préférant un modèle de consolidation différent, ne sont plus autorisées à présenter des états financiers consolidés. En ce qui concerne la finance d’entreprise, le chapitre 7 analyse les implications de différentes décisions de financement dans un nouveau échantillon de fusions et acquisitions entre institutions financières (banques et assurances) consommées dans le monde entier au cours des deux dernières décennies. En particulier, il étudie (I) la relation entre la méthode de choix de paiement (si le prix est payé en cash, en actions ou une combinaison des deux) et le choix du mode de financement d'un regroupement d'entreprises (y compris les instruments hybrides) et (II) la réaction des investisseurs à l'annonce de la combinaison. En ce qui concerne ce dernier point, l'utilisation de deux tests non paramétriques permet de détecter une relation intéressante entre la réaction du marché à l'annonce et les différents modes attendus de financement de la transaction.
Keywords: Accountings standard setting; Comptabilité; Consolidation exemption; Egroupements d'entreprises; Finance d'entreprise; Finances; Financial institutions; Gestion d'entreprise; Groupes de sociétés; IASB; IFRS 10; IFRS 3; Mergers and acquisitions; Method of payment; Politics; Politique comptable; Sources of fundings; Économie d'entreprise

Relations between quality of trademarks and cognitive and conative variables of consumers - Naumovski, Goce (Université de Strasbourg, 2018)
But de la recherche : déterminer la dépendance des caractéristiques des marques (perceptibilité visuelle, représentation graphique, le caractère distinctif, non-généricité etc.), sur les types généraux spécifiques de capacités intellectuelles et sur les caractéristiques conatives des consommateurs de la population générale, par application de nombreux tests. La recherche a été réalisée sur un échantillon de 206 sujets-consommateurs. Ils ont évalué la qualité des marques de commerce (déposées et refusées) pour différents types de produits et services (TM-1 test). Les sujets ont été testés avec 3 tests cognitifs et 6 tests conatifs. Méthodes quantitatives appliquées : paramètres élémentaires de la statistique descriptive ; corrélation ; analyse factorielle ; analyse de régression multivariée, analyse canonique des corrélations. Les résultats ont indiqué que les variables cognitives et conatives ont des relations statistiquement significatives avec les résultats de TM test (qualité des marques).
Keywords: Capacités cognitives; Caractéristiques conatives; Cognitive abilties; Comportement des consommateurs; Conative characteristics; Consommateur; Consumers; Intellectual property; Marques; Marques de commerce (droit international); Propriété intellectuelle (droit international); Trademarks

A comparative study of the effects of liquidation or business rescue proceedings on the rights of the employees of a company - Joubert, Engela Petronella (University of South Africa, 2018)
Whenever legal disciplines overlap interesting scenarios occur and differences in opinions create intellectual tension. One such interesting scenario occurs when employees’ rights are affected during a company’s liquidation or business rescue. The employees of a company are normally the last persons to find out that a company is struggling financially. They are also the only stakeholders who are in no position to negotiate their risk should the company be liquidated. It is therefore necessary to evaluate the rights given to employees during a company’s liquidation and business rescue. The fundamental ideologies of company law, insolvency law and labour law are challenged and examined to attempt a harmonizing result that respects the core of each discipline. It is crucial to determine whether an appropriate balance is struck between the interests of all the stakeholders of the company during these procedures. The aim of this thesis is to evaluate whether South Africa manages to strike this balance. If employee rights are protected whilst a company is restructured back to solvency and success, this balance will be struck. An evaluation will also be made whether employees are always better protected during business rescue than in liquidation. The study analyses employee rights in a company’s liquidation and during a company’s restructuring process. The comparative study of employee rights in liquidation and rescue is done with the jurisdictions of Australia and England – countries with similar procedures. Important conclusions show that South Africa protects employee rights during business rescue procedures the best. An appropriate balance is indeed struck between the interests of all stakeholders of a company during business rescue procedures and employees are most of the time better off after a restructuring than in a liquidation. Should the recommendations for law reform be implemented in our legislation, South Africa will overcome the few obstacles currently in its way to be seen as a world leader where employee rights are concerned in liquidation proceedings as well as business rescue.
Keywords: Australia; Bankruptcy; Business rescue; Corporate reorganizations; Employee rights; Employment contract; Great Britain; Liquidation; Ranking of claims; South Africa

Combating corruption in public procurement in developing countries : a legal analysis - Mugadza, W. T. (North-West University, 2018)
This study was motivated by the quest to find new innovative and practical ways of combating public procurement corruption in developing countries to complement the existing measures. This was achieved by comparing three jurisdictions, Hong Kong-China, Botswana and South Africa. The focus was on how each jurisdiction uses the following four measures to curb public procurement corruption: criminal measures; administrative measures; institutional measures and civil activism measures. It was established that Hong Kong uses what this study has classified as the traditional approach of combating public procurement corruption. The traditional approach is characterised by the use of a separate procurement legal framework and a separate corruption legal framework to curb public procurement corruption. Its strengths are in the strict enforcement of criminal measures that are anchored on a robust legal framework, a clear anti-corruption strategy, an independent anti-corruption agency (institutional measure), effective internal oversight and a strong political will. However, the following weaknesses of the traditional approach were identified: over reliance on criminal measures; excessive dependence on one enforcement institution; it neglects the development of administrative measures and has weak civil activism measures. It was established that Botswana uses what this study has classified as the classical approach of combating public procurement corruption. The classical approach is characterised by a procurement legal framework that incorporates very minimum anti-corruption provisions. The anti-corruption provisions in the procurement legislation are enforced by an external institution (the DCEC in the case of Botswana) which relies heavily on the criminal measures. Its strengths are the following: a strong legal framework which provides for a clear anti-corruption strategy; it has anti-corruption units in each Ministry and it has a dedicated Corruption Court. However, the classical approach has the following weaknesses: the anti-corruption agency is not adequately independent as it under the control of the executive (the President in the case of Botswana); lacks effective internal oversight mechanisms; weak political will; neglects the development of administrative measures and civil activism measures are almost non-existent save for the media. It was established that South Africa uses what this study has classified as the traditional cum silo approach of combating public procurement corruption. The traditional cum approach is characterised by multiple procurement legislation which has certain but minimum anti-corruption provisions and a separate corruption legal framework. Multiple anti-corruption agencies are prone to political interference which renders them ineffective and unfit for purpose. Its strength is in the promotion and protection of civil activism measures (right to access information, right to freedom of speech and legal protection of whistle-blowers). Notable weaknesses of the traditional cum silo approach are: the poor enforcement of criminal measures; there is no lead anti-corruption agency that spearheads and coordinates all cases of public procurement corruption; there is no clear anti-corruption strategy; the administrative measures such as debarment are poorly enforced; it has multiple anti-corruption institutions that lack focus and professionalism which results in political manipulation. The thesis concluded by suggesting a new approach, the contemporary approach to combating public procurement corruption which entails the enactment of a single procurement legislation (model law) the Public Procurement and Combating of Public Procurement Corruption Act (hereafter PPCPPC). The contemporary approach advocates for the regulation of public procurement and the combating of public procurement corruption in one legislation. This legislation (PPCPPC) takes into account, the current demands for public procurement as well as future developments of public procurement. These include but are not limited to self-cleaning, cyber-crime and public procurement corruption as well as the role of foreign convictions for debarment purposes. The envisaged PPCPPC will in addition to regulating public procurement, encompass the best criminal measures, administrative measures, institutional measures and civil activism measures. In addition, the contemporary approach through the PPCPPC proposes two new innovations: the corruption clearance certificate and a mandatory anti-corruption clause in all government contracts.
Keywords: Accountability; Administrative measures; Anti-corruption clause; Botswana; Civil activism measures; Classical approach; Combating corruption; Competitiveness; Contemporary approach; Corruption clearance; Criminal measures; Debarment; Equality; Fairness; Hong Kong; Institutional measures; Integrity; Procurement principles; Public procurement; South Africa; Traditional approach; Transparency; Value for money

The realisation of rights in terms of the Consumer Protection Act 68 of 2008 - Scott, Tshepiso (University of South Africa, 2018)
The thesis examines the enforcement of consumer rights in South Africa, and is set against the backdrop of the underlying principles and theories on the enforcement of consumer protection law. It then analyses the various forms of consumer protection law enforcement mechanisms that were in place prior to the implementation of the Consumer Protection Act 68 of 2008, and sets out why there was a need for the enactment of the Consumer Protection Act. The thesis then critically discusses the consumer protection law enforcement mechanisms introduced and/or catered for by the Consumer Protection Act. The in-depth comparative analysis against the consumer protection law enforcement dispensations in both India and the United Kingdom culminates in a critical analysis of the successes and shortcomings of consumer protection law enforcement regime in present-day South Africa; as well as recommendations (in the form of legislative amendments and practical solutions) on how the South African consumer protection enforcement framework can be improved in order to facilitate the realisation of consumer rights.
Keywords: Consumer protection; Consumer rights; Enforcement mechanisms

Internet regulation and development: the battle over the network neutrality - Melo, Lílian Manoela Monteiro Cintra de (Universidade de São Paulo, 2018)
We have arrived at crossroads in the debates about the future of the internet governance. It is high time to address the reasons why policy choices have not been sufficient to preserve the internet\'s promise to bring about development, democratic engagement, and social justice. The network neutrality is central to this debate since it intersects all internet layers and is related to most contemporary issues that will shape future of the internet. My assumption is that network neutrality\'s failures are not an unintended consequence of the regulatory system, but part of the problem. My core hypothesis is that network neutrality\'s limits mainly occur because of, first, its inability to secure all envisioned goals and, second, its decontextualized focus on innovation on the last mile of the internet distributional chain. The network neutrality debate has produced a wide variety of work embedded within economic and legal studies regarding what would be necessary to guarantee a free and innovative internet. Although this work has been often disguised under the mask of technique, it is widespread influenced by the evolutionary economics and denies the network neutrality's effects on ongoing struggles for social and economic justice. My proposition is that network neutrality debate has failed because it proved unable to address the problems related to concentrated power structures on the internet and increasing inequalities. To achieve this objective, this dissertation investigates the network neutrality debate over the last decades to identify processes and mechanisms by which its sterile arrangements came to take specific form in time and place, focusing on what such arrangements might inform about contemporary policy efforts. In Chapter 1, prevalent internet governance myths are deconstructed, presenting how specific architecture design and the corresponding network neutrality outcomes came to prevail in particular periods. Drawing upon and integration of distinct source materials, Chapters 2 and 3 identify the specific contingencies over the past decades by which a dynamic set of evolving actors, events, and institutions converged (or not) and gave rise to current network neutrality rules and dissent in the United States and Brazil. At the center of the analysis is the identification of structures and power struggles. Finally, Chapter 4 aims at presenting a new framework towards the network neutrality debate and its potential distributive effects in the global economy, taking technology not as deterministic but embedded and being embedded in all the building blocks of what we term the social.
Keywords: Economic power; ICT; Inequality; Innovation; Internet access; Internet governance; Law and development; Network neutrality; S&TS; Structure

Contract, Conflict and Cooperation: A Critical Analysis of the Common Law Approach to the Breakdown of Modern, Complex, Symbiotic Contracts - Soper, Charles Haward (University of Leicester, 2018)
The springboard of a real-world, doctrinal, and theoretical investigation of the role played by cooperation in complex modern contracts allows me to articulate and justify a deep and concrete Transcendent Duty to Cooperate (TDTC) for these contracts. The source of the TDTC is the express words and/or the background of such contracts, the commercial expectations of the parties; which reveal that successful performance re-quires cooperation. The inevitable inference from this is that parties implicitly agree to cooperate. As the duty is implicit, it follows, I argue, that there are no gaps to be filled; merely meaning to be unearthed from the words and/or the background (construction). In doctrinal work, I review cases in categories (prevention, facilitation, defect-rectification, communication, decision-making, and active cooperation), showing that the law is far from coherent but also far from incoherent. Shifting from judicial policy making and gap-filling to context/purpose based contract construction, using evidence, is possible and would provide coherence. I create a clear and enforceable definition of cooperation through analysing the opinions of around five-hundred commercial experts and synthesising those with doctrine and theory. My empirical work analyses experts’ views; collected by interview, an online survey and workshops, using vignettes developed from adjudicated/real-life cases including opinion on what cooperation is and how it is achieved. The findings of my survey are compared with others. At an abstract level, it aligns with comparable surveys and at a detailed level, it is unique. In theoretical work, I show that basing the TDTC on construction is superior and more efficient, brings coherence to the law and that it is underpinned by shared, normative, “community” values. I test the TDTC against various “hard” cases, analysing remedial issues, showing that it would not decrease certainty in English Commercial Law, and is defensible by an appeal for coherence.

Enabling intellectual property and innovation systems for South Africa's development and competitiveness - Sibanda, McLean (University of South Africa, 2018)
During the last two decades, there have been a number of policy and legislative changes in respect of South Africa’s intellectual property (IP) and the national system of innovation (NSI). In 2012, a Ministerial Review of the Science, Technology and Innovation (STI) landscape in South Africa made recommendations to improve the STI landscape and effectively the national system of innovation. The study provides a critical review of drafts of the national IP policy published in 2013 as well as the IP Framework released in 2016 for public comment. The review of the IP and the NSI are within the context of the National Development Plan (NDP), which outlines South Africa’s desired developmental goals. South Africa is part of the BRICS group of countries (Brazil, Russia, India, China and South Africa). The South African economy is characterised by a desire to move away from being dependent on resources and commodities, to becoming a more knowledge based and innovation driven economy. It is hoped that such a move would assist the country to address some of the social and economic development challenges facing South Africa, as captured in the NDP. South Africa has a functioning IP system, but its relationship with South Africa’s development trajectory is not established. More particularly, the extent to which the IP system relates to the innovation system and how these two systems must be aligned to enable South Africa to transition successfully from a country based on the production of primary resources and associated commodity-based industries to a viable knowledge-based economy is unclear. The Trade-related Aspects of Intellectual Property Rights (TRIPS Agreement) of the World Trade Organisation (WTO) provides that IP must contribute to innovation and to transfer of technology and knowledge in a manner that is conducive to social and economic welfare. Certain provisions set out the foundations of intellectual property systems within the context of each member state. This study has thus explored the complex, complementary and sometimes contested relationships between IP and innovation, with particular emphasis on the potential of an intellectual property system to stimulate innovation and foster social and economic development. The study has also analysed the interconnectivity of IP and innovation with other WTO legal instruments, taking into account South Africa’s positioning within the globalised economy and in particular the BRICS group of countries. The research involved a critical review of South Africa’s IP and innovation policies, as well as relevant legislation, instruments, infrastructure, IP and innovation landscape, and relationship with international WTO legal instruments, in addition to its performance, given the developmental priorities and the globalised economy. The research documents patenting trends by South Africans using European Patent Office (EPO), Patent Cooperation Treaty (PCT), United States Patents and Trademarks Office (USPTO) databases over the period 1996-2015. A comparative analysis of patenting trends amongst BRICS group of countries has also been documented. The study also documents new findings, observations and insights regarding South Africa’s IP and innovation systems. Some of these, particularly in relation to higher education and research institutions, are directly attributable to the Intellectual Property Rights from Publicly Financed Research and Development Act. More particularly, the public institutions are becoming relevant players in the NSI and are responsible for growth of certain technology clusters, in particular, biotechnology. At the same time, the study makes findings of a decline of private sector participation in patenting as well as R&D investment over the 20-year period. Recommendations are included regarding specific interventions to ensure coherence between the IP and innovation systems. Such coherence and alignment should strengthen the systems’ ability to stimulate innovation and foster inclusive development and competitiveness, which are relevant for addressing South Africa’s socio-economic development priorities.
Keywords: BRICS; Biopharmaceutical; Biotechnology; Commercialisation; Economic development; Flexibilities; Inclusive growth; Innovation; Intellectual property; Licensing; Patents; Start-ups; TRIPs Agreement

A critical analysis of the removal of directors by the board of directors and the judiciary under the Companies Act 71 of 2008 - Cassim, Rehana (University of South Africa, 2018)
Section 71(3) of the Companies Act 71 of 2008 has introduced into South African company law a provision which for the first time permits the board of directors to remove another director from office in certain specific instances. A further significant innovation in the Companies Act 71 of 2008 is contained in section 162, which empowers a court to make an order declaring a director delinquent or placing him under probation in specific instances. The effect of section 162 is that a court is empowered to remove a director from the board of directors. The focus of this thesis is the removal of directors from office by the board of directors and by the judiciary. The thesis explores the underpinning philosophy of the statutory provisions relating to the removal of directors from office. It also examines the impact of the power given to the board of directors and to the courts to remove a director from office. The grounds and the procedures for the removal of directors by the board of directors and the judiciary are examined. The fiduciary duties applicable to directors in removing a director from the board of directors are also explored. In addition, this thesis examines the removal of directors holding multiple positions or capacities in relation to a company, such as an employee or a shareholder with loaded voting rights. The remedies which may be relied on by a director who has been removed from office by the board of directors are examined. Recommendations are made to strengthen and improve the provisions in the Companies Act 71 of 2008 relating to the removal of directors from office by the board of directors and the judiciary. Amendments to the Companies Act 71 of 2008 are suggested to remove ambiguities; to guard against the abuse of sections 71(3) and 162; to improve the grounds and procedures for the removal of directors by the board of directors and the judiciary, and to enhance the remedies that may be relied on by a director who has been removed from office by the board of directors.
Keywords: Corporate governance; Directors and shareholders power; Directors of corporations; Fiduciary duties; Investor relations; Removal of directors from office; Stockholders' voting; Voting rights

A critical analysis of the security of foreign investments in the Southern African Development Community (SADC) region - Ngobeni, Tinyiko Lawrence (University of South Africa, 2018)
Foreign investments in SADC are regulated by Annex 1 of the SADC Protocol on Finance and Investments (SADC FIP), as well as the laws of SADC Member States. At present, SADC faces the challenge that this regime for the regulation of foreign investments is unstable, unsatisfactory and unpredictable. Furthermore, the state of the rule of law in some SADC Member States is unsatisfactory. This negatively affects the security of foreign investments regulated by this regime. The main reasons for this state of affairs are briefly explained below. The regulatory regime for foreign investments in SADC is unstable, due to recent policy reviews and amendments of key regulatory instruments that have taken place. Major developments in this regard have been the suspension of the SADC Tribunal during 2010, the amendment of the SADC Tribunal Protocol during 2014 to bar natural and legal persons from access to the Tribunal, and the amendment of Annex 1 during 2016 to remove investor access to international investor-state arbitration, better known as investor-state dispute settlement (ISDS). The regulation of foreign investments in SADC has been unsatisfactory, among others because some SADC Member States have failed or neglected to harmonise their investment laws with both the 2006 and the 2016 Annex 1. Furthermore, SADC Member States such as Angola, Democratic Republic of Congo (DRC), Malawi, Mauritius, Seychelles, Eswatini, Tanzania, Zambia, and Zimbabwe have multiple Regional Economic Community (REC) memberships. This places these Member States in a position whereby they have conflicting interests and treaty obligations. Finally, the future of the regime for the regulation of foreign investments in SADC is unpredictable, due to regional integration efforts such as the recent formation of the COMESA-EAC-SADC Tripartite Free Zone (T-FTA) and the African Continental Free Trade Area (AfCFTA). The T-FTA is entitled to have its investment protocol, while the AfCFTA investment protocol will be negotiated from 2018 until 2020. These developments entail that the 2016 Annex 1 will soon be replaced by an investment protocol at either the T-FTA or AfCFTA levels, thereby ushering a new regime for the regulation of foreign investments in SADC. The unknown nature of the future regulations create uncertainty and instability among foreign investors and host states alike. This study analyses the regulation of foreign investments in terms of Annex 1 and selected laws of SADC Member States. In the end, it makes the three findings mentioned above. In order to address these findings, the study makes four recommendations. The first is that foreign investments in SADC must be regulated at African Union (AU) level, by means of an AfCFTA investment protocol (which incidentally is now the case). Secondly, investor-state disputes must be referred to the courts of a host state, optional ISDS, the African Court of Justice and Human Rights (ACJ&HR) or other agreed forum. Thirdly, an African Justice Scoreboard (AJS) must be established. The AJS will act as a gateway to determine whether an investor-state dispute shall be referred to the courts of a host state, ISDS, the ACJ&HR or other forums. Fourthly, the office of an African Investment Ombud (AIO) must be created. The AIO shall facilitate the early resolution of investor-state disputes, so as to reduce the number of disputes that may end-up in litigation or arbitration.
Keywords: ACH&PR; AfCFTA; African Continental Free Trade Area; African Court for People and Human Rights; African Court of Justice and Human and Peoples' Rights; African Court on Human and Peoples' Rights; African Justice Scoreboard; African Union; COMESA; Commercial treaties; Customs unions; Dispute resolution; EAC; Expropriation; Foreign economic relations; Foreign investment; Free Trade Agreement; ICSID Arbitration Rules; International commercial arbitration; Investments; Investor-State Dispute Settlement; SADC; SADC Protocol; Southern African Development Community; State Responsibility; UNCITRAL Arbitration Rules

A contract theory approach to Islamic financial securities - Hanif Arbi, Lukman (La Trobe University, 2018)
The aim of this thesis is to investigate the economic and financial substance of certain contractual requirements imposed by Islamic commercial law as well as some of their implications. More attention is given to requirements that have financial implications and are related to those discussed in the contract theory literature. We divide our investigation into four parts. The first part is an examination of the fundamental transactional requirements in Islamic commercial law, focusing on those related to four primary Islamic Financial Securities (IFSs). In the second part, we use our findings to construct an alternative asset pricing methodology. We also explore our findings in the third and fourth parts using the principal-agent model of Holmström and Milgrom (1991). More specifically, we use it to respectively model the relationship between underwriters and Islamic commercial law regulators as well as consider the case of ambiguous incentive contracts. Each part of our investigation has yielded substantial contributions to the literature as follows. Firstly, our examination of Islamic commercial law principles and contracts reveals that there are indeed legal requirements which have direct implications for financial models, such as the need for a liquidity discount in receivables-based ṣukūk as they are – in principle – non-tradeable. Secondly, the asset-pricing model we have constructed allows us to examine the equilibrium return and investment levels of IFSs. This allows us to derive conditions at which one security yields higher returns than another. Thirdly, our cooperation model suggests that cooperation between underwriters and Islamic commercial law regulators is only beneficial for an issuer of a structured Islamic financial product if their synergy benefits are over a certain level. Lastly, our investigation into ambiguous incentive contracts demonstrates that it is never beneficial for principals to offer such contracts to ambiguity averse individuals as it unambiguously reduces the principal’s profit.

A critical analysis of the legal environment in respect of the private equity industry in South Africa - Oaker, Wentzel (Stellenbosch University, 2018)
This dissertation aims to answer a fundamental question relating to the South African legal and economic framework in which private equity operates. This being: To what extent does the law address/regulate the structure of private equity funds and the relationships between the various parties related to a fund, that is: investors, the fund manager and underlying portfolio investments? This thesis also discussed how the law could better regulate the private equity industry. The dissertation consists of five chapters. Chapter one raises such fundamental questions as ‘what is the nature of private equity?’ by looking at the parties involved, the private equity cycle, returns, liquidity, the risk, and the private equity market. In addition, it assesses whether private equity satisfies the criteria to be regarded as a separate asset class. Chapter two provides an analysis of the key features of private equity fund formation in South Africa. The choice of the most appropriate legal structure of a private equity fund starts with the choice of the most effective and suitable legal vehicle. Chapter two includes a discussion of the general private equity fund structure, the regulatory requirements of private equity firms, and certain regulatory considerations relevant in operating a private equity fund in South Africa. The discussion at certain instances reference private equity fund formation in foreign jurisdictions such the US, UK, Australia, and Canada. Chapter three introduces an analysis of corporate governance as it pertains to private equity funds. Firstly, it discusses the role of corporate governance regulation in stimulating investment. Secondly, it discusses the importance and benefits of corporate governance from the perspective of private equity managers; and seeks to explain the link between the private equity business model and corporate governance that is based on the assertion that there are two levels of corporate governance involved in private equity investing. The first level of governance relates to the private equity fund’s underlying portfolio investee companies and this includes inter alia, a discussion on the duties of the fund manager, particularly in their capacity as serving as directors on the boards of such companies. The second level of governance relates to the private equity fund itself which focuses on the relationship between the private equity firm and the investors that invest in the private equity fund. Chapter four examines two key impediments namely tax legislation and exit alternatives; and show how legislation could effectively address the former and how the lack of exit routes is an impediment to the growth of the local private equity industry. Chapter five states that, the development of the above mentioned regulatory framework will only be successful if the private equity industry participants themselves acknowledge and actively address the disadvantages and real risks posed by the private equity industry on the South African financial system.
URI: http://hdl.handle.net/10019.1/103466
Keywords: Investments; Private equity; Private equity funds; South Africa; Taxation

The integration of work and parenting: a comparative legal analysis - Rossouw, Elzaan (Stellenbosch University, 2018)
Given the importance of parental care to children, parents and broader society and the apparent conflict between work and adequate parental care, this study evaluates the legal facilitation of the integration of work and care across nine countries, including South Africa. The study recognises that legal operationalisation of the integration of work and care primarily takes place at domestic legislative level and shows that this happens against the backdrop of widespread recognition of the importance of the family and care at the international, regional and constitutional levels. The study builds on the reality that domestic legislation in this context consists of (a combination of) equality law and specific rights contained in employment standards legislation. The comparative review of equality law as applied in the area of the work-care conflict shows that, despite the potential and promise that equality law holds to facilitate the integration of work and care, this potential has not been realised and probably will not be in future. This necessarily shifts the focus to an approach founded on the extension of specific rights related to time off or leave, as well as flexible working, to employees in order to enable them effectively to combine work and caregiving. The comparative review of specific rights in this area leads to the conclusion that South Africa lags far behind certain developed and comparable developing countries in its legislative recognition of the importance of caregiving and in its subsequent level of employment rights extended to caregivers. Given the ample room for improvement, suggestions for legislative reform are made based on the comparative experience of other countries
URI: http://hdl.handle.net/10019.1/103776
Keywords: Child care services; Comparative law; Employee rights; Employment standards; Equity; Labour law; Labour legislation

The Impact of Private Securities Lawsuits on Accounting Conservatism and the Moderating Influence of Corporate Governance - Kerr, Ryan (Victoria University of Wellington, 2018)
This study investigates the impact of conduct which goes on to give rise to a securities lawsuit, and the filing of a securities lawsuit, on the level of accounting conservatism in financial reporting. This study also investigates the moderating influence of corporate governance on the level of accounting conservatism following conduct which goes on to give rise to a securities lawsuit, and the filing of a securities lawsuit. The study uses a sample of 617 privately enforced disclosure-related securities lawsuits against listed US firms, taken under SEC rule 10b-5 of the 1934 Securities Exchange Act, over the period 2002 to 2010. The results of the study indicate that following both the conduct that gives rise to a securities lawsuit, and the filing of a securities lawsuit, firms adopt higher levels of accounting conservatism. However, the study finds no evidence that corporate governance moderates the impact of securities lawsuits on the level of accounting conservatism.
Keywords: Accounting Conservatism; Governance; Securities Lawsuits

An evaluation of market responses to corporate disclosures in a continuous disclosure environment - Li, Hanqiao (Victoria University of Wellington, 2018)
Corporate disclosure has attracted the attention of researchers from the accounting and capital markets. Researchers have been trying to better understand how capital markets respond to corporate disclosures. This study explores the short- and the long- term market effects of corporate disclosures in a continuous disclosure environment. This study aims to find the answers to the following research questions. (1) How market (price/volume) sensitive is the information contained in each disclosure category in a continuous disclosure environment? (2) How quickly is the value-relevant information incorporated into share prices before the annual earnings announcement is released, and how can company announcements promote this timeliness of price discovery? Specifically, this study examines the extent to which the Australian share market reacts to new public information immediately after the information is released, and the impacts of announcement frequency as to different continuous disclosure categories on the timeliness of price discovery (also known as the speed of price discovery). Prior research has mostly concentrated on a single type of information event to examine the information’s market consequences by monthly, weekly or daily data. Instead, by covering all public announcements and using tick (transaction) data to calculate intraday abnormal returns and abnormal trading volumes, this study examines which type of announcement has the largest immediate market responses, and compares the magnitude (with positive/negative signs) of market reactions to different announcement categories on the Australian Securities Exchange (ASX). This study is more attractive under the Australian Continuous Disclosure Regime (CDR) because of the classification system regarding the market-sensitive announcements. Whether or not an announcement is market-sensitive is predetermined by ASX ‘specialist staff’ before the announcement is released on the market. This study investigates how the market interprets the announcement, examining market sensitivity from both the share price and trading volume movements after the announcement is available to the market. In other words, to some extent, the ‘market sensitivity tag’ shows the announcement that the market should react to, and this study reveals the announcement that the market does react to. Focusing on market-sensitive announcements, except for the ASX Query, the significant results show a positive association between announcement categories and intraday Cumulative Abnormal Returns (CARs). Share prices react the most to Progress Reports and to Asset Acquisition & Disposal, and the least to Periodic Reports and Issued Capital. Share price reactions to Distribution Announcements and Other are in the middle. There are at least two possible reasons for the different market reaction magnitudes. One is the information materiality nature: if one type of information is more important to investors than other information, this may cause higher abnormal returns on the market. The other is the information predictability: if there has been a lot of relevant information available in previous days or months, share prices could adjust to the information more smoothly. In terms of the trading volume reactions, intraday Abnormal Trading Volumes (ATVs) are observed after the release of Progress Reports, Asset Acquisition & Disposal, Issued Capital and Periodic Reports. After separating good and bad news subsamples, the results show that Progress Reports and Asset Acquisition & Disposal tend to indicate good signs to the market and cause larger trading volumes. Periodic Reports and Issued Capital could contain either good or bad news, but the trading volumes are driven by bad news. The results also reveal that company size is an important factor. Large companies tend to have relatively small market responses after information is released, which confirms that the larger companies are more stable. This study also evaluates long-term market effects of corporate disclosures by examining the timeliness of price discovery (also known as the speed of price discovery). It is the timeliness with which the full value relevant information is priced over a year before the annual earnings announcement is released. Previous literature has revealed that earnings announcements convey information, because significant stock returns or increased trading volumes are observed around the time that earnings announcements are released. However, it has also been suggested that there are other more timely information sources available that contain essentially similar or even the same value-relevant information. By the time preliminary final reports become available to the market, any potential value-relevant information has been included in the share price. The CDR again provides an attractive environment to examine the impact of corporate disclosures on the timeliness of price discovery, because listed companies have to disclose to the market before any other media sources. This enables an exploration of the relationship between the timeliness and the frequency of continuous disclosures. If the CDR is efficient in keeping investors fully informed, there should be no stock price surprise after the earnings announcement is released. Given the importance of the Preliminary Final Reports to the timeliness metric and the fact that the immediate market reaction tests only cover announcements released during trading hours, this study investigates in depth the Preliminary Final Reports and finds some evidence that companies tend to release bad news after the market closes and/or on Fridays. In terms of the impacts of announcement frequency on the timeliness of price discovery, following the step ‘All announcements – Periodic/Non-periodic announcements – Detailed categories of Non-periodic announcements’, the findings reveal that only earnings-related and cash flow announcements (Periodic Reports, Distribution Announcements and Quarterly Cash Flow Reports) can accelerate the timeliness of price discovery. Unfortunately, the results do not confirm that more announcements on the market could promote the timeliness with which the value-relevant (i.e. earning/income) information is incorporated into share prices. In addition to announcement frequency influences, the price discovery process is faster for companies with better share performance, are larger or have greater profitability. Financial companies have a timelier price discovery process than other companies; the price discovery process of financial companies was affected more by the 2008 – 2010 Global Financial Crisis than that of other companies. This study contributes to the market reaction literature by covering all categories of company announcements and comparing immediate market consequences for each type of announcement, and builds upon the timeliness of the price discovery literature by linking the announcement frequency of each continuous disclosure category to the timeliness with which annual earnings information is incorporated into share prices.
Keywords: Announcement categories; Announcement frequency; Continuous Disclosure Regime; Immediate market reactions; Market sensitivity; Timeliness of price discovery

Location data and human mobility : an evaluation of a dissonance that frames data protection and privacy rights - Andrew, Jonathan (European University Institute, 2018)
With citizens’ movements mediated by many technologies that aid our navigation the potential for omnipresent surveillance may potentially institute fundamental changes to the human condition. Locational privacy is pivotal in developing inter-personal associations and relational ties with others and its function is therefore complex, rather than solely affording a degree of independence from the observations made by others. In this respect, a more nuanced understanding of the utility of location data is required; the current hierarchy that delineates personal data from special categories of personal data does not adequately appreciate the capacity for location data to act as a proxy for other sensitive personal data. Furthermore, the binary distinction that reflects the conceptualisation of the right to privacy as a negative right, with related concepts such as identity and personality formation viewed as positive constructs, is increasingly difficult a notion to preserve. The classification and terminology of technologies can illustrate how terms and legal metaphors are developed and applied so as to bridge gaps in applying existing context and precedent. Though the designation ‘location data’ once constituted a reasonable accommodation in nomenclature as an intelligible and easily comprehensible term, even while constituting a significant oversimplification of the data it represented, technological advances have rendered the term increasingly problematic. This study asks whether the existing legal framework at the regional level in Europe is apt to provide sufficiently cogent and coherent regulation given recent developments in technologies. The review analyses the risks associated with this predilection in data processing activities that allows for the identification of ever more intimate and nuanced details of a citizen’s life, behaviours and convictions through the analysis of their location data; in turn, it shall discern the necessity of considering the resulting impacts on citizens’ fundamental rights to privacy and personal data protection.
Accepted: 2018-02-16T08:28:25Z
Keywords: Data Protection; European Union countries; Location data; Privacy

International norm conflicts through the lens of Alexy's principles theory - Böök, Birte (European University Institute, 2018)
The likelihood of clashes between international norms has increased in correlation with the upsurge in the number of specialised regimes emerging within the international legal field. The present thesis takes a closer look at the different ways in which such norm conflicts can be addressed at the international level. In particular, it distinguishes between conflict resolution based on establishing priority by means of traditional maxims, and resolution based on the weighing of clashing norms to determine which prevails in the case at hand. To do so, the thesis takes a step back from the existing literature and examines the distinction within norms between rules and principles, relying predominantly on Robert Alexy’s theory on this subject. Taking a legal-theoretical approach to the subject of international norm conflicts, this thesis shows that Alexy’s principles theory is not only transferrable to international law in theory, but that we can, moreover, identify international norms as rules and principles respectively. Distinguishing between the different ways in which conflicts are resolved depending on whether the norms involved are rules or principles, it is shown that while both approaches are susceptible to certain conceptual uncertainties and pitfalls, this dichotomy nevertheless plays an important role in the efficiency of the international legal system, ensuring that a certain balance between stability and flexibility is maintained. Ultimately, it is demonstrated that by viewing international law, and international norm conflicts in particular, through the lens of Alexy’s principles theory, we can gain a clearer understanding of the structure and application of international norms on the one hand and, as a result, how to resolve international norm conflicts on the other. Thus, drawing a distinction between rules and principles among international legal norms can be a means by which scholars (as well as judicial bodies or even states) may analyse ambiguous judicial decisions or international legal provisions, and can thus foster greater clarity in the field of international law.
Accepted: 2018-11-28T14:26:22Z
Keywords: Dispute Resolution; International Law

Finding innovative solutions to extend labour law and social protection to vulnerable workers in the informal economy - Fourie, E. (North-West University, 2018)
The world of work has changed and this includes its fundamental design, purpose and coverage of employment. Work in the informal economy has increased and in many developing and middle income countries, work in the informal economy is the norm. In South Africa as well as in other developing countries informal economy workers do not enjoy sufficient protection in terms of labour and social protection measures. These workers are not recognised, regulated or protected by labour legislation or social protection measures and can be characterised by varying degrees of dependency and vulnerability. In countries where the informal economy is increasingly creating a parallel economic world to that of the formal economy, the extension of protection by facilitating the ability of these workers to bargain collectively and the role of national and local governments become increasingly important. Women workers in the informal economy are particularly vulnerable and face discrimination on multiple grounds and levels as gender inequalities in the informal economy cut across race and class lines. Linkages between informality, gender and poverty exists, namely: the poor are more likely to work in the informal economy; more poor women than non-poor women work in the informal economy and that there is a gender gap in earnings in the informal economy as women were earning less than their male counterparts and were less likely to be organised and have social protection. It is of the utmost importance that labour and social legislation accommodates and extends protection to informal economy workers. The larger the informal economy becomes, the greater the need becomes for social and labour protection. It will be impossible to provide these workers with the protection they deserve without legislative intervention. Furthermore, this intervention must be innovative and tailor-made to successfully extend labour and social protection to informal economy workers. When considering the protection of these workers it is also of importance to explore the design and implementation of innovative and tailor-made solutions, considering for example the nature of their work and their workplace. The focus of this study is specifically on distinctive vulnerable categories of women workers in the informal economy who are without adequate labour and social protection. These categories are domestic workers, informal traders and waste pickers. It is important to consider lessons learnt in other jurisdictions to adequately address the challenges in the informal economy. This study considers interventions in two leading developing jurisdictions, namely India and Brazil. Both these countries have a high prevalence of informal workers with inadequate labour and social protection. Labour law must thus meet the challenges posed by the realities of new forms of work. The important function of labour law to protect and promote the human dignity of workers will often result in a cross-over of various subsystems of the law. If we consider human dignity as an important component of labour law, then we need to consider an interdisciplinary approach and the promotion of such an approach. This approach will mean that labour law can no longer function in isolation and other branches of the law, such as social security law, corporate law, human rights and family law will increasingly have an impact on the human dignity of workers. When considering the future of labour law and specifically in relation to the labour and social protection of women in the informal economy, it is vital that the new framework is intrinsically linked to concepts such as democracy, social justice, freedom, and human rights. International and regional institutions are playing an increasingly important role in the empowerment of women, the promotion of equality and decent work for all women. This study identifies and critically considers the relevant international institutions and instruments, the impact of international standards, regional institutions and regional labour standards, particularly those of the African Union (AU) and the Southern Africa Development Community (SADC), and other global initiatives directed at the social and labour protection of women workers in the informal economy. The South African position with reference to domestic workers appears to provide an adequate regulatory framework in respect of the regulation of these workers; however, in practice there are various challenges, including the enforcement of the legislative provisions and a disregard for the notion of substantive equality. Although domestic workers enjoy some protection, waste pickers and informal traders as own-account workers without a distinctive employee-employer relationship are excluded from most labour and social protection measures and innovative and tailor-made solutions are required. The regulation of waste pickers and informal traders in South Africa is fragmented and lacks comprehensive and uniform legislation is absent. Voice and representation is of paramount importance to these women to ensure decent work. Enabling frameworks must be established to promote this. One of the most important objectives of organisation for women workers is to promote the recognition of these women and given their vulnerabilities experienced on various levels, this recognition must be wide and include recognition as workers, citizens and members of society that must be afforded human dignity on all levels. The position of the three categories of women workers was also considered in two jurisdictions, namely India and Brazil to distil best practices with reference to these workers. The research question of this study is: How can labour law and social protection measures provide vulnerable women workers in the informal economy with the appropriate protection to ultimately give effect to decent work? The main inquiry of this thesis, therefore, is to explore the issue of extending labour and social protection to these workers through the extension of existing labour and social security rights; including, where necessary, the design and implementation of innovative and tailor-made solutions.
Keywords: Decent work; Discrimination; Domestic worker; Gender equality; Informal economy; Informal trader; Labour and social protection; Social assistance; Social justice; Social security; Tailor made provisions; Waste pickers; Women; Worker organisations

Justification for the recognition of a new nominate contract based on project defect management - Greeff, Tanya Nicole (University of Pretoria, 2018)
This research sought to establish whether the general acceptance that the common construction and engineering contracts as falling within the classification of the locatio conductio under South African law is correct. As the classification of a contract attracts specific essentialia and naturalia, and then too certain implied terms one example of an implied term that would have practical relevance is specifically investigated: The warranty against latent defects. Through this example I seek to demonstrate the relevance and importance of establishing what the classification of these contracts is, and its ensuing essentialia and naturalia. The investigation commenced by firstly considering the classification of the common building, construction and engineering contracts, with reference to the South African publications of JBCC and GCC, as well as the internationally published FIDIC Silver Book, FIDIC Yellow Book, and FIDIC Red Book, as well as the NEC ECC Option A and Option B. With alternate dispute resolution mechanisms, such as adjudication and arbitration, resulting in limited publications by way of case law and academic writing on the subject (specifically in South Africa), English law and German law were also consulted. It was established that, unfortunately, the classification of the common building, construction and engineering contracts under South African law is problematic: It does not fit the ordinary and previously accepted classifications, specifically that of the locatio conductio. This makes it questionable whether the warranty against latent defects could be, and should be, implied into any one of these contracts. The recommendation, accordingly, is that it is crucial for the construction and engineering industry to carefully consider and develop the true and relevant essentialia and naturalia applicable to these contracts. Only then will there be certainly as to what may be implied into these contracts, and what will not so be implied. Until this is achieved, the parties to these contracts, in order to have certainty, must deal with aspects such as the warranty against latent defects by way of an explicit written term in the particular contract.
URI: https://repository.up.ac.za/handle/2263/70102
Keywords: Contract; Locatio conductio

The fairness of forfeiture clauses in short-term insurance contracts - Huneberg, Samantha (University of Johannesburg, 2018)
Insurance fraud is a major issue in the insurance industry. Insurance companies around the world are all facing significant losses due to the prevalence of fraudulent claims. These fraudulent claims and subsequent losses suffered by insurers inevitably lead to a dilution of the insurance pool and result in other policyholders bearing the brunt of these losses. The inevitable solution for insurers is to hike the premiums for all other policyholders in order to compensate for their losses caused by fraudulent claims. Insurance fraud is an international problem and it is common for insurers in most jurisdictions to use forfeiture clauses. These clauses aim to protect the insurer by stating that if the policyholder should submit any type pf fraudulent claim, the policyholder will forfeit the entire claim. There has been much controversy around the validity and fairness of these clauses. This thesis seeks to provide an overview of the prevalence of fraudulent insurance claims in South Africa, England, Australia and New Zealand. Moreover, it will consider the fairness of forfeiture clauses in light of the fundamental movement towards policyholder protection in recent years both in South Africa and in those jurisdictions that form part of the comparative study. The thesis concludes that forfeiture clauses form an indispensable part of short-term insurance contracts and are justifiable and therefore lawful. It is, however, submitted that insurance companies have a duty to disclose the nature and extent of forfeiture clauses at the inception of the policy and again at claim stage. By using so-called staggered disclosure, insurers provide policyholders with the opportunity to consider their claim and the means with which to prove it in order to avoid instituting a fraudulent claim. The thesis recommends that these rules pertaining to staggered disclosure should form part of the 2018 Policyholder Protection Rules, together with a statutory definition of insurance fraud.
Keywords: Forfeiture; Insurance policies; South Africa

A South African perspective on the meaning of "beneficial ownership" in Article 10 of the OECD Model Tax Convention on Income and Capital in the context of conduit company treaty shopping - Jansen van Rensburg, Enelia Cornelia (University of Pretoria, 2018)
The use of conduit company treaty shopping structures is often regarded as an impermissible erosion of a country’s tax base. For a developing country, such as South Africa, the protection of its tax base is an important policy consideration. Arguably, one way of combatting conduit company treaty shopping structures is by including in a country’s double taxation agreements the beneficial ownership requirement set out in Article 10(2) of the OECD MTC. The study examines how a South African court would interpret this requirement in provisions in South African double taxation agreements in the context of conduit company treaty shopping involving conduit companies receiving dividends. The study firstly considers whether the beneficial ownership requirement can be regarded as an anti-avoidance rule aimed at combatting conduit company treaty shopping falling outside agents and nominee scenarios. It further considers whether the term “beneficial owner” should have a legal or economic meaning. It explores the meanings given to this term by scholars and foreign courts and the OECD in its Commentaries to the OECD MTC. The study also considers the application of the rules of interpretation contained in the Vienna Convention on the Law of Treaties when giving meaning to this term. Lastly, the study considers whether the term should have the meaning assigned to it under the domestic law of a treaty country, or under international tax law. As part of this enquiry, the meanings of the expression “beneficial owner” in South African case law and legislation are explored.
https://repository.up.ac.za/handle/2263/65660
Keywords: Beneficial ownership; Conduit company treaty shopping; OECD; OECD Model Tax Convention; Société écran; South Africa

Modifying contract law principles to accommodate automated transactions in South Africa - Ramokanate, L. L. (North-West University, 2018)
Modern electronic commerce is chiefly characterised by the use of unattended computers in the negotiation and conclusion of agreements. Commonly referred to as "electronic agents," these computers assist their users to negotiate better and profitable deals in virtual marketplaces. In South Africa, the legal force and effect of automated transactions, i.e. agreements concluded by electronic agents, is addressed in section 20 of the Electronic Communications and Transactions Act 25 of 2002 (hereinafter referred to as the ECT Act). According to section 20 (a) of the ECT Act, a valid and enforceable agreement will be formed where an electronic agent performs an action required by law for agreement formation. The same statute provides further in section 20 (b) that a valid and enforceable agreement will be formed where all the parties to a transaction or either one of them uses an electronic agent. The overall effect of these provisions is that an agreement cannot be denied legal validity and enforceability on the ground that an electronic agent was used, whether by one or both parties, to conclude it. Likewise, an agreement cannot be denied legal validity and enforceability on the ground that no human being took part in its formation. Although the ECT Act provides as a general matter that automated transactions are valid and enforceable in South Africa, that statute does not, however, create new rules for the formation of such agreements. This is made clear in section 3, which provides, amongst others, that the ECT Act should not be interpreted to exclude the application of the common law of contract to electronic transactions. Therefore, as with traditional or non-automated agreements, automated transactions too must satisfy the individual requirements of a valid contract at common law. As a matter of fact, the common law theory of contract formation is predominantly based on the assumption that human volition will always play a pivotal role in the making, acceptance or rejection of offers. For that reason, this research proceeds on a strong hypothesis that common law rules and principles pertaining to the formation of agreements are either insufficient or inadequate to accommodate the validity of agreements concluded by computers without the immediate intervention of their users. Consequently, the aim of this research is to discuss how the rules and principles of the common law of contract can be modified or developed in order to accommodate, within the common law theory of contract formation, the statutory validity of automated transactions in South Africa. The discussion of this research is limited to five legal issues, namely the basis of contractual liability in automated transactions, the analysis of offer and acceptance in automated transactions, the time and place of contract formation in automated transactions, the incorporation of standard terms and conditions in automated transactions, and the treatment of mistakes and errors in automated transactions. These issues are discussed first with reference to South African law, primarily with the purpose of determining the extent to which relevant common law rules and principles provide adequate solutions to specific challenges posed by automated transactions. To the extent that relevant common law rules and principles do not provide adequate solutions to the challenges of automated transactions, recommendations are made in this research for their development or modification. As shall be demonstrated in the course of this work, in relation to some of the abovementioned legal issues, the development or modification of common law rules has been done by the ECT Act. These "statutory developments or modifications of the common law" are also discussed in this work, primarily with the aim of determining the extent to which they provide adequate solutions to specific challenges posed by automated transactions. To the extent that these statutory modifications of the common law do not provide adequate solutions to the challenges of automated transactions, recommendations are made in this work on how the relevant provisions of the ECT Act may be interpreted by courts of law or amended by Parliament in order to strengthen the response of that statute. The abovementioned legal issues are also discussed in this work with reference to US and UK law, primarily with the purpose of determining how the law addresses the challenges of automated transactions in these jurisdictions, and to draw valuable lessons for the development or modification of South African contract law.
Keywords: Automated transactions; Autonomous electronic agents; Contract formation; Contract law; Passive electronic agents

Strict product liability in South Africa : an analysis of the concept of "defect" and the statutory defences available to the supply chain - Tennant, Sarah-lynn (University of Pretoria, 2018)
Defective products cause harm to persons and property on a daily basis. Product Liability law has accordingly evolved as a specialised area of the law of delict which seeks to prevent product accidents from happening and provides compensation in the event that defective products nevertheless reach the consumer market. Accordingly product liability regimes generally have both ex ante components such as product standards, recall mechanisms and liability provisions which are aimed at deterrence and risk-spreading as well as provisions that are applied ex post to provide redress and compensation. Designing an appropriate legal framework to underpin a product liability regime is a daunting task that involves achieving of an appropriate balance between the interests of various parties inter alia those of consumers, suppliers and the broader community. In recent decades many countries have migrated from a fault-based product liability regime to a regime which purportedly imposes strict liability on the whole supply chain. This bold move in modern product liability was pioneered in the United States who has since returned to fault-based liability for design and warning defects whilst returning strict liability in respect of manufacturing defects. After many years South Africa has joined the group of countries that applies strict liability to all defects regardless of their type. Notably the product liability regime introduced into South African law by means of the Consumer Protection Act 68 of 2008 (“CPA”) resembles the main features of the EU Product Liability Directive 85/374/EEC. The EU Model has also been taken over by Australia when they transitioned to a purportedly strict product regime in 1992. During this process the thesis also considers whether, by adopting the European model, South Africa has taken over a model which has been criticised by some American authors as outdated and based on 1965 strict product liability rhetoric as contained in section 402A of the Restatement (Second) of Torts which approach has since been discarded in the US in favour of the hybrid approach contained in the US Restatement (Third): Product Liability. This thesis focuses on product liability ex delicto. Its main aim is to interrogate and evaluate the product liability provisions contained in section 61 of the CPA, specifically with regard to the pivotal concept of defect and the statutory defences the Act has introduced. It details South Africa’s journey from the fault-based common law of product liability to the purportedly strict regime espoused by the CPA, which regimes operate parallel to each other. This is done to facilitate an understanding of the differences between the two regimes and specifically to aid interpretation and application of the product liability provisions in the CPA that deal with defectiveness and the new statutory defences. In order to obtain further guidance on how the concept of “defect” and the statutory defences in the CPA should, or could, be interpreted and applied the thesis initially considers the general foundational principles underlying product liability law and how this area of law has evolved in the United States, being the origin of modern product liability law. However, given that the South African regime of “strict” product liability ex delicto has its roots in the EU Directive and resembles some of the adapted features of the Australian product liability regime contained in the comprehensive Australian Consumer Law, the main comparative focus is on these two jurisdictions.
URI: https://repository.up.ac.za/handle/2263/70768
Keywords: Defective product; Product liability; South Africa; Supply chain

Ex Aequo et Bono as a Response to the ‘Over-Judicialisation’ of International Commercial Arbitration - Teramura, Nobumichi (UNSW Sydney, 2018)
Ex aequo et bono is a long-lived legal concept that enables arbitrators to decide a dispute based on notions of fairness instead of a strict application of legal norms. Jurists generally agree that arbitrators authorised to decide commercial disputes ex aequo et bono can more easily tailor arbitral procedure to achieve an efficient and fair dispute resolution process. They therefore agree that ex aequo et bono arbitration maximises procedural flexibility. However, this flexibility is now perceived more as a negative rather than a positive, despite the potential of ex aequo et bono to mitigate growing concerns about the ‘over-judicialisation’ of arbitration – the increasing formalisation and inefficiency of arbitral procedure. Commentators usually assert that ex aequo et bono introduces excessive unpredictability into arbitration and encourages arbitrators to abuse their discretion. As a result, ex aequo et bono has remained unpopular to this day. This thesis challenges this overly negative conception of ex aequo et bono. It does so particularly under the UNCITRAL Model Law, as an important foundation stone of the global commercial arbitration regime. The thesis investigates significant divergence in the understanding of ex aequo et bono across state jurisdictions and international arbitration institutions. It also analyses the core trends in actual legal practice and in thinking about the principle. The thesis thereby demonstrates that the Model Law requires arbitrators to ensure that their arbitral awards are based on three objective elements: contract terms, trade usages, and mandatory rules of law. Accordingly, while the Model Law allows arbitrators deciding ex aequo et bono to invoke their subjective conceptions of fairness as the ultimate gap-filler when discerning the intention of the parties, the scope for doing so is not unduly expansive. Further, the refinement of various legal theories underpinning international commercial arbitration has enabled parties to determine and challenge more readily the arbitrators’ subjective ideas of fairness. The thesis therefore concludes that the flexibility inherent in ex aequo et bono needs to be both re-evaluated and rejuvenated. It urges the international arbitration community to adopt a revitalised conception of ex aequo et bono to counter-balance the encroaching ‘over-judicialisation’ of arbitration.
Keywords: AI; Amiable composition; Arbitrage; Arbitragem; Arbitration; Arbitration theory; Artificial Intelligence; Blockchain; Cryptocurrency; Ex aequo et bono; Inteligência artificial; Intelligence Artificielle; International commercial arbitration; Trade usages; UNCITRAL Model Law

Aspects of the taxation of company distributions in South Africa - Tredoux, Liezel Gaynor (University of Johannesburg, 2018)
As a company distribution is a means by which wealth is transferred, it is a fertile ground for tax law reform to broaden the tax base and protect South Africa against base erosion and profit shifting. The South African government has identified the corporate tax structure, and many specific corporate tax rules, as areas in South African law in need of reform, and through which the policy objectives of stimulating foreign direct investment, promoting economic growth, and creating more employment opportunities can be achieved. This study involves an analysis on two levels: the corporate tax structure; and the specific tax legislation governing company distributions in South Africa. These aspects are contrasted with comparable rules in Australia and Canada. The study also evaluates the extent to which these laws conform to the normative values of equity, efficiency, certainty, and transparency, with the aim of suggesting improvements to promote South Africa’s current policy objectives. There are a variety of design models for a corporate tax structure. In the context of distributions, the ideal design should resolve whether tax should be paid on profit earned by a company, and also be levied on a second level, on distributions made to the company’s shareholders. Certain jurisdictions merge these two levels of tax to create a single taxable event which avoids the economic double taxation of income. There is, however, no dominant or universal model and several solutions can be mooted. Australia follows an imputation system which taxes corporate income at the first level of tax but grants a tax credit to shareholders on distribution, which means this income is taxed only once. Canada applies a hybrid integration system which also combines the two levels of tax and grants a tax credit to certain individual shareholders on distribution. However, the principles applied in these two models differ. The South African corporate tax structure is a hybrid, dual-rate system in terms of which different rates apply to corporate income and distributions to shareholders. All three systems offer relief for taxpayers which partially eliminates double taxation, with Australia having eliminated it fully for resident shareholders. In broad terms, a company distribution can be made by a company to its shareholders through either a return on capital or a return of capital. The policy approach adopted by the South African government is that all net accretions of wealth by the taxpayer should be taxable. Despite government’s intentions, there is a significant difference in the taxation rules applied to returns of an income nature (dividends and income), on the one hand, and returns of a capital nature (returns of capital, distribution of assets in specie) on the other. In addition, the net accretion of wealth is not always taxable on distribution to shareholders. In most instances the tax liability in respect of the return of capital is either deferred, or alternative rules are created which deviate from the principles and immediate tax liability that apply to returns on capital (dividends and income). In certain instances this deviation is justified, but in others it could lead to inequity between taxpayers and a narrowing of the tax base – both undesirable effects. A number of proposals are made to improve the law applicable to the taxation of company distributions as regards specific transactions. These are aimed, principally, at protecting the South African tax base against base erosion and profit shifting, and aligning South Africa’s tax law with international trends. The study finds that through the application of its hybrid dual-rate corporate tax system, South Africa has reduced economic double taxation to some extent, and that it is unnecessary for South Africa to integrate company- and shareholder-level tax. In addition, a variety of changes are suggested to improve the tax legislation applicable to specific company distributions, and to promote equity, certainty, and revenue collection. The South African tax legislation regulating company distributions is, in the main, fit for purpose, although there is room for improvement when it comes to simplicity, structure, and certainty.
Keywords: Company distributions; Contributed tax capital; Corporate tax; Dividend reinvestment plans; Dividends tax; Economic double taxation; Taxation

Shareholders' claims for reflective loss in international investment arbitration - the rule and its demystification - Vanhonnaeker, Lukas (McGill University, 2018)
In recent years, investor-State tribunals have often permitted shareholders' claims for reflective loss despite the well-established principle of no reflective loss applied consistently in domestic regimes and in other fields of international law. Investment tribunals have justified their decisions by relying on definitions of "investment" in investment agreements that often include "shares", while the no-reflective-loss principle is generally justified on the basis of policy considerations pertaining to the preservation of the efficiency of the adjudicatory process and to the protection of other stakeholders, such as creditors. Although these policy considerations militating for the prohibition of shareholders' claims for reflective loss also apply in investor-State arbitration, they are curable in that context and must be balanced with policy considerations specific to the field of international investment law that weigh in favor of such claims: the protection of foreign investors in order to promote trade and investment liberalization.
https://escholarship.mcgill.ca/concern/theses/s1784p10r
Keywords: Arbitrage; Arbitragem; Arbitration; International Arbitration; International Investment Arbitration; Investments; Reflective loss; Shareholder claims

Contractual renegotiations and International investment arbitration : a relational contract theory interpretation of investment treaties - Florou, Aikaterini (Institut d'études politiques, 2017)
The relationship between international investment treaties and the underlying contracts remains a highly disputed matter in international investment law. This thesis explored the contract-treaty interaction by using the renegotiation of regulatory contracts in the sector of energy infrastructure as a natural experiment, with a particular emphasis on the arbitral disputes that arose from the Argentine crisis. It deployed to this end an original analytical framework drawing from transaction cost economics and relational contract theory. The result of the novel combination of these two analytical frameworks is the construction of an interpretative methodology that takes an integrated approach to the two instruments – the contract and the overarching treaty – in a way that achieves a more sustainable balance between the competing public and private interests. In particular, the thesis rests on three arguments: the first is the relational-contract nature of dynamic treaty standards, which require the long-term cooperation of the parties. The second is the status of these vague standards as default rules complemented by the provisions of the underlying contracts, which are also relational, and act as gap-fillers. The last, normative argument is that the relationship between these (default) treaty rules and the (gap-filling) contractual provisions should be determined by transaction cost economics, and specifically the goal of economizing on the transaction costs of bounded rationality and opportunism when and interpreting relational treaty standards. La relation entre les traites internationaux d’investissement et les contrats sous-jacents reste un sujet très contentieux dans le domaine du droit international de l’investissement. Cette thèse explore l’interaction entre le contrat et le traité en utilisant la renégociation des contrats règlementaires dans le secteur de l’infrastructure énergétique comme un exemple d’ « expérience naturelle », en se focalisant en particulier sur les litiges arbitraux découlant de la crise économique en Argentine. A cette fin, un cadre analytique original, s’inspirant de l’économie des coûts de transaction et la théorie du contrat relationnel. Le résultat de la combinaison originelle de ces deux cadres analytiques est la construction d’une méthodologie interprétative proposant une approche d’intégration entre les deux instruments – le contrat et le traité – d’une manière apportant plus d’équilibre entre les intérêts publics et privés souvent opposés. La thèse est fondée en particulier sur trois arguments : le premier est la nature des standards dynamiques des traités comme contrats relationnels exigeant la coopération des parties à long terme. Le deuxième est le statut de ces standards vagues comme règles par défaut, complémentés par les provisions des contrats sous-jacents, qui sont aussi relationnels et fonctionnent comme « gap fillers ». Le dernier argument, normatif, est que la relation entre ces règles (par défaut) des traites et les provisions contractuels doit être déterminée par l’économie des coûts de transaction, et en particulier le but d’économiser les coûts de transaction découlant de la rationalité limitée et l’opportunisme durant l’interprétation des standards relationnels des traités.
Keywords: Arbitrage commercial international; Contrats internationaux; Economie des coûts de transaction; Interprétation des traités; Relational contract theory; Théorie du contrat relationnel; Transaction cost economics; Treaty interpretation

Essays on Bank risk, capital and Lending - Alraheb, Tammuz (Université de Limoges, 2017)
Cette thèse examine trois questions importantes dans le secteur bancaire, à savoir le risque, les fonds propres et le crédit. Elle comprend trois essais empiriques. Le premier chapitre analyse l'impact du «printemps arabe» et de la crise financière mondiale de 2007-2008 sur la stabilité du secteur bancaire dans la région MENA. Les résultats montrent que le «printemps arabe» n'a pas eu d'effet négatif sur la stabilité des banques, alors que la crise financière mondiale a considérablement réduit leur stabilité. Le deuxième chapitre étudie le rôle joué par l'environnement institutionnel dans la mise en place de coussin de fonds propres par les régulateurs ou par les banques en interne. D’après les résultats, pour que les ratios de capital réglementaire soient efficaces, l'environnement institutionnel ne doit pas être négligé lors de la mise en place de ces ratios. Le troisième chapitre étudie les différents effets des droits des consommateurs et des créanciers sur le coût des prêts. Les résultats révèlent que le coût des prêts augmente en présence de lois strictes sur la protection des consommateurs, tandis que l'augmentation des droits des créanciers réduit ce coût.
Keywords: Bank Capital Structure; Bank foreign expansion; Bank loan growth; Banque expansion à l'étranger; Banques; Consommateur (protection); Cost of intermediation; Coût de l'intermédiation; Creditors' rights; Crise économique (2008); Croissance du crédit bancaire; Droits des créanciers; Structure du capital de la Banque

The Seller's right to cure under article 48 United Nations Convention on contracts for the international sale of goods - Mirambell i Fargas, Miquel (Universitat Pompeu Fabra, 2017)
In principle, contracts are enforceable mutually beneficial agreements. In the event of a breach of contract, many national, supranational, and international legal systems—as well as recent European harmonization projects on private law—turn to cure regimes for the furtherance of such (assumed) contractually generated welfare. Namely, a mandatory Nachfrist-mechanism, a hierarchy of remedies, and debtor’s (in sales law: seller’s) rights to cure—before and after performance date—are normative devices intended to perform and preserve contracts, employing purportedly better, more cost-effective remedies for breach. Discussion of the utility of these legal institutions undisputedly belongs to the debate on modern contract law. In this thesis, one of these cure-oriented devices is exhaustively analyzed: the seller’s right to cure after performance date under Article 48 CISG1. Whereas according to paragraph (1) the seller—provided that certain preconditions are met—can impose subsequent performance on the aggrieved buyer, under paragraphs (2-4) they can merely offer cure within a period of time, irrespective of any preconditions. Article 48 CISG’s systematic setting, comparative law framework, origin, forerunners, preconditions for existence—general and specific—performance in practice, legal consequences—with regards to both the breach-of-contract regime and the availability of other remedies under the CISG—, and economic-behavioural implications are exegetically analysed. A particular focus is given to the allocation of contractual risk (see epigraph 3.2.9). Finally, conclusions are drawn at two levels: one concerning the CISG’s regime and another related to general Contract law. En principio, los contratos son acuerdos ejecutables mutuamente beneficiosos. En caso de incumplimiento del contrato, muchos sistemas jurídicos nacionales, supranacionales e internacionales—así como los recientes proyectos europeos de armonización en derecho privado—recurren a regímenes de subsanación para promover el bienestar que presumiblemente se ha generado con el contrato. A saber, un mecanismo de un Nachfrist obligatorio, una jerarquía de remedios y derechos del deudor (en compraventa: del vendedor) de subsanar—antes y después de la fecha de cumplimiento—son instrumentos normativos destinados a dar cumplimiento a los contratos y a preservarlos por medio de remedios, a priori, económicamente más eficientes. La discusión sobre la bondad y utilidad de estas instituciones indudablemente pertenece al planteamiento de un derecho de contratos moderno. En esta tesis se analiza exhaustivamente uno de estos instrumentos de subsanación: el derecho del vendedor a subsanar después de la fecha de entrega en virtud del artículo 48 CISG2. Mientras que de acuerdo con su párrafo (1) el vendedor –reuniendo ciertas condiciones previas– puede imponer una ulterior ejecución al comprador perjudicado; en virtud de los párrafos (2-4), éste solamente puede ofrecer una subsanación dentro de un plazo, pero independientemente de cualquier condición previa. Del citado artículo 48 se analizan exegéticamente el entorno sistemático, el marco en derecho comparado, el origen, los precursores, las condiciones previas para la existencia—generales y específicas—, su ejecución en la práctica, las consecuencias jurídicas—en el régimen del incumplimiento del contrato y en la disponibilidad de otros remedios bajo la Convención—así como las implicaciones económicas y conductuales. Se hace una contribución en relación con la asignación del riesgo contractual (véase infra 3.2.9). Finalmente, se extraen conclusiones a dos niveles: uno enfocado al régimen de la Convención y otro relativo al Derecho de contratos en general.
URI: https://www.tdx.cat/handle/10803/404845
Keywords: Artículo 48 CISG2; CISG; Derecho del vendedor; Seller's right

Conflict of treaty-norms in investment arbitration - Atanasova, Dafina (Université de Genève, 2017)
The study analyses the process through which investment arbitral tribunals identify and resolve conflicts between investment standards of protection and norms from other international regimes relevant for the merits of the dispute. It questions the validity behind the current approach that tribunals adopt, under which arguments based on extraneous norms are overwhelmingly unsuccessful and proposes its' transformation in three respects. First, rather than being a mere means of interpretation, as in current practice, a broader pool of international norms must be applied to the substance of investment disputes. Second, the concept of normative conflict must be broadened if one is to address the actual challenges that inter-regime conflicts pose for international law. Third, fleshing out the modalities under which one could use private international law as a source of inspiration in public international law context, the study offers best practices for approaching the types of conflict commonly found in investment disputes.
Keywords: Arbitrage; Arbitrage d'investissements; Arbitragem; Arbitration; Diversification; Droit international; Droit international privé; Fragmentation; International courts and tribunals; International law; Investissements; Investment arbitration; Investments; Private international law

Regional trade integration and co-operation in Southern Africa : the case of the Southern African Development Community (SADC) - Mathebe, Mpubane Mox (University of South Africa, 2017)
Mercantile Law
Keywords: Economic integration; Foreign economic relations; Foreign trade regulation; Free Trade; Monetary unions; SADC; Southern African Development Community

The regulation of unsolicited electronic communications (SPAM) in South Africa : a comparative study - Tladi, Sebolawe Erna Mokowadi (University of South Africa, 2017)
The practice of spamming (sending unsolicited electronic communications) has been dubbed “the scourge of the 21st century” affecting different stakeholders. This practice is also credited for not only disrupting electronic communications but also, it overloads electronic systems and creates unnecessary costs for those affected than the ones responsible for sending such communications. In trying to address this issue nations have implemented anti-spam laws to combat the scourge. South Africa not lagging behind, has put in place anti-spam provisions to deal with the scourge. The anti-spam provisions are scattered in pieces of legislation dealing with diverse issues including: consumer protection; direct marketing; credit laws; and electronic transactions and communications. In addition to these provisions, an Amendment Bill to one of these laws and two Bills covering cybercrimes and cyber-security issues have been published. In this thesis, a question is asked on whether the current fragmented anti-spam provisions are adequate in protecting consumers. Whether the overlaps between these pieces of legislation are competent to deal with the ever increasing threats on electronic communications at large. Finally, the question as to whether a multi-faceted approach, which includes a Model Law on spam would be a suitable starting point setting out requirements for the sending of unsolicited electronic communications can be sufficient in protecting consumers. And as spam is not only a national but also a global problem, South Africa needs to look at the option of entering into mutual agreements with other countries and organisations in order to combat spam at a global level.
Keywords: Anti-spam laws; Commercial electronic messages; Consumer law; Direct marketing; Electronic commerce; Electronic communications; Electronic mail (e-mail); International cooperation; Right of privacy; Spam (Electronic mail); Telemarketing; Unsolicited commercial communications; Unsolicited electronic communications

A critical appraisal of secured transactions over personal property in Nigeria: legal problems and a proposal for reform - Otabor-Olubor, Iyare (Nottingham Trent University, 2017)
The thesis contemplates the need for Nigerian policy makers to undertake a reform of secured transactions law to meet international best standards, building upon earlier, unsuccessful, efforts by lawmakers, and drawing upon international benchmarks. It critically analyses the Registration of Security Interests in Movable Property by Banks and Other Financial Institutions in Nigeria (Regulation No.1 2015) 'CBNR' published on 2 February 2015. The CBNR, with a primary aim of facilitating affordable credit, and to modernise secured transactions law through the use of personal property as collateral, has departed from its previous position which it inherited from England. This thesis has drawn comparisons between the CBNR and prior reform initiatives particularly the Draft Law 2009 prepared by the Centre for the Economic Analysis of Law (CEAL). These reforms, which were not implemented, recommended wholesale changes to harmonise all existing secured transactions law in Nigeria. The CBNR does not follow this approach, but instead, adopts a piecemeal approach to reform. Correspondingly, this forms the framework within which this study has been undertaken with reference to whether a piecemeal or wholesale reform is now required. This thesis has followed the International Finance Corporation (IFC) approach which focuses on a three-stage secured transactions reform strategy - modernisation of the existing legal framework; establishment of an electronic collateral registry; a concerted effort towards building capacity. With the assistance of international secured transactions legal frameworks such as the UNCITRAL Legislative Guide on Secured Transactions 2007, and its Registry Guide 2014, the CBNR has been benchmarked against these adaptable legal frameworks for the purpose of harmonising secured transactions law, in search of the international best practice which may be desirable for Nigeria. The thesis identifies and discusses at length several problems and inconsistencies associated with the CNBR, and the thesis makes suggestions for a wholesale reform of the Nigerian secured transactions law. This thesis builds on existing knowledge on secured transactions law reform with particular reference, and usefulness, to sub-Saharan African countries and other developing countries that wish to attempt a similar reform of this nature.
https://irep.ntu.ac.uk/id/eprint/31955/
Keywords: Nigeria; Secured transactions; Security interest; Sûretés mobilières

The impact of climate change law on the principle of state sovereignty over natural resources - Van Wyk, Sanita (Stellenbosch University, 2017)
This dissertation serves to expand the means within international law by which to address the global interdisciplinary crisis that is climate change. The principle of sovereignty over natural resources is identified as a principle of international law, evolutionary in nature, fundamentally connected to the international legal climate change regime, and able to be impacted by the effects of climate change. The gravity of climate change is illustrated, as is the intricacy and composition of the international legal climate change regime. In the process, a particular shortcoming of the international legal climate change regime is identified, namely the lack of state compliance with climate commitments made in terms of the Kyoto Protocol 1997 and the Paris Agreement 2015. The gravity of the effects of climate change warrants the repositioning of any principle of international law that is able to address this shortcoming of the international legal climate change regime and increase the effectiveness of the regime. In this regard it is determined, more specifically, that the gravity of the effects of climate change warrants a reinterpretation and reconfiguration of the principle of sovereignty over natural resources. Climate change, forming part of the general, growing, global concern for environmental conservation and sustainable development, influences the interpretation and configuration of state rights and state duties in terms of the principle by eliciting an interpretation that restricts state rights and expands state duties. Furthermore, the gravity of the effects of climate change on the well-being of people, warrants a reinterpretation and reconfiguration of the principle of sovereignty over natural resources as a people-oriented principle as opposed to the conventional state-oriented principle, and ought to be applied with due regard to the rights of people in terms of the principle. The right of people in terms of the principle of sovereignty over natural resources, is identified as the right to economic selfdetermination, which gives effect to the right of people to dispose freely of natural resources. Should this right be promoted in future applications of the principle of sovereignty over natural resources, the right may well be established as constituting a significant basis on which people are able to hold states accountable for climate commitments made in terms of the Kyoto Protocol 1997 and the Paris Agreement 2015. In this way, the principle of sovereignty over natural resources, specifically the implementation of the right of people to dispose freely of natural resources in terms of the principle, presents a negative incentive for state compliance with climate commitments and can contribute to addressing the lack of state compliance within the international legal climate change regime. In summary, this dissertation proposes that the grave effects of climate change warrant a repositioning of the principle of sovereignty over natural resources that allows it to constitute a contribution to climate change law and the global fight against climate change.
URI: http://hdl.handle.net/10019.1/101171
Keywords: Climatic changes; Convention on Climate Change 1997; Convention on Climate Change 2015; Environmental law; Kyoto Protocol; Natural resources; Paris Agreement 2015; Self-determination; Sovereignty; United Nations Framework

Financial Development, Integration and Access to Finance in Africa - Essien, Grace Etim (University of Leeds, 2017)
This thesis is made up of three empirical studies that fall under the general classification of international and financial economics, particularly the study focuses on the financial system of selected African countries. The first empirical study presented in Chapter 2 examines the role of financial development in improving the effect of FDI on the economic growth of some African countries. Investigations were conducted to pinpoint which financial structure could provide the best improvement by applying the bank-based vs. market-based debate. Results from the regression analysis conducted show that the effect of FDI on economic growth becomes significant only when financial development measures were factored in. Analysis of results indicate that development of the overall financial system of African countries would be more beneficial in comparison to developing either the banks or financial markets alone. Chapter 3 empirically measures the level of financial integration in Africa’s Regional Economic Communities (RECs) using beta and sigma convergence to measure the speed and degree of financial integration in four RECs. These chapter also theoretically examines how regional financial integration contributes to financial development and economic growth in Africa. Analysis of the results show that Africa’s RECs are integrating at a relatively slow and diverse rate. Therefore, policy makers in Africa would need to focus on reform strategies that would strengthen financial integration in their regions. A fully financially integrated system would contribute immensely to financial development and promote sustainable economic growth. The fourth chapter investigates the effect of access to finance on firms’ productivity. Using cross-sectional firm-level data to estimate the effect of access to finance on labor productivity, total factor productivity (TFP), and the stochastic frontier trans-log model. This study estimates an instrumental variable (GMM) model to address potential endogeneity bias between access to credit and firms’ productivity. The results obtained show that the lack of access to finance negatively affects the productivity of firms in Africa. This study suggests that the development of a balanced financial system should be of topmost priority to policy makers. This ensures that more finance is channelled towards those firms whose productivity depends heavily on the availability of finance irrespective of their characteristics. This would result in firms increasing their investments in productivity-enhancing activities, which would benefit long-term economic growth

The taxation of small business in developing countries - AKM, Atiqul Haque (Monash University, 2017)
The thesis attempts to explore an efficient policy and administrative framework to tax the small businesses in developing countries. In order to approach the policy and administrative problems concerning the taxation of small business in developing countries this thesis asks How can small businesses be efficiently taxed in developing countries? This thesis over eight chapters qualitatively explores this research question. The analyses conclude that first, in a typical developing country a well-designed simple to follow presumptive tax regime is more efficient than the actual account based tax system. Second, this thesis argues that the noncompliance of small businesses in developing countries may not be adequately explained by the standard expected utility based compliance models. The leading tax compliance models which mainly emphasise on the perceived reward from evasion might ignore some crucial factor that constitutes the tax compliance environment of small businesses in developing countries. This thesis illustrates broadly the typical tax compliance environment of small businesses. It argues that a simple to follow tax system that requires a minimal level of taxpayer compliance would attract a section of small taxpayers into the formal tax net. Third, this thesis demonstrates that there are crucial differences between typical urban and rural businesses. A small business tax regime should have a separate set of presumptive instruments for each class of small business in order to make an efficient estimate of their economic activities. Fourth, this thesis analytically examines the presumptive methods and their practical applications. The findings suggest that in developing countries presumptive tax methods have been adopted mostly in arbitrary manner, without the objective considerations to many crucial design issues. Fifth, this thesis has developed a focused analysis on the taxation of urban small businesses in the contexts of developing countries. This thesis analyses some crucial characteristics of urban small businesses and stresses that enterprise formalization should be a key element of urban small business tax policy. For a meaningful expansion of the tax net, tax administration should put more focus on urban small businesses as these businesses have relatively more potential to grow as more stable and sustained taxpayers. This thesis concludes that a turnover based presumptive taxation is more efficient to tax the urban small businesses. Lastly, this thesis explores the issues concerning the taxation of rural small businesses. This thesis reports that the overall tax burden on the agricultural income had substantially declined over the last few decades. Developing countries should not ignore the tax potential of the rural taxpayers. In a typical developing country an asset based presumptive tax system is more efficient to tax the agricultural income of the rural small businesses. This thesis has argued that it would be more efficient to adopt a single asset based presumptive income tax replacing all the prevailing taxes on the agricultural income such as agricultural land tax, wealth tax and income tax.
Keywords: Fiscal policy; Small business taxation; Taxation administration; Taxation in developing countries; Taxation law; Taxation of rural small business; Taxation of shadow economy; Taxation of urban small business; Taxation policy

Towards responsible lending in Namibian consumer credit law : a comparative investigation - Asheela, Ndatega Victoria (University of Pretoria, 2017)
The regulation of consumer credit in Namibia mainly is provided for by the Usury Act 73 of 1968 and the Credit Agreements Act 75 of 1980. These legislative enactments originated in South Africa and were applied in South West Africa during the period of South Africa’s mandate over what is now the Republic of Namibia. Despite the fact that these enactments are over 35 years old, they are substantially unchanged. In response to an awareness of the threat of consumer over-indebtedness and other events such as financial crises, the purpose in this thesis is to undertake a situational analysis of the debt prevention measures as provided for by the Namibian legislative framework and the extent of protection these measures afford consumers in terms of irresponsible credit and over-indebtedness. A broad survey of the policies aimed at promoting responsible lending benchmarks the Namibian consumer credit regulatory framework against the leading international best principles which have been developed in response to global economic challenges. The Namibia Financial Institutions Supervisory Authority in the 2014 Microlending Bill proposes to introduce responsible lending practices in the form of a compulsory pre-agreement assessment of the prospective consumer before providing them with credit. In a comparative investigation, the creditworthiness assessment and related measures central to the responsible lending regimes in South Africa and Australia are considered. Measuring the Namibian consumer credit regulatory framework against these recent developments, it is submitted that the current debt prevention measures are inadequate in protecting consumers from irresponsible credit lending and the risk of consumer over-indebtedness. This thesis supplies reasons for the need in Namibia to update the regulatory structure of the credit industry in order to protect consumers. As a contribution to the promotion of a culture of responsible lending in the Namibian consumer credit market, the thesis proposes the introduction of responsible lending measures in Namibia’s consumer credit legislative framework.
URI: https://repository.up.ac.za/handle/2263/65659
Keywords: Consumer credit; Debt; Namibia

The impact of threshold agreements on the organisational rights of minority trade unions - Esitang, Temogo Geoffrey (University of Pretoria, 2017)
The rights of freedom of association, to organise and to bargain collectively are recognised internationally and form part of the constitutional framework of progressive and democratic states. The full enjoyment of these rights by trade unions often is hindered by the imbalance in the power relations between the employer and the representatives of the workers, hence the need for statutory intervention. The Labour Relations Act 66 of 1995 (LRA of 1995) postulates a collective bargaining regime which is voluntarist in nature and strengthens its effectiveness through a set of organisational rights and the right to strike. Incidentally, the current statutory framework for the enjoyment of organisational rights has had a direct impact on the enjoyment of the right to freedom of association and the right to organise. It is accepted that possession of the right to collective bargaining is internationally recognised as the basis of the authority to set thresholds of representivity in the workplace. The organisational rights framework in this context has been directly impacted upon. It is this direct impact that necessitates an enquiry to determine whether South Africa’s framework on the acquisition of organisational rights conforms to international standards set by the ILO and the Constitution, 1996. This thesis argues that the policy choice of the South African labour relations system in respect of some of the consequences of majoritarianism insofar as representation in individual cases is concerned does not necessarily foster the ideals of the Constitution, 1996 and the principles of international labour standards. The model of democracy as envisaged in the Constitution, 1996 is not one that promotes exclusivity. However, the effect of section 18 of the LRA of 1995, which allows threshold agreements, arguably may foster such exclusivity in the workplace. This situation has resulted in industrial democracy being a terrain of endless conflict between employers and labour, even more among trade unions themselves. As a result, the rivalry between unions in workplaces is exacerbated. The original intent behind the organisational rights of trade unions and their right to strike was to bolster their capacity to bargain collectively. It was meant to get them to focus on collective bargaining gains they can secure and to bargain more effectively. However, the current framework that favours majority trade unions has the effect of minority trade unions generally finding their existence threatened and their being systematically excluded from the acquisition of organisational rights. This study questions the power of majority trade unions to enter a collective agreement with an employer in the workplace and set unjustifiable thresholds of representivity in respect of organisational rights. This arrangement creates a hurdle in respect of the provisions of the LRA that seek to promote industrial democracy, the enjoyment of the rights to freedom of association, to organise and to engage in collective bargaining. Recent amendments to the LRA of 1995 are an attempt to mitigate the effect of sections 18 and 20 on the enjoyment of organisational rights. The CCMA, inter alia, has been granted powers to grant organisational rights to trade unions that do not meet the set threshold in terms of the empowering provisions of the LRA of 1995 if they meet certain requirements. However, these amendments do not go far enough to prevent employers and majority trade unions from continuing to set unjustifiable thresholds that can have potential to replace the determinations of the CCMA. Therefore, the study discusses the question whether the provision in the LRA of 1995 on the setting of thresholds of representivity for the acquisition of organisational rights and the concomitant amendments are in line with the democratic model envisaged by the Constitution, 1996 and to international labour standards which recognise the rights to freedom of association of minority trade unions. This research concludes by advancing recommendations pertaining to threshold agreements and the rights of minority trade unions and to what extent it is justifiable to permit them to enjoy them.
URI: https://repository.up.ac.za/handle/2263/68000
Keywords: Collective bargaining; Employer; Employeur; Labour Relations Act; Representatives workers

An appraisal of selected tax-enforcement powers of the South African revenue service in the South African constitutional context - Fritz, Carika (University of Pretoria, 2017)
There is tension between the South African Revenue Service’s duty to collect taxes on the one hand, and its duty to respect taxpayers’ rights on the other. An environment where there is clearly respect for the rights of the taxpayer may indeed result in increased voluntary compliance. This thesis constitutes a comparative appraisal of whether the following enforcement powers of the South African Revenue Service (“SARS”) in the South African constitutional context, namely (i) SARS’ power to conduct searches and seizures in order to verify compliance and investigate the commission of offences; (ii) the “pay now, argue later” rule; and (iii) the appointment of a third party on behalf of a taxpayer are in accordance with the Constitution of the Republic of South Africa, 1996 (“Constitution”). It is argued that these powers do not necessarily conform to the Constitution’s values and the fundamental rights contained in the Bill of Rights in Chapter 2 of the Constitution. To address the apparent shortcomings in the current dispensation, the thesis compares these enforcement powers of SARS with similar powers afforded to the revenue authorities of Canada, Australia, New Zealand and Nigeria. Important conclusions are drawn from this comparative review and a number of recommendations for law reform are proposed which, if implemented, would align these enforcement powers with the provisions of the Constitution. The recommendations entail, inter alia, that the seizure component of a search and seizure process should be treated separately, that half of the payment obligation should be suspended until the dispute is heard by an impartial forum, and that an objective measure must be in place to ensure that a taxpayer is able to afford basic necessities when a third party appointment is made.
URI: https://repository.up.ac.za/handle/2263/62233
Keywords: Recouvrement fiscal; South Africa; Tax-enforcement power

Governing activities in outer space: responsibility, liability, regulation and the role of insurers - Harrington, Andrea (McGill University, 2017)
As we have seen from the numerous high profile launch failures and accidents that have occurred between 2014 and 2016, space activities are still ultra-hazardous in nature, despite sixty-plus years of technological development. These activities range from essential to modern life (ex., telecommunications) to futuristic and forward thinking (ex., space tourism). In order for these activities to not only continue, but also develop and grow, this inherent risk must be managed.Further complicating the risk dynamic in outer space, States are required to take liability and responsibility for the activities of their nationals in space, including private entities and individuals. The reality of this relationship is that while States wish to promote the development of their domestic space industries, they will also usually require certain levels of insurance and indemnification to protect the State against potentially costly mishaps.With regard to outer space, political will is lacking at an international level to create new binding rules for activities in space. Likewise, States are reluctant to unilaterally impose stricter (even if ultimately beneficial) regulations on their entities for fear that their domestic industries will flee abroad to greener pastures, creating a regulatory prisoner's dilemma. These factors create a scenario where the major space insurers responsible for writing policies across national boundaries may be uniquely positioned to enforce or at least promote mechanisms to increase safety and sustainability in the commercial space industry. Increasing safety and sustainability in outer space may help to keep premium costs from growing out of control for these hazardous activities, as well. Thus, this thesis addresses three fundamental questions: 1)From a legal and policy perspective, is there a regulatory void that needs to be filled, at least temporarily?2)Are insurance companies in a position to be able to fill or partially fill that void?3)If so, how, and what actions can they undertake to improve their ability to execute that governance function?In answering these questions, this manuscript-based thesis explores the existing body of space law and common practices in space activities, including notable lacunae, and applies theories of "insurance as governance." This approach permits both analysis of the existing status of the industry and recommendations to increase the viability of space activities moving forward.
Identifier: https://escholarship.mcgill.ca/concern/theses/hm50tv199
Keywords: Air and Space Law; Droit des assurances; Insurance law; Insurers; Liability insurance; Liability insurer; Responsability

China's legal obligations in the field of foreign investment : how trade agreements influence the formation of investment agreements? - Hua, Yuting (European University Institute, 2017)
Since deeper 'open-door' domestic reform in 1992, China has consistently maintained its position as the largest foreign direct investment (FDI) recipient among developing countries. In recent years China is going global as well. Accompanied with a large amount of outbound FDI, the level of debt is also increasing. Thus it is necessary for China to adopt a sustainable development policy and behave based on rules. China needs to work with the world to promote a rules-based investment climate. At a multilateral level, China joined the World Trade Organization (WTO) in 2001 and promised general and specific obligations on market entry and non-discrimination principles. Bilaterally, only after 2001, China has started negotiating preferential trade agreements (PTAs). The first part of the thesis analyses China’s legal obligations in investment agreements in pre- and post-WTO entry phases. Chapter 1 introduces China’s investment policy before 2001. Chapter 2 clarifies China’s commitments on non-discrimination principles under the WTO agreements, especially China’s Protocol of Accession. Chapter 3 compares Chinese BITs and PTAs with regard to investment principles. The second part of the thesis concerns interpretation on substantive and procedural provisions. Chapter 4 tries to answer the question of whether and how do tribunals consider jurisprudential concepts developed in the case law of the trade regime when resolving investment cases. Chapter 5 examines different remedies in trade and investment agreements. It is important for China to keep compliance with its commitments in international agreements, otherwise, it would face countermeasures which are highly costly. Also, China can implement competition rules in its domestic market for improving firms’ efficiency. Meanwhile, a balancing approach which emphasizes corporate social responsibility is equally important for China’s companies going global.
Keywords: Foreign investment; Foreign trade regulation; WTO; World Trade Organization

The African Union and the Development of African International Criminal Law - Kahombo, Balingene (Freien Universität Berlin, 2017)
This study is situated in the context of the regionalisation of international criminal law. It deals with the development of African international criminal law under the aegis of the African Union (AU). It aims to examine the factors which inform this development, the concept and the content of regional law so laid down for the African continent. The primary objective has been the exploration of theoretical and practical bases for the establishment of a viable system of African regional criminal justice in order to deal with crimes against peace and security in Africa, which put in danger African regional public order. The thesis also examines the relationship between African international criminal law and the global system of international criminal justice, currently dominated by the International Criminal Court (ICC) and the United Nations Security Council. The systemic analysis of these different issues have enabled to reach three main conclusions. First, the development of African international criminal law is not simply a conjectural consequence of the crisis observed within global international criminal law. It is also and chiefly the result of the policy of self-reliance of the AU and its member states aiming to protect and defend African regional public order through the recourse to regional institutions of criminal accountability. Second, the African Union is consequently promoting a system of African regional criminal justice based on three optional models of justice, namely the delegation of jurisdiction to a member state, the creation of hybrid courts with participation of regional judges and the establishment of a regional criminal court. Together with those crimes against peace and security that are of specific concern to the African continent, these models of justice form the core of the content of African international criminal law. However, the viability of the system towards delivering efficient justice remains problematic. There are numerous challenges to overcome, including ratifying the Malabo Protocol of June 2014 instituting the “Criminal Court of the African Union”, promoting judicial cooperation of African states and finding financial resources to support the Court’s actions. Third, African international criminal law is not a replacement of global international criminal law in the continent. There is rather a coexistence of norms and institutions which commands a certain degree of coordinated relationships to avoid competing actions and so inefficiency of justice. This thesis discusses two main approaches to consistent relationships between African regional criminal law and the global system of international criminal justice, namely the hierarchical model and the cooperative approach. It proposes a third alternative approach, that is, the regionalisation of the ICC in conjunction with the principle of regional territoriality.
Keywords: African Court of Justice and Human and Peoples' Rights; African Union; International Criminal Court; International Criminal Law; Regional Territoriality; Regionalisation; Universal Jurisdiction

Sustainable biofuel regulation and production in the SADC region : a comparative analysis - Kandala, Lupwana Jean Jacques (University of Johannesburg, 2017)
Keywords: Biofuel; Biomass energy; SADC

Trade, labour and sustainable development: an integrated perspective - Khan, Zobaida (McGill University, 2017)
Some contemporary challenges for global trade regulation and labour governance arise from the barriers between questions of law and social justice, and development policy and distributional issues. This thesis attempts to address some of these regulatory or governance challenges by exploring the interactions between sustainable development (SD), trade regulation, and social or distributive justice. Borrowing from multiple disciplines, i.e. law, international relations, and development economy, and focusing on the problems of low-income countries, this thesis examines the potential and importance of a broad ideational objective in introducing transformative changes in different regulatory or governance mechanisms. This thesis does not discuss ways to link trade regulation or labour governance with SD; rather here the possibilities of operationalizing SD, within the global trade regulatory site or transnational governance mechanisms, are explored from a capability perspective. It is argued that a capability-based understanding can resituate some questions on trade-SD interaction and introduce important behavioural changes in the functioning of the World Trade Organization (WTO). Yet, ongoing operationalization of capability-based SD requires effective market complementary interventions from governance mechanisms operating at different spaces and with diverse actors. Certain emerging transnational governance mechanisms, which connect broader social or distributional issues such as labour governance with trade opening or economic cooperation, attempt to provide crucial market complementary interventions. Taking examples from the recent transnational safety initiatives for Bangladeshi garment workers and relying on a broad conceptualization of the social or distributional issues, it is argued that attention to capability enhancement produces a much more compelling form of labour governance mechanism at these hybrid sites. With a focus on capability-based SD, a model of transformative linkage is proposed for effective labour governance. The model demands that fundamental and redistributive rights of labour are interconnected and appropriate labour governance requires a stronger form of corporate responsibility. Analyzing the interaction of diverse rules, governance processes and mechanisms, with the demands of marginalized forces the global hegemony of capital is juxtaposed with available options and possible alternatives.
https://escholarship.mcgill.ca/concern/theses/g158bk90k
Keywords: Corporate Social Responsibility; Labour; Social justice; Sustainable development; Trade regulation

Three Essays in Bank Financial Reporting - Liu, Yi (McMaster University, 2017)
This thesis investigates three important issues on bank financial reporting quality: 1) the impact of banks’ retail versus wholesale funding structure on their earnings quality, 2) the implications of economic and monetary policy uncertainty for banks’ earnings opacity, and 3) the relationship between banks’ bad time history and accounting conservatism. In the first essay, we examine the implications of banks’ funding strategies for banks’ earnings quality. We find that banks’ greater reliance on retail deposits over wholesale funds is negatively and significantly associated with the magnitude of earnings management through discretionary loan loss provisions, the likelihood of meeting-or-beating earnings benchmark, and the extent of income smoothing through loan loss provisions. This finding is consistent with the arguments that retail deposits are relatively more stable and information-insensitive, represent a more conservative business model, and attract more intensive monitoring from the Federal Deposit Insurance Corporation (FDIC) than wholesale funds, thereby improving banks’ financial reporting quality. In the second essay, we investigate whether economic and monetary policy uncertainties affect banks’ earnings opacity. When economic and monetary policies are relatively uncertain, it is easier for bank managers to distort financial information, as unpredictable policy changes make assessing the existence and impact of hidden “adverse news” more difficult for investors and creditors. Policy uncertainty also increases the fluctuation in banks’ earnings and cash flows, providing additional incentives for bank managers to engage in earnings management. Our results show that uncertainty in economic and monetary policy is associated with greater magnitude of discretionary loan loss provisions, higher likelihood of just meeting-or-beating the prior year’s earnings, and lower levels of accounting conservatism, suggesting that economic and monetary policy uncertainties lead to higher banks’ earnings opacity. In the third essay, we examine the impact of banks’ bad times on the conservatism of accounting policy. Specifically, we investigate two types of bad times: banks’ own past experiences of undercapitalization and their experiences of witnessing the failures of other banks in state-wide and county-wide crises. We find that both types of banks’ bad times are positively related to timelier recognition of earnings decreases versus earnings increases in accounting income. We also find that following exposure to bad times, banks increase their allowance for loan losses. Collectively, our results suggest that bank-specific bad times and macro-level banking crises lead to greater bank accounting conservatism. These findings support the arguments that banks exposed to past crises overweight their bad time history, and become more cautious and pessimistic about their future earnings performance and loan quality.

The notion of award in international commercial arbitration-lessons from French and English law - Marchisio, Giacomo (McGill University, 2017)
For the past twenty years, international commercial arbitration scholarship has mainly focusedon the private dimension of international arbitration. Part of a greater movement toward the privatization of justice and law, this understanding of the discipline has obscured arbitrators'adjudicative role. By reflecting on different adjudicative models and by analyzing the form andcontent of arbitral decisions, new light can be shed on our understanding of international commercial arbitration.
https://escholarship.mcgill.ca/concern/theses/12579v86z
Keywords: Arbitrage; Arbitragem; Arbitration; Award; Commercial Arbitration; English law; French law; International Arbitration; International commercial arbitration

Virtual property : towards a general theory - Pałka, Przemysław (European University Institute, 2017)
The primary contribution of the thesis is a theory enhancing the legal understanding of the phenomenon of virtual property, encompassing presentation of data and a new conceptual framework to interpret it. The author argues that the normative debates concerning the phenomenon have underestimated the importance of understanding and conceptualizing it first, and aims at amending this gap. The ‘virtual property phenomenon’ refers to the users of internet platforms and online computer games ‘possessing’ virtual items – digital objects that exist within these services – and getting into economic and social relations concerning these items, with other users, service providers and third parties. These relations are regulated by different types of service-specific rules – contractual and the ‘code’ – created unilaterally by the service providers, who additionally retain the ability to interpret and enforce them, using ‘digital force’, i.e. by modifying and deleting virtual items, and blocking users’ accounts. The primary challenge stems not from the fact that the phenomenon is not regulated, but from the fact that lawyers lack words – terms and concepts – to even conduct a meaningful debate about it, or how to respond to it. The thesis consists of six chapters. Firstly, the author describes the phenomenon and analyzes the theoretical and regulatory legal challenges posed by its emergence. Secondly, he critically assesses the state of the art. Thirdly, a methodology to address these challenges is proposed, which can also be used in other research projects concerning law and technology. Fourthly, the author explains how the process of digitalization has fundamentally challenged the assumptions that private law held about the structure of reality, and proposes new doctrinal tools to conceptualize it. Fifthly, the author presents a legally useful concept of virtual items, and argues that granting users property rights over them might not be the optimal means of realizing the property goals. Finally, the author proposes a normative solution, a correction of private law, responding to the new type of inequality in relations, namely a user protection law.
Accepted: 2017-12-21T14:08:02Z
Keywords: Computer games; Internet; Possession (Law); Property

Libraries in the digital renaissance law and policy for book digitization - Panezi, Argyri (European University Institute, 2017)
This dissertation examines the phenomenon of book digitization and the legal challenges for the creation of digital libraries. It explores whether the current copyright framework supports libraries in the digital era as they strive to remain the institutional guardians of our literary treasures. The thesis hypothesis is that the current framework is unsuccessful or inadequate in supporting libraries. To test this hypothesis and identify the legal inefficacies the dissertation examines context, i.e. the history and rationale for applying copyright rules to books and libraries, the copyright rules as applied to libraries before and after digitization was possible, various digitization projects and the practical challenges that digitization brought about, and, the relevant litigation which has started on both sides of the Atlantic covering over a decade now. Furthermore, the thesis explores normative directions of copyright rules, including their exceptions, applicable to libraries in the digital era. It ultimately proposes that among various players claiming this role, libraries, given their institutional functions and capabilities, should be attributed rights to digitization and a favorable legal framework for providing access to digital material.
Accepted: 2018-01-08T09:36:41Z
Keywords: Copyright; Digital libraries; Electronic data processing; Electronic information resources; Intellectual property; Propriedade intelectual; Propriété intellectuelle

Consumer arbitration in South Africa and its effect on the consumer's right to redress and enforcement - Rantsane, Ditaba Petrus (University of Pretoria, 2017)
The thesis entitled "Consumer arbitration in South Africa and its effect on the consumer‘s right to redress and enforcement" notes with concern the outdated and inadequate nature of the Arbitration law currently applied in South Africa. The fact that the Act was enacted in 1965 and has never been amended highlights the desperate need to review the prevailing arbitration law with a view to aligning it with the current needs of the business world. The thesis addresses the concern that consumers are not adequately protected by the current arbitration law and thus substantially develops the discourse on the topic of arbitration in situations of unequal bargaining power. It raises three primary research questions in this context. The first question reads thus, if private arbitration is properly conducted should it still provide the parties with the envisaged benefits? Secondly, is private arbitration constitutional, especially as it impacts upon consumers‘ contracting with large corporations? Thirdly, is the private arbitration process as it is currently applied, constitutional as far as it denies parties an appeal on merits against an award that is clearly wrong? The thesis attempts to answer these questions and offer recommendations for the South African Law Reform Commission (SALRC) within the specific context of commercial arbitration. In addressing these research questions, the thesis incorporates a brief overview followed by a detailed discussion of the Arbitration law framework in South Africa and abroad. The discussion of arbitration abroad is done in order to identify best practices, which could be adapted to suit the South African environment. International Arbitration law receives attention and a few observations regarding how selected foreign jurisdictions treat arbitration. Finally, the thesis explores the possibility of establishing an independent institution that will be fully equipped to handle arbitration proceedings from inception to completion.
URI: https://repository.up.ac.za/handle/2263/67886
Keywords: Consumer arbitration; Consumer rights

Non-discrimination in international economic law - Risvas, Michail (University of Oxford, 2017)
This thesis examines the jurisprudence of the World Trade Organization (WTO) Panels and Appellate Body (AB) and investment tribunals on non-discrimination clauses contained in the WTO agreements and investment agreements respectively. The thesis puts forward an alternative conceptual perspective through which the interpretation of non-discrimination provisions in international economic law could be analysed. It is argued that nondiscrimination obligations (as every legal rule to a greater or lesser extent) are inherently indeterminate. This is a fortiori the case in regard to non-discrimination provisions due to their link to the concept of equality. The concept of equality is open-ended and value-laden: its content depends on the prioritisation of different values. Thus, equality in the economic sphere can accommodate different conceptions which reflect different ideological approaches in relation to regulation, economic development and the proper role of the State in the economy. International courts and tribunals enjoy broad discretion in selecting which conception of equality to adopt when interpreting non-discrimination clauses. This indeterminacy is a positive characteristic of international economic regimes. Both the WTO and the investment arbitration regime are equipped with institutional characteristics which enable the contestation of different ideological approaches and promote pluralism. In the WTO context, this role is fulfilled by the institutional structure of the organization which facilitates the dialogue between the WTO members and the WTO Dispute Settlement System. In the realm of international investment arbitration, the mechanism of party-appointed arbitrators, despite its shortcomings which can be addressed, ensures value pluralism.
https://ora.ox.ac.uk/objects/uuid:23e7e195-c657-46d0-9a21-bde0c793dc45

Creditors' rights in business rescue proceedings in terms of South Africa's Companies Act 71 of 2008 - Rugumamu, Victor William (University of KwaZulu-Natal, 2017)
The focus of this study is the protection of creditors’ rights in South Africa’s statutory business rescue regime provided for in Chapter 6 of the Companies Act 71 of 2008. In this analysis, three issues in particular are addressed in depth. The first is the creditors` power to initiate the business rescue process. The second is the position of creditors between the commencement and the termination of the business rescue process. The third issue is to suggest (on the basis of experience drawn from reported case law and academic criticism of the current business rescue statutory provisions) an improved model that will more effectively safeguard creditors’ rights in South Africa’s business rescue regime. In exploring these issues, I give a critical review of pertinent literature. With respect to the first issue, I conclude that the legislative provisions granting creditors the right to seek a court order initiating the business rescue process are open to criticism. By contrast, a resolution of the board of directors for the commencement of business rescue is a simpler route. With regard to the second issue I conclude that the company’s creditors have considerable influence in the business rescue process. Overall, the current statutory business rescue regime is intended to give a voice to all major stakeholders in the company’s continued solvent existence. In the event of certain irresoluble disputes in the course of that process, the judiciary has the final say. A substantial number of judicial decisions have provided interpretations of the statutory provisions, and the trend has been to try to restore financial ailing companies to solvency and viability where there is a reasonable prospect for success in this regard. In my conclusion, I propose a legislative model that seeks to strike an optimum balance between the competing and sometimes conflicting interests of the various interested parties and I suggest reforms directed at enhancing the protection of creditors’ rights. This thesis takes account of South African legislation and legislative amendments as at 31 December 2016 and of decisions of the South African courts up to and including those handed down during April 2017 and reported in the saflii on-line law reports. Since a substantial part of this thesis was written from outside South Africa, the author relied heavily on the safllii data base of judgments of the South African courts, rather than on hard copy law reports which take time to reach their destination by post.
Keywords: Financial distress; Liquidation; Rationale for business existence

Integrating healthcare quality concerns into a competition law analysis : mission impossible? - Stavroulaki, Theodosia (European University Institute, 2017)
Healthcare markets have started being created in Europe. Indeed, some European countries, such as the UK and the Netherlands, have started adopting the choice and competition model for healthcare delivery. Taking as a starting point that as health systems in Europe move towards market driven healthcare delivery, the application of competition law in these systems will increase, the goal of this doctoral thesis is (a) to identify some of the competition problems that may be raised in light of the reality that especially in hospital and medical markets the pursuit of competition and the pursuit of essential dimensions of healthcare quality may inevitably clash (b) to demonstrate that competition authorities would be unable to address some of these competition problems if they did not pose and address a fundamental question first: how should we define and assess quality in healthcare? How should we take healthcare quality into account in the context of a competition analysis? In delving into these questions, this doctoral thesis explores how the notion of healthcare quality is defined from antitrust, health policy and medicine perspectives and identifies three different models under which competition authorities may actually assess how a specific anticompetitive agreement or hospital merger may impact on healthcare quality. These are: (a) the US market approach under which competition authorities may define quality in healthcare strictly as choice, variety, competition and innovation (b) the European approach under which competition authorities may extend the notion of consumer welfare in healthcare so that it encompasses not only the notions of efficiency, choice and innovation, but also the wider objectives and values European health systems in fact pursue (c) the UK model under which competition authorities may cooperate with health authorities when they assess the impact of a specific transaction on healthcare quality. The thesis identifies the main merits and shortcomings of these models and emphasizes that what is crucial for the adoption of a holistic approach to healthcare quality is not only the model under which healthcare quality is actually integrated into a competition analysis but also competition authorities’ commitment to protect all dimensions of this notion.
Accepted: 2018-01-08T08:10:01Z
Keywords: European Union countries; Medical care; Medical laws and legislation; Medical policy; Unfair competition

Problems regarding exemption clauses in consumer contracts : the search for equitable jurisprudence in the South African Constitutional realm - Tembe, Herman C. (University of Pretoria, 2017)
URI: https://repository.up.ac.za/handle/2263/65730
Keywords: Consumer contracts; Exemption clause; South Africa

The responsibility of private actors in the internal market : private actors taking over? - Trommer, Jan (European University Institute, 2017)
The picture presented and often referred to in EU internal market law and legal scholarship is clear. Within the internal market private actors are the recipients of rights and public authorities are constrained in their (regulatory) powers. The notion of this new individualism is bound up with capacities, powers, and resources that empower private actors to engage in the internal market and cross-border situations; ultimately serving the objectives the internal market seeks to attain. Yet, within thinew individualism a conceptually different class of private actors has emerged that is constrained in economic freedoms, i.e. through obligations, rather than being empowered in the context of the internal market. This thesis will enquire the reasons that led to the development of this counter-culture. Why did it emerge? To what extent does this phenomenon affect the roles of private actors in the internal market? I will demonstrate that under the counter-culture private actors are responsibilized and transformed into ‘competent authorities’, i.e. alternative forms of regulatory authority, in the internal market. Private actors are placed into systems of shared responsibilities the relationships of which are coordinated by EU internal market law. In this regard, the concept of responsibility will serve as a tool to bridge the gap between the new positions EU internal market law allocates to private actors and the emerging legal consequences, i.e. allocation of obligations or tasks. The legal contexts of EU free movement law, EU discrimination law, EU food safety law and EU data protection law will serve as case studies against which the construed conceptual framework will be tested. Under the counter-culture the new individualism is no longer only about the exercise of self-interests. Rather, this form of the new individualism comes with a requirement to give account to the interests of other actors within the internal market.
Keywords: Commercial law; European Union countries; Free Trade; Trade regulation

Identification of the parties to the employment relationship: An appraisal of teleological interpretation of statutes - Van Staden, Marthinus Jacobus (University of Pretoria, 2017)
The study, entitled “Identification of the parties to the employment relationship: an appraisal of teleological interpretation of statutes”, is a legal-interdisciplinary doctrinal investigation situated within the fields of labour law and the interpretation of statutes. It concerns itself with the proper interpretation of labour legislation in general and the interpretive question as to who should be party to the employment relationship in particular, within the context of the advent of constitutionalism and the proliferation of and the increase in the importance of labour legislation. In law, meaning-generation is a function of statutory interpretation and every application of a text to particular circumstances entails interpretation. The protection extended by labour legislation is only extended to those persons who are defined as “employees”. The study describes the teleological model of statutory interpretation, which aims to give effect to the purpose of a legislative provision in light of constitutional values. The study explores the five elements of (teleological) interpretation that should be considered when interpreting concepts such as “employee”: the text, the context, the telos (or values), the history and the comparative dimension. The chief findings of the study includes: that legislation has become an indispensable source of contemporary labour law; that the courts have adopted a teleological approach to the interpretation of statutes; that the courts have, in interpreting the term “employee”, adopted a teleological approach to the interpretation of statutes; and that the interpretations advanced by the courts have not had the profound effect envisaged by the Constitution on the transformation of society.
URI: https://repository.up.ac.za/handle/2263/65631
Keywords: Employment relationship; Labour law; Parties

The international legal framework on business and human rights and its domestic operationalisation : strategic litigation on mining and a healthy environment in South-Africa - Verdonck, Lieselot (Ghent University, 2017)
The debate on business and human rights attracts the interest of many parties, and regularly makes the headlines. On 19 January 2017 De Morgen, for instance, ran the following headline: “These banks do business with companies that violate human rights and nature”. The discourse suggests that few question that business enterprises should respect human rights. The legal meaning and consequences of associating 'business' with 'human rights' remain contentious, however. By clarifying the existing legal framework this thesis seeks to rationalize the debate. Special attention is paid to enforcing the responsibility of business enterprises for human rights through domestic judicial remedies. The analysis is concretised through a case study on adverse human rights impacts of environmental degradation caused by mining in South Africa. Based on the findings of the study, the thesis reflects on how the international legal framework on business and human rights should be developed further.
http://hdl.handle.net/1854/LU-8535402
Keywords: Business; CSR; CSR disclosure; Human rights; International law; RSE; South Africa

The liability of trade unions for conduct of their members during industrial action - Mlungisi, Ernest Tenza (University of South Africa, 2016)
South Africa has been experiencing a number of violent strikes by trade unions in recent times. The issue is not only to hold unions liable for damage caused during strikes, but also to reduce the number of violent strikes. This study investigates if victims of such violence can hold trade unions liable for the violent acts committed by their members during industrial action. The Labour Relations Act, 66 of 1995 (LRA) makes provision for the dismissal of employees who commit misconduct during an unprotected strike. It also provides the remedy of an interdict and a claim for just and equitable compensation which can be made against the union, during an unprotected strike. It is further possible to hold the union together with its members liable for damages in terms of the Regulation of Gatherings Act, 205 of 1993 (RGA). The study argues that a strike or conduct in furtherance of a strike that becomes violent could lose protection and the trade union should consequently be held liable, in terms of the LRA and/ or the RGA, for damages caused by its members. This study investigates the position in Canada, Botswana and Australia to determine if there could be any other basis upon which to hold trade union liable for the conduct of its members. The study recommends that the common law doctrine of vicarious liability should be developed by the courts to allow trade unions to be held liable for damages caused by members during violent industrial action. Policy considerations and changing economic conditions and the nature of strikes in the Republic favours the expansion of the doctrine of vicarious liability to trade union member relationship.
https://uir.unisa.ac.za/handle/10500/23172
Keywords: Common law; Industrial relations; Interest arbitration; Labor unions; Liability (Law); Secret ballot requirement; South Africa; Strikes and lockouts; Tort liability of labor unions; Trade union denial; Trade union liability

A critical review of the treatment of dominant firms in competition law : a comparative study - Munyai, Phumudzo S. (University of South Africa, 2016)
In South Africa compliance with competition law has become a major concern for firms that achieve and maintain certain levels of success and growth in the market, as their actions are often a source of complaints and litigation by rivals and competition authorities. With substantial financial penalties often levied against them for a variety of conduct deemed to constitute an abuse of their market position, dominant firms must constantly be aware of the likely impact of their business strategies and actions on both rivals and consumers. What were once thought to be normal and economically sound business practices and decisions, such as cutting prices to attract customers, have now acquired new meanings, with devastating consequences for dominant firms. So, are dominant firms under attack from competition law? In this study I aim to determine this. I track the historical development of competition law in three jurisdictions: South Africa, America, and the EU, with the aim of identifying traces, if any, of hostility towards dominant firms in the origins of competition law. I further investigate whether the formulation and enforcement of certain aspects of existing abuse of dominance provisions manifest as hostility towards dominant firms. While acknowledging the important role that competition law enforcement plays in promoting competition and enhancing consumer welfare, I conclude that significant unjustified economic and legal prejudice is suffered by dominant firms as a result of the way in which certain abuse of dominance provisions have been formulated and applied. I also offer appropriate recommendations.
Keywords: Abuse of dominance; Anti-monopoly; Anticompetitive effects; Anticompetitive harm; Antitrust law; Causation; Competencia; Competition Appeal Court; Competition Commission; Competition Tribunal; Competition law; Consumer harm; Consumer welfare; Counterfactual; Dominant firms; Exclusionary conduct; Hostility; Monopoly; Super-dominant; Unilateral conduct

The timing of the passing of property and risk under the English Sale of Goods Act 1979, the CISG and the Libyan law: the interplay between the principle of party autonomy and the default rule - Aboukdir, Anwar (University of Stirling, 2016)
This thesis attempts to critically and comparatively analyse the issues relating to the passing of property and risk under the United Nations Convention on the Contract for International Sale of Goods (CISG) and English Law (SGA). The passing of property and risk plays a central role in the area of international legislation in relation to sales contracts. These elements can be the most significant components in contracts of sale between parties, whether in the international or domestic field. The reason is founded on their legal nature and the close relationship between them. The passing of property and risk has been a central issue for practitioners, judges and lawyers dating back to the Roman period and several ideas have been proposed to resolve it. Where the situation is different for contracts of sale in relation to the passing of property and risk, whether in the domestic or international field, it still creates many unresolved problems, because of ongoing changes in the field of modern commerce, which may contribute to unfair implications between the parties. It has been observed in this thesis that both English law and the CISG adopt the party autonomy principle, where the intention of the parties - whether in relation to the passing of property or risk - is the basic rule. However, the difference lies in the default rules. While English law involves default substitutional rules, which apply in cases where there is an absence of an expressed or implied indication regarding the intention between the parties, the CISG lacks such default rules regarding the transfer of property, which could be viewed as its main weakness, although the CISG does involve such provisions with respect to the transfer of risk. This thesis willdiscusses, the legal nature of the rules in relation to the passing of property and risk, and the role of the party autonomy principle, and the impacts and legal difficulties that might arise through the application of these rules, whether they are default rules or based on the party autonomy principle. It will also examine the legal gaps and weaknesses of both legal systems in an attempt to identify such legal difficulties and to find appropriate solutions and remedies.

Towards a suitable domestic arbitration process in Nigeria - Bamgbose, Ademola Jonathan (University of Warwick, 2016)
The Nigerian judicial system is currently in a state of distress. Not only has the judiciary been trailed by allegations of corruption, incompetence and god-fatherism amongst others, the wheels of justice in Nigeria are slowly grinding to a near halt. This is because of the large and growing case list of courts as well as the recurrent industrial strike actions embarked upon by court staff. As a solution to this crisis, stakeholders have put forward a number of suggestions, one of which is the use of alternative dispute resolution methods like domestic arbitration, as a solution to the problems of the judiciary and as a viable alternative to the court system. As we will however come to see in this thesis, Nigeria’s Arbitration and Conciliation Act 1988 (“Arbitration Act”), which is based on the UNCITRAL Model Law 1985, is not only outdated, it is also for many reasons not suitable and relevant to a developing country as Nigeria. For example, the existing Arbitration Act fails to take the legal and social idiosyncrasies of the Nigerian nation into consideration. Furthermore, the Act fails to incorporate the pre-existing and judicially recognized customary arbitration practice into the Act. In addition, the Nigerian Arbitration framework contains a number of anti-arbitration provisions, which have clearly inhibited the growth of domestic arbitration in Nigeria. Moreover, between 1988 and now, a number of beneficial changes have occurred within the sphere of arbitration and from which the Nigerian arbitration framework can draw lessons. All these among others, make the Nigerian Arbitration Act an unsuitable alternative to the court system in Nigeria. This thesis therefore recommends a bespoke domestic arbitration framework, which takes account of the legal and social idiosyncrasies of the Nigerian nation as well as recent but relevant domestic arbitration practices in similar jurisdictions as Nigeria. Among other recommendations, the proposed framework borrows a leaf from the deeply rooted and judicially recognised customary arbitration practice in Nigeria. Furthermore, in a bid to identify and incorporate relevant provisions and practices that have emerged within the sphere of domestic arbitration between 1988 and now, we undertake a comparative analysis of the Ghanaian Alternative Dispute Resolution Act 2010, the UNCITRAL Model Law 2006, the English Arbitration Act 1996 as well as the Uniform Act on Arbitration 1999 of OHADA. It is believed that this modern but tailored framework will encourage the use of domestic arbitration in Nigeria and by extension ameliorate the problems in the judicial system.
URI: http://webcat.warwick.ac.uk/record=b3059548~S1
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration (Administrative law); Ghana; Nigeria

Sovereign wealth funds in international economic law - Dekastros, Michail (European University Institute, 2016)
Sovereign Wealth Funds have been the new 'rising star' of the global economy for a few years. Host States have reacted to their rise cautiously and have quite frequently cited 'national security' as a justification for maintaining an absolute degree of freedom in regulating their entry into their markets. This thesis is arguing that a substantial proportion of regulatory concerns that surround the operation of SWFs are actually not of a national security nature—at least as perceived by the relevant instruments regulating investment in International Economic Law. As a consequence, the current regulatory framework screening SWFs investments a priori is both legally and normatively problematic and, in fact, it constitutes a form of protectionism. As an alternative, this thesis suggests that SWFs ought to be primarily regulated after their entry into Host States' markets. In that context, a proper conceptualisation of the principle of non-discrimination that takes into account the 'regulatory unlikeness' between SWFs and other market suppliers/investors will allow the Host States to properly regulate them after their entry into their markets. Such a conceptualisation – contrary to usual analyses – draws heavily from International Investment law in order to interpret the relevant provisions of the GATS.
Keywords: Foreign investment; International law; Sovereign wealth funds

Accountability of multinational corporations for human rights violations under international law - Mnyongani, Freddy (University of South Africa, 2016)
Jurisprudence
Keywords: CSR; Corporate Social Responsibility; Corporate governance; Human rights; International business enterprises; Liability for human rights violations; RSE; Social responsibility of business; Tort liability of corporations

Enforceability of Arbitral Awards Containing Interest: A Comparative Study between Sharia Law and Positive Laws - Althabity, Mohammad M. (University of Stirling, 2016)
The dynamics of our globalised world open the way for international trade and transactions between different countries; this may lead to conflicts in laws where transactions and trade may be subject to different legal systems. One of the biggest issues in international commercial law is disputes over the charging of interest, for example with regard to late payment, interest-based loans, or compensation for damages. Interest disputes are considered to be a complex area of law and even more complex in the international field. At the international level, interest claims may be connected to many areas of commerce and thus governed by various laws, which are different from one country to another; moreover, each country has its own interest rate and such rates are changeable according to the nature of law and economics under some jurisdictions. Furthermore, the concept of interest itself is affected by influences such as religious beliefs and economic, political and cultural trends. Interest can be treated as a substantive or a procedural matter. The settlement of these disputes therefore faces difficulties. Arbitration, as a method for settlement of disputes, is characterised by special features that assist in resolving these issues; but it faces some obstructions, especially in international commercial arbitration. The practices of arbitral tribunals and national courts in this regard are different. The results of different interpretations, approaches, and theories with regard to arbitration, at the pre-arbitration, during arbitration and post-arbitration stages, may also differ widely due to the diversity of financial and legal systems such as Common Law, Civil Law and the Islamic legal system – Sharia Law – across different countries. Each legal system has a different methodology and theories, even within an individual country under one legal system, and a state within a federal system has its own laws, which may have different interpretations in this respect. The New York Convention of 1958 on enforcing foreign arbitral awards was established in favour of arbitral awards and for the purpose of unifying international rules of arbitration. This Convention provides some procedural and substantive rules for the enforcement of foreign arbitral awards, but also provides some grounds for refusal. These rules have been affected by different interpretations under different jurisdictions and legal systems, which lead to different perspectives on the matter of charging interest and settlement by arbitration. The outcome of applying the NYC under these interpretations often has the opposite of its intended effect: the rejection of foreign arbitral awards. Due to such ambiguities, courts occasionally intervene in arbitration in all its stages. The interventions of national courts occur in three stages: enforcement of the arbitration agreement, enforcement of the contract under the applicable law to the agreement, and enforcement of the foreign arbitral award. The confusion between substantive and procedural laws also creates confusion with respect to public policy, non-arbitrability and enforceability. In addition, there may be a lack of clarity on the scope of arbitration with respect to the parties’ agreement, whether or not the parties have agreed to the interest rates and periods and whether or not they have agreed to the authority of the arbitrator. These issues affect the enforceability of an arbitration agreement, the law applicable to the disputed contract, the freedom of parties, the authority of the arbitrators and the enforceability of the awarded interest. The thesis studies how arbitral awards containing interest have been interpreted across the three aforementioned legal systems under the NYC 1958 in Saudi Arabia, Egypt, the UAE, England, France, and the US and the enforceability of such awards.
https://dspace.stir.ac.uk/bitstream/1893/23090/1/Enforceability%20of%20Arbitral%20Awards%20Containing%20Interest.pdf
Keywords: Arbitrage; Arbitral award enforcement; Arbitration; Chari'a law; Sentence arbitrale; Sharia Law

An investigation into customer accounting in customer-focused organisations - Bates, Ken (Victoria University of Wellington, 2016)
Management accounting information should aid management in the design and implementation of strategy. Firms adopting a customer-focused strategy need customer accounting (CA) metrics. Yet accounting literature provides limited insights into what CA metrics are used, how they are used, or what factors influence CA measure choice or hinder more widespread adoption of CA practices. This thesis enhances knowledge of actual CA practices as they operate in firms with a customer-focused strategy and uses contingency theory to explain the choice of CA practices and their use in three exploratory case studies consisting of two national banks and a global courier company. The two strategic business units in Alphabank employ locally-developed, activity-based costing systems to produce CA information. Personal Banking incorporates a ‘customer needs met’ variable into a customer lifetime value measure used to segment customers based on potential profitability. Business Banking is smaller and currently uses historical customer profitability analysis at the individual customer level. Despite Alphabank’s overall customer-focused strategy, only product profitability is reported at executive level, and tensions between finance and operations potentially hinder more widespread CA usage. Betabank offers excellent customer service, but despite being very customer-focused they do not measure customer profitability. Executives use predominantly aggregate financial figures with a focus on net interest margin. Service excellence is paramount and Betabank do not consider financial CA useful as they do not segment customers. However, they extensively use non-financial customer related measures to monitor excellent customer service provision in order to enhance future profitability. The courier company uses activity-based costing to produce historical customer profitability analysis which reports direct margin, gross margin and earnings before interest and tax. The analysis discloses significant profitability differences between customer segments, and even between individual customers within segments where customer relationship management is employed. They do not measure full customer lifetime value but the next year’s customer profitability can be modelled using historical cost drivers. Financial CA measures drive initiatives to enhance customer profitability and/or trigger price negotiations. Non-financial CA measures are used to drive the customer-focused strategy and enhance profitability. The three cases demonstrate a considerable diversity in their usage of financial CA practices, with Betabank choosing to use no financial CA at all. Competitive intensity and the use of customer relationship management are found to be key drivers of CA usage at the individual customer level. Segmental customer profitability analysis is used when a large number of customers receive standard services at standard prices. No individual customer profitability analysis is needed for such homogenous customers as they can be efficiently managed using revenue. Non-financial CA measures were found to be widely used and hence a key contribution of this study is that in practice customer-related, non-financial performance measures are a key component of CA practices and may be extensively used to drive a customer-focused strategy. From case analysis a contingency-based framework has been develop which identifies combinations of factors with strong interrelationships and common influences on the choice and usage of CA measures. This framework provides three main groupings of contingent factors (type of competitive advantage, level of customer heterogeneity, and stage of organisational development) which together potentially have strong predictive power in relation to the nature of CA measures which benefit firms with a customer-focused strategy.
Keywords: Bank; Courier; Customer Accounting; Customer Profitability Analysis

Value and risk effects of financial derivatives: Evidence of corporate governance on hedging, speculation and selective hedging strategies - Tashfeen, Rubeena (Victoria University of Wellington, 2016)
This study investigates whether there is a relationship between corporate governance and derivatives, whether corporate governance influence in firms impacts the association between derivatives and firm value, and whether corporate governance influence affects the association between derivatives and cash flow volatility, stock return volatility and market risk. This study uses two different data samples of publicly traded firms listed on the New York Stock Exchange. The first sample comprises a panel of 6900 firm year observations and the other consists of a panel of 6234 firm year observations both over the eight-year period from 2004-2011. With regard to whether there is a relationship between corporate governance and derivatives, the findings from the empirical results show that corporate governance does influence derivatives and therefore is an important determinant in the firm’s decisions to use derivatives. Of the thirteen corporate governance variables examined, board size, institutional shareholders, CEO age, CEO bonus, CEO salary, insider shareholders and total CEO compensation show significant association with derivatives. This study finds that derivative users exhibit higher firm value on account of the corporate governance influence, which is correspondingly largely insignificant for derivative non-users. Further the research indicates that the impact of corporate governance varies according to the different types of risks examined. Generally, the board of directors and CEO governance mechanisms reduce stock return volatility to achieve hedging effectiveness. This supports the view that directors and management take actions to reduce stock return volatility to protect their personal portfolios without having to bear the costs of hedging themselves. With respect to cash flow volatility, the board of directors and CEO related corporate governance mechanisms largely exhibit increased risk to show evidence of speculative behavior. It supports the perceptions that managers and directors have a strong motivation to show higher earnings to protect jobs and reputation and to enhance compensation. All the shareholder governance mechanisms encourage risk taking with respect to stock return volatility, without any increase in firm value. This is in line with research findings of market granularity by institutional and other larger block holders to indicate that these investors increase stock price volatilities and play the markets for their own financial gain. Besides they have little interest in diversifying firm risk as they already have well protected portfolios and would not want to incur additional costs of hedging. The study finds evidence of association between corporate governance and hedging, speculation and selective hedging. Of the thirteen corporate governance variables examined in the study board diversity consistently shows hedging effectiveness, with accompanying increase in firm value. While board meetings, institutional shareholders, block shareholders, CEO age, CEO base salary and CEO compensation exhibit exclusive speculative behavior. The remaining corporate governance mechanisms: board size, insider shareholding, CEO tenure, CEO bonus and audit committee size, show evidence of selective hedging behavior. The concurrent hedging and speculative behavior evidenced in this study supports literature in respect of selective hedging by non-financial firms. It also validates the idea that corporate governance delves in risk allocation strategies that have been evidenced by past research. The results remain unchanged, after using alternative measures for firm value and firm risk, and alternative methods of analyses.

Protection of agency workers in South Africa : an appraisal of compliance with ILO and EU Norms - Aletter, Candice Joy (University of Pretoria, 2016)
This thesis is a policy-based study of the regulation of agency work in South Africa. It is set against the contextual background of a recent legislative overhaul and an increase in the number of precarious workers. The study aims to appraise the extent to which the South African regulatory framework complies with international norms in respect of agency work. The research considers how German and Namibian regulation might improve the current model of the regulation of agency work in South Africa. The study identifies the purpose of labour law in South Africa as offering diversified rights as well as being economic in nature. The premise upon which the thesis is based is a social justice approach to the function of labour law. An analysis of ILO and EU regulations on agency work is conducted, and identifies a combined list of norms in respect of the protection of agency workers. South Africa?s labour law policy approach is explored together with the amended regulation on agency work. A comparison is drawn with foreign countries? regulations and policy approaches: the appraisal identifies shortcomings in South Africa?s regulatory model. The study focuses on the evolutionary improvement of agency workers? protection based on international approaches. The research culminates by formulating an amended model for the regulation of agency work in South Africa, in which these proposed adaptations seek to remedy the shortcomings which were observed in the appraisal process.
URI: https://repository.up.ac.za/handle/2263/60060
Keywords: Agency work; EU Regulations; ILO; Labour law; South Africa

A rights-based approach to foreign agro-investment governance in Cameroon, Uganda and South Africa - Ashukem, Jean-Claude Nkwanyuo (North-West University, 2016)
The practice of foreign agro-investment (FAI) for the production of food crops and biofuel crops has been a recent phenomenon in sub-Saharan Africa and other developing countries. In fact, the present era of climate change has caused foreign countries to acquire vast tracts of land - often through multinational corporations - in order to propagate biofuel or expand their home industries abroad. Practices of FAI have resulted in a form of land grabbing, as local communities are often evicted from their land without their consent. FAI activities are reported to have considerable impact on people in areas where they occur, which range from environmental to social and economic impacts. There is compelling evidence that FAI land deals are not transparent and inclusive, which raises pertinent concerns with respect to participatory rights, access to information, the compatibility of property rights, environmental protection and the protection of the rights and interests of local communities generally, among other issues. The lack of respect for and protection of local communities’ rights and interests during FAI land deals and activities form the crux of this study. In this light, the overall aim of this thesis is to investigate and ascertain how the procedural aspects of a rights-based approach (RBA) could be used to provide adequate protection to local communities’ rights and interests during FAI activities in Cameroon, Uganda and South Africa. The study is premised on the notion of a RBA to FAI governance and captures the procedural aspects of the right to access to information, public participation and the right to access to justice in international, regional, sub-regional and national human rights legal regimes. It is argued that because these rights have the potential to significantly contribute towards the protection of the rights and interests of people that are adversely affected by development activities, their incorporation remains useful and relevant in the FAI context. It is further claimed that the implementation of the procedural RBA in FAI land deals could strengthen the ability and capacity of the state to increase opportunities for more meaningful dialogue with local communities, while concomitantly helping the state to fulfil its international and national obligations as a duty-bearer to respect, protect and fulfil the rights and interests of its people. In addition, procedural rights encompass elements of good governance and democracy and could be used as a necessary and vital tool to prevent a government’s exercise of arbitrary power generally and in the context of development activities. This is predicated on the belief that procedural rights serve inter alia to strengthen democratic structures and processes and to curb corruption and the mismanagement of national resources, and ultimately to promote sustainable development. In this study, it is argued that a RBA generally and its procedural aspects specifically could play an important role in setting the standards and defining the processes that are appropriate to repudiate the unacceptable impacts of FAI and simultaneously address distributive concerns with the hope of promoting and ensuring more responsible and sustainable FAI. Conversely, the absence of such a normative baseline suggests that large-scale land transfer under the guise of FAI practices would endlessly levy an unacceptable toll on the fundamental rights of the vulnerable host population. The first step in this thesis is to analysis the theoretical concepts of governance and good governance in order to establish the eventual objective of what FAI governance and good FAI governance should entail. A further component of the theoretical analysis includes an analysis of a RBA and a RBA to FAI governance. These components are investigated in order to determine a possible solution to the impacts of FAI activities from a rights-based perspective. Second, the thesis investigates and analyses the procedural aspects of a RBA espoused in international, regional and sub-regional legal regimes. It distils generic characteristics and minimum requirements of the RBA for good FAI governance to be used as benchmarks in the context of project development-related activities, including FAI. As benchmarks, the international, regional and sub-regional legal regimes provide minimum criteria to which the legal frameworks of countries must adhere to and conform with. This part also examines the procedural RBA frameworks in Cameroon, Uganda and South Africa and critically evaluates the legal frameworks in these countries against the distilled generic characteristics and minimum requirements of the RBA in terms of good FAI governance. Third, the thesis concludes with a set of recommendations on the procedural RBA frameworks in Cameroon, Uganda and South Africa. These recommendations are meant to address the current lacunae in these domestic procedural RBA frameworks, and to propose measures designed to enable a situation where the rights and interests of local communities are better protected in the event that FAI land deals are concluded.
Keywords: ACCESS TO INFORMATION; ACCESS TO JUSTICE; Foreign agro-investment; Good governance; Land grabbing; Procedural rights; Public participation; Rights-based approach

Contracts as regulation model : applications and legal implications in over-the-counter financial markets - Borowicz, Maciej Konrad (European University Institute, 2016)
We develop a conceptual model of contracts as regulatory instruments in over-the-counter (OTC) financial markets. The model is informed by the functional understanding of financial regulation as addressing problems of counterparty risk, liquidity, information and systemic risk and structural understanding of regulation as a process of standard-setting, monitoring and enforcement. The justification of conceptualization contracts as regulatory instruments is found in the nature of the political economy considerations that inform the definition of certain contracts used in OTC financial markets. While many scholars rely on conceptualization of the said contracts as boilerplate, we argue that there exist important qualitative differences between boilerplate and regulatory contracts, which we link to a broader spectrum of interests taken into account in their definition in the process of standard-setting. The model and its application to loan and derivatives markets help to highlight the impact of governance features of the organization developing the contract and the regulatory competition to which the organization is exposed on the scope of the regulatory function. We also use a number of indicators and attributions to examine the effectiveness of regulatory contracts. While the contractual model displays some weaknesses in terms of both standard-setting (conflicts of interest) and enforcement (reliance on delegation) compared to its better established counterpart – the organizational model associated with exchanges – the contractual model helps to account for important self-regulatory features of OTC financial markets and offers suggestions as to how the structure of OTC financial markets can be improved.
Accepted: 2016-06-21T15:10:25Z
Keywords: Derivative securities; Financial risk management; Over-the-counter markets

Dealing with trade defence instruments in the context of economic integration in Africa - El Taweel, Khaled (University of Pretoria, 2016)
The launching of the T-FTA in June 2015 presents an opportunity for accelerating regional integration in Africa towards the establishment of a single market through deepening COMESA-EAC-SADC integration. This milestone can contribute positively to African development. Nevertheless, it faces different structural and technical challenges, including the risk of aggressive export strategies and unfair trade practices, which may wipe away a substantial part of the integration gains. This could undermine African integration plans and the largely infant industries in Africa, especially since many African countries lack sufficient technical skills, institutional capacity, and the legal framework to deal efficiently and effectively with unfair trade practices and to respond to situations which may require the application of emergency tools to better adapt to economic challenges. Apart from Egypt, Morocco, Tunisia, South Africa and Zambia national Trade Defence Instruments (TDIs) are not well developed. This could further constrain the ambitious African plans of economic integration. The thesis concludes that, although an effective TDI system is crucial for African integration as it can provide the required protection for African infant industries and unlock the potentials of African economic integration, the current African TDI systems are not effective. This is confirmed by the limited resort to TDIs in the African continent and the general perception that an effective TDI system is not a priority on the integration agenda. The concluded T-FTA TDI legal regime is not supportive for African integration plans in the long run. Africa should envisage how to upgrade its TDI system to make better use of the tools available under the WTO to deal with unfair trade measures, including anti-dumping to face dumped imports, countervailing measures to face subsidized imports, and safeguard measures to temporarily suspend concessions in the face of surge in imports. Africa can improve its national and regional TDIs system by learning from more developed TDI systems incorporated by other economic blocks such as the EU, NAFTA, Mercosur, and ASEAN. This thesis submits that the EU TDIs system is the most suitable to the African integration objectives. This submission is made while recognising the different level of development on both sides. The thesis submits that the long-term objective of the T-FTA is to have a regional investigating authority. It draws several recommendations to enhance African TDI system by working on five main categories: (A) The strategic direction; (B) The institutional framework; (C) Enhancing engagements; (D) Application of TDIs; and (E) The supportive factors.
URI: https://repository.up.ac.za/handle/2263/60043
Keywords: Economic integration; Trade defence instruments; Unfair trade practices

Collective action in comparative and empirical perspective: towards a socio-legal theory - Fortes, Pedro Rubim Borges (University of Oxford, 2016)
This DPhil thesis enhances existing understandings of collective action through a comparative and empirical study. Empirical analysis of economic, political, juridical, and social dimensions of the Brazilian experience reveals that some central understandings in existing literature are not borne out in this empirical context. In particular, the assertion that low monetary incentives for individuals hinder growth in use of collective action is strongly challenged. The Brazilian experience is contextualised through comparative analysis of three legal traditions of collective action: class actions; collective redress; and civil public actions. The Brazilian system presents a setting with potential for regulatory enforcement of consumer protection law, but rare episodes of consumer compensation or the imposition of punitive damages on corporations. With low monetary incentives, the growth of collective actions is explained by non-monetary incentives and investment in social capital through development of institutional trust and legal institutions. Collective actors develop their organisational infrastructure and perform their roles as representatives through institutional dynamics of concentration, competition, cooperation, and deference. The coexistence of multiple institutional actors in the regulatory space reduces agenda control, increases opportunities for consumer participation, and increases oversight of regulatory capture. The categories of diffuse, collective, and homogeneous individual rights explain the role of law in establishing procedural pathways and special features. This study is broadened through analysis of the legal environment and the potential regulatory impact of collective actions on the social relationships between businesses and consumers. I also evaluate limitations and possibilities regarding access to justice, judicial economy, compensation, and deterrence. This thesis indicates the possibility of developing a socio-legal theory of collective action, which would enhance our understanding of the complex dynamics at play by going beyond analysis of the consumer experience as merely an economic transaction or a legal object, analysing them instead as a complex social relationship.
Keywords: Collective action; Consumer (protection); Consumer compensation; Droit de la consommation

'You wouldn't steal a car' vs 'information wants to be free' : regulatory failure of copyright law through the prism of systems theory - Gracz, Katarzyna (European University Institute, 2016)
The thesis aims at explaining current regulatory crisis of copyright law (understood as its inability to regulate social dynamics as regards production, reproduction, dissemination of and access to information goods) through the application of systems theory. It refers to the concept of autopoietic legal system in order to draft a model representing the ecosystem in which copyright law functions. This model not only allows for observing copyright regime as it stands currently but also for analysing how it evolved over time. It scrutinises the interdependencies between the legal system and other constituent elements of its ecosystem: politics, economy, art, science, technology, religion, mass media, education as well as non-functionally differentiated segments of society: circles of relatives and friends. The main goal of this analysis is to highlight the fact that the current regulatory crisis of copyright is the result of the legal system's failure to equally acknowledge all the diverse rationalities constituting its ecosystem. The primary hypothesis of the study is that the core of the problem may be attributed to the divergence between legal norms, and competing non-legal copynorms constructed in the process of co-evolution within various elements of the model in question. In the analysis all the relevant copynorms understood as segmented social norms regulating social dynamics with respect to production, reproduction, dissemination of and access to information goods have been reconstructed to indicate their potential to oppose legal regulations. The thesis pivots around the concept of reflexive justice which refers to the equal acknowledgement of colliding rationalities. It concludes with the firm statement that copyright law in the digital environment needs profound reform. The concept of reflexive justice as developed within the systems theoretical approach is perceived by the author of this thesis as the most promising starting point for the new philosophy of copyright law.
Accepted: 2016-05-17T13:43:06Z
Keywords: Copyright; Intellectual property; Sociological jurisprudence

Transparency and dispute settlements : a study of the agreements on sanitary and phytosanitary measures and technical barriers to trade - Karttunen, Marianna (European University Institute, 2016)
Transparency of trade regulations by all WTO Members is essential for open, fair and predictable trade relations. Because of the negative integration process followed by the WTO Agreements, a myriad of different regulations apply in all WTO Members and have the potential of affecting international trade. With the progressive lowering of tariffs since 1947, these differing regulations remain the most significant barriers to trade, and the most difficult to reduce. The Agreements on Sanitary and Phytosanitary (SPS) measures and on Technical Barriers to Trade (TBT) provide the most comprehensive frameworks to address the costs arising from such regulatory diversity, through extensive obligations on regulatory transparency and cooperation and introducing elements of positive integration. Does transparency, within the SPS and TBT Agreements prevent disputes from rising, or ensure all Members access necessary information to raise more and better disputes? Through a presentation of the legal obligations and institutional framework of the two agreements (Part I), an in-depth analysis of the issues encountered by WTO Members in the implementation of the two Agreements and raised as trade concerns in the SPS and TBT Committees (Part II), and a study of the factors leading to disputes and transparency's role in addressing them (Part III), this thesis will demonstrate that transparency as it exists under the two agreements has the potential to both complement dispute settlement, by giving equal access to information for Members to raise disputes, and substitute dispute settlement, by fostering dialogue between Members before their frictions escalate to formal disputes. In this sense, the strength of the WTO legal and institutional system goes well beyond its dispute settlement system, with enforcement of WTO obligations fostered by better information sharing and dialogue among Members themselves, through non-judicial means.
Keywords: Food adulteration; Food inspection; Foreign trade regulation; Non-tariff trade barriers; Produce trade

Remedies for passengers for flight delays caused by force majeure - Ko, Li-Juan (McGill University, 2016)
This thesis intends to justify the necessity to propose an alternative remedy mechanism to current air carriers' obligations in offering complimentary services to passengers in force majeure delays. This mechanism mitigates disputes arising from passengers' dissatisfaction with air carriers' services. The proposal is the result of extensive research arising from a fundamental question: Who should be responsible for damages and/or inconvenience resulting from flight delays caused by force majeure? The source of information for this thesis stems from a combination of the analysis of case law and statutes on one hand, and experience drawn from professional practice and cultural context on the other. This thesis discusses the intersection of international conventions, national legislation, and the practice and expectations of air carriers and their passengers. The thesis specifically examines and highlights the inadequacies of relying on existing international conventions to provide a harmonized solution for flight delay claims. In terms of national remedy mechanisms, research and analysis have been focused on the advanced aviation markets in the West, such as the US and the EU, and on the emerging markets in the East, such as Mainland China and Taiwan. The research and analyses reveal how national laws, which are deeply influenced by socio-economic, political and cultural factors, trigger distinct conflicts of interest between air carriers and passengers. During the course of reviewing the legal jigsaw and uncertainties in current legal practice, the findings revealed more issues. In brief, making more laws cannot guarantee an effective solution for flight delay claims, especially in different jurisdictions. Accordingly, the findings support that a novel solution, free from the uncertainties and complexities in the current legal framework, is needed to resolve passengers' claims or expectations resulting from force majeure delays. Essentially, this novel solution is to form an alternative remedy mechanism that includes a fund and codes of conduct. The fund will implement a risk-sharing function among stakeholders that will include passengers, air carriers and airport managing entities. To mitigate disputes, the proposed codes of conduct will include guidelines to operate the fund with the aim of mutual respect between passengers and air carriers. In so doing, the remedy mechanism will provide equitable answers to the question: "Who should be responsible for damages and/or inconvenience resulting from flight delays caused by force majeure?"
Identifier: https://escholarship.mcgill.ca/concern/theses/fn1071806
Keywords: Air carriers' obligation; Alternative remedy; Flight delay; Force majeure; Remedies

The coordination of controlled foreign company legislation and international business taxation in developing economies with specific reference to South Africa - Lambrechts, Hendrik Frederik Johannes (University of Johannesburg, 2016)
This research is aimed at making out a case for the taxation of foreign source income in countries with developing economies. To this end the argument is presented that it is possible to tax foreign source income in a way that optimally coordinates the revenue entitlements of countries with developing economies, with the entitlement of multinational enterprises operating within their area of jurisdiction, to maximum profitability. It is proposed that this result may be achieved through the careful coordination of controlled foreign company (CFC) legislation and international business taxation in domestic law. To support this proposition, the following issues are addressed: a theoretical and conceptual framework for the implementation of a regime of foreign source income taxation in a country with a developing economy; an evaluation of the efficacy of the CFC legislation implemented in South Africa from which lessons in relation to the implementation of foreign source income taxation regimes in other developing countries are distilled; how the coordination of the interaction between a CFC regime, a domestic business income taxation regime, and an international business income taxation regime is effected; and an exposition of the factors that should be taken into account in the drafting of CFC legislation. To illustrate the possible real-world realisation of the coordination between CFC legislation and international business taxation in a country with a developing economy, model CFC provisions are drafted followed by an explanatory note on these provisions.
Keywords: Controlled foreign corporations; Double taxation; Foreign Corporations; International economic relations; South Africa; Taxation

Social legitimacy in the internal market : a dialogue of mutual responsiveness - Mulder, Jotte (European University Institute, 2016)
Social legitimacy is conventionally conceived to encompass an empirical notion based on the idea that, lacking societal acceptance, a (political or legal) regime will eventually disintegrate. This concern is reflected in the original compromise of 'embedded liberalism', which stands at the basis of the internal market of the European Union. The primary law set up of the internal market, indeed, shares the idea that the benefits of a joint commitment to free trade can only be achieved in a sustainable way if combined with an acknowledgement of domestic societal objectives within the same frameworks. Nevertheless, social legitimacy will eventually depend on the institutional design and structural rationales that embed societal values within such regimes and vice versa. This perspective is further developed, normatively, on the basis of the work of Karl Polanyi and adopted to critically assess the structural rationales that are developed within internal market adjudication, which the thesis approaches as a separate field of social ordering within the European Union. Thus, social legitimacy is developed as a requirement that perceives the legitimacy of internal market law on the basis of the extent to which it can respond and integrate social practice and values. On this point the thesis finds that the internal market lacks a sufficiently developed rationale or "common language" that is able to address the normative concerns of social legitimacy. Societal realities are often valued within a metric that risks doing violence to potentially genuine and worthwhile aspects of Member States' 'social spheres'. The thesis develops that the normative claims of social legitimacy are best addressed on the basis of a rationale of mutual responsiveness, which is considered a necessary but underdeveloped element of the constitutional form and social purpose of the internal market that is implicit in the constitutional theory of transnational effects. From a perspective of mutual responsiveness, the social purpose of the internal market is not to condition choices that necessarily require the market to trump the social sphere - or the opposite- to allow the social to necessarily trump the market. Mutual responsiveness advances a more holistic approach that conceives the market and the social, literally, as 'communicating vessels'. The normative concerns of social legitimacy and the potential of mutual responsiveness to address these normative claims are the central and connecting elements throughout the thesis.
Keywords: Commercial law; European Union countries; Free Trade; Trade regulation

Developing efficient dispute resolution solutions for international commercial disputes: ways to address concerns associated with the combined use of mediation and arbitration by the same neutral - Nigmatullina, Dilyara (The University of Western Australia, 2016)
Securing fast, inexpensive and enforceable redress is vital for the development of international commerce. In a changing international commercial dispute resolution landscape, the combined use of mediation and arbitration, and particularly a combination where the same neutral acts as a mediator and an arbitrator (same neutral (arb)-med-arb), has emerged as a dispute resolution approach offering these benefits. However, to date there has been little agreement on several aspects of the combined use of processes, which the literature often explains by reference to the practitioner’s legal culture. There is a heated debate in the international dispute resolution community as to whether it is appropriate for the same neutral to conduct both mediation and arbitration. When the same neutral acts as a mediator and an arbitrator, caucuses become a primary concern. This is largely due to the danger that an arbitrator will appear to be, or actually be biased, and the risk that the process may offend the principles of due process.A review of the literature shows that the combined use of mediation and arbitration raises more questions and concerns than it offers answers and solutions. This thesis proposes remedies for this situation. The purpose of this thesis is twofold. First, to investigate ways to address concerns associated with the same neutral (arb)-med-arb, which should allow parties to benefit from time and cost efficiencies of the process and the ability to obtain an internationally enforceable result. Second, to examine whether the perception and use of the same neutral (arb)-med-arb varies depending on the practitioner’s legal culture. The research involved an analysis of legal sources complemented by a two stage empirical study conducted through questionnaire and interview.The thesis identifies three major ways to address concerns associated with the same neutral (arb)-med-arb: 1) the involvement of different neutrals in combinations, 2) procedural modifications of the same neutral (arb)-med-arb, and 3) the implementation of safeguards for using the same neutral (arb)-med-arb. It demonstrates that not all of these ways will achieve the goals of fast, inexpensive and enforceable dispute resolution. The results support the conclusion that the perception and use of the same neutral (arb)-med-arb varies throughout the world depending on the practitioner’s legal culture. This and other factors ultimately affect the choice of ways to address concerns associated with the same neutral (arb)-med-arb. Further to these significant results, the thesis argues that the same neutral (arb)-med-arb is not a ‘one-size-fits-all’ process. Other combinations discussed in the thesis require more attention from practitioners and academics.This thesis makes a substantial and original contribution to the understanding of combinations in international commercial dispute resolution in four ways. First, the empirical study is the first study to investigate specifically the use of combinations in international commercial dispute resolution. Its results shed light on the use of combinations in international commercial dispute resolution, their common triggers, the way in which the processes are combined most frequently, and the most common forms of recording the outcome of combinations. Second, the thesis synthesises existing ways of addressing concerns associated with the same neutral (arb)-med-arb in international commercial dispute resolution and groups them into the three major categories mentioned above. Third, having identified that there is scope for a more widespread use of combinations in international commercial dispute resolution, the thesis provides recommendations on how to enhance the use of combinations. Finally, the thesis highlights several areas where future research is needed.
https://research-repository.uwa.edu.au/en/publications/developing-efficient-dispute-resolution-solutions-for-internation The UWA Profiles and Research Repository
Keywords: Arbitrage; Arbitragem; Arbitration; Combined processes; Commercial; Dispute resolution (Law); International; Legal culture; MARD; Mediación; Mediation; Mediação; Médiation; Same neutral

The Regulation of Promotional Competitions in South Africa - Strachan, Daniel Petrus (University of Pretoria, 2016)
Promotional competitions are competitions in which prizes are awarded by lot or chance in order to promote goods or services. Due to the chance element, these competitions are often categorised as lotteries or gambling. Initially, South African legislation did not make provision for the running of promotional competitions, but this situation changed when the Lotteries Act, 1997 came into force. Currently, promotional competitions are regulated by the Consumer Protection Act, 2008 (CPA). This thesis examines the regulation of promotional competitions in South Africa. It commences with a background discussion, which touches on the relevant terminology and some sociological aspects. It then considers the consequences of gambling and the need for and nature of regulation, and deals with the marketing and consumer protection contexts. This is followed by a brief overview of the global and South African history of gambling, lotteries and promotional competitions, which includes a discussion of South African case law. Foreign law relating to promotional competitions in New Zealand and Great Britain is explored in order to compare this to the South African position. This is followed by an examination of the current regulation of promotional competitions in South Africa, including a discussion regarding the interplay between the CPA and the Lotteries Act and a detailed analysis of the CPA’s provisions. The self-regulation of promotional competitions is discussed as well. The concluding chapter of this thesis contains recommended solutions for the problems identified in the analysis of the relevant legislation.
URI: https://repository.up.ac.za/handle/2263/56056
Keywords: Competencia; Competition law; Concurrence (droit); Consumer law; Droit de la consommation

Water as public property : a parallel evaluation of South African and German law - Viljoen, Germarié (North-West University, 2016)
With the introduction of the National Water Act 36 of 1998 (NWA) in South Africa’s water regulatory regime, the foundations of the country’s existing water law system changed fundamentally. The NWA was promulgated with the primary aim to reform the law relating to water resources. The preamble to the NWA states that water is “a scarce natural resource that belongs to all people.” Section 3 of the NWA continues along similar lines and stipulates that all water use rights fall under the centralised control of the state or public trustee to inter alia improve the distribution, management, use, conservation and equality of access to this scarce resource. Statutory transformation of this nature has inevitable and important legal implications. It has for example been argued that the changed system has brought about a reallocation and redefinition of property rights to natural resources; a transformation which will inevitably impact the nature, form, extent, limits and protection of access and use rights that can be acquired in water as a natural resource. In an effort to understand the extent of the legal transformation brought about by the concept of public trusteeship, this thesis considers the impact of the concept in the broader South African water law context. The concept of public trusteeship is a novel concept in South African jurisprudence, without established links to existing principles of law. This thesis subsequently focuses on how and to what extent the German property law concept of őffentliche Sache may inform the development and interpretation of the South African concept of public trusteeship as entrenched in the NWA. Consequently, this thesis commences with an exposition of information on the idea of property and the relevance and importance of the different property rights regimes against which both the South African and German property regimes can be evaluated. This is followed by a description of the South African property rights paradigm and its different property concepts. The research introduces a novel take on the discussion of the regulation of rights in natural resources in South Africa, namely a “stewardship ethic of public trusteeship”. As a stewardship ethic could potentially influence the regulation of property in natural resources and even perhaps the property regime within which water as natural resource is regulated in South Africa, the next section of the research proceeds with a historical account of the South African water law dispensation. Although the historical review indicates that the concept of public trusteeship is not part of South Africa’s common law heritage, some of its principles find application in the common law concept of res publicae. The conclusion is that the concept of public trusteeship does not merely (re-) introduce the res publicae concept into the South African water realm. The concept of public trusteeship is a novel concept that was statutorily introduced into the South African water regulatory framework in terms whereof “ownership” of water resources vests in the national government, and are consequently administered on behalf of the nation and generations yet to come. A separate section of the research analyses and contextualises the concept of őffentliche Sache as it functions in German law to offer new insight into the implications that the statutorily introduced concept of public trusteeship might have on water as property and the property regime within which water is regulated in South Africa. This guides the study to the next section of the research, which illustrates that the concept of őffentliche Sache is at the basis of the German water regulatory framework. The conclusion of the study proposes an understanding of the concept of public trusteeship in South Africa based on lessons learned from the German concept of őffentliche Sache.
Keywords: Constitutional property; German water regulatory framework; National Water Act; Property; Property rights regime; Public property; Public trusteeship; Res publicae; Water rights; Öffentliche Sache

Determinants and Growth Impact of Foreign Direct Investment in West African Economic and Monetary Union (1980-2010) - Laleye, Abimbola Nicaise (University of Lagos, 2015)
This study’s aim is to assess the trends and the macroeconomic determinants of FDI and to estimate its impact on economic growth, using West African Economic and Monetary Union (WAEMU) and its member countries (Benin, Burkina Faso, Cote d’Ivoire, Guinea Bissau, Mali, Niger, Senegal and Togo) as a case study. In order to achieve the objectives of the current study, the panel cointegration method is employed for the period that expands from 1980 to 2010. This method is constituted of three steps: first, running the panel unit root tests; secondly, run the panel cointegration tests to establish a long-run relationship between the included variables; and thirdly, to run the two models of this study. All this is supplemented by Granger causality test in order to determine the direction of causality between the two variables of FDI and economic growth in WAEMU and its member countries. The findings show that: (i) the variables market size, trade openness, human capital, infrastructure development, financial development, macroeconomic stability, exchange rate and political stability are significant determinants of FDI in WAEMU and in its member countries; (ii) not all the variables affect the same way FDI inflows in WAEMU and in each one of the WAEMU member countries; (iii) there is a positive relationship between FDI and economic growth which implies that FDI stimulates economic growth in WAEMU and its member countries; (iv) this study finds a causality relationship between FDI and economic growth, which runs from FDI to economic growth not from economic growth to FDI: meaning there is a unidirectional linkage between FDI and economic growth in WAEMU; (v) the study also finds that at cross-sectional level, FDI only causes economic growth, not the opposite: this implies that there is also a unidirectional linkage between FDI and economic growth in each WAEMU member country and its runs from FDI to economic growth. Therefore, it is important that the enabling environment should always be provided not only in WAEMU but also in its member countries in order to attract more foreign direct investment and further to stimulate the xiv country’s economic growth. Thus, this study recommends the followings, at the local or country level: first, improvement of the image of WAEMU countries. Rapid economic growth could result in an increase in foreign direct investment inflows, not only in WAEMU but in each one of the WAEMU member countries. But, this has to be done with more attention given to conditions (i.e. key variables) such as fair trade policy with abroad, development of infrastructure and financial system, availability of human capital through a sound human training and formation. At regional or WAEMU level, governments should set up policy that guaranties macroeconomic stability and political stability.
https://ir.unilag.edu.ng/handle/123456789/4079
Keywords: Co-integration; Determinants of FDI; FDI; Foreign direct investment; WAEMU; West African Economic and Monetary Union

International Standards for Commercial Mediators - To, Christopher (University of Stirling, 2015)
This paper talks about the international standards for commercial mediators. It introduces the standards of eight different jurisdictions and afterwards, evaluates whether there should be one accrediting standard for all international commercial mediators. In the introduction chapter, the paper talks about the problems with the current legal system and then explains the growth of mediation in today’s society. By discussing the nature and practice of mediation, whether mediation should be compulsory or voluntary in light of Article 6 of the European Convention on Human Rights, rationale of the various jurisdictions covered, the paper then talks about the attributes that make a good mediator as well as the accreditation and training of mediators. From chapter two to chapter nine, the paper focuses on eight jurisdictions in which mediation is firmly enshrined within one legal culture to those that are just embarking on the concept (namely Australia, New Zealand, Indonesia, Malaysia, India, Hong Kong, California and Canada). Each chapter talks about the developments of commercial mediation, law and institutions as well as training and accreditation of mediators within their respective jurisdictions. In the concluding chapter, it discusses whether there should be one accrediting standard for international commercial mediators by exploring the advantages and disadvantages of having one accrediting standard as well as the author’s analysis and point of view on the subject.
Keywords: Commercial mediator; International standards; Mediation; Mediator; Médiateur

Disputes in the Digital era : the evolution of dispute resolution and the model ODR system - Lekkas, Zissis (Université Toulouse 1 Capitole, 2015)
Le sujet de la thèse est la résolution en ligne des litiges (ODR) et l'objectif de la thèse est de proposer un modèle de système ODR basé sur l'expérience du mouvement de résolution des différends. ODR n’est pas un phénomène isolé de ces derniers temps, mais en raison de l'évolution des conflits et la résolution des différends. Initialement, les différends survenus entre les parties à la proximité géographique et pour laquelle les tribunaux traditionnels sont le principal moyen de résolution. Cependant, comme les gens ont commencé à voyager de plus grandes distances et de communiquer de loin, les conflits ont évolué comme ils ont augmenté en nombre, sont devenus frontière plus complexe et de plus en plus transversale. Résolution des différends évolués en règlement des différends parallèle et alternatif (ADR) a été utilisée. Cependant, les conflits ont évolué une fois de plus quand le monde est entré dans l'ère numérique. Non seulement les conflits sont devenus encore plus transfrontalier, mais de nouveaux conflits sont apparus qui proviennent exclusivement dans le cyberespace. Afin de satisfaire aux exigences de l'ère numérique, la résolution des différends fit sortir le concept de l'ODR. ODR est née de la combinaison de l'ADR et de la technologie de l'information et de la communication (TIC) de l'ère numérique. D'autres moyens de règlement des différends ont été transférés dans le monde virtuel et ont donné naissance à la résolution des litiges en ligne. ADR et ODR sont examinés largement, et l'examen comprend leurs concepts, leur origine, les principales formes de négociation, de médiation et d'arbitrage et leurs équivalents en ligne, ainsi que leurs avantages et leurs inconvénients. La thèse illustre l'évolution des conflits et la résolution des différends de l'ère analogique, lorsque la résolution des différends était face à face, à l'ère du numérique, lorsque les différends sont réglés dans le cyberespace. Il démontre que l'ODR est une nécessité de l'ère numérique, mais aussi qu'il a le potentiel pour être un moyen révolutionnaire, efficace et réussi à résoudre les différends; d'une manière qui sera l'avenir de la résolution des différends. Sur la base de l'expérience accumulée par l'examen de l'évolution de la résolution des différends et sur ? Lla base des conclusions tirées, la thèse formule une proposition pour le système ODR. La thèse décrit le système ODR, de son processus en trois étapes et la nécessité de l'arbitrage en ligne, sur le réseau ODR, la régulation du système ODR, l'architecture technologique des fournisseurs ODR, leur financement, ainsi que les mesures nécessaires de la sensibilisation et la confiance afin que ODR remplit son plein potentiel.
Keywords: Arbitrage; Arbitragem; Arbitration; Commerce électronique; Modes électroniques de règlement des litiges; Online Dispute Resolution; Système ODR

Economic and Empirical Analysis of Contractual Dispute Resolution - Miller, Samuel Mark (Vanderbilt University, 2015)
This dissertation uses Python-based programming to retrieve and analyze a sample of approximately 400,000 material contracts that companies filed with the Securities and Exchange Commission between 2001 and 2013, focusing on the dispute resolution mechanisms specified therein. The first chapter considers the effectiveness of two state-level efforts to attract dispute resolution business, examining how specialized “business courts” and the Revised Uniform Arbitration Act affected arbitration and choice-of-forum clause use in these material contracts. The second chapter examines whether and how companies and executives “customized” their arbitration clauses in response to Internal Revenue Code Section 409A, which increased both the likelihood and the complexity of potential disputes between these parties. The third chapter considers how companies and executives responded when the Supreme Court overturned the Ninth Circuit’s anomalous refusal to enforce employment-related arbitration clauses. Each chapter finds that contracting parties adjusted their dispute resolution provisions in response to the policy change(s) at issue – suggesting that for the sophisticated parties in my dataset, these provisions receive careful thought and are not mere “boilerplate.”
URI: http://hdl.handle.net/1803/11146
Keywords: Arbitrage; Arbitragem; Arbitration; Contracts; Dispute resolution; Econometrics

Arguments in favour of reconceptualising the fair and equitable treatment (FET) standard in international investment arbitration : developing countries in context - Islam, Rumana (University of Warwick, 2015)
The Fair and Equitable Treatment (FET) standard is the most important and, because of its flexible nature and its status as a ‘catch-all’ provision, most controversial investment protection standard in international investment treaties. The standard imposes the most far-reaching obligation of any aspect of such treaties. This thesis’ core contention is that the current investment tribunals’ interpretation of the FET standard prioritises the interests of foreign investors and neglects the perspectives of host developing countries. Therefore there is a pressing need to reconceptualise the interpretation of the FET standard. In service to depicting the perspectives of host developing countries, this thesis advances an understanding of classifications such as ‘developing’ and ‘developed’ that reflects the issues and challenges that these countries face in the investment dispute context, such as their lack of resources, administrative capacity, technology, and infrastructure, as much as the economic and social level of development international organisations generally emphasise in their classifications. It addresses socio-political circumstances such as political instability, social unrest, conflict and its aftermath, social and political transition, and economic crises and their impact on host developing countries in the investment dispute context. Through a detailed study of the approaches they have taken to such issues in their interpretation of the breach of FET standard in disputes involving host developing countries, it shows that current investment tribunals have taken inconsistent and inadequate approaches to the issues host developing countries face. It argues that a reconceptualised interpretation of the FET standard which acknowledges the developmental issues and challenges this thesis has identified would accommodate the needs of the host developing countries while continuing to give reasonable protections to foreign investors and therefore serve the needs of the system as a whole.
URI: http://webcat.warwick.ac.uk/record=b2766071~S1
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration and award; Developing countries; Dispute resolution (Law); Equity; Foreign investment; Free trade agreemtment; International business enterprises; Investments; Unfair competition

The Economics of tort law applied to Internet intermediaries : example of intellectual property - Lefort, Marine (École nationale supérieure des mines de Paris, 2015)
La responsabilité des intermédiaires d'Internet fait débat dans un univers numérique de plus en plus complexe. Les intermédiaires offrent des services en ligne. Ils créent ou facilitent des transactions entre des parties tierces (hébergement, e-commerce, fournisseurs d'accès…). A la fin des années 1990, un consensus s'est établi sur l'instauration d'une responsabilité limitée pour ces acteurs, dans le but de favoriser leur développement ainsi que celui d'Internet par des externalités croisées. Cependant, l'apparition régulière de nouveaux usages a induit des externalités négatives affectant certains agents économiques. La multiplication récente de décisions de jurisprudence parfois contradictoires, en particulier dans le domaine de la propriété intellectuelle, vient désormais remettre en cause cette exemption. Elle fait naître un risque juridique pour les intermédiaires d'Internet. Ces-derniers doivent alors prendre en compte ce nouveau contexte dans leurs modèles d'affaires. Notre recherche étudie les comportements spécifiques que la responsabilité des intermédiaires d'Internet engendre à travers l'exemple de la propriété intellectuelle. En premier lieu nous décrivons l'évolution historique de cette responsabilité. Nous développons ensuite un modèle théorique simple qui explore l'influence du risque légal dans un contexte de concurrence entre un intermédiaire et un ayant droit du copyright. Enfin nous étendons ce modèle de concurrence aux différents comportements de protection que peuvent choisir les intermédiaires.
Keywords: Competencia; Competition law; Concurrence; Economie du droit; Intellectual property; Intermédiaires d’Internet; Internet; Internet intermediaries; Law and Economics; Propriedade intelectual; Propriété intellectuelle

Joint Development of Offshore Polar Oil and Gas Resources and the United Nations Convention on the Law of the Sea - Abrahamson, John (Australian National University, 2015)
This thesis examines whether the establishment of Joint Development Zones (JDZs) for the development of offshore oil and gas resources in the Arctic and Southern Oceans can effectively resolve competing continental shelf and outer continental shelf (OCS) claims arising under the provisions of Article 76 of the United Nations Convention on the Law of the Sea (LOSC). One of the effects of global warming has been increased interest in oil and gas activity in the Arctic region, however there is significant concern as to the related environmental risks. The Environmental Protocol to the Antarctic Treaty currently suspends exploration for state parties for oil and gas in the Southern Ocean, however current exploration has been reported. A JDZ may be defined as an inter-governmental arrangement of a provisional or permanent nature, designed for joint exploration and exploitation of the hydrocarbon resources of the sea-bed. JDZs are generally based on agreements to suspend sovereignty claims and share offshore oil and gas in the JDZ region. The thesis was prepared to contribute to the prevention of potential international conflicts over offshore oil and gas resources. State claims may be based on historic claims, interpretation of treaties, and LOSC exclusive economic zone (EEZ), continental shelf, and OCS delimitation provisions. LOSC provides dispute resolution alternatives, including referral to the International Court of Justice and international arbitration. A significant number of states have, however, preferred to adopt JDZ agreements. The methods used for the thesis included analysis of LOSC maritime delimitation provisions, existing JDZ agreements, the terms of model JDZ agreements, and analysis of current Arctic and Southern ocean maritime boundary disputes. The principal thesis conclusions are: - JDZs can resolve resource disputes as demonstrated by the existing international state practice in adopting JDZs. JDZ regimes are not a universal panacea, however, and successful JDZs are based on the continued political support of the respective states; - LOSC maritime boundary delimitation provisions may not resolve boundary disputes, which can arise due to issues including conflicting sovereignty of land territory; - Specific Arctic and Southern Ocean disputed regions have similar characteristics to existing JDZs. JDZs may therefore potentially apply to resolve these disputes; - JDZs can potentially provide solutions for disputed boundaries, such as between United States/Canada (Beaufort Sea), United States/Russia (Bering Sea) in the Arctic Ocean region, and between United Kingdom/Argentina/Chile in the Southern Ocean; - JDZ should be adapted to better protect and preserve the marine environment, and to provide a significant liability regime similar to the Greenland regime; - JDZs should support a framework of regional governance, including Arctic Council or Antarctic Treaty representation in the respective JDZs; and - Potential game changing events may affect the use of JDZs in the future, including political and technological developments, and significant oil and gas discoveries. The result of the thesis conclusions is to prove the hypothesis that JDZs can effectively resolve resource conflicts in the Arctic and Southern Ocean regions.

The Vienna Sales Convention and private international law - Wethmar-Lemmer, Marlene Muriel (University of Johannesburg, 2015)
The United Nations Convention on Contracts for the International Sale of Goods (the CISG or the Vienna Sales Convention) was adopted at a diplomatic conference of the United Nations held in Vienna during 1980. The Convention came into force on 1 January 1988. According to its preamble, the Convention is based on the premise that “the adoption of uniform rules which govern contracts for the international sale of goods and take into account the different social, economic and legal systems would contribute to the removal of legal barriers in international trade and promote the development of international trade”. The CISG has proven to be successful in its endeavour and currently has 74 member states representative of all legal traditions. As an international convention, the CISG has been lauded for its “simplicity, practicality and clarity”. Schlechtriem observed that the CISG has now gained worldwide acceptance. It has even been stated that the CISG has established a “world law on international sales” and that it has influenced several domestic sales laws. It is submitted that the CISG constitutes an important component of modern international commercial law or of the modern lex mercatoria. Therefore, a study that aims to establish a better understanding of the scope and functioning of the CISG and its relationship with domestic law, is of special relevance for the international business and legal community. The two basic methods of the unification of law, ie the unification of substantive law and the unification of private international law, have both been utilised in the field of the international sale of goods. The CISG is the most notable example of first mentioned method of unification.
Keywords: CISG; Choice of law clause; Conflict of laws; Contracts for the international sale of goods; Convention de Vienne; Export sales contracts; Lex mercatoria; Party autonomy; Sales; UNIDROIT Principles

Employee participation and voice in companies: a legal perspective - Botha, Monray Marsellus (North-West University, 2015)
Recently, South African company law underwent a dramatic overhaul through the introduction of the Companies Act 71 of 2008. Central to company law is the promotion of corporate governance: companies no longer are accountable to their shareholders only but to society at large. Leaders should direct company strategy and operations with a view to achieving the triple bottom-line (economic, social and environmental performance) and, thus, should manage the business in a sustainable manner. An important question in company law today: In whose interest should the company be managed? Corporate governance needs to address the entire span of responsibilities to all stakeholders of the company, such as customers, employees, shareholders, suppliers and the community at large. The Companies Act aims to balance the rights and obligations of shareholders and directors within companies and encourages the efficient and responsible management of companies. The promotion of human rights is central in the application of company law: it is extremely important given the significant role of enterprises within the social and economic life of the nation. The interests of various stakeholder groups in the context of the corporation as a “social institution” should be enhanced and protected. Because corporations are a part of society and the community they are required to be socially responsible and to be more accountable to all stakeholders in the company. Although directors act in the best interests of shareholders, collectively, they must also consider the interests of other stakeholders. Sustainable relationships with all the relevant stakeholders are important. The advancement of social justice is important to corporations in that they should take into account the Constitution, labour and company law legislation in dealing with social justice issues. Employees have become important stakeholders in companies and their needs should be taken into account in a bigger corporate governance and social responsibility framework. Consideration of the role of employees in corporations entails notice that the Constitution grants every person a fundamental right to fair labour practices. Social as well as political change became evident after South Africa's re-entry into the world in the 1990s. Change to socio-economic conditions in a developing country is also evident. These changes have a major influence on South African labour law. Like company law, labour law, to a large extent, is codified. Like company law, no precise definition of labour law exists. From the various definitions, labour law covers both the individual and collective labour law and various role-players are involved. These role-players include trade unions, employers/companies, employees, and the state. The various relationships between these parties, ultimately, are what guides a certain outcome if there is a power play between them. In 1995 the South African labour market was transformed by the introduction of the Labour Relations Act 66 of 1995. The LRA remains the primary piece of labour legislation that governs labour law in South Africa. The notion of industrial democracy and the transformation of the workplace are central issues in South African labour law. The constitutional change that have taken place in South Africa, by which the protection of human rights and the democratisation of the workplace are advanced contributed to these developments. Before the enactment of the LRA, employee participation and voice were much-debated topics, locally and internationally. In considering employee participation, it is essential to take due cognisance of both the labour and company law principles that are pertinent: the need for workers to have a voice in the workplace and for employers to manage their corporations. Employee participation and voice should be evident at different levels: from information-sharing to consultation to joint decision-making. Corporations should enhance systems and processes that facilitate employee participation and voice in decisions that affect employees. The primary research question under investigation is: What role should (and could) employees play in corporate decision-making in South Africa? The main inquiry of the thesis, therefore, is to explore the issue of granting a voice to employees in companies, in particular, the role of employees in the decision-making processes of companies. The thesis explores various options, including supervisory co-determination as well as social co-determination, in order to find solutions that will facilitate the achievement of employee participation and voice in companies in South Africa.
Keywords: CSR; Collective bargaining; Corporate Social Responsibility; Corporate governance; Corporate law; Disputes; Economic democracy; Employee participation; Empowerment; Fairness; Industrial democracy; Joint decision-making; Labour law; Matters of mutual interest; Shareholders; Social justice; Stakeholders; Workplace forums

Convergence of international trade and investment law in practice : how should investor-state arbitral tribunals engage with trade norms? - Chevry, Jonathan (European University Institute, 2015)
This thesis aims to provide an analytical framework to which investor-State arbitral tribunals can refer in cases where international trade law is invoked. The starting point of the present study is the trend in commentary on international trade and investment law, which makes the argument that international trade and investment law should be reconciled due to the clear "convergence" between (some of) their constitutive elements. This convergence argument is not misguided: there are similarities between the underlying principles of global trade and investment and, as such, a better coordination of these principles would be helpful for several reasons. Such reasons include legal certainty, reduction of transaction costs, better coherence in the operation of international agreements that now combine both trade and investment provisions, to name a few. However, no matter how reconcilable or converging the two disciplines may be, their enforcement mechanisms are structurally different and are likely to remain so even if the reforms towards a modernization of the investment dispute settlement (currently discussed at the EU policy level) are eventually implemented in the near future. In light of this last point, it is possible to claim that integration between trade law and investment law will only have limited or even negative effects if the trade and investment adjudicators continue to exercise their functions in an isolated manner, without taking cognizance of (i) the norms contained in the other discipline and (ii) the other adjudicator's scope of authority. Effective convergence of trade and investment entails a two-way process pursuant to which one adjudicator can use (i.e. take into account, refer to, apply, interpret and enforce) the law of the other and vice-versa. The thesis envisages one of the two dimensions of this process, namely the use of trade law by the investment adjudicator. Looking into the details of the convergence argument, the role of investment dispute settlement mechanism and the use of trade norms over the past two decades by litigants and arbitrators, the present study identifies both the legal techniques and obstacles these actors shall apply or go beyond in order to use trade norms in the most appropriate way and, more importantly, benefit from this use.
Accepted: 2015-12-09T14:30:56Z
Keywords: Arbitrage; Arbitragem; Arbitration; Foreign investment; Foreign trade regulation; International commercial arbitration

A comparative reappraisal of debt relief measures for natural person debtors in South Africa - Coetzee, Hermie (University of Pretoria, 2015)
The purpose of this thesis is to do a comparative reappraisal of debt relief measures available to natural person debtors in the South African insolvency law. Although the broader South African natural person insolvency system currently includes three statutory debt relief procedures, namely, the sequestration procedure regulated by the Insolvency Act 24 of 1936, the administration order procedure in terms of the Magistrates Courts Act 32 of 1944 and the debt review procedure found in the National Credit Act 34 of 2005, not all natural person debtors have access to the system. The majority of this marginalised group are debtors with no income and no assets (the so-called No Income No Asset (NINA) debtors). Also, only one measure provides real debt relief in the form of a statutory discharge of debt. Furthermore, the existing measures have developed in a haphazard fashion which has led to a multiplicity of procedures, regulators and forums that resulted in ineffectiveness, inequality and uncertainty. The larger system therefore lacks proper policy considerations. This thesis provides the reasons for reform by, amongst others, arguing that the present situation is unconstitutional as it unreasonably and unfairly discriminates against the NINA group of debtors in particular. It measures the broader South African system against internationally accepted principles of efficient and effective natural person insolvency regimes. In this regard it is found that the system as a whole is seriously deficient. With reference to international principles and guidelines as well as suitable attributes found in foreign jurisdictions, the thesis concludes with suggestions for real law reform. Both substantive and procedural recommendations are made.
URI: https://repository.up.ac.za/handle/2263/52372

A Comparative Study on Customs Tariff Classification - Colesky, Theo (University of Pretoria, 2015)
The field of customs is commonly referred to as that of imports and exports. It is perceived as a maze of processes, procedures, and forms required to enable a customs administration to perform their wide range of responsibilities. One of the responsibilities of a customs administration is the collection of duties, which necessitates classification of the goods in question. This study sets out to determine the extent of customs control in relation to tariff classification in South Africa. The starting point is the establishment of the foundations of customs, both internationally and in South Africa. After origin and valuation, tariff classification is the third technical customs-related focus area. An analysis of the responsibilities of the customs administration in South Africa confirms the importance of revenue collection and, subsequently, tariff classification. As a result of South Africa’s membership of the World Customs Organization, specific obligations in relation to tariff classification are incurred. The implementation and application of the international provisions are considered and compared in South Africa, Australia, and Canada. Not only is South Africa’s existing legislation considered, but also two new Acts. It is found that despite similarities in the implementation of the Harmonized System Convention into the legislation of the three countries, South Africa’s existing legislation makes the most detailed provision for the Harmonized System and its aids. This is based on the finding that the legislation in Australia and Canada, as well as the two new Acts in South Africa, do not have the same comprehensive provisions. A critical review of the varying processes of classification in the three countries suggests that more suitable and effective processes could be implemented in South Africa. In addition, a synopsis of some of the principles developed in case law is provided and compared. In relation to facilitation, the access to relevant information and the adequacy thereof, as well as the availability of rulings, are considered. Differences in the approach to dispute resolution in the three countries are furthermore provided. Proposals are made to address the discrepancies in the implementation and application of the legislation, the process of classification, the principles developed in case law, the enhancement of related guides, the publication of tariff classification rulings, and the extent of facilitation and dispute resolution. Finally it is recommended that an independent and expert tribunal is established to adjudicate technical customs matters.
URI: https://repository.up.ac.za/handle/2263/42838
Keywords: Comparative study; Customs tariff classification

The Investment Treaty Regime and Public Interest Regulation in Ghana: Perspectives in Constitutionalism and General International Law - Dagbanja, Dominic (University of Auckland, 2015)
There is extensive literature on conflict of legal norms and interests in international investment law. The dominant discourse is on the implications of treaty-based investment protection for sovereign regulatory autonomy. Mainstream scholarship critical of the scope and effect of investment treaties has taken the legal status of these treaties for granted. Little systematic attention has been paid to the capacity of states to make investment treaties and the obligations states can or cannot agree to under those treaties in light of their public interest obligations. Yet, this issue is of fundamental importance for three reasons. First, the case for states’ regulatory autonomy arises out of their primary duty to regulate in the public interest. This duty has its legal justification in national constitutions and international law. Second, treaty obligations are founded on the existence of legal norms necessary for the treaty to come into existence and which define the juridical consequences attached to the conclusion of the treaty. These matters are also determined by national constitutions and international law. Third, the limitations inherent in state-specific defences in international investment disputes settlement compel a proactive rethink of the conclusion of investment treaties and how they are interpreted. The question this thesis assesses with reference to Ghana then is: does a state that is legally required to act both under the terms of its constitution and international law in the public interest have the capacity to conclude investment treaties that expressly prevent or abridge the exercise of its public interest regulatory powers, and how should treaties adopted in breach of these obligations be interpreted? To address this question, three areas of public interest regulation that have featured prominently in investment arbitration serve as case studies: the jurisdiction of municipal courts, environmental protection and development policy. Based on the impact and potential limitations of standards of investment protection on these areas, the thesis argues that some treaties are incompatible with the public interest regulation obligations of Ghana under the Constitution and international law. The core proposition of the thesis is that the legal source and public purpose of the State’s powers prevent it from concluding agreements that directly prohibit public interest regulation or indirectly achieve that effect. Accordingly, the thesis proposes that the express and implied limitations on the duty to regulate in the public interest placed on investment treaty making powers of the State must inform the making of investment treaties and their interpretation. By its approach, this thesis establishes a principled basis for reflection on the limits to the State’s capacity to conclude investment treaties and on how they should be interpreted.
http://hdl.handle.net/2292/28285
Keywords: Ghana; Investment treaty; Investments; Public interest

The Disclosure and Use of Social and Environmental Information by Libyan Banks - Elsakit, Omer M (Griffith University, 2015)
There is increasing interest in social and environmental issues throughout the world, especially in developed countries, where governments, organizations, and society well recognise the impact of business activities on the environment and society. Consequently, companies have potentially no alternative but to behave in a responsible manner, socially and environmentally, and to prove this by disclosing information about their related conduct. In this regard, banks play two important roles: first, as providers of social and environmental information in much the same manner as nonfinancial companies; and second, as providers of finance, by encouraging—if not obliging—bank customers to consider society and the environment in their bank-financed projects. Banks fulfil the latter role by requiring social and environmental information from companies when making lending decisions. Only a few Libyan studies have examined social and environmental issues in relation to economic activity, and these have generally revealed low levels of disclosure practice by organisations, including banks, in these areas. In addition, many changes have taken place in the Libyan economy and banking sector in recent years, including the establishment of a market exchange; decreased government participation in economic activities; and increased growth of the private sector that results, especially in the banking sector, with the entrance of foreign investors. These changes have placed a new emphasis on bank operations and the participation of banks in the Libyan economy. Thus, studying Libyan banks, in terms of their role in the environment and society, has attracted growing interest. As such, the core objective of this thesis has been to investigate the position of Libyan banks in relation to social and environmental issues and disclosure by considering their dual role as both providers and users of such information.
Keywords: Banks and banking; Environmental policy; Finance and environment; Libya

A level playing field for "open skies": the need for consistent and harmonized regulation of Aviation - Fitzgerald, P. Paul (McGill University, 2015)
Various initiatives by regulators in different jurisdictions over the past two decades have completely reshaped the airline industry in ways that were unimaginable in 1992. From an industry dominated by Pan Am and Trans World Airlines (TWA), and newly privatized airlines such as British Airways, today's industry is dominated by government-owned intercontinental airlines based in the Middle East and carrying passengers the majority of whom are ultimately destined for States other than the States where the airlines are based. Insufficient thought has been given to whether this evolution is desirable, whether it involves profound competitive distortions or whether it is in the public interest that the majority of Australians visiting Europe are carried by an airline based in neither jurisdiction or that a similar claim might be made with respect to traffic between South Asia and the Americas. This thesis examines the events that have reshaped the international aviation industry over the two decades between 1992 and 2012. It will critically analyze the major developments and the regulatory responses and highlight some of the incompatible and disjointed regulations that are in effect at either end of international routes. It ultimately proposes that Australia, Canada, the European Union (EU), New Zealand and the United States (US) form a small international organization, to be known as the Open Skies International Aviation Block (OSIAB). OSIAB would be based on expanding the membership of the US-EU Joint Committee foreseen in the 2007 US-EU Open Skies Agreement and expanding its scope to cover every aspect of the regulation of international commercial aviation. This thesis argues such a forum is necessary to ensure that regulations in different countries are aligned so that competitive distortions potentially caused by regulatory disharmony are minimized, thus allowing the international airline industry to compete on the level international playing field that so many international agreements have promised to create.
Identifier: https://escholarship.mcgill.ca/concern/theses/nz8062944
Keywords: Aviation; Aviation regulation; Transport aérien

The regulatory function of contract law : comparative law and economics approach - Gramcheva, Lyubomira (European University Institute, 2015)
This thesis challenges the traditional view of national contract laws as facilitative regimes and argues that contract law on the national level has been progressively re-oriented to perform an efficiency-driven regulatory function. To develop the argument the thesis studies the contract law remedial regime of two common law and one civil law jurisdiction – the US, England and Bulgaria, in two specific contracts – the sale-of-goods and the construction contract. The introductory chapter puts the main theme in context and outlines the project. Exploring the limits of promissory theory and neoclassical economics, the second chapter develops an innovative interdisciplinary methodology joining the new institutional economics with the comparative law method. The third, fourth and fifth chapters offer taxonomies of remedies, types of contracts and remedial effects to set the stage for a meaningful comparison across the different legal traditions. Since economic theory has advanced most in the study of incentives generated by damages, the third chapter focuses on the latter remedy and shows that the common law classification of damage measures (expectation, reliance, restitution), on which traditional law-and-economics accounts are based, can be applied to study a civil law jurisdiction like Bulgaria. Distinguishing discrete and long-term contracts and demonstrating that the differentiation between sale-of-goods and construction contracts in the compared national legal systems does not necessarily go along the lines of the discrete/long-term distinction in economics, the fourth chapter argues that the positive comparison should be made with an eye on the market for substitute performances even if the compared factual scenarios are classified under different legal categories in the different jurisdictions. For the uninitiated, the fifth chapter reconstructs and criticises the standard economic model rationalising damages as incentives. The final chapter applies the approach developed here to contractual termination. The exemplary analysis identifies trends in the compared legal systems and suggests that all of them converge in charging the termination remedy with a regulatory function. Finally, I generalise to make some bolder claims about contract law.
Accepted: 2016-01-11T14:07:16Z
Keywords: Contracts; Law and economics; Public law (Economic aspects)

International taxation of cross-border digital commerce - Kadikov, Artem (University of Oxford, 2015)
This thesis discusses jurisdiction to tax cross-border digital commerce. The primary objective is to consider the reasons for the erosion of jurisdictional links, or nexus, between countries and taxpayers' digital activities and evaluate possible solutions for addressing such nexus erosion. Whilst it is argued that digital commerce is impossible to ring-fence due to digital technologies transcending all industries, the main focus of this research is on automated business models as case studies for the broader tax issues applicable across the entire digital economy. Using cloud computing, online advertising and e-tailing models as examples of digital commerce in the narrow sense, this thesis demonstrates that the proxies for establishing jurisdictional nexus have become increasingly fluid, thereby challenging the traditional international tax regimes for profits and consumption taxation. Numerous policy solutions have been proposed in order to rectify nexus erosion, including global and territorial tax models. Unlike the previous research in this area, this thesis focuses on the nexus elements of such proposals and assesses their viability in the light of the wider Internet governance jurisprudence. Global tax solutions, such as global e-commerce taxes and formulary apportionment, are analysed in the context of the international governance regime for the technical Internet infrastructure. Territorial virtual tax solutions, such as virtual permanent establishments, withholding taxes and destination cash flow taxes, are considered in the light of the Internet jurisprudence on the 'effects' and 'targeting' nexus standards. It is argued that, given the lack of technical and political infrastructure, none of the proposed routes would be viable from a practical perspective in the near future. It is concluded, therefore, that a practical solution would involve retaining the traditional profits and consumption tax models, whilst testing a narrow version of the digital targeting nexus standard as a backstop anti-abuse measure. It is envisaged that the limited anti-avoidance provision would subsequently pave the way for a comprehensive long-term solution, as digitisation continues to transform global commerce.
Keywords: Corporations; Digital commerce taxation; Double taxation; E-commerce taxation; Electronic commerce; International Trade; International business enterprises; Internet governance; Internet jurisdiction; Internet taxation; Jurisdiction to tax; Taxation

Equal treatment as a principle to guide the regulation of intangibly transferred content : a case study on e-books using the examples of copyright exhaustion, reduced rates of VAT and fixed book pricing - Linklater, Emma (European University Institute, 2015)
Using e-books as a case study, this thesis considers whether the principle of equal treatment could play a role in driving more consistent and rational regulation of markets where content is available in both tangible and intangible formats. At present, although the content is the same, these formats are often subject to different rules. This difference in treatment has opened up discussions about whether current legal frameworks should be amended and in these discussions actors with very different standpoints have consistently invoked the language of equality to justify their varied stances. However, in these discussions there is no clear elaboration of what equality means or how it can be used, leading to abstract debates and eventually to arbitrary decisions. The thesis attempts to fill this gap by building a framework based on outcome equality to decide if intangible book formats should be treated ‘like’ tangible ones. It uses the objective underlying the existing rule as the standard for establishing likeness or difference and advocates that functional equality, rather than formal equality, is desirable because this takes account of the differences in the functionalities between content formats: Intangibility impacts on the functioning of the rule in question (e.g. quantitatively increased ease of circulation and copying) and it is only if these impacts can be neutralized that functional equality can be achieved. The framework is applied to the case studies of copyright exhaustion, reduced rates of VAT and fixed book pricing. These have been chosen in recognition of the range of decision-making powers between the national and EU levels in this cultural sector. Overall, the analysis shows that rationality can be inserted by using equal treatment as a guide, but that consistency is more difficult to achieve given the interaction between national and EU influences in the book market.
Keywords: Copyright; Cultural policy; Electronic publishing; European Union countries; Intellectual property

Establishing continental sovereignty in Africa: risk and opportunity in financial integration - lessons for Africa from a legal perspective - Ngwafor Ndeh, Edwin (University of Glasgow, 2015)
This thesis identifies and defines the new African sovereignty. It establishes a modern sovereignty in Africa hatched from the changing nature of sovereignty in which countries come together at various levels or grades of partial surrender of national sovereignty in order to work closer together for their mutual advantage and benefit. To this end, the narrative zooms in on the central issues within the realms of money matters whereby a new model of monetary sovereignty and monetary solutions is designed in an attempt to ease the recurring tensions and challenges of modern national sovereignty in the continent of Africa. As such, this discussion will offer a historical journey through the constitution of sovereignty, to the birth of the nation state and international public law. It develops the theory of the changing nature of sovereignty within the modern state and opens new lines of inquiry for Africa. In this regard, it draws from juxtaposing and mixing elements of regional and global financial integration as well as retaining national financial sovereignty features to form this new design which I dub continental sovereignty. At its core, the thesis will deal with the legal aspects that stem from the co-mingling of legal systems of nation states and communities at the regional and global levels within the context of financial integration. The argument is that the rule of law remains sacrosanct in monetary management. Effective financial integration is the result of properly structured and managed legal frameworks with robust laws and institutions whether at a national, regional or global level. However, the thesis reveals that in order to avoid undermining the progress of Africa’s financial integration project, any solution for Africa must be immersed within a broader global solution where development issues are addressed and resolved and Africa can form a more central part in all relevant international discussion fora. The work will expound these issues by applying them within a regional and global context, with the state of affairs in Africa forming the nucleus. This application consequently presents the six key themes of the thesis which will be considered therein. They are: a.) regional advantage: which exploits the possibilities of deeper and further financial integration between smaller communal arrangements; b.) regional risk and exposure: the extent to which this deeper form of financial integration can spiral out of control if effected too quickly and too ambitiously; c.) global advantage: which considers the merits of global financial integration and the influence exerted by financial laws on the global financial architecture; d.) global risk and exposure: which considers the challenges of global financial integration especially within the background of the Global Financial Crisis 2007-2008; e.) African challenge: which considers the extent to which this analysis impacts the African economic and financial integration agenda; and f.) development challenge: which examines the extent to which global development issues impact the African solution (continental sovereignty) and the need for any solution for the continent to be roped into a broader global solution within which Africa can form an important part. Even though the thesis requests an optimistic undertone on the progress made so far, it unearths the African problem of multiple national sovereignty and multiple overlapping regional sovereignty constituted as the ‘spaghetti bowl’ dilemma. As such, the unique contribution to knowledge on financial integration in Africa can be echoed in these words: Africa‘s financial integration agenda has had little success in authenticating a systematic and dependable legal framework for monetary management. Efforts made have been incomplete, substandard, and not carefully followed through particularly reflected in the impuissant nature of the judicial enforcement mechanisms. Thus, the thesis argues that, any meaningful answer to the problems dogging the continent is inter alia deeply entrenched within a new form of cooperative monetary sovereignty. In other words, the thesis does not prescribe the creation of new laws; rather it advocates the effective enforcement of existing laws.
Keywords: African Integration Project; Crisis response; Financial crisis; Financial integration; Regional systems; Regulation of financial markets; continental sovereignty

The sui generis and intellectual property protection of expressions of folklore in Africa - Nwauche, Enyinna Sodienye (North-West University, 2015)
This thesis articulates an optimum framework for the protection of expressions of folklore in Africa using a number of African countries – South Africa, Kenya, Ghana and Nigeria as case studies. This thesis argues that the existing sui generis and intellectual property rights protection in African countries are grossly inadequate in protecting expressions of folklore in these countries. An optimum framework for the protection of expressions of folklore would constitute a combination of the positive and negative protective model elaborated and implemented through a human and people's rights framework that recognises that communities that produce expressions of folklore should own and control how their intellectual property is protected. While a positive protective model explores how intellectual property rights such as copyright, trademarks, designs and performances may protect expressions of folklore through the endowment of such rights on communities, negative protective models examine how state and national competent authorities protect expressions of folklore on behalf of communities. An optimum framework for the protection of expressions of folklore recognises that regional and international perspectives are critical for the protection of folklore in third party countries and expressions of folklore that occur in contiguous countries. A regional perspective is important for Africa countries because of two regional intellectual property organisations in Africa (ARIPO – African Regional Intellectual Property Organisation) and OAPI (African Intellectual Property Organisation) that have established minimum standards for the protection of expressions of folklore. Norm setting and standards in international organisations such as WIPO (World Intellectual Property Organisation); UNESCO (United Nations Educational Cultural and Scientific Organisation); and the WTO (World Trade Organisation) significantly impact the protection of expressions of folklore in Africa. A human and peoples' rights framework explores how national and regional legal systems in Africa recognise entitlements of communities in the protection of the expressions of folklore they produce. In this regard, the normative framework of communities in terms of their customary law is also explored.
Keywords: ARIPO; African Regional Intellectual Property Organization; Communities; Customary law; Expressions of folklore; Ghana; Indigenous people; Intellectual property; Intellectual property rights; Kenya; Nigeria; Peoples' rights; South Africa; Sui generis; WIPO; World Intellectual Property Organization

Exploring shared governance as an alternative institutional model for the Southern African development community - Nyathi, Mkhululi (University of Pretoria, 2015)
The Southern African Development Community (SADC) was initially established as a coordination conference in 1980 and was transformed into a treaty organisation in 1992. Challenges of lack of coordination, inefficiency and lack of policy harmonisation led to the amendment of the Treaty in 2001. While the amendment of the Treaty served to address some of the challenges of the organisation, it failed to address the core challenge of the democratic deficit inherent in SADC s governance framework. While the SADC Treaty has as part of its principles and objectives the observance and promotion of democracy and the rule of law, both in its own processes and in its Member States, the design of the SADC institutions does not reflect these normative values. Governance of SADC is characterised by excessive executivism under the overarching powers of the Summit of Heads of State or Government. This democratic deficit is most prominently evidenced by the suspension and eventual disbandment of the SADC Tribunal, the only judicial organ of the organisation. The suspension and disbandment of the Tribunal, in addition to the obvious issue of legality that it raises since it was done in the absence of Treaty amendment, also raises the fundamental question of decision making in SADC in general, as the current treaty framework does not provide for meaningful conversation between and among the key institutions of SADC in matters involving policy formulation and implementation. There is also no institution with a strong oversight role in SADC. There is need for constitutional change in SADC if the organisation is serious in its commitment to achieve its objectives, which it has defined as its Common Agenda. This study proposes a treaty based reform process that is informed by the institutional model of shared governance. One of the several core tenets of this model is that in an organisation, there should be meaningful conversation among the internal stakeholders before a decision is made. For such conversation to be meaningful, there should be the broadest possible exchange of information among the components of an organisation. The proposals made by this study include transforming the Secretariat into an effective institution that formulates SADC laws and policies as well as their implementation frameworks; creation of a SADC parliament that would play a meaningful role on the amendment of the SADC Treaty and in the adoption of the budget; and an independent and accessible judicial body with significant powers of review. Shared governance as conceptualised in this study is not a substitute for, nor does it compete with related concepts like constitutionalism, separation of powers, the rule of law and participatory democracy, but in fact complements them. In addition to these proposals, there is a recommendation for the adoption of a robust access to information regime in which the shared governance institutional model would be anchored. There is also a recommendation for a new regime of law making through community legal instruments that would be directly applicable in Member States as opposed to the largely ineffective protocols.
URI: https://repository.up.ac.za/handle/2263/52280
Keywords: Civil society engagement; SADC; Southern African Development Community

The complex case for another hard look : transnational pharmaceutical regulation and the pedagogical role of courts - Rizzi, Marco (European University Institute, 2015)
The thesis argues for a 'pedagogical' role for courts in the US and EU in ameliorating the increasingly transnational regulation of pharmaceutical product safety through complementary monitoring of the outputs of regulatory processes. The study is divided into two parts. First, the thesis explores the regulatory institutional design in the US and EU. The parallel development of the FDA and EMA suggests that both markets have achieved consolidated domestic/regional regulatory frameworks, which do however show multiple weak spots. These vulnerabilities are aggravated by a strong push towards transnationalisation of regulatory procedures: domestic systems are now permeated by potentially disruptive exogenous elements (e.g. the ratification of transnationally negotiated protocols and increasing reliance on foreign clinical trials data). The thesis explores issues of effectiveness of safety delivery and legitimacy of rule-making processes to suggest scope for improvement in both areas. The second part considers the potential contribution of the judiciary, particularly national courts in the US and EU, to investigate whether the exercise of complementary judicial governance can enhance the effectiveness and legitimacy of an otherwise essentially closed and self-perpetuating system. A selection of cases grounds the claim that, through liability litigation, courts have the capacity to improve the safety levels delivered by regulation and thereby to contribute to output-based legitimacy of the institutional design. This claim is tested in light of acknowledged strengths and limitations of court processes and with regard to differentiating elements at the national level, particularly regarding access to justice. The concluding argument reassembles the results of the study to recommend the existing tool of domestic litigation as a response to certain vulnerabilities in pharmaceutical regulation. The 'hard look' doctrine described by Sheila Jasanoff grounds the normative claim for a 'pedagogical' role for courts, enhancing regulation beyond the outcome of isolated cases – ad adiuvandum rather than contra.
Accepted: 2015-11-04T16:35:28Z
Keywords: Drugs; European Union countries; Pharmaceutical industry; Pharmaceutical regulation; Pharmaceutical right; United States

Public-private cooperation in transnational regulation - Schmidt, Rebecca (European University Institute, 2015)
This thesis examines the emergence of transnational regulatory cooperation between public and private actors. It inquires why a private regulator and an international organisation may enter into a cooperation agreement in order to regulate particular issues, and what this tells us about the relationship between ‘expertise,’ ‘authority’ and ‘legitimacy’ in particular domains of global governance. The argument put forward in the thesis is that different types of regulators cooperate because, in an unsettled global space with no hierarchical framework, it is necessary for them to acquire sufficient authority to secure compliance with their regulatory agenda. In order to acquire and maintain such authority, regulators must be perceived as legitimate and their regulation as effective. Cooperation can open venues for participation and deliberation and for the exchange of necessary competences (particularly expertise); and thus ultimately can help regulators establish and strengthen their authority. Another important finding of this research is that cooperation can develop into more long-lasting network structures. These networks are often of a multi-level nature. As such, they traverse local, national, and international spaces. The thesis then develops the idea of ‘networks of constitutionalization’ to describe the observation that bilateral arrangements as examined here generate ordering effects which extend beyond the two parties. Consequently they become the basis for norm creation and adoption for different types of actors located in the networks formed around the issue area. Thus, even in pluralistic structures, eventually a certain kind of constitutionalization can emerge putting into question sharp divisions between ‘pluralist’ and ‘constitutionalist’ interpretations of a developing global (legal) order. This work also encompasses two case studies: the ISO 26000 process, whereby the ‘private’ technical standard setter ISO concluded separate cooperation agreements with the ILO, the OECD and the UN Global Compact; and a case study on ‘Sport and Environment’ that focuses on the long-standing cooperation between the IOC and the UN Environmental Programme.
Accepted: 2015-04-16T14:24:52Z
Keywords: International Law; Law and Globalization

Labour rights and working conditions in corporate codes of conduct: an assessment of the legal dimension, in different national contexts, of selected multinational corporations’ corporate social responsibility commitments - Tiemeni, Thierry Galani (University of the Western Cape, 2015)
At the heart of this thesis is the notion of Corporate Social Responsibility (CSR), an innovative concept deep-rooted in the globalisation phenomenon. The notion of CSR entails the much-debated duty of businesses, not only to comply with international and local standards in terms of, inter alia, labour rights and working conditions, human rights and environmental protection, but also to be at the forefront of voluntary and uplifting actions geared toward addressing societal issues and concerns. For corporations, it is about moving from the traditional approach of business as an activity with the sole purpose of realising profit towards acknowledging the need to integrate societal and environmental issues and concerns into their business purposes. The thesis examines selected multinational corporations’ (MNC) approaches to CSR as contained in their codes of conduct, in an effort to reach a comprehensive understanding of the purpose, interest and practices of businesses engaging in CSR activities. Particular attention is given to the analysis of labour orientated measures implemented by selected MNCs as they undertake to voluntarily act as proponents of the theory of the necessity of socially responsible businesses. The aim is to comparatively assess the legal dimension and the relevance, in different countries, of these MNC CSR commitments. The first part of the thesis is theoretical and has the purpose to present a comprehensive analysis of CSR against the current legal framework, at a global scale and within the context of selected countries. The thesis will explore the notion of CSR in order to present its definition and characteristics, briefly retrace its history, differentiate it from related and/or similar concepts, and finally assess the extent of its introduction and adaptation into various national and international institutional frameworks. Even though initially addressing the issue of CSR in the current legal framework as a whole, the scope of the thesis will ultimately be reduced to focus only on labour-related aspects of CSR. The aim of the thesis is to assess MNC’s CSR commitments, and subsequently highlight the interaction between CSR, labour and employment legal frameworks (at national and international level) and the effective implementation of labour rights and working conditions as observed in the context of different countries. More importantly, the thesis will also include a comparative analysis of CSR principles included in selected MNC codes of conduct, in order to assess the extent of their compliance with national labour legislation, international labour standards, as well as the standards and principles set by national and international CSR instruments and institutions. The purpose of such an exercise is to thoroughly assess the impact of a national context - in terms of national legal, economic, social and industrial framework - on the legal dimension, and the relevance of MNCs CSR commitments. A crucial argument developed in the thesis refers to the fact that MNC codes of conduct may have the potential to impact on labour rights and working conditions of a MNC across the different countries into which the MNC operates. Finally, considering the fact that as a topic CSR is a potentially controversial subject, it is necessary to point out, from the onset, that the thesis engages with the subject from a critical perspective. The approach therefore entails critically analysing and discussing MNC commitments and practices as observed in different countries, so as to be able to ascertain and comprehend the impact of a national context on the content, the relevance and the legal dimension of MNC codes of conducts
Keywords: Code of conduct; Corporate Social Responsibility; Labour rights; Multinational corporations; Working conditions

Synthetic securitisation in South African law - Wessels, Francois Claassens (University of Pretoria, 2015)
The objective of this thesis is to critically analyse synthetic securitisation schemes in South African law as synthetic collateralised debt obligations using primarily credit default swaps (CDSs). This transpires from the perspective of primarily company law, and secondarily securities law and the law of contract. It includes a contextualised study of these schemes with regards to their origins, their significance regarding the recent financial crisis, and their rationales micro-economic influence and Basel capital requirements. Not only are the participants, such as parties acting in a primary role and secondary role and special-purpose institutions, studied, but also the obligations between these parties, such as the CDS contract, and the meaning of commercial paper, the legal nature of credit-linked notes, the business of a bank, and the influence of recent case law. It also includes a consideration of synthetic securitisation schemes in terms of the Collective Investment Schemes Control Act 45 of 2002. Furthermore, the role of systemic risk and moral hazard is explained, as well as the interaction between synthetic securitisation schemes, credit rating agencies and the function of risk management. The CDS is compared with insurance contracts, and a discussion of the 2014 International Swaps and Derivatives Association Credit Derivative Definitions is incorporated. For legal comparison, the South African model is compared with Canadian law and its unfunded credit derivatives in the light of recent regulation, and compared to German law and its prevalence of funded credit derivatives. Finally, suggestions are made as to the future of synthetic securitisation schemes.
URI: https://repository.up.ac.za/handle/2263/53208
Keywords: Company law; Debt obligation; Securities Law; Securitisation; South Africa; Titrisation

A South African perspective on some critical issues regarding the OECD model tax convention on income and on capital, with special emphasis on its application to trusts - Du Plessis, Izelle (Stellenbosch University, 2014)
Trusts are used for a variety of purposes, both in South Africa and abroad. Like so many other entities, trusts often do not function only in one jurisdiction and may therefore be exposed to international double taxation. South Africa, like most other states, enters into bi-lateral double taxation treaties, to limit the effects of international double taxation. Most of these treaties are based on the OECD Model Tax Convention on Income and on Capital (the OECD MTC). The South African trust is a unique creature. It is not based on the dual ownership concept on which most common law trusts are based, yet, it is not a juristic person either. The question that this research aims to address is how South Africa will interpret and apply certain provisions of the OECD MTC to trusts. Although the South African position is investigated, it is compared to the positions of the United Kingdom, Canada and the Netherlands. The dissertation starts with an analysis of the trust law in each of the relevant states, followed by an overview of the taxation regime governing trusts (and the parties thereto) in each state. The status of double taxation treaties and their interpretation are examined before certain critical provisions of the OECD MTC are analysed to determine how South Africa will apply these provisions to trusts. Hence it is explored whether a trust will be regarded as a person, whether it may be a resident and a beneficial owner for purposes of the OECD MTC. Furthermore, possible solutions for conflicts of attribution in the application of double tax conventions to trusts are investigated. The dissertation concludes that South Africa will regard a trust as a person for purposes of the OECD MTC. Moreover, some types of trusts may be viewed as residents and as beneficial owners for purposes of the OECD MTC. The solution proposed in the OECD’s Partnership Report should be applied to resolve conflicts of attribution involving trusts.
URI: http://hdl.handle.net/10019.1/95878
Keywords: Double taxation; Income tax; International taxation; OECD Model Tax Convention; South Africa; Taxation; Treaties; Trusts and trustees

An Analysis of Delay in Enforcement of Contractual Judgments as Impediment to Foreign Direct Investments (FDI) in Nigeria - Rabiu, Ahmed (Ahmadu Bello University, 2014)
Foreign Direct Investment (FDI) is about economic prosperity and wealth creation of developing economies, (FDI) brings with it capital, technology, it provides a platform for the creation of jobs and links to the world economy which brings development. The New Partnership for Africa’s Development [NEPAD] asserts that to meet its developmental challenges, Africa will have to rely more on foreign direct investment [FDI] than aid. Given the fact, the aid flows to Africa have significantly declined over the years and that the continent has now to compete with other countries for the same resources needed for development. Therefore, [NEPAD] places greater emphases on the importance of foreign direct investment [FDI] as Africa’s new engine of economic growth, particularly in the manufacturing and agricultural sector, as opposed to the oil and gas and other natural resources. However, the contribution firms, and foreign direct investment [FDI] make to the society is determined principally by the investment climate. There are many features of a good investment climate, aside of legal framework, provision of security and maintaining infrastructure, which provide the opportunities and incentives for the investment to flow and flourish and create confidence in the mind of the investors, to invest productively, and they include strong and vibrant contract enforcement. Delays or uncertainties in the enforcement of contractual rights erode the value of property rights and diminish the opportunities and incentives to invest. Therefore, the process of seeking redress through the normal court system is too protracted and unsatisfactory to continue to serve as primary recourse option of executives and potential investors, and this also explain the slow of improvement in FDI in the manufacturing and agricultural sector inflow to Nigeria. There are additional reasons for all these difficulties and hurdles that constitute a clog to an efficient contractual enforcement. The legal system that made judges of regular courts to also handle election petitions and other ad-hoc assignments to the detriment of the regular pending commercial cases before the courts. Secondly, there currently distinct rules for each state of the Federation and there number of civil procedure rules required to be complied with to move cases through the system from filing to judgment enforcement. This has created additional and unnecessary procedures that elongate the process of contract enforcement. Thirdly, despite these enormous powers of the Sheriff and bailiffs in the process of trials and enforcement of contractual judgments, in Nigeria majority of the bailiffs in all our courts including the courts of records are either retired police or military officers with no formal training on their powers and obligations in accordance with the provision of the law.The dissertation mainly recommended the creation of Commercial courts or Commercial divisions throughout the federation to handle contractual and commercial cases; secondly, Secondly, it is recommended for the unification and adoption of a single the civil procedure rules throughout the country. Lastly to institutionalize the training and retraining of sheriffs and court bailiffs on the provisions of the rules as it relates their functions of giving effect to court orders and judgment.These would go a long way in providing an effective and speedy movement of civil cases through the system of trial and subsequent enforcement in our courts, which may further create confidence and improve the investment climate for the inflow of the Foreign Direct Investment (FDI) in to Nigeria.
Keywords: Contract; Enforcement; FDI; Foreign direct investment; Impediment; Investments; Judgments; Nigeria

Cross-border resolution of banking groups: old demons, current progress, future challenges - Pnevmonidis, Ilias (Université de Genève, 2014)
This contribution focuses on the development of bank resolution regimes as a credible antidote to the ‘too big to fail' problem. The main objective of the analysis is to demonstrate the repercussions and challenges resulting from the implementation of bank resolution schemes on a cross-border level. This work is a selective survey of specific legal questions, which remain relatively unaddressed by academic literature and international standard-setting bodies (e.g. bank resolution triggers or safeguards for bank creditors under bank resolution) or still problematic (e.g. resolution planning or cooperation and information exchange between resolution authorities), in particular when applied in a cross-border context. The author aims to shed more light to the complexities of cross-border bank resolution while trying to answer to the fundamental question: have we ended the ‘too big to fail' problem?
Keywords: Bank-failures; Bank-insolvency; Bank-resolution; Financial-crisis; Insolvency; Systemic-risk; Too-big-to-fail

The position of the whistle-blower in South African law - Isparta, Louise Dorothy (University of South Africa, 2014)
The position of the whistle-blower is known to be a precarious one, with the whistle-blower often either regarded as a hero or a reprehensible traitor. Various pieces of legislation have attempted to remedy their precarious position, especially within the employment relationship, and in which the whistle-blower more often than not has the most to lose. The study at hand has the specific objective of comparing the position of the whistle-blower in terms of South African Law, against 16 specific measurables, and in comparison with the position of the whistle-blower in New Zealand, Australia (Victoria) and the United Kingdom. In the main, the protection offered to the whistle-blower within the South African context, is embodied within the Protected Disclosure Act 26 of 2000 (hereinafter referred to as the “PDA”).In examining the protection afforded to the whistle-blower in South Africa, it is concluded that the framework involved extends much further than just the mere provisions in the PDA. However, there are admitted challenges in respect of this framework as discussed, both legislative and non-legislative, especially in respect of duties of disclosures placed on persons in circumstances in which concurrent protection is not afforded to the whistle-blower. With reference to the comparison in respect of the measurement parameters set, it was found that the PIDA (UK) meets the least amount of the measurements set, with the PDA A (Australia, Victoria) meeting the most of the measurements; the PDA NZ is equally balanced in meeting and not meeting the measurements and the PDA meeting less of the measurements than not, but still meeting more than the PIDA. It was found that had it not been for the catch-all provision contained in section 4 (1) (b) of the PDA, the PDA would have ranked last.
Keywords: Disclosure of information; Lanceur d’alerte; Protected Disclosure Act; Protected disclosure; Public Interest Disclosure Act; Whistle blowing; Whistle-blower

Complex ownership structures, banks' capital structure and performance - Zedek, Nadia (Université de Limoges, 2014)
Cette thèse examine l’impact de la structure actionnariale sur la structure du capital et la performance des banques commerciales européennes sur la période 2002-2010. Elle est composée de trois essais empiriques. Le premier chapitre teste l'effet de la divergence entre les droits de contrôle et les droits pécuniaires d'un actionnaire ultime sur l’ajustement du ratio du capital à son niveau optimal et sur l’offre de crédit par les banques. Les résultats montrent qu’en présence de divergence entre les droits de contrôle et les droits pécuniaires, les banques n’émettent pas du capital pour augmenter leur ratio et, au contraire, elles réduisent leur taille en ralentissant leur offre de prêts. Le chapitre 2 teste l’effet de cette divergence sur la rentabilité et le risque bancaires en temps normal et en temps de crise. Les résultats montrent que bien qu'une divergence entre les droits de contrôle et les droits pécuniaires soit associée en temps normal à une rentabilité plus faible et un risque plus élevé elle a, à contrario, amélioré la rentabilité et contribué à la résilience des banques pendant la crise financière de 2007-2008. Le troisième chapitre teste si le réseau des actionnaires auquel la banque est liée au sein d’une chaîne de contrôle affecte la relation entre la diversification et la performance. Les résultats montrent que la présence des investisseurs institutionnels dans les chaînes de contrôle aide les banques à tirer des bénéfices lorsqu’elles diversifient leurs activités.
Keywords: Actionnariat; Banques; Banques européennes; Capital; Capital Structure; European Banking; Ownership; Structure du capital

Essays in competition policy - Khimich, Aleksandra (Université Toulouse 1 Capitole, 2014)
Dommage économique causé par les cartels: une évaluation pour les pays en voie de développement (En collaboration avec Marc IVALDI, L'École d'économie de Toulouse et CEPR et Frédéric JENNY, ESSEC Business School, Paris) : La détection et la sanction des cartels reste toujours d'une grande importance pour les autorités de la concurrence développées en raison d'une compréhension claire de leur danger potentiel, et donc des avantages de leur dissuasion. Néanmoins, les pays en développement ont souvent du mal à créer ou à renforcer leur autorité de la concurrence - l'exécution d'une division antitrust est coûteuse et la preuve à l'appui concernant les avantages potentiels est toujours manquante. Présente étude fournit la preuve quantitative manquante. Elle propose une évaluation du dommage économique total causé par les cartels en termes de chiffre d'affaires affecté par les pratiques collusoires ainsi qu'en termes de profits excessifs des ententes découlant de surcharge des consommateurs. Les résultats suggèrent que le préjudice économique totale estimé en termes de profits excessifs divisés par le PIB correspondant peut atteindre jusqu’à 1%. En outre, comme la probabilité annuelle maximale de découvrir une entente déjà existante est estimée à environ 24%, il est suggéré que le dommage économique réel dépasse nos estimations, au moins quatre fois. / Évaluation de la précision des outils proposés dans les lignes directrices sur les fusions (En collaboration avec Marc Ivaldi, L'École d'économie de Toulouse et CEPR et Jérôme Foncel, EQUIPPE, Université de Lille) : Présente étude propose une évaluation complète de la précision de deux outils proposés par les lignes directrices sur les fusions les plus avancés - le critère traditionnel HHI et un plus récent UPP - et défini les conditions économiques qui favorisent les prédictions trompeuses. Les simulations de Monte-Carlo sont utilisées pour créer des économies qui sont utilisés pour mesurer les effets des fusions et d'évaluer la performance des outils d'évaluation choisis. Les résultats suggèrent que le test HHI à une capacité très faible de déterminer le potentiel de l'augmentation des prix lorsqu'il est appliqué à un marché de produits différenciés. Dans son tour, le test UPP peut aussi être très trompeur, même si l'on a une information parfaite sur les principaux ingrédients nécessaires pour le calculer. L’étude démontre que certains d'erreurs de type I et de type II se produit parce que les tests de type UPP par construction ne tiennent pas compte de la ‘pression’ sur le prix subie par le partenaire de fusion. Elle aussi explique comment ce dernier peut être réglé en tenant compte du degré de transmission croisé correspondant. / Le rôle du degré de transmission croisé dans les évaluations des fusions : Présente étude démontre que l'ignorance de l’effet de transmission croisé, et en particulier de son signe, peut conduire à des conclusions erronées dans presque toutes les étapes d’évaluation d’une fusion, y compris la procédure de définition du marché et l'évaluation des effets coordonnés et unilatéraux. Par conséquent, l’étude aussi offre un examen des propriétés de l'ensemble de la matrice des degrés de transmission dans un cadre suffisamment général et en même temps plus pratique pour les concentrations horizontales et tire les caractéristiques exactes des systèmes d'offre et de demande qui affectent le signe du degré de transmission croisé.
Keywords: Cartels; Competencia; Competition law; Concurrence; Conditions économiques; Droit international; Pays en voie de développement; Politique de la concurrence

Arbitration in administrative contracts : comparative law perspective - Lin, Ching-Lang (Institut d'études politiques, 2014)
Il a été longuement discuté de savoir si le système d'arbitrage est applicable pour régler les litiges administratifs qui concernent certains contrats administratifs ou d’autres sans rapport avec le contrat administratif. Dans cette thèse, les trois questions spécifiques sont analysées tour à tour : (1) Est-il possible pour un arbitre ou un tribunal arbitral de trancher des questions relevant du droit administratif? (2) Y a-t-il, ou devrait-il y avoir, des limitations à l'autorité des arbitres et des tribunaux arbitraux? (3) Enfin, après la délivrance d'une sentence arbitrale, quel rôle devrait jouer l'État dans la phase de contrôle judiciaire? La première question concerne l'arbitrabilité et a été discutée dans la première partie (FIRST PART: ARBITRABILITY). La deuxième question a été discutée dans la deuxième partie (SECOND PART: PARTICULAR QUESTIONS OF ADMINISTRATIVE MATTERS IN ARBITRATION PROCEDURE). Enfin, sur la dernière question a fait l’objet d’une troisième partie (THIRD PART: JUDICIAL REVIEW AND EXECUTION OF ARBITRATION AWARD). Dans cette thèse, nous avons comparé les systèmes de quatre pays (Canada, Chine, France, Taïwan). En conclusion, nous pouvons donc conclure que l’évolution de la conception du contrat administratif implique de nombreux aspects, y compris les aspects juridiques, économiques, politiques et même culturels. Le développement de la fonction de contentieux administratif, comme ‘’subjectivement orienté" ou "objectivement orienté" aura une incidence sur l'acceptation de l'arbitrage en matière administrative. Dans l'ensemble, l'arbitrage sera plus acceptable dans les systèmes dont la fonction est plus ‘’subjectivement orientée" que dans ceux dont la fonction est "objectivement orientée". While arbitration has traditionally been considered as a means to resolve private disputes, its role in disputes involving administrative contracts is a crucial question in administrative law. In brief, the three specific questions are (1) Can arbitrators or arbitral tribunals decide issues involving administrative law? and (2) Is there, or should there be, any limitation on the authority of arbitrators or arbitral tribunals? (3) Moreover, after the issue of an arbitration award, what role should the State play in the judicial review phase? The first question, the issue of arbitrability, is discussed in part 1 (FIRST PART: ARBITRABILITY). The second question will be discussed in part 2 (SECOND PART: PARTICULAR QUESTIONS OF ADMINISTRATIVE MATTERS IN ARBITRATION PROCEDURE). Finally, on the question of what happens after the arbitration award, we will discuss judicial review in part 3 (THIRD PART: JUDICIAL REVIEW AND EXECUTION OF ARBITRATION AWARD). We compare legal systems between the four countries: in France, in Canada, in China and in Taiwan. We believe that an administrative contract, at least in its function and conception, is gradually becoming different from a private contract. Innovation with respect to administrative contracts will also reflect the concentration and function of the administrative litigation systems in each country. In addition, the “objective” or “subjective” function of administrative litigation will also affect the degree of arbitrability, as well as arbitration procedures. Taken together, arbitration will be more acceptable in systems whose function is more “subjectively oriented” than in those whose function is “objectively oriented". Finally, “the arbitration of administrative matters” traditionally has been an important question in administrative and arbitration law. In the future, we will continue to see it shine in the doctrine and jurisprudence of both the administrative and arbitration law fields.
Keywords: Administrative litigation system; Arbitrability; Arbitrabilité; Arbitrage; Arbitragem; Arbitration; Arbitration award; Contentieux administratif; Contrats administratifs (exécution); Judicial review; Litige; Légalité objective; Objective and subjective function; Prerogative of administrations in contracts; Sentence arbitrale (contestation); Études comparatives

Human capital disclosure in corporate annual reports - Adelowotan, Michael Olajide (University of South Africa, 2014)
It is generally acknowledged that human capital intangibles are major value drivers in the new economy characterised by information and technology. The main purpose of this study is to examine the extent to which companies listed on the Johannesburg Stock Exchange disclose information on human capital related issues. The study combined both qualitative (literature reviews and content analysis) and quantitative (survey questionnaire) methods to collect data of 60 corporate annual reports (CARs) of listed companies in South Africa from survey questionnaires administered on various categories of preparers and users of these CARs. The study made use of 91 human capital disclosure checklists developed from literature reviews for the purpose of data collection. The data analysis was done with the aid of Atlasti-a qualitative data analysis software and SPSS- a quantitative data analysis software. The findings show that majority of the items on the disclosure checklist are not yet disclosed in the CARs even though most of the items on the checklist are adjudged to be useful for organisational value creation. In view of the initial findings of this study, a human capital disclosure framework is recommended.
Keywords: Annual report; Corporation reports; Discretionary disclosures; Human capital; Human capital disclosure framework; Intangible assets; Intangible property; Intellectual capital; Mandatory disclosures; Personnel management

Substantive equality, affirmative action and the alleviation of poverty in South Africa : a socio-legal inquiry - Katiyatiya, Luyando Martha (Stellenbosch University, 2014)
Substantive equality is a constitutional imperative, hence the need for strategies that attempt to realise it for the sake of genuine social reconstruction. The principle of equality runs through all other rights in the South African Constitution. Be that as it may, equality is an elusive concept, which makes its achievement an ambitious task. Nonetheless, there are strategies that attempt to bring to the fore the ‘substance’ of the concept in order to ensure the actual realisation of socio-economic benefits. Such strategies include, among others: social security, education, economic empowerment, skills development and affirmative action. This study will focus on the latter of these strategies, namely affirmative action. Although affirmative action is practised around the world, one of the (many) criticisms of the policy is that it fails to bring about substantive or structural change. In other words, it may change the racial and gender composition of the classroom or the workplace, but does not address the challenges that cause the disadvantages of marginalised groups in the first place. It is arguable that affirmative action has increased inequality in South Africa by benefiting the apex of the class structure and not the majority of the population living in abject poverty. This study develops a theoretical analysis of the link between status (race, sex and ethnicity) and socio-economic disadvantage, and the central question that the study addresses is the following: How can the policy of affirmative action be redesigned to ensure that it benefits the socio-economically disadvantaged? A secondary question that is investigated is whether affirmative action can contribute to the development of human capacities in the context of poverty alleviation. It is arguable that substantive equality facilitates the adoption of strategies (such as affirmative action) to address socio-economic inequality, poverty and social exclusion. The research suggests that a paradigm shift is necessary in order to reconceive of affirmative action as a policy that does not only focus on ensuring ‘equitable representation’ of disadvantaged groups in the workforce or the classroom, but also provides for the development of human capacities. This can be achieved if one adopts an expansive view of affirmative action and if one utilises class as one of the numerous criteria for determining the beneficiaries of the policy.
URI: http://hdl.handle.net/10019.1/86607
Keywords: Affirmative action programs; Equality before the law; Politics and government; Public welfare; Social conditions; South Africa

Harmonising the law of sale in the Southern African Development Community (SADC) : an analysis of selected models - Shumba, Tapiwa (Stellenbosch University, 2014)
It is generally recognised that diversity of laws may act as a barrier to the development of trade, both at international and regional level. In a globalised era, trade is necessary for economic development and ultimately for the alleviation of poverty. Although the WTO has done extensive work towards the removal of tariff barriers, there is also a need to focus on addressing non-tariff barriers which include legal barriers to trade. Institutionalised legal harmonisation at an international level has provided the necessary impetus for the development of harmonised laws in the area of international trade. The creation of regional economic communities within the purview of the WTO has also given rise to the necessity of legal harmonisation to facilitate intra-regional trade. A number of regional economic communities and organisations have noted legal harmonisation as one of their areas of regional cooperation. This study focuses on the need to harmonise the law of international sale within the SADC region in order to facilitate cross-border trade. The study points out that the harmonisation of sales laws in SADC is important for the facilitation of both inter-regional and intra-regional trade with the aim of fostering regional integration, economic development and alleviating poverty. Although the necessity of harmonising sales laws has been identified, no effort to this end exists currently in the SADC region. This study addresses the mechanisms by which such harmonisation could be achieved by analysing three models which have been selected for this purpose, namely the CISG, the OHADA and the proposed CESL. The main issues addressed include whether SADC Member States should adopt the CISG, join OHADA, emulate the CESL or should use any of the other instruments as a model for creating a harmonised sales law for SADC. In conclusion, it is observed that SADC has its own institutional and operational mechanisms that require a process and instrument tailor-made for the unique needs of the region. It is recommended that SADC should create its own common sales law based on the CISG but taking into account lessons learnt from both the OHADA system and the CESL. A number of legislative, institutional and operational transformative and reform mechanisms are recommended to enable the creation of such a community law and ensure its uniform application and interpretation.
Keywords: Africa; Economy; Foreign trade promotion; International unification; Mercantile law; Regional disparities; SADC; Southern African Development Community; Trade law

International sales contracts in Congolese law : a comparative analysis - Kahindo, Nguru Aristide (University of South Africa, 2014)
To regulate and facilitate are the main functions of legal rules. These purposes are achieved by a harmonised legal system by which the law becomes identical in numerous jurisdictions. The process to unify the law of sale internationally started in the 1920s and culminated, in 1988, in the implementation of the CISG. This Convention intends to provide clarity for most international sales transactions by regulating the formation of contracts, and the rights and obligations of the seller and the buyer resulting from the contract. The CISG has these days enjoyed much ratification and influenced a number of legislation reforms worldwide. Despite the role it played during the drafting process of the CISG, the DRC has not yet ratified it. Instead, the country continued to rely, until recently, on colonial legislations which had become out-dated, and inadequate to meet modern international sales contracts requirements. The situation appears to have been improved a year ago as the effect of the adoption of OHADA law whose Commercial Act is largely inspired by the CISG. Because the introduction of OHADA law in the DRC is very recent, this study intends to assess the current state of Congolese sales law by comparing it with the CISG and South African law, which is non-CISG but modernised. The comparative study aims at establishing whether current Congolese law, as amended by OHADA law, is sufficient or has shortcomings; if it has some, it aims to identify those shortcomings, and make suggestions for their improvements. After discussion, it has been discovered that the ratification of OHADA law has significantly improved Congolese domestic sales law. Given that there remain certain unresolved shortcomings in Congolese international sales law, however, the study ends by a proposal for the accession of the DRC to the CISG in order to fill them.
Keywords: Congo (Democratic Republic); Congolese contract law; Congolese sales law; Contracts; Export sales contracts; Formation of the contract; International sales law; OHADA law; Obligations of the buyer; Obligations of the seller; Sale of goods; South Africa; South African contract law; South African sales law

An evaluation of the predictive value of bank fair values - Ehalaiye, Oludimu Oluseun (Victoria University of Wellington, 2014)
This thesis examines whether the net asset fair values of banks possess predictive ability for the banks’ future cash flows and earnings. This is an important issue considering the arguments for and against the wider use of fair value accounting for banks’ financial instruments and the claim by some that fair values during economic recessions (where markets may be illiquid) are irrelevant and largely unreliable. A number of studies have found that the explanatory power of bank fair values when compared to traditional historical cost are more value-relevant based on capital market reactions. However, there is a very limited literature on how bank fair values are related to the future performance (e.g. earnings and cash flow) of banks. This study fills this gap by providing empirical evidence on the relationship between U.S. bank fair value disclosures and banks’ future performance as measured by operating cash flows and earnings over a three-period future horizon. Furthermore, the thesis provides evidence on the relationship between bank fair values, in terms of the levels classification introduced during the 2008 global financial crisis, and the future performance of banks, thus showing whether market illiquidity affected the underlying relationships. The study examines two distinct periods. The first study period, 1996-2005, was based on annual data of banks with minimum total assets of $US150 million as of year 1996. The second study period from 2008-2010 (this period encompassed the global financial crisis period and also the levels classification of bank fair values according to SFAS 157), was based on quarterly data of banks with minimum total assets of $US150 million as of the first quarter of 2008. The thesis provides strong evidence that there is a predictive relationship between bank fair values and future bank performance. The evidence is strong during the first study period from 1996 to 2005 where the current net asset fair values of on-balance sheet financial instruments of banks were significantly associated with future operating cash flows and operating earnings of such banks over a three-year future time horizon. However, the predictive relationship between net asset bank fair values and operating cash flows is stronger than the predictive relationship between net asset bank fair values and operating earnings. In the second study period, from 2008 until 2010 the empirical results show strong evidence that there is a predictive relationship between level 1 and level 2 bank fair values and future operating cash flows. The findings from the empirical results were that the current quarter’s level 1 and level 2 net asset fair values of banks were significantly associated with the future quarters’ operating cash flows of such banks. The level 3 net asset fair values of such banks in most cases were not significantly associated with the banks’ future quarterly operating cash flows. The corresponding relationships for operating earnings were that the current quarter’s level 1 net asset fair values of banks were positively associated with the future quarters’ operating earnings of such banks. However, the level 2 net asset fair values of banks were negatively associated with the future quarters’ earnings of such banks. This result is in contrast to the results obtained when the predictive relationship between level 2 bank fair values and future operating cash flows was evaluated, where it is found that both level 1 and level 2 net asset bank fair values are positively related to future quarterly bank cash flows. Further empirical analysis showed that a possible reason behind this disparity was that there was a structural change in the relationship between bank operating cash flows and operating earnings over the course of the first and second study periods, where, in particular, for the second study period (which includes the period of the global financial crisis) there was a systematic downward bias in operating earnings relative to the operating cash flows of the sampled banks. This in turn makes operating earnings a poor proxy for operating cash flows during the second study period. The findings from this study provide confirmation that net asset fair values have predictive ability as argued by Ball (2008); Barth (2006b) and Tweedie (2008). The study findings that net asset fair values have predictive ability is consistent with the FASB’s view that the asset values shown in firm financial statements should communicate information about the potential future financial performance of the affected firms (FASB 2010:17). Furthermore, the study also confirms that objectively determined bank fair values based on market prices rather than model based bank fair values provide greater predictive value in relation to future performance as measured by operating cash flows. Lastly, this thesis showed that during the first study period (where there was no financial crisis) that bank size, capital adequacy and growth prospects, had little impact on the results obtained, while for the second study period, there were cases where bank size and bank capital ratios did have a significant impact on the predictive relationship between bank fair values and future cash flows. The study contributes to the fair value accounting and accounting standard-setting literature and highlights that fair values have predictive ability, especially with respect to future operating cash flows of banks, both during and outside of periods of financial crisis.
Keywords: Economic forecasting; Fair value; Predictive value

A macro-financial theory of corporate financing and forecast modelling of market movements - Sutton, David (Victoria University of Wellington, 2014)
This thesis identifies a gap in existing theories of corporate finance. This gap is an implication of a Keynesian-Minskian analysis of markets and market-based economies. From a founding theoretical perspective rooted in the view that markets are not reliably efficient the case is developed that past price trend extrapolation is an important factor in corporate financing decisions. At a macro-financial level, companies repurchase equity over periods of strong market rises, while increasing debt at the same time. During periods of sustained, substantial market decline debt is retired and large new equity issues occur. This change in corporate financing is implicitly expensive as relatively low prices are realised for the new stock issued at these times. These factors suggest that conventional theories of corporate financing decisions that rely on corporate rationality and optimisation do not provide a compelling fit with observations in the period 1980-2012. Moreover, inference to Minsky’s (1986) argument that companies are compelled through market declines to shore up their balance sheets provides a better fit with the evidence. These arguments form the basis for the development of the ‘extrapolative expectations’ theory of corporate finance. The second major development in this thesis draws on the theoretical development outlined above to create market movement description and prediction models. These models operate on data drawn from the US Standard & Poors 500 index over the period 1980-2012. Two primary models are developed using binomial logistic regressions. The dichotomous dependent variables are drawn as quarters of market rise (1) or no rise (0), and market falls (1) or no fall (0), respectively for the ‘buy’ model and the ‘sell’ model. Variables tested and those found to add to an explanation of the dependent variables include: corporate debt flows, corporate equity flows, corporate dividend flows, interest rates, market volumes, and historical market levels. Each variable is tested for up to ten lags (two-and-a-half years). Collectively, the variables add to our understanding of those factors influencing (or at the least, signalling) market levels, enabling quarter ahead market forecasts to be made with greater accuracy than arises from an assumption of a random walk. This conclusion crystallises the view that company macro-financial flows and prices are an important cause or signal of future market direction.
Keywords: Corporate financing; Financial Accounting; International Accounting; Macro-financial; Minsky

Dispute resolution in transnational securities transactions - Andreotti E Silva, Tiago (European University Institute, 2014)
This PhD thesis explores how the legal infrastructure for dispute resolution in transnational securities transactions can be improved, considering the regulatory and legal limits of the financial sector in each jurisdiction under study (US, Europe and Brazil). The two main objectives of the work are to a) identify the problems that currently exist for a dispute resolution mechanism in the securities area that can be used transnationally and b) propose solutions that can create a safe legal environment that can be used by the investor in case regulatory rules or the terms of the transaction are breached. The work is justified by the fact that financial markets are legal constructions, making legal certainty and the mechanisms available to enforce the terms of a transaction and apply regulatory rules, especially to the investor that is part of the transaction, essential for the own existence of financial markets. Therefore, the existence of transnational financial markets also depends on the existence of a transnational legal infrastructure, at least broad enough to protect the interest of investors. The argument developed through the work is that the creation of a transnational legal infrastructure depends on the type of dispute that is considered, since not only each type of dispute has its own peculiarities, but the national dispute resolution systems are also built based on the type of dispute that will be submitted to it. To create transnational dispute resolution systems for securities transactions, I propose the use of collective mechanisms of dispute resolution based on the initiative of private parties, the use of arbitration and the establishment of cooperation networks among national alternative dispute resolution mechanisms used to solve financial disputes.
Accepted: 2015-01-15T16:55:51Z
Keywords: Dispute resolution (Law); Financial market; International finance; Security (Law)

Nuclear energy in Africa : a legal framework for sustainable energy access - Barnard, Michelle (North-West University, 2014)
The promotion of sustainable development is an objective shared by African Union (AU) member states and the pursuance thereof is expressly mandated by the Constitutive Act of the African Union, 2000 and the Treaty Establishing the African Economic Community, 1992. Lack of access to modern energy sources, such as electricity and the heavy reliance on traditional biomass as primary energy source are factors contributing to the non-achievement of the promotion of sustainable development. These factors are collectively referred to as energy poverty. The African Continent as a whole has limited, and in some instances, lack access to modern energy sources while the majority of its population relies heavily on traditional biomass as primary energy source. Africa can accordingly be classified as an energy poor region–a situation which does not bode well for the promotion of sustainable development. Access to reliable, affordable, economically viable, socially acceptable and environmentally sound energy services and resources is fundamental to socio-economic development. Mitigating the impacts of energy poverty and more specifically lack of access to modern energy sources on the sustainable development of Africa depends upon ensuring increased access to modern energy sources. The above-mentioned instruments furthermore contain provisions which link regional cooperation on the formulation of coordinated regional law and policy on areas/matters of common concern with the achievement of the objective of promoting sustainable development in Africa. One of the areas of common concerns listed is that of energy. Regional cooperation must accordingly be geared towards the effective development of the continent‘s energy and natural resources; promoting the development of new and renewable energy in the framework of the policy of diversification of sources of energy; and establishing an adequate mechanism of concerted action and coordination for the collective solution of the energy development problems within the AU. The formulation of coordinated energy law and policy should take place with reference to the specific sources of energy to be regulated. In this regard, the provisions of the Abuja Treaty and other sub-regional energy access initiatives list various sources of energy as forming part of a diversified AU energy mix – one of which is nuclear energy. In this study recommendations are made as to what should be embodied in a coordinated AU regional nuclear legal framework aimed at regulating increased access to nuclear energy capable of contributing towards the promotion of sustainable development. The recommendations are based on an examination of relevant international, regional and sub-regional legal instruments and other initiatives.
Keywords: African Union; Coordinated legal framework; Energy access; Energy poverty; Nuclear energy; Regional cooperation; Sustainable development

Regulating trade in petroleum under the WTO Regime: trade rules vs. reality of the petroleum industry - Bitenov, Gani (McGill University, 2014)
This thesis critically assesses the effectiveness of WTO legal rules in the regulation of international trade in petroleum and highlights potential conflicts between competing resources of energy from the WTO regime’s perspective. The theoretical framework of the thesis is built on the concepts used in natural resource economics, trade theories and international relations. On the basis of Hotelling’s rule of natural resource economics, it proposes a model that reconciles the use of petroleum and the development of renewable sources of energy in the power generation sector, which prospectively can be adopted with respect to the transport sector and other sectors involving energy use. The proposed model may improve global sustainable development. However, it is argued that WTO rules are not properly designed to regulate trade in petroleum and, if applied without due respect to specific issues pertaining to the petroleum industry, would obstruct the achievement of the social optimum, and detrimentally affect the national economies of WTO members and global welfare in general. To improve the WTO system, I propose a reformation of its normative ideology through the introduction of the strategic trade policy theory in complement to the neoclassical theory of trade, at least when trade in energy is concerned. On the basis of the study of the applicability of WTO rules to trade in petroleum and a review of proposals put forward by other scholars to improve the regulation of trade in energy, it is argued that the most effective way to improve the trading regime is to negotiate a new general agreement on trade in energy.The role of the WTO in the regulation of trade in energy is analyzed through a regime management theory borrowed from international relations studies. It is argued that the WTO as a regime manager is capable of improving the regime by properly maintaining the existing equilibrium and by initiating, and leading in negotiations of a new equilibrium.
https://escholarship.mcgill.ca/concern/theses/ws859j68h
Keywords: Petroleum industry and trade; Trade regulation; WTO trade rules

Three Essays on Financial Distress and Corporate Bankruptcy - Chen, Donghui (McMaster University, 2014)
This thesis explores three important issues in financial distress and corporate bankruptcy: bankruptcy venue choice and creditor recovery, the efficiency of Chapter 11 corporate bankruptcy and distressed exchanges, and the bankruptcy ripple effect on peer firms’ investment policy.
Keywords: Bankruptcy; Contagion effect; Corporate Bankruptcy; Distress exchange; Efficiency; Financial distress; Forum shopping; Insolvency

Reconciling international investment law and sustainable development with respect to host state's right to regulate : the legal impact of sustainable development objective on indirect expropriation standard and its legitimate expectations sub-element - Dubava, Ilze (European University Institute, 2014)
This thesis seeks to determine whether the evolution of international law has allowed for the concept of cultural genocide to be addressed in spite of its non-codification. It firstly provides an assessment of the evolution of the concept of cultural genocide, from a technique to a process of genocide, also known as 'ethnocide'. Acknowledging that the codification of the concept is unlikely in the future, it therefore undertakes a study of the evolution of international law with regard to the main components of the concept, namely genocide, culture and group. The evolution of the legal concept of 'genocide' raises the question of the interpretation of the international definition of genocide, which is enshrined in the 1948 Convention on the Prevention and Punishment of the Crime of Genocide, so as to encompass instances of cultural destruction. The state of international and domestic judicial practice illustrates the limits of an evolutionary interpretation. In contrast, international law has evolved considerably in relation to the protection of some groups and their culture, so that customary international law, and especially international human rights law, may be deemed to prohibit group cultural destruction and consequently entail State responsibility. The thesis argues that this evolution could ground the articulation of an international law-based approach to the concept of cultural genocide both by allowing for its criminalisation through the crime against humanity of persecution and by providing tools for a stronger framework of State responsibility, especially in the context of genocide prevention. Furthermore, this approach would give rise to the possibility of further conceptualising reparation for the intended cultural damage. Against this background, the thesis firstly draws conclusions as to the irrelevance of enclosing the debate exclusively at the level of the genocide legal framework and, secondly, as to the relevance of cultural genocide as a 'paralegal concept', an understanding which would drive the interpretation of international legal norms, especially in cases involving indigenous peoples' cultural harm.
Accepted: 2014-07-14T15:02:04Z
Keywords: Economic aspects; Economic development; Foreign investment; International Law; Investments

The impact of the unfair commercial practices directive (2005/29/EC) on contract law - Đurović, Mateja (European University Institute, 2014)
This thesis examines the relationship between the law on unfair commercial practices and consumer contract law. The thesis develops the claim that Directive 2005/29/EC, on unfair commercial practices (UCPD) has had a strong impact on the content of consumer contract law, despite the declaration concerning the independence between both branches of law contained in Article 3(2) UCPD. In order to substantiate this claim, the thesis examines the implications for consumer contract law of the main components of the regulatory regime laid down by the UCPD, namely, (1) the notion of average consumer, (2) the duty to trade fairly, (3) the duty of information and (4) the remedies. By looking both at the theoretical underpinnings and at the actual operation of this regulatory regime, the thesis casts light on the way in which the UCPD has shaped consumer contract law. The thesis further shows that this is an ongoing phenomenon whose ramifications may be far-reaching, for it implies that the UCPD is powerfully fuelling the Europeanization of contract law.
Accepted: 2015-02-09T12:46:29Z
Keywords: Consumer protection; Contracts; European Union countries

Establishing an international registration system for the assignment and security interest of receivables - Jon, Woo-Jung (Oxford University, 2014)
Legal systems around the world vary widely in how they deal with the assignment of receivables. This legal variety makes it difficult for financiers to conduct their international receivables financing business. This thesis suggests an International Registration System for the Assignment and Security Interest of Receivables (‘IRSAR’) and proposes a model international convention for the IRSAR (‘proposed IRSAR Convention’), which could help financiers to overcome the obstacles they currently encounter. Under the proposed IRSAR Convention, the international assignment of receivables would be regulated by a unified legal system with respect to priority and perfection. The IRSAR would facilitate international project financing. Furthermore, the IRSAR would enable companies to raise finance from greater ranges of investors around the world through international receivables financing and to dispose of non-performing loans more easily. The proposed IRSAR Convention would succeed the UN Convention on the Assignment of Receivables in International Trade in the attempt of establishing a registration system for international assignments of receivables. The proposed IRSAR Convention confines its scope of application by defining the assignor (or the security provider), inventing the concept of ‘Vehicle for the International Registration System’ (‘VIRS’). The proposed IRSAR Convention applies where the assignor or security provider is a VIRS. An assignment of a receivable where the assignor is a VIRS and a security interest in a receivable where the security provider is a VIRS could be registered in the IRSAR. Under the proposed IRSAR Convention, priority of assignments of and security interests in receivables is determined by the order of registration in the IRSAR. The proposed IRSAR Convention would be a receivables version of the Cape Town Convention. With respect to the contents and effect of registration, it would prescribe a notice-filing system along the lines of that adopted in the UCC Article 9. With respect to the operation of the registration, it would adopt an automatic online registration system operating 24 hours a day, 365 days a year like the International Registry under the Cape Town Convention.
Keywords: Comparative law; Contract; Property law; Restitution; Tort

Chapter 4 offer regulation under the 2008 Companies Act - Labuschagne, Frederik J. (University of Pretoria, 2014)
Chapter 4 of the Companies Act of 2008 aims to regulate offers to the public of securities and is reviewed against the principles which underscore the regulation of offerings. An overview of the historical development of the company which is parallel to the regulation of securities shows the crystallized principles which are compared against the development and enactment of the current regulatory regime. The concept of “complete law” as key element to effective regulation is discussed and applied in the review of Chapter 4 determining the effectiveness of the dispensation. The three determining concepts of regulation: the “offer,” “securities” and “public” are studied against the definitions which determine regulation and the inclusion of secondary market regulation of unlisted securities. Serious shortcomings in the process are identified. These errors, together with the practical problems of defining and regulating the secondary market in Chapter 4 read with the remainder of the delineating definitions, concludes that the current system is not in line with the principles of regulation and the Grundnorm of fraud prevention, resulting in Chapter 4 falling under the concept of “incomplete law” resulting in a high probability of enforcement failure and inefficiency. A comparative overview related to the jurisdictions of the United Kingdom and the United States follows with recommendations aimed at amending Chapter 4 relating to the regulatory regime in toto as well as the regulation of unlisted securities in the secondary market.
URI: https://repository.up.ac.za/handle/2263/45981
Keywords: Companies Act; Offer regulation

Legitimation of the economic community of West African states (ECOWAS): a normative and institutional inquiry - Nwankwo, Chidebe (Brunel University, 2014)
This thesis was submitted for the degree of Doctor of Philosophy and awarded by Brunel University LondonThis study is an attempt at determining the normative legitimacy of the Economic Community of West African States (ECOWAS). At its core, it scrutinizes the current mandate of the organization following the layering of economic integration objectives with human rights protection, sustenance of democracy, and the rule of law. The study discusses the elements of legitimacy across disciplines mainly, international law, international relations and political science. Legitimacy is eventually split along two divides, the normative and descriptive/sociological aspects. The study traces the normative content (shared/common values) underlying integration in Africa, concluding that integration has been born on new ideals such as human rights, democracy and the rule of law. Expectedly, Regional Economic Communities (RECs) as building blocks of the prospective African Economic Community (AEC) under the African Union (AU) regime are mandated to play a vital role in moving the continent forward upon these values. The inquiry is extended to the institutions of ECOWAS to determine their capacity to effectively implement the new mandate of the organization and operate supranationally. In the process, key legal and institutional shortcomings are discussed, particularly in relation to national institutions. It is argued that while human rights protection enhances the normative legitimacy of ECOWAS, it must not be pursued in isolation. Economic integration and protection of citizens’ rights are co-terminus and mutually reinforcing. Hence, community institutions must reflect this link if they are to be effective. The study concludes on the note that, while ECOWAS possesses layers of legitimacy, and have carried out legitimation steps, it cannot be considered a legitimate organization if Member States continue to be non-compliant with community objectives and if key legal questions remain unaddressed. It is submitted that ECOWAS is merely undergoing legitimation, whether it can eventually be considered a legitimate organization is dependent on addressing the identified challenges
Brunel University Research Archive
Keywords: AU; Democracy; ECOWAS; Human Rights; Humanitarian Intervention; Legitimacy; Peace and Security; Regional integration

The action for injunction in EU consumer law - Ogorzałek, Magdalena (European University Institute, 2014)
In 1998 the European Union adopted a new self-standing instrument of collective enforcement - the Action for Injunction. Until then, the main focus was on the improvement of the position of the individual consumer through the adoption of substantive consumer law directives. The Injunction Directive provides for a general framework on consumer law enforcement in national and cross-border litigation. Qualified entities, public agencies and/or consumer organisations, are granted legal standing. National courts are bound to mutually respect the standing of EU wide registered qualified entities. Outside these clear-cut rules on the mutual recognition of standing, the Injunction Directive remains largely silent. The implementation into 28 Member States swiftly revealed the rather limited harmonising effect. The thesis investigates and explains how despite the legally approved diversity, the Injunction Directive contains the potential to turn diversity into convergence. The key to understanding the potential is the thesis of dualism of enforcement measures. Read together with the Annex the Injunction Directive establishes the deep interconnection between collective and individual enforcement, of substantive and procedural enforcement, of judicial and administrative enforcement. The different levels and means of enforcement should not be regarded separately but should always be looked at in their interplay, in their mutual institutional design and their mutual impact. Evidence for convergence can be found in the Invitel judgment of the ECJ and in the practice of consumer organisations via co-ordination actions across borders by which they overcome the boundaries of collective vs. individual or judicial vs. administrative enforcement. Regulation 2006/2004 re-adjusts the dualistic structure of enforcement in favour of public bodies and promotes convergence through para-legal means, through new modes of enforcement, through co-operation and co-ordination outside courts and in open interaction between administrative bodies, to which consumer organisations are admitted on approval only.
Accepted: 2015-02-09T14:17:54Z
Keywords: Consumer protection; European Union countries; Injunctions

The role of competitors in the enforcement of state aid law - Pastor Merchante, Fernando (European University Institute, 2014)
State aid law is made up of rules and procedures whose main characters are the Member States – as the addressees of the norms – and the Commission – as their enforcer. The prominent position of these two actors often overshadows the impact that the administration of the rules on State aid has on private undertakings, be it the beneficiaries of State aids or their competitors. This thesis is concerned with the latter. The aim of the thesis is to assess the extent to which competitors may rely on the rules on State aid to protect themselves against the potentially harmful effects of subsidies and other forms of state, financial assistance to firms. This endeavour raises two challenges. The first challenge is to identify the channels through which competitors may voice their interest in the context of a system of governance to which they are in principle alien. This is the issue of access. The second challenge is assess the likelihood that the Commission shall heed to the concerns voiced by competitors. In other words, the challenge is to gauge the power of influence that competitors may exert through each of these channels. This is the issue of leverage. In order to carry out this inquiry, the thesis scrutinizes the means of redress available to competitors before national courts (“private enforcement”), as well as the opportunities that they have to make their voice heard in the course of the Commission’s procedures (“public enforcement”) – namely, the possibility to lodge complaints, the possibility to participate in the consultation phase of Article 108(2) TFEU and the possibility to seek the judicial review of State aid decisions.
Accepted: 2015-02-09T14:56:15Z
Keywords: Antitrust law; European Union countries; Government aid; Restraint of trade; Subsidies; Unfair Competition

Competition law and standard essential patents : oscillating between protection of patent rights and access to standards - Petrovčič, Urška (European University Institute, 2014)
This thesis explores the way in which EU and U.S. antitrust rules address opportunistic conducts that emerge in the context of standard essential patents (SEPs). The analysis finds that the two systems have very different scopes in addressing those practices: conduct lawful under U.S. antitrust law is condemned by the EU competition law and vice versa. In contrast to other fields of antitrust, the differences between the EU and U.S. approach do not arise from the application of different legal standards, but rather reflect the core divergences in the statutory texts that address unilateral practices. The analysis also shows that both in the European Union and in the United States, competition authorities have tried to increase the scope of competition law—first, by stretching the antitrust doctrines outside established borders, and second, by advocacy measures designed to avoid opportunism related to SEPs. The thesis shows, nonetheless, that both approaches are problematic and a more cautious strategy is needed to avoid the risk of injecting imbalance in the standardization context.
Accepted: 2014-10-02T12:32:07Z
Keywords: Antitrust law; Competencia; Competition law; European Union countries; Patent licenses; Unfair Competition; United States

The requirement of consent for the transfer of shares and freedoms of movement : toward the liberalization of private limited liability companies : a comparative study of the laws of Portugal, France, Italy, Spain, the United Kingdom and the United States and its interplay with EU law - Vicente, Lécia (European University Institute, 2014)
Toward the Liberalization of Private Limited Companies – A comparative study of the laws of Portugal, France, Italy, Spain, the United Kingdom and the United States and its interplay with EU law’, I try to shed light on the dynamics of private limited liability companies (PLLCs), and how they can be legally designed to become efficient units of economic development in Europe and the United States. I take a social sciences approach to the legal question: How does the design of clauses establishing restrictions on transfer of shares of private limited liability companies affect investment made in these companies and their consequent development? To answer this question, I develop two parallel lines of investigation. First, I undertake an embedded historical study to trace the evolutionary patterns of PLLCs in six countries. Furthermore, I longitudinally track the standards of behavior of market agents in the selected jurisdictions. Second, I develop my legal research by looking at an anomaly regarding the transfer of shares and changes in the ownership structure of these business organizations. Transfer of shares in PLLCs is, for the most part, regulated by default rules which impose restrictions on transfers. Typically, the parties do not contract around these default rules. The anomaly lies in the fact that, even though shareholders of these companies do not opt out of these rules, shareholders often ignore them and/or breach them at a later stage.
Keywords: Business enterprises; Corporate law; Limited liability; Private companies

Economies of scope, modularity and property rights in software technologies - Özaygen, Altay (Université Evry-Val-d’Essonne, 2013)
Cette thèse étudie le rôle des différents régimes de propriété intellectuelle (DPI) et évalue ses conséquences sur l'industrie du logiciel. En outre, ce travail porte sur l'équilibre entre deux modèles de logiciels, celui des logiciels privés et celui des logiciels libres et open source, et cherche à évaluer leurs effets sur la performance des entreprises. Ainsi nous discutons dans un premier article les facteurs clés de la cinquième révolution technologique à travers le concept de paradigme technoéconomique (Freeman et Perez, 1988) et nous considérons l'open source comme le principal de ces facteurs. D'autre part, nous étudions les trois aspects des technologies logicielles. Les caractéristiques structurelles des logiciels, c'est-a-dire les économies de gamme (Panzar et Willig, 1981; Teece, 1980) et la modularité (Parnas, 1972; Langlois et Robertson, 1992) représentent les deux premiers. Le régime de propriété intellectuelle, qui est a l'origine des particularités institutionnelles du logiciel (Mazzeloni et Nelson, 1998b), représente le troisième aspect. Au sein de cette thèse nous utilisons différentes méthodologies et considérons plusieurs technologies logicielles pour répondre à nos questions de recherches. Les économies de gamme de logiciels sont étudiées à travers une simulation multi-agents. La recherche sur la modularité est effectuée par une analyse des brevets sur la technologie d'indexation de vidéo. La question des DPI est examinée dans deux chapitres différents. Dans un premier chapitre, une analyse de données de panel est faite pour démontrer l'effet du brevetage et de la contribution au projet du noyau Linux sur la performance des entreprises. Le second chapitre traite quant à lui d'un cas particulier où l'innovation ouverte est réalisée par un groupe de recherche en ingénierie du logiciel au sein d'Alcatel-Lucent Bell Labs, Nozay, France. Ces exemples uniques ne peuvent conclure sur aucune tendance macro sur l'industrie du logiciel, mais cette thèse vise à alimenter les discussions sur les droits de propriété intellectuelle au sein de l'industrie du logiciel.
Keywords: Analyse de brevets; Industrie – Logiciels; Intellectual property; Logiciels libres; Modularity; Open source; Propriedade intelectual; Propriété intellectuelle; Software industry

Copyright : rebalancing the public and private interests in the areas of education and research - Wang, Jia (Stellenbosch University, 2013)
The general public should have wide access to copyrighted materials for education and research. However, since the current copyright law system subtly favors copyright holders, it is time to re-evaluate copyright law to ensure it meets its original purpose of promoting the learning of the society. The research primarily focuses on how to broaden copyright limitations and exceptions for the public to access and use learning materials. Within the framework of the copyright law system, other mechanisms that allow users to access copyrighted materials at a reasonable price also are considered. Such mechanisms include an efficient collective copyright management system and various licensing schemes. In an information network environment, it is time for developing countries to reform copyright law in order to promote education and research. It is hoped the findings of this study not only benefit South Africa and People's Republic of China, but also provide insights and guidelines to other developing countries with similar conditions.
URI: http://hdl.handle.net/10019.1/85834
Keywords: China; Copyright; Economic aspects; Education and copyright law; Effect of copyright on ICT; Freedom of information and opinion; Globalization and education; Information and communication technology; Intellectual property; South Africa

The influence of the Consumer Protection Act 68 of 2008 on the common law of sale - Barnard, Jacolien (University of Pretoria, 2013)
The purpose of this thesis is to investigate to what extent the Consumer Protection Act 68 of 2008 (CPA) influences the common law of sale in South Africa. “Common law of sale” refers to the essentialia of sale (the minimum characteristics that parties must have consensus on to conclude a valid sale). The parties must have consensus on the intention to buy and sell, the things sold and the purchase price. The common law of sale also refers to the common law duties of the parties, the duties of the seller in particular (conversely therefore the rights of the buyer). The primary duties of the seller which will be investigated are: a. the duty of safe-keeping (including and investigation into the passing of benefit and risk doctrine); b. the duty of delivery and transfer of ownership; c. the warranty against eviction; and d. the warranty against latent defects. The primary common law duties of the buyer to pay the purchase price and accept the thing sold are included in the investigation as well. The formalities required in certain sale agreements, that wording must be in plain language as well as the buyer’s cooling-off rights are also investigated. An investigation into the influence of the CPA on the common law of sale in South Africa warrants a systematic framework and modus operandi which are: a. an investigation into the historical background of the common law of sale and its principles in the Roman law and Roman-Dutch law; b. a critical analysis of the position where the CPA is not applicable (the common law position); c. an extensive analysis and critical evaluation of the relevant provisions of the CPA and the influence thereof on the common law of sale; d. a comparative analysis of the appropriate provisions in Scotland and Belgium; e. a conclusion of the influence of the CPA on the common law of sale (whether the particular common law of sale principle is confirmed, amended or excluded in terms of the Act); and f. recommendations (taking into account the comparative analysis) regarding the rectification of uncertainties and ambiguities that arose as a result of the investigation. It is also important to remember that the existing principles of the common law of sale will still be applicable for transactions and agreements which fall outside the application of the Act. The golden rule to keep in mind when investigating the influence of the CPA on the common law of sale is to determine which approach and interpretation will be most beneficial to the consumer.
https://repository.up.ac.za/handle/2263/32798
Keywords: Common law of sale; Consumer Protection Act; South Africa

Three Essays on Bank Lending and Corporate Finance - Chen, Liqiang (McMaster University, 2013)
This thesis includes three essays on several important topics in empirical finance: Chief Executive Officer (CEO) risk-taking incentives, the cost and syndicate structure of bank loans and corporate investments with internal funds. This thesis contributes to these aspects of finance literature and the three essays are presented in Chapter 2, 3 and 4. The first essay investigates how implicit contractual relationship between creditors and borrowers attenuates the conflict of interest between creditors and shareholders that arises from CEO compensation contracts when a corporation can be considered a nexus of explicit and implicit contractual relationships among stakeholders. We find that bank loans for firms with CEOs who are provided with risk-taking incentives have higher spreads and shorter maturities. A relationship between the lender and its borrower mitigates the influence of incentives for CEO risk-taking on loan spread and loan maturity. Such a relationship is especially beneficial for informationally opaque firms. The results are robust to the endogeneity of relationships and the simultaneous determination of loan spread, loan maturity and collateral requirements. Our results highlight the importance of the interaction between explicit and implicit contractual relationships to a firm’s borrowing cost. The second essay investigates the effects of a borrowing firm’s CEO risk-taking incentives on the structure of the firm’s syndicated loans. The conflict of interest between creditors and shareholders arising from CEO risk-taking incentives is a major concern of borrower moral hazard for syndicate lenders, which require intensive monitoring by lead arrangers in a syndicate. When CEO risk-taking incentives are high, syndicates are structured to facilitate better due diligence and monitoring efforts. These syndicates have a smaller number of total lenders and are more concentrated, and lead arrangers will retain a greater portion of the loan. Moreover, we examine the factors that affect the link between CEO risk-taking incentives and syndicate loan structure. CEO risk-taking incentives have a lesser effect on the syndicate structure when lead arrangers have a good reputation and have a prior lending relationship with a borrowing firm. By contrast, CEO risk-taking incentives have a greater influence on syndicate structure when borrowing firms are informationally opaque, are financially distressed or have low growth prospects. The third essay studies corporate investments with internal funds when firms face real investment friction using a sample of U.S. oil companies from 2003 to 2011 before and after the 2008 financial crisis. We show that firms’ capital expenditures are more sensitive to their lagged cash holdings than to their contemporaneous cash flows. By making investments with realized cash holdings, firms can avoid the investment adjustment costs that are incurred when investing with uncertain cash flows. We also show that cash flow policies are affected by liquidity constraints following the 2008 financial crisis: firms build up more cash reserves from cash flows, cut back payouts and raise more debt to maintain cash holdings.
Keywords: Bank lending; Cash flows; Cash holdings; Corporate Finance; Executive compensation; Financial Management; Investments; Managerial incentives

Legal aspects of privately financed infrastructure projects (PFIPs) in China: the case for international standards - Liang, Shuang (University of Leeds, 2013)
This thesis discusses the reform and improvement of Chinese legislation on Privately Financed Infrastructure Projects (PFIPs), to develop the PFIP model in China, under the protection of Chinese laws, so that its implementation in China may reach international standards. Existing Chinese laws are found to be insufficient in reducing risks to PFIPs because of certain shortcomings. Therefore, it is necessary to reform and improve Chinese legislation on PFIPs, to prevent their failure. The Legislative Guide and Model Provisions drafted by UNCITRAL are treated as the international standards to guide Chinese legislation reform on PFIPs. Other countries’ laws on PFIPs provide supplementary reference. This thesis addresses its aim in four steps: First, the current Chinese legislative and institutional framework on PFIPs is reviewed, with discussion on establishing a more appropriate legislative and institutional framework, to facilitate the development of PFIPs in China through the principles of transparency, fairness, long-term sustainability and the elimination of undesirable restrictions. Second, Chinese laws on the concessioner selection procedure in PFIPs are reviewed, with discussion on possible improvements to the laws to achieve international standards of fairness and transparency. Third, current Chinese laws and policies which affect the various contracts involved in PFIPs are reviewed, with discussion on these may be improved to achieve international standards. Fourth, the PFIP dispute settlements that may be used in China are reviewed, with discussion on the necessity to remove certain undesirable restrictions in relevant Chinese laws. Following the rapid rise in the practical use of PFIPs in China, this thesis offers a strong theoretical basis for suggesting a reform of Chinese legislation on PFIPs. It also provides a general basis for any national reform of laws on PFIPs in any other countries.

The collection of value added tax on online cross-border trade in digital goods - Van Zyl, Stephanus Phillipus (University of South Africa, 2013)
Technological advances have had a major impact on traditional retail shopping changing it from a physical undertaking to a completely digitised experience where consumers buy digital media online. VAT systems that do not specifically provide for, or which have not been adapted to cope with, technology-driven advances, generally do not provide for the adequate levying and collection of VAT on cross-border digital trade. The South African VAT system is no different. The taxation of e-commerce should not artificially advantage or disadvantage e-commerce over comparable traditional commerce, or unnecessarily hinder the development of e-commerce. This thesis determines whether the South African VAT Act 89 of 1991 in its current form, can be applied adequately to raise and collect VAT on cross-border digital transactions. Where shortcomings in the VAT Act are identified, the harmonised VAT rules of the European Union (EU), together with the Organisation for Economic Cooperation and Development (OECD) proposals on consumption taxes, are analysed and discussed to seek possible solutions and make recommendations.
Keywords: Anonymising technology; B2B transactions; B2C transactions; BIT-rate tax; Banker-customer confidentiality; Blocked VAT account; Consumption taxes; Cross-border digital trade; Electronic commerce; Electronically supplied services; European Union; European Union countries; Fractionated VAT; OECD; South Africa; Taxation; VAT collection model; Value-added tax

Open-source software and the rationale for copyright protection of computer programs - Karjiker, Sadulla (Stellenbosch University, 2013)
The rationale for the legal protection of copyright works is based on the perceived need to encourage the creation of works which are considered to be socially beneficial. By awarding authors proprietary rights in their creations, copyright law allows authors the ability to earn direct financial returns from their efforts, and, thus, copyright law provides the required incentives for authors to create copyright works. Since the early days of commercial software development, copyright protection has been extended to computer programs; thus, by providing such protection it was assumed that their production should be encouraged, and that without such protection they will not be produced to the extent required by society. Comparatively recently, we have witnessed large-scale production of open-source software, which is licensed on generous terms, giving users the right to freely use, modify and redistribute such software. By adopting such licensing terms, the authors of open-source software are unable to charge licensees a fee for permission to use their software, which is the reward which copyright assumes authors seek to create such software. This development has made it necessary to re-evaluate the rationale for copyright protection of computer programs, and determine whether the continued protection of computer programs is justifiable. This study seeks to first establish a coherent theoretical justification for copyright protection, which it is submitted should be an economic justification, rather than a moral justification. The legal analysis in this work seeks to establish whether the copyright protection of computer programs is consistent with the economic justification for copyright protection. In particular, the analysis focuses on the current scope of copyright protection, and seeks to establish whether such protection is excessive, stifling creativity and innovation, and, thus, imposing too high a social cost. It is contended that copyright doctrine has generally sought to minimise these costs, and that current scope of copyright protection of computer programs leaves enough creative room for the production of new software. Despite the fact that the effect of open-source software licences is that authors are unable to earn the direct financial rewards which copyright enables authors to earn as an incentive to create such software, their authors continue to have financial incentives to create such software. Commercial firms who invest in open-source software do so because they seek to provide financially-rewarding related services in respect of software, or because it serves to promote sales in their complementary products. Similarly, the participation of individual computer programmers is largely consistent with the standard economic theories relating to labour markets and the private provision of public goods. Individuals are principally motivated by economic motives, such as career concerns. Copyright protection gives participants the choice to opt for the direct financial rewards which its proprietary protection enables, or the more indirect financial rewards of open-source software development. It is submitted within this research that rather than undermining the rationale for copyright protection of computer programs, the development of open-source software has illustrated that copyright protection allows for the emergence of alternative business models, which may be more economically advantageous to authors.
URI: http://hdl.handle.net/10019.1/80044
Keywords: Computer programs; Copyright law; Intellectual property; Open-source software

A comparative study of law and practice of arbitration in Kenya, Nigeria and Zimbabwe, with particular reference to current problems in Kenya - Torgbor, Edward Nii Adja (Stellenbosch University, 2013)
Arbitration as a mode of dispute settlement has been growing steadily all over the world. The momentum for commercial arbitration in particular was provided by the 1985 UNCITRAL Model Law on International Commercial Arbitration (“the Model Law”). Legislation based on the Model Law has been enacted in many countries. The arbitration laws of three of these countries, Kenya, Nigeria and Zimbabwe, are selected for consideration in this dissertation because of their common origins, similar statutes, similar problems, shared experiences, and their regional distribution. As the writer’s arbitration practice is based in Kenya, that jurisdiction is the primary, albeit not the only, source and foundation for this work, the focal point of reference and the citations from the law and practice incorporated in this research. The work consists of three chapters. Chapter one is a brief introduction and an overview of arbitration. This is followed by the statement of the research question, the justification for the research, methodology and the structure and content of the dissertation. Chapter two describes the legal and contextual framework for the investigation of the research questions in the selected jurisdictions of Kenya, Nigeria and Zimbabwe. Customary Law arbitration is included as a significant feature of African arbitration law. The UNCITRAL Model Law, the Arbitration Act, 1995 (Kenya), the Arbitration and Conciliation Act, 1988 (Nigeria), the Arbitration Act, 1996 (Zimbabwe), the Arbitration Act, 1996 (England), and the South African Draft Arbitration Bill are all used as legislative or statutory points of reference in the discussion of the research questions. Chapter 3 contains the main focus of the dissertation in which six recurrent arbitration problems in Kenya are discussed in the context of domestic arbitration. The research investigates (i) the illusiveness of consent as the basis for consensual arbitration (ii) jurisdictional challenges (iii) the procedural powers of the arbitral tribunal (iv) the disruptive effect of adjournments and postponements on the arbitral process (v) constraints on the granting of interim relief and (vi) the enforcement of the arbitral award. Original, creative and innovative proposals in response to these problems include: the express legislative recognition of the manifestation of consent in both the verbal and written forms of the arbitration agreement, the use of the constructive dispute resolution technique, statutory recognition of customary law arbitration, the use of an expedited arbitration procedure, the award of exemplary and punitive damages in arbitration, a code of sanctions to facilitate the arbitration process, and a simplified method of enforcement and execution of the arbitral award. The dissertation concludes with reflections on the future of arbitration in Africa, and the need for modernization and harmonization of arbitration laws for peaceful resolution of disputes and serious conflicts across Africa. The aim of this study is best illustrated by a short story: In the early nineties there was a man, untrained in any known discipline, who strutted court corridors, trade centres and market places, carrying a placard advertising himself to lawyers, traders and marketers as “An Arbitrator and Private Judge”. He attracted business, charged a handsome percentage fee on the value of the claim, was duly paid, until officialdom caught up with him and put paid to his burgeoning career as “Arbitrator-Judge”. But the reckless enthusiasm spawned by his wit and imagination, and the idiosyncratic practices in dispute resolution persisted and are manifest in Kenyan arbitration culture today. The need to remove bad practices, avoidable impediments, and inefficiency in the arbitration culture of Kenya in order to make its procedures and processes more efficacious, is the heart of this study.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration and award; Comparative law; Dispute resolution; Kenya; Nigeria; Zimbabwe

Análisis y modelización de la adopción de los sistemas de recomendación en el comercio electrónico - Cabal Cruz, Claudia Constanza (Universidad Internacional de Andalucía, 2013)
Tesis doctoral (Lectura 07/02/2013). Director: Francisco José Martínez López (Universidad de Granada). Tribunal: Martínez López, Francisco José, Univ. de Huelva, presidente; Padilla Meléndez, Antonio (secretario); Ortigueira Sánchez, Manuel (vocal); Luna Huertas, Paula (vocal); García Ordaz, María Mercedes (vocal). Se puede afirmar que la historia de las relaciones entre los individuos y las organizaciones se divide en dos, antes y después de la aparición de Internet, la penetración de los PC y de la banda ancha. En el campo organizacional, las Tecnologías de la Información y las Comunicaciones (TIC), se refieren al amplio espectro de tecnologías de base de los Sistemas de Información, y que se constituye en un importante recurso, que facilita la continua adaptación del Sistema de Información a los cambios internos y del entorno. La aplicación de los sistemas de información a las actividades organizacionales, caso concreto que nos interesa, el marketing, se constituye en una herramienta para que la empresa se mantenga competitiva en el mercado. Las relaciones de intercambio desarrolladas en los mercados electrónicos posibilitan la comunicación bidireccional entre las partes y entre cada una de ellas y el propio medio, exigiendo a las organizaciones implementar un marketing interactivo en términos de producto, precio, distribución y comunicación, en el que consumidor dirija el proceso de intercambio. El desarrollo del comercio en los mercados electrónicos y las aplicaciones de los sistemas de información al marketing, han tomado características del comercio tradicional y han sido adaptadas al electrónico, caso específico la adaptación que han realizado una gran cantidad de empresas comerciales en la Web a las recomendaciones a sus usuarios a través de los sistemas de recomendación (RS), entendidos como sistemas que realizan recomendaciones de productos que están buscando, o basadas en sus gustos o preferencias. Este es tema central de este trabajo, pero no enfocado a su parte técnica, sino a la comprensión de los factores que explican el comportamiento online de los consumidores frente a los RS de determinada website (WS), por lo que se propone un modelo teórico, sustentado por once hipótesis principales y otras subordinadas, la cuales son el resultado de la integración reflexiva de la Teoría de la Acción Razonada, de la adaptación Trust-TAM y de la Teoría del Comportamiento Planeado. Del análisis y corroboración del modelo, se puede concluir que el proceso de adopción del sistema de recomendación de cierto website se conforma sobre la base que a) el usuario percibe la opinión de otros con respecto al uso de los sistemas de recomendación en general y del particular de un determinado website; b) el grado de confianza que le merece al consumidor la interacción e información proporcionada por el sistema de recomendación; c) la percepción de utilidad de uso del sistema de recomendación que tiene su usuario; y d)la actitud del individuo hacia el sistema de recomendación de un website particular.

The concept ‘fairness’ in the regulation of contracts under the Consumer Protection Act 68 of 2008 - Stoop, Philip Nicolaas (University of South Africa, 2013)
The thesis analyses the concept ‘fairness’ in consumer contracts regulated by the Consumer Protection Act 68 of 2008, mainly from the perspective of a freedom and fairness orientation. It discusses the evolution of ‘fairness’ as background to a more detailed discussion of the classification of fairness into substantive and procedural fairness. The thesis examines dimensions of fairness, factors which play a role in the determination of fairness, and fairness- oriented approaches in an attempt to formulate a framework for fairness in consumer contracts. The main aspects that should be taken into account to justify a finding of fairness, or to determine whether a contract is fair, are identified. This analysis addresses, too, the extent to which the fairness provisions of the Consumer Protection Act are appropriate (with reference to the law of South Africa, Europe, and England).
Keywords: Consumer contracts; Consumer protection law; Contracts; Contractual fairness; Freedom of contract; Law of contract; Liberty of contract; Procedural fairness; Standardized terms of contract; Substantial fairness

The problem of systemic violation of civil and political rights in Cameroon : towards a contextualised conception of constitutionalism - Enonchong, Laura-Stella (University of Warwick, 2013)
Post-independent Cameroon has grappled with the problem of systemic violation of civil and political rights (CPR) despite a transition from single party dictatorship to multiparty democracy in the 1990s. Various legislative measures including the adoption of a supposedly ‘rights friendly’ constitution in 1996 have done little to ameliorate that problem. This thesis adopts a concept of constitutionalism, based on contemporary international standards, to analyse the problem of CPR violations from the perspective of the constitutional arrangements in Cameroon. It examines the system of separation of powers, the method of securing judicial independence and the mechanisms for judicial review. The argument is made that the problem can be attributed in part to the predominant influence of the French civil law system in Cameroon’s bijural legal system. Although for historical reasons, Cameroon operates both the English common law and the French civil law, constitutional developments have continued to be influenced by the latter which lends itself to practices that are not sufficiently supportive of constitutionalism as defined herein. The thesis, however, goes further to explore how the constitutional system could be reinforced to provide a more conducive framework for the protection and enhancement of CPR. Drawing on two strands of arguments, one highlighting features of the common law system that can be more supportive of constitutionalism and the other which highlights the value of indigenous antecedents of constitutionalism, the thesis proposes the development of a contextual model which is more reflective of Cameroon’s peculiar legal and socio-political circumstances. It proposes what is described as an Optimal Integrative Approach (OIA) as a framework for developing a contextual model, more conducive for the protection and enhancement of CPR in Cameroon.
URI: http://webcat.warwick.ac.uk/record=b2689324~S1
Keywords: Cameroon; Civil rights; Constitutional law; Human rights; International law and human rights; Politics and government

Bridging the GAAP? : IFRS in accounting practice - Hartmann, Berit (Jönköping International Business School, 2013)
This thesis investigates how International Financial Reporting Standards (IFRS) come to act within an organizational context. In particular, the thesis explores how the requirements for goodwill accounting and leasing influence organizational calculative practices, transforming and shaping operations management. Drawing on actor-network theory, this study moves away from a priori distinctions, following the construction and mobilization of accounting numbers across institutionalized boundaries within and around the organization. The empirical investigation took place in a large, worldwide active media group that is listed on a European stock exchange. The group is a particular interesting setting because of its diverse business structure and its German code-law accounting roots. Business combinations are a major growth factor within the industry and a high degree of decentralization in the organization placed responsibility for investment decisions at low hierarchical levels. Goodwill accounting and impairment testing were therefore highly significant calculative practices in the group. The study finds that the constitutive role of the financial reporting standards in the organization both solves tensions and dilemmas around the number and creates new ones when crucial interests are lost in translation. These tensions and dilemmas arise between the aim of standardization and closure for the construction of a legitimate value of the future, and the aim to mobilize numbers in order to motivate and create value for a future. Originally intended for the financial representation of organizational substance and performance, the standards become associated with operations management activities, helping to create the faithful records that sum up the organization. This interrelation helps to close concern around the representation of the future in a ‘fair’ value by distributing the calculative practices over a wide network of actors spanning inside and outside the organization. However, the relationship also forces a connection between calculations and ambitions that otherwise would have preferred to stay separate. This thesis offers a new perspective on IFRS implementation by emphasizing organizational activities. Through a focus on integration and the link between financial and management accounting, the ‘implementation problems’ highlighted in previous literature gain a refined theorization. When taking organizational practice seriously, integration becomes a process that may find temporal stability but will never be final. In the process, conflicts might be solved but new dilemmas will arise. In turn, concepts like decision usefulness, comparability and earnings management cannot exist in a stable form but are rather constructed in networks that disregard commonly assumed boundaries inside and around the organization.
JIBS Dissertation Series, ISSN 1403-0470 ; 094 URN: urn:nbn:se:hj:diva-23148 OAI: oai:DiVA.org:hj-23148 DiVA, id: diva2:689238
Keywords: IFRS; International Financial Reporting Standards

Entrepreneurial financing decisions, venture capital ownership and bargaining power - Heughebaert, Andy (Ghent University, 2013)
It is widely acknowledged that entrepreneurial companies play a key role in shaping a local economy. Entrepreneurial companies are a source of growth and innovation for an industry and provide jobs for the local population. However, entrepreneurs of high growth oriented companies rarely have the capital to finance their innovative ideas themselves and therefore also have to accept the risks associated with assessing and acquiring the necessary finance resources from other investors. The goal of this dissertation is to study the impact of venture capital (VC) finance on such entrepreneurial finance decisions. Although VC investors are a highly focused and specialized kind of investors that offer a wide range of differentiated services, it is to date still unclear how VC investors may reduce agency costs for other potential investors. The first study of this dissertation studies the effect of VC finance and associated VC ownership for finance decisions from other investors who have the potential to invest in these companies. This study demonstrates that VC ownership results into a larger supply of finance for the entrepreneurial company. Second, I find that VC ownership results into an even larger positive effect on capital investment decisions from equity investors as VC finance is typically also associated with the implementation of an equity-oriented corporate governance mechanism in entrepreneurial companies. VC ownership does not have an effect on the supply of finance from financial debt investors, however. Nevertheless, I find that debt finance is equally available for companies with VC ownership as compared to companies without VC ownership, which is a surprising result given the high risk associated with high growth companies that raise VC finance. Another important finding of this study is that the positive effect of VC ownership is stronger for repeated VC finance versus non-repeated VC finance. In fact, these results indicate that the effect of VC finance for entrepreneurial companies’ finance decisions is considerably larger if VC investors commit to further finance the company. The second study of this dissertation extends the first study and explores the effect of VC ownership on entrepreneurial finance decisions in different institutional settings. Although the effect of VC ownership is not limited to one specific institutional context, this study shows that its impact on entrepreneurial finance decisions is stronger in countries with a better quality of law enforcement and in countries where the entrepreneur is able to obtain a fresh start after bankruptcy. Specifically, in countries with a better enforcement of law, VC investors are more effective in reducing agency problems between entrepreneurs and potential investors. The attractiveness of a fresh start after bankruptcy will also be higher for an entrepreneur who raised VC finance, as VC investors focus more on maximizing the value of their portfolio rather than on the survival of individual firms. The third study acknowledges the fact that VC investors are not all equal and explores which VC investor types have more bargaining power versus the entrepreneur and how such differences in VC investor bargaining power affect company valuations in VC investment rounds. VC investor bargaining power is important because company valuations are the outcome of negotiations between the VC investor and the entrepreneur. We show that university VC firms and government VC firms negotiate lower valuations compared with independent VC firms. The proprietary deal flow of university VC firms and the limited competition in niche markets in which government VC firms compete will directly increase their bargaining power versus the entrepreneur, which these VC investor types then further exploit by negotiating lower company valuations compared with independent VC investors. Although differences in VC investor type did not affect entrepreneurial finance decisions in the first and second study, they do affect the equity stake that an entrepreneur will have to give up in order to raise VC finance and in order to a have a greater access to entrepreneurial finance from potential investors in the future.
http://hdl.handle.net/1854/LU-4096609
Keywords: Bargaining power; Financing decision; Venture capital

A Comparative Analysis of the Efficacy of the General Anti-Avoidance Rule as a Measure Against Impermissible Income Tax Avoidance in South Africa - Kujinga, Benjamin Tanyaradwa (University of Pretoria, 2013)
This thesis comparatively analyses the SA income tax general anti-avoidance rule (GAAR) in s 80A-L of the Income Tax Act 58/1962 and similar rules in Australia, Canada, the UK and the judicial doctrines in the US and the UK. It is argued that, while the SA GAAR may serve as a deterrent, it is going to have limited efficacy against impermissible tax avoidance due to the uncertainty it creates. It is argued that uncertainty will cause judicial activism to protect permissible tax avoidance, extensive and inconsistent judicial interpretation and confusion amongst taxpayers and SARS as to what constitutes permissible or impermissible tax avoidance. This thesis ends by recommending certain amendments, based on the comparative analysis, to the SA GAAR which can reduce uncertainty and thus improve it efficacy.
URI : https://repository.up.ac.za/handle/2263/33430
Keywords: General Anti-Avoidance Rule; Income tax; South Africa

The development of a commercial law structure in the SADC with specific reference to OHADA - Leno, Ngaundje Doris (University of Pretoria, 2013)
In a region where there is diversity of laws, the author maintains that law reform is a catalyst for investment and development. This thesis aims at demonstrating that OHADA provides practical lessons for the development of a uniform commercial law structure in the SADC. This is following OHADA’s success in developing uniform commercial rules that are directly applicable in the contracting states. To achieve this, the thesis uses a “structured focused comparison” methodology that allows for two separate, but structurally linked accounts of the structures of both organisations. In exploring the structures of both organisations, the thesis endeavours to: determine whether there is the need for the development of a commercial law structure in the SADC; whether such a structure can be developed within the current SADC structure and whether OHADA can serve as a possible model for the SADC. The findings show that no part of the African continent has witnessed regional legal reform on the scale of that initiated by OHADA. It equally reveals the absence of a uniform commercial law structure in the SADC and the lack of supranational structures to adopt full panoply of business laws and to preserve the uniformity of laws in the member states. The findings from this thesis provide evidence that there is the need forthe development of a commercial law structure in the SADC and improvement of the current SADC structure. There is no doubt that thi swould do away with legal uncertainty in cross-border commercial transactions among SADC states.
Accepted: 2016-05-20T09:04:41Z URI: https://repository.up.ac.za/handle/2263/52731

A Proposed discharge dispensation for consumer debtors in Tanzania - Maghembe, Ngwaru Jumanne (University of Pretoria, 2013)
The Tanzanian private sector is growing, partly due to the state’s efforts to conform to the global economy. As the economy expands and the National Microfinance Policy of 2001 is realised, more and more credit has been made available to consumers. As a direct consequence of the increase of credit, the number of over- indebted consumers in Tanzania is on the rise. The current debt relief system is regulated by the Tanzanian Bankruptcy Act no. 9 of 1930, a piece of colonial legislation. Unfortunately this law is ineffective, costly and outdated. Some of the problems identified in this study with this debt relief regime include the lack of a cost- effective alternative to bankruptcy and its total reliance on the judiciary, an institution that is itself overburdened and requires reform. The purpose of this study is to make recommendations for the reform of the current debt relief system and propose a debt relief dispensation for consumer debtors in Tanzania that will efficiently cure over- indebtedness. A wide comparative investigation was undertaken in this study of selected common law, civil and mixed legal systems that have substantial experience with the boom in over-indebted consumers now facing Tanzania. A number of solutions were borrowed from these systems that may potentially solve Tanzania’s debt relief problem. One of the main findings of this thesis is that, over time, developed jurisdictions that rely on credit in the private sector appear to be converging on the same type of procedures and moderate philosophies for consumer debt relief. These include less judicial supervision for debt relief procedures, less freedom of choice for over-indebted consumers when it comes to the type of procedures available, and mandatory surplus income repayments for debtors who can afford it. In order to address the problems of the Tanzanian debt relief system, this thesis proposes a complete overhaul of the administration of debt relief procedures in Tanzania and the introduction of a combined alternative to bankruptcy that consists of three joint procedures. A number of amendments are also proposed for the Bankruptcy Act no.9 of 1930. This thesis states the status of legal developments as they were in the selected jurisdictions on 31 December 2012.
https://repository.up.ac.za/handle/2263/32961
Keywords: Bankruptcy Act; Current debt relief system; Tanzania

The regional integration of African trade mark laws: challenges and possibilities - Mupangavanhu, Yeukai (University of the Western Cape, 2013)
Keywords: African Union; Differences; Harmonisation; Intellectual property; Regional integration; Similarities; TRIPs; Trade Mark Directive; Trade marks; Unification

Challenges to political and economic intergration in Africa : A socio-Legal perspective - Mwanawina, Ilyayambwa (North-West University, 2013)
This study is concerned with integration efforts on the African continent. This study sets out to investigate the politico-legal and economic impediments to regional and continental integration efforts in Africa. The documents, processes, and organs of the African Union, as the main continental organisation, are the focal point of this study. In order to achieve this, the study primarily adopted a qualitative approach since the literature involved in this work could not be reduced to a quantitative concept. The study ensured that the premises and the conclusions in this work conform to the principles of reliability and validity and in addition the elimination of bias in this was curtailed by validation and triangulation. This was achieved by the fact that the arguments in this work were not only based on qualitative arguments but, where possible, quantitative data was brought in to validate/ triangulate the qualitative arguments. Evidently, the study would have been incomplete if it did not discuss and evaluate the many regional economic communities that have been established to further the objectives of the Treaty establishing the African Economic Community. One of the major premises that this study discovers is that there is a direct and demonstrable relationship between democracy and economic progress; genuine and sustainable development has to be fostered primarily by securing peace and stability on the African continent. Some of the other key findings of the study include that; a) the ultimate goal of the African Union is full political and economic integration leading to the United States of Africa; b) overlapping memberships to a custom unions are highly detrimental to the state since it has to subscribe resources and political will to two or more different arrangements. c) overlapping memberships cause confusion, inertia and most importantly legal uncertainty thereby stifling trade liberalisation efforts; d) many African states still guard their sovereignty closely and that many perceive that yielding their sovereignty to a continental body is tantamount to losing their independence; e) the African Union infrastructure still lacks supra-national and national institutions that are capable of implementing its values; f) the African Union infrastructure does not contain an institutionalised mechanism for the promotion and management of Union affairs at national level; g) the NEPAD initiatives, the APRM process and the functions of the Peace and Security Council play a positive role in African politico-legal and economic development. It has however been shown that these mechanisms are more reactive than preventative and as such intervene too late in the internal affairs of member states; h) armed conflicts cause a reduction in the per-capita Gross Domestic Product growth rate of a nation experiencing a civil war/ conflicts. i) the African Union has regressed from the original timelines of the African Economic Community. The highest regression being Phase 2 which involves the most critical element of strengthening of African regional integration arrangements and the harmonisation of policies concerned. A thirteen (13) year postponement is noted in this regard. j) Africa's poor intra-trade performance is also attributed to the limited progress among African countries in fostering structural transformation. This structural transformation relates to the building of roads, bridges, railway lines and power grids; In order for the African continent to re-position itself in an attempt to harness the benefits of regional integration, some of the recommendations that the study makes are that; a) the African Union grant supra-national status to institutions of the Union for the equitable and speedy attainment of integration; b) the Union and member states should as soon as possible create mechanisms with decision making powers to manage Union affairs at regional and national level; c) the operationalization of the Pan African Parliament should be pursued with the utmost determination to bring the Parliament to full functionality as a Continental legislative body; d) the operationalization of the African Court of Justice and Human Rights be completed as soon as possible in order to allow the body to function as a fully-fledged continental judiciary. This will ensure that the development of integration jurisprudence from an international law perspective is not delayed. The Court will also pursue the enforcement of Human rights norms and practices; e) the Union should further lead the continent in the following sectors with clear and predictable deliverables; i) the establishment and upgrading of regional land, air, and other means of transportation and communication; ii) the creation of a cross-border power and energy generation and distribution network; iii) the establishment, advancement, and diversification of regional financial and commodity markets; iv) the establishment of a regional higher education system by facilitating wider access through specialization in regional integration; The study further acknowledges that these recommendations are not conclusive since the study of regional integration is still at its infancy and many other ideas on how to strengthen African regional integration still await discovery.

Corporate Restructurings in Zimbabwe : a Legal Analysis of the Regulation of Corporate Mergers and Acquisitions in Zimbabwe - Nzero, Ignatious (University of Pretoria, 2013)
The Zimbabwean economy rapidly declined over the past two decades. A record hyperinflationary environment and a collapse of the financial service sector coupled by lack of external lines of credit created a difficult operating environment for corporate businesses. Businesses thus either closed down operations or resorted to survival strategies. Corporate mergers and acquisitions emerged as natural favoured strategies in implementing survival corporate restructuring transactions. However, the success of such strategies largely depends on the effectiveness of the merger regulatory framework, that is, its ability to promote beneficial corporate restructuring transactions on one hand and to maintain the competitive structure of the market on the other hand. This research analyses the current merger regulatory framework in Zimbabwe and assesses whether it is suited to promote beneficial corporate restructuring transactions implemented through mergers and acquisitions without unnecessarily distorting the competitive structure of the market. Employing the failing firm doctrine as the focal point, the research identified a number of shortcomings within the current merger regulatory framework that impacts upon its ability to effectively promote beneficial corporate mergers and acquisitions without sacrificing the competitive market structure. Selected comparative jurisdictions were used to draw various lessons for Zimbabwe. The aim of the comparative study was not to provide an exhaustive analysis of these jurisdictions but to identify specific arrears that can be used to develop and suggest an effective merger regulatory framework for Zimbabwe. In order to remedy the identified shortcomings inherent within the current Zimbabwean merger regulatory framework, this thesis proposes a number of amendments to the current Competition Act [Chapter 7:01] of 1996. These proposed amendments are aimed at bringing clarity, flexibility and strengthening the merger regulatory framework including the institutions tasked with such. The research is primarily a legal analysis of the Zimbabwean merger regulating statute and its implications on any decisions made by the competition authority. As such, the thesis states the status of legal development in Zimbabwe and the selected comparative jurisdictions as of 31 July 2013.
URI: https://repository.up.ac.za/handle/2263/53211

Climate change and Africa : the normative framework of the African Union - Pallangyo, Daniel Mirisho (North-West University, 2013)
There is enough evidence on how climate change consequences will adversely affect Africa despite the fact that it is the continent that has least contributed to the problem. The international climate change regime recognises Africa's vulnerability to climate change and provides for special treatment under the United Nations Framework Convention on Climate Change (the UNFCCC). Thus, the international climate change regime presents an opportunity for African countries to adapt and mitigate the consequences of climate change through the UNFCCC mechanism. However, the international climate change legal regime has not been able to adequately assist African countries to address the consequences of climate change under the vulnerability principle. Although the current international climate change regime requires developed countries to reduce their greenhouse gas (GHG) emissions, Africa needs to take steps itself to address the problem, because it is most vulnerable to the consequences of climate change. The African Union (AU) could play a great role in ensuring that the international climate change regime addresses the consequences of climate change in the region. This could be done through fostering strong African common positions during international climate change negotiations. A strong common position could strengthen African bargaining power and might result in more funding, capacity building and technology development and transfer for adaptation and mitigation programmes under the UNFCCC-Kyoto Conference of Parties. However, reaching a strong common position requires the cooperation of the AU member states. In this context, African regional integration is an opportunity for the AU to foster such cooperation among member states. The Treaty Establishing the African Economic Community (the Abuja Treaty), the Constitutive Act of the AU and the Protocol on the Relations between the AU and Regional Economic Communities (RECs) prioritise regional economic integration and call for states' cooperation, but the call has not yet been heeded. To realise deep and viable African integration, there must be a well-structured institutional and legal framework that defines the relationship between the AU, the AEC and the RECs. African regional integration is also seen as an avenue whereby the AU can create its own regional climate-change regime. In this regard, the AU's and RECs' normative framework on climate change is examined in order to assess whether it adequately integrates climate change issues. This study finds that although Africa is most vulnerable to the consequences of climate change, the AU's and RECs' normative framework on climate change is weak and inadequate to address the problem. The Framework should integrate climate change issues in order to achieve sustainable development. The AU should also ensure that member states ratify the relevant treaties and protocols (the Maputo Nature Convention and the Protocol establishing the African Court of Justice and Human Rights) that have not yet been ratified in order that they may become operational. The Maputo Nature Convention puts sustainable development in the forefront of attention as a reaction to the potentially conflicting environmental and developmental challenges facing the continent (such as climate change), but it is not yet in force. This work finds that human rights law can strengthen the AU's role in addressing climate change through its normative framework. The human rights approach to climate change under the African Charter on Human and Peoples' Rights (the Banjul Charter) is a viable avenue because human rights law forms the basis for states' responsibility based on human rights obligations and principles. The extraterritorial application of the Banjul Charter presents an avenue for AU institutions such as the Human Rights Commission and the African Human Rights Court to curb the effects of climate change through a human rights lens. The future of the AU is presented within the context of a set of recommendations that identify strong African regional integration as an avenue through which the AU can foster the cooperation of member states to address the consequences of climate change in the AU's and RECs' normative frameworks. General recommendations are made on the need for the international climate change regime to pay more attention to issues of funding, capacity building and technology development and transfer on the basis of the vulnerability principle and in relation to the principles of equity and common but differentiated responsibilities and respective capabilities. Also, the AU needs to strengthen its legal and institutional structures to ensure deep African integration that is capable of addressing common challenges such as the consequences of climate change.
Keywords: African Charter on Human and Peoples Rights; African Economic Community (AEC); Climate Change; EAC Treaty; ECOWAS Treaty; Human rights; International climate change regime; Normative framework; Regional integration; SADC Treaty; State cooperation; The Constitutive Act of AU

The harmonisation of rules on the recognition and enforcement of foreign judgments in the Southern African Customs Union - Rossouw, Mandi (University of the Western Cape, 2013)
The thesis considers the approaches followed by the European Union with the Brussels Regime, the federal system of the United States of America under the ‘full faith and credit clause’; the inter-state recognition scheme under the Australia and New Zealand Trans- Tasman judicial system; as well as the convention-approach of the Latin American States. It finds that the most suitable approach for the SACU is the negotiation and adoption by all SACU Member States of a multilateral convention on the recognition and enforcement of foreign judgments, comparable to the 1971 Convention of the Hague Conference on Private International Law; the EU Brussels I Regulation and the Latin-American Montevideo Convention, as complemented by the La Paz Convention. It is imperative that a proposed convention should not merely duplicate previous efforts, but should be drafted in the light of the legal, political and socio-economic characteristics of the SACU Member States. The current legislative provisions in force in SACU Member States are compared and analysed, and the comparison and analysis form the basis of a proposal for a future instrument on recognition and enforcement of foreign judgments for the region. A recommended draft text for a proposed Convention on the Recognition and Enforcement of Foreign Judgments for the SACU is included. This draft text could form the basis for future negotiations by SACU Member States
Keywords: Civil and commercial transactions; Cross-border litigation; Foreign judgments; International Trade; Recognition and enforcement; Regional integration; Trade facilitation

Interim Measures in International Commercial Arbitration: A Comparative Study of the Egyptian, English and Scottish Law - Shalaan, Wael S. E. (University of Stirling, 2013)
Interim Measures are viewed as an essential means to protect parties‘ rights in international commercial arbitration disputes. Most Arbitration Laws and Rules have recognised the arbitral tribunal‘s power to grant such measures. The success of this system relies on the court‘s assistance of the tribunal during the process. This relationship between the tribunal and the court is something vague under Egyptian Law, since there are no clear rules addressing the matter. Hence, this research examines the theories that explain the tribunal‘s authority and the relationship with the authority of the court. This study uses a comparative analytical approach in terms of analyzing relevant legal texts to determine the optimal legal approach to the issue. The purpose of the study is to address deficiencies in the Egyptian law – the Code of Civil Procedure and Egyptian Arbitration Law – and compare it with English, Scottish Arbitration Acts and international arbitration systems, laws, and practices. The findings of this research offer several recommendations that could help achieve a successful and smooth arbitration process. This study identifies and explains types of interim measures and explores the international practice of every type. It gives some important recommendations for future development and improvement of the Egyptian law. It also makes general recommendations that would help improve the efficiency of the English and Scottish laws.
Keywords: Egyptian Arbitration Act; English Arbitration Act; Interim Measures; International Commercial Arbitration; Provisional Measures; Scottish Arbitration Act

Cession of Life Insurance Policies in securitatem debiti : a Practical Perspective - Sunkel, Kelly (University of Pretoria, 2013)
The security cession of the rights under life policies marries two separate areas of the law: The Law of cession and the Law of Insurance. This makes for a complex union since varying common law and statutory principles find application, and in reality trade practices also play a role. In theory a cession in securitatem debiti may take one of two possible constructions, namely a pledge or a fiduciary security cession, and each has its own advantages and disadvantages. Disparity arose when judicial preference was given to the pledge construction while academics preferred the other. The problem, however, was larger than a disagreement as to the better construction. The underlying problem was that there was a lack regarding clarity as to the practical operation of security cession of life policies, in addition to the problems surrounding the construction thereof. As a solution to this problem some academics have suggested legislative intervention. The South African Law Reform Commission, nevertheless, advised against it in 1991 and was of the opinion that the issue was one which our courts would eventually solve. In the 22 years since then, our courts have merely confirmed its preference for the pledge construction. The intricacies of security cessions of life policies have seen no further judicial development. It is probable that the courts do not have enough practical information at hand to advance this area of the law. An investigation into the operation of such cessions in practice was thus necessary. The outcome of the practical investigation reveals that legislative intervention is indeed a viable solution especially since the issues are too complex for the courts to solve. As part of this work, legislation has been drafted and it is recommended that this is inserted into the Security by Means of Movable Property Act .
Keywords: Life Insurance; Security Cession

Legal risk and compliance risk in the banking industry in South Africa - Terblanché, Janet René (North-West University, 2013)
The Basel Committee on Banking Supervision has defined operational risk, legal risk and compliance risk. However, the definitions might not be adequate for countries with a hybrid legal system, such as South Africa. This study aims to provide a practical solution to the problems faced by countries with a hybrid legal system wishing to comply with the Basel Committee’s standards. It is argued that compliance, compliance risk and regulatory risk should all be viewed as constituent components of legal risk, and in turn necessarily also of operational risk in a hybrid legal system. Legal risk is a wide concept which includes all aspects of a legal system, while compliance risk is a narrower concept which only includes the codified aspects of a legal system. Legal risk therefore includes compliance risk. However, the opposite is not true as compliance risk does not include legal risk, and the two concepts are decidedly shown not to be synonymous in a mixed legal system.
Keywords: Basel Committee; Compliance; Compliance risk; Legal compliance; Legal risk; Operational risk; Regulatory compliance; Regulatory risk

Direct taxation and the internal market: assessing possibilities for a more balanced integration - Yevgenyeva, Anzhela (University of Oxford, 2013)
The role of the Court of Justice of the European Union in the process of direct tax integration in the European Union (EU) has been widely discussed in the academic literature, while another important actor, the European Commission, has attracted much less attention. The Commission’s input is commonly perceived to be limited to the right of legislative initiative. This study questions such an oversimplified interpretation and draws a more nuanced picture of EU tax harmonisation by integrating an analysis of the complex regulatory approaches adopted by the Commission for the establishment and smooth functioning of the Internal Market. It is argued that the past decade brought a notable change in the Court-dominated pattern of direct tax integration. This change is apparent first in the evolution of enforcement strategies under Articles 258 and 260 TFEU; and second, in the increased reliance upon non-binding regulatory measures. Both developments have strengthened the role of the Commission, supplying it with more possibilities for influencing national direct tax systems, despite the reluctance of Member States to agree upon legislative harmonisation. Against this background, the procedural and substantive problems associated with these instruments require closer examination. The normative scope of this research covers the key procedural problems related to the infringement procedure and non-binding regulatory measures. The empirical component explores the Commission’s enforcement and coordination practices, drawing particular attention to two case studies: the tax treatment of losses in cross-border situations and exit taxation. Following the analysis of enforcement and coordination in the field of direct taxation, the study argues the need and proposes potential solutions for (i) the developing of a more comprehensive procedural framework for the infringement procedure and non-binding regulatory acts; (ii) the strengthening of accountability mechanisms; and (iii) the enhancing of the effectiveness of their application.
Keywords: Direct taxation; EU Law; Enforcement; European Law; Exit tax; Good governance; Infringement procedure; Internal Market; Non-binding coordination; Soft law; Tax coordination; Tax integration; Tax treatment of losses; Taxation

Statutory regulation of forced sale of the home in South Africa - Steyn, Lienne (University of Pretoria, 2012)
The home of a debtor has never enjoyed specific statutory protection against forced sale in the individual debt enforcement and insolvency procedures in South Africa. In Jaftha v Schoeman and Others; Van Rooyen v Stoltz and Others (2005 (2) SA 140 (CC)) and Gundwana v Steko Development CC and Others (2011 (3) SA 608 (CC)), the Constitutional Court recognised that in the individual debt enforcement process execution against a debtor's home, even where it has been mortgaged in favour of a creditor, may constitute an unjustifiable infringement of the right to have access to adequate housing, provided by section 26 of the Constitution. The effect of these decisions is that, in every case in which a creditor seeks to execute against a person's home, a court must consider "all the relevant circumstances" to determine whether execution is justifiable, in terms of section 36 of the Constitution. The absence of a properly constructed framework, incorporating clear substantive and procedural requirements, within which these recently established principles must be applied, has led to divergent approaches in the courts and a lack of clarity regarding circumstances in which execution against a debtor's home will be permitted. Further, courts have not considered the impact of section 26 and other rights on the position where a debtor's home is realised by the trustee of an insolvent estate in terms of the Insolvency Act 24 of 1936. This has given rise to a number of unanswered questions as well as to a lack of predictability that potentially hold adverse consequences for bond finance, commerce, and the economy generally. The need to balance the competing interests emphasises the necessity for a coherent contextual framework within which forced sale of a debtor's home may occur. This thesis examines issues surrounding forced sale of a debtor's home in South Africa. It compares the position in other legal systems and suggests mechanisms and an appropriate method, or process, for inclusion in statutory provisions to regulate the forced sale of a debtor's home in both the individual debt enforcement and insolvency procedures in South Africa.
Keywords: Forced sale; Vente forcée

The legal and institutional framework for the enforcement of online consumer arbitration awards: evidence from Australia and Sri Lanka - Kananke, Chinthaka Liyanage (La Trobe University, 2012)
Keywords: Australia; Commercial law; Conflict of laws; Consumer protection; Dispute resolution; Electronic commerce; Sri Lanka

Disability, discrimination and equal opportunities : a comparative labour law study - Harmse-Truter, Laurentia (University of Johannesburg, 2012)
This study aims to investigate the different ways in which the position of people with disabilities can be addressed. Antidiscrimination legislation can play a very important role. Efforts to create equal opportunities must, however, not be limited to legislative initiatives and policy declarations. There is an urgent need for education and training of this minority group. 7 Systematic efforts to heighten public awareness of civil rights and in particular the recognition of the rights of the disabled community are imperative. This study aims to bring home the truth that "disability rights are an idea and ideal whose time has come. ,, When addressing the issue of disability discrimination (or for that matter any kind of discrimination) several principles need to be addressed, the most important being the following: The meaning of the concept of "equality" needs to be established. The fact that all people are equal, does not necessarily mean that all people must be treated the same. When speaking about disability discrimination one must know who forms part of the protected class. For that reason the first issue that must be addressed is the definition of "disability": This leads to the next question, namely which individuals should be protected by anti-discrimination laws and should they benefit from affirmative action measures? What is meant by the term "discrimination"? Is it at all permissible to distinguish between groups of people and, if so, when and which standards are to be applied? What role can anti-discrimination legislation fulfil in the struggle for equality? When dealing with anti-discrimination legislation, what is required in order to prove discrimination and what remedies must be available to an aggrieved party? Normally, in case of criminal action proof is required beyond reasonable doubt and in case of civil action on the balance of probabilities. 10 Civil action offers more effective remedies, but should it be punitive in nature (by awarding damages to the aggrieved party) or non-punitive (by putting the aggrieved party in his/her "rightful place")? What sort of enforcement mechanism is needed? Is it a task for the ordinary tribunals or rather a special body created for that purpose? What defences should be available to an employer accused of discriminatory practices? Who should benefit from enforcement? Only the individual victim or all members of that group? Is anti-discrimination legislation sufficient or is something in addition called for? If positive measures are required, what form must these measures take? This study will address these questions specifically with relation to people with disabilities.The "equality principle" will first be studied. Thereafter the concept of "disability" will be defined. There is a movement away from a medical model of disability towards a social model that takes account of the disabling effects of attitudes and structural barriers on the position of disabled people. Then the concept of "discrimination" will be addressed. Discrimination has many different forms and can take place in different contexts In the following chapter possible solutions to the problem of disability discrimination will be raised. Thereafter follows an important comparative analysis of different jurisdictions on international, supra-national and national level. Different jurisdictions have reached different stages in addressing this problem. The factual analysis of each jurisdiction will include the existence of any anti-discrimination legislative measures, the scope of the protected class, applicable employment provisions, defences available to employers, and the success achieved in addressing the problem. The contentious issue of affirmative action measures will also be addressed. By drawing inferences from the comparative study, suggestions will be made for future developments in South Africa. The conclusion is reached that it is imperative for South Africa to draft disability anti-discrimination legislation that takes account of the needs of this minority group. Legislative initiatives, however, are not enough and must be supported by various programmes aimed at the disabled themselves and the community that they live in. Only then can human rights become a reality also for people with disabilities.
Keywords: Comparative law; Discrimination; Employment; Labour law; People with disabilities

The legal implications of harmonising labour laws in the Southern African Development Community (SADC) region - Okharedia, Akhabue Anthony (University of South Africa, 2012)
The purpose of this research is to explore the need for, and the legal implications of, harmonising labour laws in the Southern African Development Community (SADC). Chapter One highlights a number of factors that call for the harmonisation of labour laws in the SADC region and discusses some of the reasons why labour laws are not well developed in the region. The influence of globalisation on labour standards in southern Africa and the influence of regionalism on the harmonisation of labour laws are discussed at length. The inference that could be drawn from this discussion is that for a regionalisation process in southern Africa to be successful, there is an urgent need to harmonise the region’s labour law system. This thesis confirms that Southern Africa has many lessons to learn from the regional harmonisation of labour law in the European Economic Community and the current European Union. The implementation of international labour standards in southern Africa is investigated. The main areas examined include (1) freedom of association, (2) collective bargaining, (3) forced labour and (4) discrimination. The findings of this investigation show that there is no uniformity in the implementation of International Labour Organisation (ILO) standards in the SADC region and, therefore, it is recommended labour law should be harmonised in terms of ILO standards. In respect of the benefits to be derived from the harmonisation process, an empirical investigation was conducted in the SADC region and the following is recommended: the harmonisation of labour law in the SADC region will help with the implementation of ILO standards, protection of workers against the economic power of employers in the workplace and maintaining similar benefits for migrants in the region.
Keywords: Child labor; Collective bargaining; Compulsory labour; Discrimination in employment; Discrimination in the work environment; Droit du travail; Forced labour; Freedom of association; Harmonisation; International Labour Organization; International Labour Standards; Labour law; SADC

A proposal to guide future draft article provisions for a model harmonised international commercial arbitration law code (HICALC) in the Middle East and North Africa or a uniform Arab arbitration law - Ayad, Mary Boulos (Macquarie University, 2012)
MENA law codes are a well-crafted blend of civil and Islamic law in which civil law principles do not contravene with Islamic provisions. They were originally based on Sanhuri’s codes to varying degrees. Yet, common law principles derived either from English common law or Islamic customary usages are unidentified and thus ignored. Here, this lacuna is rectified through a comparative analysis of the primary data (eg, cases, statutes and arbitral award decisions), adding common law and uncodified Islamic custom to MENA law codes. The purpose of this comparative analysis is to allow common legal principles found at civil, common and Islamic law to be distilled in the service of creating a new harmonised international commercial arbitration law code (HICALC) or uniform Arab arbitration law (UAAL) for adoption in the MENA.1 These principles already form part or all of the legal systems in the MENA. They can be readily assimilated into a harmonised or uniform code. Would this new harmonised code lead to higher arbitral award enforcement in the MENA? According to the evidence the answer is yes. The author understands that at the present time the HICALC articles are ambitious and as such they are a beginning point and can initially be taken as a harmonised international commercial arbitration common rule (HICACR). A brief overview of the history of harmonisation is given. An assessment of the status of the laws and traditions of the MENA was carried out. A comparative analysis of the relevant differences and similarities of the case study countries (Egypt and the United Arab Emirates) was carried out to show the gaps in the laws and areas requiring reform. An analysis of enforcement of arbitral awards was carried out. The unique problems that ICA and IIA encounter in the MENA as derived from an analysis of cases and the laws therein are expounded in consideration of matters pertaining to enforcement. A comparative analysis of universal principles which must be included in a new code, including custom, was carried out. An analysis of the unique features and unique needs of the MENA was carried out in order to inform the Draft Article Provisions. An analysis of important international legal instruments dealing specifically with international arbitration and the gaps therein is given. The draft articles for a HICALC or uniform Arab arbitration law were derived as a result of these multiple layers of analysis. The matters of compétence de la compétence, expropriation, interest, public policy and sovereign immunity are highlighted as the most important areas requiring urgent reform. The results of this research are suggested Draft Article Provisions for a model Harmonised International Commercial Arbitration Law Code (HICALC) or a uniform Arab arbitration law. Future drafters may refer to and revise these articles for implementation. The synthesis of theory and practice addresses doctrinal matters that arise in international investment arbitrations and international commercial arbitration, with a focus on investor–State arbitrations. This synthesis provides a new theoretical conception of the jurisprudence of international arbitration, particularly in regard to the matters of res iudicata, precedent and expansion of arbitral tribunal powers and jurisdiction.
Keywords: Arab countries; Arbitrage; Arbitragem; Arbitration; Arbitration Law; Arbitration and award; Commercial law; Commercial law (Islamic law); Common rule; Dispute resolution; HICACR; HICALC; Harmonised International Commercial Arbitration; International commercial arbitration; MENA law codes; Middle East; North Africa; UAAL; Uniform Arab arbitration law

Financial liberalisation and economic growth in ECOWAS countries - Owusu, Erasmus Larbi (University of South Africa, 2012)
The thesis examines the comprehensive relationship between all aspects of financial liberalisation and economic growth in three countries from the Economic Community of West African States (ECOWAS). Employing ARDL bounds test approach and real GDP per capita as growth indicator; the thesis finds support in favour of the McKinnon-Shaw hypothesis but also finds that the increases in the subsequent savings and investments have not been transmitted into economic growth in two of the studied countries. Moreover, the thesis also finds that stock market developments have negligible or negative impact on economic growth in two of the selected countries. The thesis concludes that in most cases, it is not financial liberalisation polices that affect economic growth in the selected ECOWAS countries, but rather increase in the productivity of labour, increase in the credit to the private sector, increase in foreign direct investments, increase in the capital stock and increase in government expenditure contrary to expectations. Interestingly, the thesis also finds that export has only negative effect on economic growth in all the selected ECOWAS countries. The thesis therefore, recommends that long-term export diversification programmes be implemented in the ECOWAS regions whilst further investigation is carried on the issue.
Keywords: ARDL-Bounds testing approach; Capital accounts liberalisation; Co-integration; ECOWAS; Economic Community of West African States; Economic growth; Economic stablization; Financial crises; Financial liberalisation; Ghana; Interest rates liberalisation; Ivory Coast; Monetary Policy; Nigeria; Stock market developments

Board Structure, Ownership Concentration and Intellectual Capital - Zhang, Meiyi (Victoria University of Wellington, 2012)
This thesis investigates the influence of board structure and ownership concentration on the level and value relevance of intellectual capital disclosure. This thesis is motivated by the limited post-IFRSs (International Financial Reporting Standards) adoption intellectual capital disclosure studies carried out in a less stringent regulatory environment of New Zealand, and limited research addressing the determinants of the level and value relevance of intellectual capital disclosure. Based on an application of agency theory, cost-benefit theory and value relevance approach, this thesis argues that firm-specific factors are expected to have a significant impact on the level and value relevance of intellectual capital disclosure. Within the agency theory, board structure and ownership concentration mitigate agency costs by enhancing the monitoring function of the board over managers’ opportunistic behaviour, which consequently influence the level of intellectual capital disclosure. In addition, as New Zealand has less tough rules in relation to board structure and ownership concentration, it is expected that these relationships will be more easily identified in the New Zealand context. Second, as most of the intellectual capital disclosure is voluntary, this disclosure is subject to a firm’s cost-benefit analysis. Cost-benefit theory suggests that a firm should not fully disclose its information unless the benefits outweigh the costs of the disclosure. Therefore, the level of intellectual capital disclosure is also influenced by the factors that determine the costs and benefits of the disclosure. Finally, this thesis adopts the value relevance approach to measure the quality of the disclosure. It is expected that the factorsassociated with the level of the disclosure also influence the value relevance of the intellectual capital disclosure. This thesis is based on a sample of 155 firms listed on the New Zealand Exchange covering a total of 519 firm-years over the period between 1 January 2008 and 31 August 2011. A self-developed disclosure index and multiple regression analysis are employed to test the hypothesised relationships. Overall, the results indicate that the average level of intellectual capital disclosed by New Zealand listed firms is low and the human capital component is the most frequently disclosed intellectual capital component. The results provide strong evidence that board structure characteristics, including board size and independence, have a significant positive impact on the level of intellectual capital disclosure. There is strong evidence for a non-linear relationship between ownership concentration and the level of intellectual capital disclosure, which is robust to various types of intellectual capital (i.e. human, relational and structural capital). The results show marginal evidence that board gender diversity has a positive impact on the level of intellectual capital disclosure. In terms of the value relevance of intellectual capital disclosure, only board size has a positive impact on the value relevance of the intellectual capital disclosure. In the individual component analysis, board independence is found to have a significant positive impact on the value relevance of the human and relational capital disclosures. This thesis provides the most recent evidence on the influence of board structure and ownership concentration on the level and value relevance of intellectual capital disclosure in a less stringent regulatory environment of New Zealand. These findings have important implications to regulators, and assist information users in the interpretation of the voluntary intellectual capital disclosure.

Lex mercatoria in international arbitration theory and practice. Vol 1 - Elcin, Mert (European University Institute, 2012)
This dissertation suggests a new theory of lex mercatoria that takes into account the complex and spontaneous order of international commerce. Since the emphasis is put on the nature of this order, the concept of lex mercatoria is examined as an ex post governance mechanism resolving contractual disputes with a view to maintaining and restoring the order of international commerce, without focusing on the traditional distinction of the doctrine between national and non-national legal rules applicable to the substance of such disputes in explaining the concept. The aim is to reflect lex mercatoria’s subtle effect on the practice of international arbitration, and to provide an explanation of lex mercatoria as a solution to the problems of the institution of international arbitration in terms of uncertainty and unpredictability of awards, rather than representing it as a factor aggravating those problems. Lex mercatoria is defined as the law of adjudication of the disputes arising from international commercial contracts on the basis of a few substantive and procedural principles, under which the reasonable expectations of the parties to a particular contract become the single source of their contractual rights, obligations and risk allocations. The argument is that lex mercatoria can be applied to both the choice of law analyses and the substance of the disputes in international arbitration. In choice of law analyses, lex mercatoria addresses specific difficulties relating to the conflict of laws through a principled decision making, such as the applicable conflict rules, and the interpretation of the parties’ intentions as to the applicable substantive rules. In its substantive application, lex mercatoria deals with, either as lex contractus or as lex fori, the interpretation, supplementation and correction of the contract as well as the applicable national laws in accordance with the basic principles, on which the order of international commerce rests.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration and award; Commercial law; Conflict of laws; Foreign trade regulation; Law merchant

Lex mercatoria in international arbitration theory and practice. Vol 2 - Elcin, Mert (European University Institute, 2012)
This dissertation suggests a new theory of lex mercatoria that takes into account the complex and spontaneous order of international commerce. Since the emphasis is put on the nature of this order, the concept of lex mercatoria is examined as an ex post governance mechanism resolving contractual disputes with a view to maintaining and restoring the order of international commerce, without focusing on the traditional distinction of the doctrine between national and non-national legal rules applicable to the substance of such disputes in explaining the concept. The aim is to reflect lex mercatoria’s subtle effect on the practice of international arbitration, and to provide an explanation of lex mercatoria as a solution to the problems of the institution of international arbitration in terms of uncertainty and unpredictability of awards, rather than representing it as a factor aggravating those problems. Lex mercatoria is defined as the law of adjudication of the disputes arising from international commercial contracts on the basis of a few substantive and procedural principles, under which the reasonable expectations of the parties to a particular contract become the single source of their contractual rights, obligations and risk allocations. The argument is that lex mercatoria can be applied to both the choice of law analyses and the substance of the disputes in international arbitration. In choice of law analyses, lex mercatoria addresses specific difficulties relating to the conflict of laws through a principled decision making, such as the applicable conflict rules, and the interpretation of the parties’ intentions as to the applicable substantive rules. In its substantive application, lex mercatoria deals with, either as lex contractus or as lex fori, the interpretation, supplementation and correction of the contract as well as the applicable national laws in accordance with the basic principles, on which the order of international commerce rests.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration and award; Commercial law; Conflict of laws; Foreign trade regulation; Law merchant

Innovation and Intellectual Property: Strategic IP Management and Economics of Technology - Holgersson, Marcus (Chalmers University of Technology, 2012)
Innovations and technological developments have been recognized for their central importance for economic success and growth at least since the 1930s. Intellectual property (IP) and intellectual property rights (IPRs), such as patents, trade secret rights, and copyrights, have during more recent decades caught increasing attention, and, mainly due to various developments at macro level, IP has become an important source of competitive advantage at micro level in many industries. This has led to an increased importance of strategic IP management, and the related research field has been growing since the late 1990s. This thesis aims to contribute to this growing field, and the first purpose of this thesis is to explore and explain strategic and innovation related IP management practices, and the managerial and economic consequences of such practices. Apart from the growing importance of IP management in general, an increased focus on open and collaborative approaches for creating innovations has led to a need for new and adapted IP management skills. The second purpose of this thesis is therefore to develop managerial and economic frameworks, models, and tools to be used in the intersection between IP management and open innovation practices. These purposes are addressed in a cover paper and six appended research papers of theoretical/conceptual as well as of empirical nature, being based on interviews, questionnaires, patent statistics, and document studies. In connection to the first purpose the results show that, while many small firms have problems with properly benefitting from the patent system, large firms have increasingly developed their IP strategies, especially their patent strategies. The purpose is then not only to appropriate monopolistic returns from innovations but also to govern various forms of open innovation. Large firms were found to in a first step increase their patenting (in terms of quantity), and in a second step focus more on selective, quality-oriented, and internationalized patenting. Additional results show that the internationalization leads to a convergence in managerial choices of output markets for patenting worldwide, in parallel with market and technology diversification. Further, a case from mobile telecommunications illustrates the role of IP management in the governance of open innovation systems. Finally, two cases from the automotive industry illustrate the IP-related problems that arise in connection to divestments and other types of disintegrations (‘IP disassembly problems’), and how IP management can mitigate them. This leads to the second purpose, related to the development of models, tools, and frameworks for IP management in relation to open innovation. First, the thesis provides a conceptual framework of innovation openness, especially pinpointing the role of IPRs. This framework emphasizes three key dimensions of innovation openness: resource distribution, technology governance, and technology accessibility. Second, a framework for managing the IP disassembly problem is presented, enabling increased exit opportunities and decreased transaction costs. Third, a method for determining fair, reasonable, and non-discriminatory royalties in licensing collaborations is developed, applicable to multilateral licensing deals. It stands clear that contemporary IP management is not (and has never been) only about maximizing excludability. Strategic IP management must therefore be developed and integrated with technology and corporate management in order to foster success at the micro level of firms, and thereby also at macro level. Developments in IP management skills (e.g., sourcing, control, commercialization, licensing, valuation, pricing) and IP contracts will then most likely lead to increased efficiency of interorganizational technological relationships and quasi-integrated organizational forms, and thereby also to increased innovativeness and economic development.
ISBN 978-91-7385-761-1 Doktorsavhandlingar vid Chalmers tekniska högskola, Ny serie nr 3442 ISSN 0346-718X
Keywords: Adresse IP; Economie numérique; Intellectual property; Propriedade intelectual; Propriété intellectuelle

Effectiveness of the Beneficial Ownership Test in Conduit Company Cases - Jain, Saurabh (Victoria University of Wellington, 2012)
Countries enter into double tax agreements with the economic objective of preventing double taxation of cross-border transactions. To achieve this objective, the contracting states agree reciprocally to restrict their substantive tax law. That is, a major policy of double tax agreements is to reduce double taxation of residents of states that are parties to the agreement. Residents of third states sometimes contrive to obtain treaty benefits typically by interposing a person or a conduit entity in one of the contracting states. In order to ensure that a resident of a contracting state who claims treaty benefits is entitled to them in substance, double tax agreements should be interpreted according to their substantive economic effect. Generally, double tax agreements follow the pattern of the OECD Model Tax Convention. The OECD Model Convention addresses the double taxation of dividends, interest and royalties, commonly collectively known as "passive income", in Articles 10, 11 and 12 respectively. These provisions usually operate by reducing withholding tax imposed by a source state on passive income that flows from the source state to a resident state. In order to prevent a resident of a third state from obtaining a source state withholding tax reduction by interposing a person or a conduit entity in the resident state, the OECD Model Convention requires the immediate recipient of passive income to be the "beneficial owner" of that income. That is, the OECD Model Convention requires the immediate recipient to be an owner in a substantive economic sense. Courts and commentators have difficulty in interpreting and applying the concept of beneficial ownership to conduit entities that are corporations, commonly referred to as "conduit companies". They have attributed the cause of the difficulty to the absence of a definition of the term "beneficial owner" in the OECD Model Convention. This thesis argues that the difficulty in applying the beneficial ownership concept to conduit companies has arisen not because of the absence of the meaning of the concept, but because logically and from an economic perspective the concept cannot be applied to companies in general, not to conduit companies in particular. The beneficial ownership test was meant to be a test of economic substance. From an economic perspective, the benefit or the burden of a contract entered by a company is economically enjoyed or borne by its shareholders. That is, in substance a company cannot be considered as owning income beneficially. From this consideration, it follows that conduit companies can never be considered entitled to treaty benefits. Nevertheless, the OECD Model Convention applies the beneficial ownership test to conduit companies pursuant to an assumption that at least in some cases conduit companies can be the beneficial owners of passive income. The Model Convention's assumption is based on the legal perspective that courts conventionally adopt. According to this legal perspective, companies hold income beneficially because they exist as separate legal entities from their shareholders. Courts find themselves battling these opposing perspectives when applying the beneficial ownership test to conduit companies. In order to make income tax law work efficiently, courts that are obliged to determine whether to honour claims to treaty benefits made by conduit companies have preferred to employ the legal perspective. Courts have justified this approach by adopting surrogate tests for the actual beneficial ownership test. Most of the surrogate tests do not relate to the concept of ownership at all. This thesis categorises the surrogate tests as "substantive business activity" and "dominion". By analysing reported cases, the thesis identifies deficiencies in these tests. One of the proposed outcomes of the thesis is to suggest an alternative approach for deciding conduit company cases. The thesis suggests that courts should consider an arrangement as a whole and investigate reasons for the existence of an immediate recipient of passive income in the specific corporate structure. The thesis also recommends amendments in the official commentary on Articles 10, 11 and 12 of the OECD Model convention in order to address the conceptual shortcomings inherent in those Articles.
Keywords: Double taxation; OECD Model Tax Convention; Tax law

Full protection and security in International Law - Magnusson, Finnur (Universität Wien, 2012)
The thesis covers one of the investment standards of international investment law, namely the full protection and security standard. In Part I, the study is introduced in terms of structure and substance. Chapter 1 provides a description of the scope of the research topic and a definition of its terms and structure. Chapter 2 covers the historical development of the full protection and security standard. Part II deals with three fundamental issues concerning the standard: sources, interpretation and content. Chapter 3 contains a discussion dealing with the various sources of the standard. Each source will be studied independently. Chapter 4 will address general issues with regard to interpretation, such as to what extent the Vienna Convention on the Law of Treaties influences the process of interpretation. Chapter 5 deals with the content of the standard of full protection and security, including conceptual issues relating to the substantive elements of which the standard consists. Moreover, the chapter will ask questions as to which underlying issues are needed to explore when a due diligence assessment is made in order to determine whether a state has fulfilled its obligations to provide protection and security. Part III deals with issues relating to the violations of the standard. In Chapter 6, the violations of the standard and their many manifestations will be analyzed. The chapter will address whether certain fact-based scenarios can be established in which the standard is most commonly violated. Finally, Chapter 7 contains a summary of findings.
Keywords: Arbitral Awards; Bilateral Investment Treaties (BITs); Due diligence; Full protection standard; Full security standard; ICSID; International Investment Law; International law; Investment standards; Investments

Legal challenges of cross-border insolvencies in sub-saharan Africa with reference to Tanzania and Kenya: a framework for legislation and policies - Masoud, Benhajj Shaaban (Nottingham Trent University, 2012)
Although a substantial body of literature has developed in recent years in the area of cross-border insolvency, this scholarship has been dominated by scholars from the United States and Europe, so that a perspective from most of Sub-Saharan African (SSA) countries is lacking. This study addresses this perspective. It makes an in-depth examination and discussion of the challenges that SSA countries face in reform and application of cross-border insolvency law given the ever-growing multinational trade and investment. The study focuses on the risk of failure of SSA legislative processes to properly address the potential challenges of cross-border insolvencies in a manner that is sensitive to the local contexts and which provides a balance with international insolvency benchmarks. It examines cross-border insolvency theories; the global drivers for convergence of insolvency law through global insolvency norms; and the implications for cross-border insolvency regulations arising from cross-border trade and investment arrangements, such as the bilateral investment treaties, before considering the state and future of the legislative frameworks of SSA countries.
Nottingham Trent Institutional Repository (IRep) https://core.ac.uk/works/7793942/
Keywords: Cross-border Insolvency; Insolvency; International insolvency

The Business Trust and its role as an entity in the financial environment - Nel, Ebenhaéser Cornelis (Nelson Mandela Metropolitan University, 2012)
The trust figure in South Africa has undergone an interesting process of evolution during the last century – from a mere gratuity or private tax evasion tool to a proper family protection, business entity, investment, and structured finance vehicle. Its flexibility and multi-functionality positioned the trust as an ideal legal institution for many innovative ideas in the search for holistic business structures, economic empowerment transactions, general estate planning and risk protection initiatives, and ultimately, its application as financial instrument and structured finance entity. The development of both traditional and synthetic securitisation schemes in South Africa has been investigated, with some emphasis on the application of the special purpose institution, which may be in trust form. It is submitted that the application of the trust figure has developed without any significant contribution from the local legislator. A sound legal and regulatory framework is crucial for the creation of a strong future environment for legal and financial vehicles. The question is, however, whether the current South African legal framework for the application of the business trust, and also as a vehicle for financial instruments, is adequately sound and robust in light of the standards set in the international business and financial environment. It is submitted that the hybrid nature of the South African legal landscape is conducive for the development of sound legal systems in an ever-changing legal and economic reality. It is further submitted that in the development of proper legal frameworks, South Africa should position itself particularly in its context as a Southern African developing democracy. The South African trust development is compared with that of some foreign jurisdictions as well as with international conventions and treaties of relevance. Some recommendations for necessary changes are made and it is submitted that such future development of the trust figure should not take place haphazardly, but within the context of a structured regulatory model
NMU Archives and Exhibition Centre
Keywords: Asset-backed financing; Corporations; Taxation; Trusts and trustees

A legal analysis of the application of articles I and III of the GATT 1994 on the economic development of ECOWAS member states - Ogbonna, Joseph Ifeanyichukwu (Brunel University, 2012)
This dissertation examines the tension inherent in the relationship between the Economic Community of West African States (ECOWAS) as Member States Parties of the GATT/WTO and the GATT/WTO regime. It focuses specifically on the tension triggered off by the requirements of Article I – the Most-Favoured-Nation principle (MFN) and Article III – the National Treatment principle (NT) GATT 1994. It shows that while the non-discrimination principles are meant to promote trade liberalisation and economic growth, they produce the opposite effect in developing and least developed countries like ECOWAS and aggravate the tension between those countries and the WTO. It argues that the MFN is used to deny market access to the developing countries by exposing them to stiff but unequal competitive conditions and the NT to deny national governments the policy space to protect and promote national industries, employment and economic growth. It challenges the general assumption that the MFN and the NT are good and in the interest of all the WTO Members and rather identifies them as lynch-pins of economic development in the ECOWAS region. It also shows, contrary to the assumption of non-participation, how the ECOWAS High Contracting Parties are adapting their trading systems and harmonising their laws to the key provisions of Articles I and III of the GATT. It shows that the principles of non-discrimination are the outcome of the standard-setting procedures legally formulated as the SPS and TBT Agreements which favour the developed countries and how the Dispute Settlement Body has rejected the ‘aims-and-effect’ approach, taken a literal approach, overly emphasising trade liberalisation to the neglect of market access and economic development. This dissertation concludes that it is pre-mature for ECOWAS to assume Articles I and III obligations and recommends using the provisions of Article XXIV to build up effective influence through regional organisations and incrementally uniting to transform the GATT.This study is funded by the Brunel Law School
Keywords: ECOWAS; GATT; Tension; WTO; World Trade Organisation

Essays in corporate restructuring, reputation and law - Polo, Andrea (Oxford University, 2012)
This dissertation consists of three essays which examine topics at the intersection of law and finance. The first essay investigates the role of regulatory sanctions and reputational damage in financial markets. We study the impact of the announcement of enforcement of financial and securities regulation by the UK’s financial regulators on the market price of penalized firms. We find that reputational sanctions are very real: their stock price impact is on average almost 9 times larger than the financial penalties imposed. Furthermore, reputational losses are confined to misconduct that directly affects parties who trade with the firm (such as customers and investors). In the second essay we analyze the costs and benefits associated with secured creditor control in bankruptcy. We do it by studying the highly contested practice of UK pre-packs, where a deal to sell the business is agreed before publicly entering into bankruptcy. Contrary to widespread criticism that this procedure leads to collusion, we find no evidence of exploitation of conflict of interests and we find that it preserves the value of the business and maximizes recovery in circumstances in which a public announcement of bankruptcy would destroy value. In small businesses where secured creditors are concentrated the benefits of their control seem to outweigh the costs. Finally, in the last essay we examine whether mandatory shareholder voting prevents wealth destruction in corporate acquisitions. We study the UK setting where all large transactions must have shareholder approval. We observe that such Class 1 transactions always get consent. Nevertheless, there is a striking difference between the performance of acquirers between Class 1 and other transactions. The finding is most pronounced for transactions in a narrow neighbourhood of the size threshold, and is robust to a large set of controls for confounding effects.

Public assets financing in Nigeria : the imperatives for legal reforms to unlock domestic financial resources and foreign capital for infrastructure development - Soyeju, Olufemi Olugbemiga (University of Pretoria, 2012)
Infrastructure is one of the main parameters of economic growth and a country‘s competitiveness depends on the provision and maintenance of efficient and productive infrastructure assets. However, Nigeria, like most countries in Sub-Saharan Africa has the lowest quantity and poorest quality of stocks of infrastructure assets in the world and this phenomenally poor infrastructure has remained an impediment to development in the country. Decades of sub-optimal investment, poor maintenance culture and the fact that the required infrastructure investments could not be accommodated within the available fiscal space as a result of budgetary constraints have all contributed to the Nigeria‘s infrastructure deficit. The immediate outcome of this however is that the available infrastructure assets across the Nigerian landscape are in decrepit state and absurdly inadequate. Besides, the present demand for basic infrastructure services has grown astronomically out-stripping the supply capacity of the existing ones. Closing the infrastructure financing gap will however require increased investment by private investors through creative financing in an enabling legal and financial environment. Outside the budgetary constraints, the absence of efficient maintenance and management of infrastructure assets and quality service delivery by the public sector are some of the reasons why procurement of public infrastructure stocks by government through the traditional approach is no longer plausible and hence, the general appeal of the public-private partnership framework. However, despite all the potentials, the public private partnership technique in Nigeria has not made an appreciable impact in closing the infrastructure gaps due to lack of access to long-term financing. It is against this back-drop that this study has sought to investigate how reforms of the legal and financial infrastructure could widen access to financing through innovative financial resource mobilization in scaling-up infrastructure development and service delivery to the teeming Nigeria population. Therefore, the central thesis of this study is that the inadequacy of appropriate laws and inefficient financial system are partly responsible for the huge financing gaps in the Nigeria‘s infrastructure market and with the legal and financial reforms, an enabling legal and financial environment that would open up space for resource mobilization through innovative financing techniques and sources will be created thereby widening access to long-term financing and increasing the appetite for private investment in the nation‘s public infrastructure assets and services. So, the overarching objective of this thesis is to explore how legal and financial system reforms can facilitate the development of financial models and instruments that can help mobilize financial resources to fund infrastructure and bridge the huge infrastructure financing gaps in Nigeria in a sustainable fashion. Given the infrastructure poverty that constrains economic growth and development in Nigeria, the outcomes of this proposed study would help inform the need for the legal and financial system reforms to unlock resources in addressing the problems of financing gaps in infrastructure projects development in Nigeria. Besides, such outcomes based on the Nigerian experience in infrastructure financing and development may be turned into valuable knowledge for policy –making and further research in Nigeria. Copyright
https://repository.up.ac.za/handle/2263/24525
Keywords: Foreign capital; Infrastructure; Legal reform; Nigeria; Public assets

Understanding fiduciary duties: conflict of interest and proper exercise of judgment in private law - Valsan, Remus (McGill University, 2012)
This dissertation analyses the content and justification of the notion of fiduciary duties in private law relations. The thesis promotes the following understanding of fiduciary duties: in a legal relation where one party undertakes to act in the interests of another, and acquires decision-making authority over the other's interests, such party undertakes a core duty to exercise his best judgement in the other's interests. The core judgement duty requires a fiduciary to exercise judgement based on relevant considerations. While what constitutes a relevant consideration can be determined objectively, the weight to be ascribed to each relevant factor is left at the fiduciary's subjective appreciation.Due to the existence of this core duty, the law imposes a set of proscriptive duties. The proscriptive duties require a fiduciary to manage situations of conflict of interest. Their purpose is prophylactic: they aim to prevent self-interest (or another duty to exercise proper judgement) from affecting the reliability of fiduciary's judgement in a conscious or subconscious way. The proscriptive duties protect the core duty to exercise judgement and, as a result, the beneficiary's right to a proper exercise of judgement by the fiduciary.
https://escholarship.mcgill.ca/concern/theses/wd376141g
Keywords: Conflict of interest; Fiduciary duties; Judgment; Private law

Corporate Governance and the Relationship between Default Risk and the Earning Response Coefficient - Zakaria, Nor Balkish (Victoria University of Wellington, 2012)
This study examines the effect of corporate governance on the relationship between default risk and the earnings response coefficient (ERC). Using a sample of 2,004 firm-years comprising 334 firms listed on the Bursa Malaysia over a six year period from 2002 to 2007, this study tests whether corporate governance mitigates the effect of default risk on ERC while controlling for the established determinants of ERC — beta, growth, earnings persistence and size. Using reverse regression, the study confirms that beta is negatively related to ERC and that growth, earnings persistence and size are positively related to ERC. Default risk is found to be negatively related to ERC thus confirming that beta is only a partial measure of risk relevant to ERC. Corporate governance — as indicated by audit quality, audit committee expertise and independence, and board independence and board shareholding — mitigates the negative effect of default risk on ERC. The results of the study hold both for the pooled sample of 2,004 firm-year observations and on a year by year basis for the 334 firms in the sample. The results are also found to be robust to various sensitivity tests including to alternative measures of the variables. The study thus provides systematic and comprehensive additional evidence on the determinants of ERC. Of itself this is an important contribution to the literature but especially so given that the evidence comes from Malaysia — an emerging economy — whereas the existing empirical literature relates mainly to developed countries.
Keywords: Corporate governance; Default risk; Earnings response coefficient

The Protection of Privacy in the Workplace: A Comparative Study - Gondwe, Mimmy (Stellenbosch University, 2011)
The importance of privacy lies in the fact that it represents the very idea of human dignity or the preservation of the ‘inner sanctum’. Not surprisingly, however, operational concerns of employers and technological developments combine continuously to challenge the preservation of privacy in the workplace. Employees the world over are exposed to numerous privacy invasive measures, including drug testing, psychological testing, polygraph testing, genetic testing, psychological testing, electronic monitoring and background checks. Hence, the issue at the heart of this dissertation is to determine to what extent privacy is protected in the South African workplace given advancements in technology and the implications (if any) for the right to privacy as such. A secondary aim of the dissertation is to attempt to provide a realistic balance between the privacy concerns of employees and the operational needs of employers in this technological age. As such the main focus of dissertation falls within the sphere of employment law. In order to provide an answer to the research issue discussed above, the dissertation addresses five ancillary or interrelated issues. First, the broad historical development of the legal protection of privacy is traced and examined. Second, a workable definition of privacy is identified with reference to academic debate and comparative legislative and judicial developments. Third, those policies and practices, which would typically threaten privacy in the employment sphere are identified and briefly discussed. Fourth, a detailed evaluation of the tension between privacy and a number of selected policies and practices in selected countries is provided. More specifically, the dissertation considers how these policies and practices challenge privacy, the rationale for their existence and, if applicable, how these policies and practices – if necessary through appropriate regulation – may be accommodated while simultaneously accommodating both privacy and the legitimate concerns of employers. The selection of these practices and policies is guided by two considerations. At the first level the emphasis is on those challenges to privacy, which can be traced back to technological developments and which, as such, foster new and unique demands to the accommodation of privacy in the workplace. The secondary emphasis is on those policies, which are representative of the fundamental challenges created by new technologies to privacy. To effectively address the above issues the dissertation uses the traditional legal methodology associated with comparative legal research, which includes a literature review of applicable law and legal frame work and a review of relevant case law and a comparative study of selected foreign jurisdictions.
URI: http://hdl.handle.net/10019.1/17849
Keywords: Privacy infringements; Privacy protection; Right of privacy

Aspects of the nature and online resolution of domain-name disputes - Hurter, Eddie (University of South Africa, 2011)
The thesis analyses selected aspects of domain-name law, mainly from the perspective of trade-mark law. It discusses the evolution of the domain-name system and how it operates as background to a more detailed discussion of the theoretical classification of domain names. The thesis then examines the interplay between trade marks and domain names, and the resolution of domain-name disputes resulting from the inherent tension between these two systems. The main principles of domain-name dispute resolution are identified by way of an analysis of the panel decisions handed down in terms of the international Uniform Dispute Resolution Policy (UDRP) and the South African domain name dispute resolution regulations. This analysis always addresses, too, the extent to which national trade-mark law principles (with reference to the laws of South Africa, the United Kingdom, and the United States of America) apply, and the extent to which this is appropriate.
Keywords: Abusive domain name registration; Cybersquatting; Dispute resolution; Domain names; ICANN; Intellectual property; Internet Corporation for Assigned Names and Numbers; Internet domain names; Nominet Dispute Resolution Service; Trademarks; Typosquatting; WIPO domain name processes; Well known trade marks; World Intellectual Property Organization

Culture of international arbitration and the evolution of contract law - Karton, Joshua David Heller (University of Cambridge, 2011)
Keywords: Arbitrage; Arbitragem; Arbitration; Contract law; International Arbitration

Public employment and the relationship between labour and administrative law - Loots, Barbara Evelyn (University of Stellenbosch, 2011)
The focus of this study is the rights-based normative overlap of labour and administrative law in public employment. As the judiciary appeared to be unable to agree on a unified approach to the application of the rights to fair labour practices and just administrative action to public employment, it was clear that the complexity and multi-dimensional character of the debate required analysis of existing approaches to the regulation of the public employment relationship. The following initial research question was formulated: To what extent does (and should) the constitutionalised rights to fair labour practices (s 23) and just administrative action (s 33) simultaneously find application in the regulation of public employment relationships? In answering this question, certain realities had to be acknowledged, the most important being that the debate in question jurisprudentially revealed itself to be a jurisdictional turf-war between the Labour and High Courts, rather than proper consideration of the relevant substantive arguments and underlying normative considerations. This called for an additional dimension to be added to the research question, namely consideration of the extent to which the ss 23 and 33 rights are informed by variable and possibly different normative principles and whether these rights allow for cooperative regulation of public employment in accordance with the doctrine of interdependent fundamental rights. This became the primary focus of the study. In an attempt to simplify the debate, a deliberate decision was taken to limit the scope of the normative study to South Africa with its own historic influences, structures and constitutional considerations. The study shows that both labour and administrative law (as constitutionally informed) share concern for equity-based principles. This is evident from the flexible contextually informed perspectives of administrative law reasonableness in relation to labour law substantive fairness, as well as a shared concern for and approach to procedural fairness. Once simplified, and in the absence of any undue positive law complexity, the public employment relationship, at both a normative and theoretical level, furthermore shows no substantive status difference with private employment relationships. It is, however, accepted that there are job and sector-specific contextual differences. In the absence of substantive normative conflict between these branches of law and in the absence of a fundamental (as opposed to contextual) difference between public and private employment, there appears to be no reason to ignore the constitutional jurisprudential calls for hybridity, otherwise termed the doctrine of interdependence. The idea of normatively interdependent rights expresses the Constitution’s transformative vision (through the idea of flexible conceptual contextualism) and recognises that human rights may overlap. This also means that where such overlap exists, rights should be interpreted and applied in a mutually supportive and cooperative manner that allows for the full protection and promotion of those rights. In giving expression to the interdependent normative framework of constitutional rights, these norms (absent any substantive rights-based conflict) should then be used by the judiciary as an interpretative tool to align specific labour law and general administrative law in the regulation of public employment relationships.
URI: http://hdl.handle.net/10019.1/6683
Keywords: Administrative law; Employment law; Labour law

The external relations of company groups in South African law : a critical comparative analysis - Stevens, Richard Arno (University of Stellenbosch, 2011)
Groups of companies are part of the realities of the modern economic system. Despite the fact that such groups often function as a single economic entity, the legal point of departure remains that each company within the group of companies is a separate juristic person. The result of this is that a creditor of a company within the group can, in principle, only enforce his claim against the company which he contracted with or which caused him harm. Should he wish to claim from the holding company or other solvent companies within the group, he would have to rely on an exception to the doctrine of separate juristic personality, viz the possibility of piercing the socalled corporate veil. This dissertation is a comparative study of the extent to which the law protects a creditor of an insolvent company within a group. The applicable laws of Australia, Germany, New Zealand, the United Kingdom and the United States of America, were investigated and compared to the South African position. The dissertation concludes that the South African legal treatment of the problem is unsatisfactory and that the law should be amended through appropriate legislation.
URI: http://hdl.handle.net/10019.1/6883
Keywords: Company groups; Creditors; South African companies; South African law

Nigeria, oil and gas exploration and the Niger delta question : a study in corporate social responsibility - Bribena, E. K. (North-West University, 2011)
This thesis addresses issues of the Niger Delta question which represents one of the most intractable sources of socio-political destabilization in the Niger Delta region of Nigeria. The study is on the intricate dynamics amongst the Nigerian state, the transnational oi l corporations, the oil producing communities and the insurgent militia conflict. It investigates and explicates the "paradox of plenty" and the "resource curse", the "absentee government" and "state capture" and the debilitating effects of petroleum politics in Nigeria. The economic exploitation of the Niger Delta region's vast crude oil reserves by transnational oil corporations and government authorities is juxtaposed with the spectre of environmental degradation, human rights violations, and the recurrent rule of impunity. The protracted problems of the Niger Delta region thus, provide us with a pertinent analytical and contextual framework for the study of the dynamics and issues of transparency in other African petro-dollar states. It is argued in this study that the Niger Delta crisis is a conflict of values and fight for resources arising from decades of unacceptable standards of oil exploration and the absentee character of the Nigerian State. By its very nature, the study called for a qualitative approach, supplemented by unstructured interviews using aide memoirs with selected officials, on the basis of their innate knowledge of the subject matter. The legal comparative research method, with a historic component also played an integral role in this study. Some key findings and conclusions: 1. The study found that the Niger Delta crisis graduated from mère political agitations for state creation and provision of social amenities to extreme acts of hostage-taking and a twist of violence as a result of treating a major problem affecting the development of the Niger Delta people with levity for too long a period. 2. The study found that the on-going crisis in the Niger Delta region of Nigeria is a conflict of values and fight for resources amongst the oil-bearing people of the Niger Delta, transnational oil corporations and the Nigerian Government. 3. The study established some causal nexus between oil and poverty; oil and corruption; and, oil and human rights abuses. 4. That, the Niger Delta crude oil conflict is essentially a manifestation of state capture and inertia on the part of the Nigerian Government. 5. The study found that the Niger Delta economies are "criminalized" and are often characterized by conditions of anarchy and impunity. And this disorder is embedded in the dynamics of resource extraction, the nature and role of "shadow" state actors, as well as the interplay and patterns of relationships between organized criminal syndicates and the transnational oil corporations in the host communities. The study recommends, inter alia: I. That steps be taken by government to re-define its philosophy of national economic development from a state-driven to citizens-driven philosophy. To this end, Nigeria must seek to develop by developing its citizens, the aggregate of whose satisfactory living conditions should form the criteria for measuring national development. II . That effort must be made to steer the nation towards proper fiscal federalism. The present "food is ready" economy whereby federating units are enslaved to national "cake sharing" instead of value generation, discourages entrepreneurship and sustainable development. It promotes undue dependency on petroleum products, inequity and ethnic distrust. Ill. That Nigeria needs productive resource control, not just development in the sense of house and bridge building. What is needed is a noticeable leap in the standard of living in the Niger Delta. Thus, people and not federal accounts must be the object of improvement. IV. It is recommended that government should ensure robust, independent and co-ordinated oversight of the oil industry including its impact on human rights. V. Transnational oil corporations should undertake full corporate social responsibility and comprehensive assessment of the social and human rights impacts of all oil and gas projects, ensuring that adequate information is provided to affected individuals and communities and that the process is transparent. VI. It is strongly recommended that an Oil Pollution Liability Trust Fund should be established by the Federal Government in concert with oil companies. The fund will be made up of a percentage of tax levied on oil companies and a percentage of earnings of the Federal Government from oil. The fund should be used in ameliorating the conditions of the impacted environment and people. It is hoped that these findings and recommendations will go a long way in the quest for significant environmental and social improvements in the Niger Delta region of Nigeria.
Keywords: CSR; Corporate Social Responsibility; Nigeria; Petroleum industry and trade

Common good and the concept of expropriation in international law on foreign investment: Determinacy of substance in legitimacy of structure - Falsafi, Alireza (McGill University, 2011)
This thesis, exploring the rule of law for international rules, offers a human bond of common good between determinacy of substance and legitimacy of structure of rules in order to evaluate international obligations of States in international law on foreign investment. In an in-depth exposition of the theoretical underpinnings and practices underlying the normative structure of rules in international law, the thesis critically questions the legal reasoning embedded in—and the authority of rules borrowed from—principles and precedents or moral and political evaluations by arbitrators in interpretation of States' contractual, customary, and treaty obligations in investment arbitrations. With crucial moral, political, social and economic ramifications for the constitutional functions of States and concomitant interests of their human members implicated in the concept of expropriation in international law, the thesis provides a framework of legitimacy in a common good approach with structural criteria of recognition and coherence for the interpretation of States' obligations in investment arbitration. Coherence brings to the fore conflicting demands of justice requiring fresh evaluation divesting a general rule of its authoritative force, and recognition brings to the fore the validation of the power to engage in moral and political evaluation. Together, these structural criteria offer a common good approach of legitimacy to test the authority of States' obligations and the power of arbitrators in hard cases. By virtue of these criteria, the thesis characterizes the nature of substantive property rights of corporations and corresponding obligations of States in foreign investment as contingent and consensual in contrast with the absolute and constitutional rights of human beings in human rights. Through coherence and recognition, the thesis also portrays a supreme status for customary international law for the normative structure and substance of States' contractual or treaty obligations in the interpretation of hard cases in international law on foreign investment. The thesis espouses a new horizon for legal reasoning in foreign investment arbitration that eschews the lex lata veneer for lex ferenda propositions manufactured from precedents and principles, on the one hand, and the sheen of law for the conception of justice of investor-State arbitrators, on the other, in cases of hard confrontation between the demands of justice.
https://escholarship.mcgill.ca/concern/theses/dv13zz300
Keywords: Expropriation; Foreign investment; International law

Copyright in the digital environment : ontologies of copyright and digital works - Filippi, Primavera De (European University Institute, 2011)
The advent of Internet and digital technologies has radically transformed the way information is being produced and consumed. The consequences for copyright law are twofold. While digital media provide new opportunities for authors to produce and disseminate their works to the public, they simultaneously encourage and facilitate copyright infringement. Traditionally, in order to ensure compliance with the law, the copyright regime could rely upon the properties of physical media to constitute a natural barrier against copyright infringement. As the medium went digital, however, its properties became a catalyst for infringement. Designed for the physical world, the structure of the copyright does not adequately address the issues inherent to digital media. Private regulation therefore came into play in order to resolve the problem. While restrictive licensing agreements combined with technological measures of protection purport to reestablish a technological barrier against copyright infringement, permissive licenses such as Creative Commons purport to reduce the scope of protection granted by default under the law. Although differing in method, these approaches share a common goal: to realign the properties of the work with the properties of the digital medium by readjusting the legal attributes and technical characteristics of digital copies. As a legal concept, however, the notion of a copy must be precisely defined. After performing an ontological analysis of the copyright regime within the scope of the Functional Requirements for Bibliographic Records and the Information Artifact Ontology, the research concludes that physical copies fundamentally differ from their digital counterpart. While the former qualify as a token, the latter qualify as a class that is capable of multiple instantiations. Moreover, given that the identity of a digital copy can no longer be defined by its physical characteristics, it is fundamentally for the copyright license to determine the scope of the copy to which it refers.
Keywords: Copyright; Digital media; Electronic data processing; Intellectual property; Internet

The effects of state succession on cultural property : ownership, control, protection - Jakubowski, Andrzej (European University Institute, 2011)
The purpose of this study was to investigate the legal effects of state succession on cultural property. This is not a new topic of international law. Indeed, the attempts to provide a legal framework for the cultural aspects of state succession have been undertaken in international practice and legal scholarship since at least the mid-nineteenth century. Initially, these were strictly bound to the origin of the European nation-state, determining its territorial boundaries accordingly to ethnic and cultural divisions. However, the concept of cultural property in international law has evolved towards a broader, more human-oriented idea of cultural heritage. Such a conceptual shift has occurred in the last fifty years, marked by the gradual recognition of the fundamental role performed by cultural manifestations in the preservation of human dignity and the continuous development of all mankind. This study discusses to what extent the practice and the theory of state succession reflect this evolution. It attempts to reconstruct the principles regulating interstate arrangements with regard to such matters, contextualizing them in a broad historical and geographical framework. Particular attention has been paid to the question of state succession to international cultural heritage obligations. This piece of work explores their content, sources and status in state succession. It explains that nowadays the preservation and enjoyment of cultural heritage do not constitute the exclusive concern of state sovereignty. On the contrary, such values are of general interest to the international community as a whole. Therefore, the study advocates a new doctrinal approach, based both on the principles of international cultural heritage law and human rights law. This implies the limitation of the contractual freedom of states in the matter of cultural agreements, in favour of the continuity of international cultural heritage obligations in cases of state succession. Finally, the study proposes a list of guiding principles relating to the succession of states in respect of tangible cultural heritage, which may contribute to the further development of international practice.
Keywords: Cultural property; Property protection; State succession

Reformulating corporate residence: a coherent response to international tax avoidance - Loomer, Geoffrey (University of Oxford, 2011)
This thesis analyzes the concept of corporate residence, with particular reference to the law in the UK and Canada. It explores why corporate residence is relevant in tax policy, how corporate residence is understood in law, and how revenue authorities respond to the use and alleged 'abuse' of residence rules. Part I argues that the residence of taxpayers generally (individual or corporate) remains a relevant factor in international tax design, that taxation of corporations on the basis of residence has some justification, but that there is a disjunction between meaningful residence-based taxation and current definitions of corporate residence in domestic law and tax treaties. The formulations of residence based on incorporation, central management and control, and place of effective management, particularly as applied to multinational enterprises, are considered and are found to be deficient. Part II critically analyzes the major policy responses of the UK and Canadian governments to the exploitation of corporate residence. It argues that key legislative and administrative responses to international tax avoidance activities, for both outbound and inbound investment, are purportedly based on the acceptance of formal corporate residence yet undermine that concept in an effort to impose tax or refuse treaty relief based on where economic interests actually exist. The responses considered are the application of controlled foreign companies legislation to offshore subsidiaries, the invocation of treaty anti-abuse rules with respect to offshore intermediaries, and the use of overarching general anti-avoidance measures to challenge varied structures that rely on offshore entities. These haphazard anti-avoidance rules are overlaid with revenue authorities' indignation at the motivations that underlie many corporate relocations. It is argued that a more coherent approach would be to focus on the objective reality or unreality of corporate establishment, by reformulating corporate residence in domestic law and tax treaties.
Keywords: Economics Law; International business; International taxation; Multinational enterprises; Resident companies; Tax avoidance; Tax planning; Taxation

The dilemma of national security and international cooperation in outer space: space technology trade and proliferation controls and their impact on global civil space cooperation - Mineiro, Michael (McGill University, 2011)
In this thesis space technology trade and proliferation controls are analyzed, focusing on two substantive issues that illustrate the challenges and opportunities of reform. The first substantive issue examined is the challenge of domestic law and policy reform in light of international regulatory divergence. This issue is examined through a case study of the U.S. commercial communication satellite export control regime. The second issue is the international implications of space technology trade and proliferation control on global civil space cooperation. The unifying demonstration of this doctoral thesis is that States operate in an international legal system that perpetuates a self-justified security dilemma whose basis originates in the sovereign legal right of States to produce, procure, and maintain space technologies of a military nature. As a result, the international legal system governing space technology trade and proliferation creates a tension between perceived national security needs and the benefits of global cooperation.

Fairness in class action settlements - Piché, Catherine (McGill University, 2011)
To be made effective, class action settlements must be negotiated fairly, be perceived as fair and reasonable by the settlement parties such that they agree to their terms and substance, and be characterized as fair, reasonable and adequate by a court at the occasion of a settlement approval hearing. But how is settlement fairness defined, in a collective litigation context? By which process is the evaluation of fairness made and the approval given by the court? What role does the court correspondingly have, in that context? This thesis explores the legal policy and reasoning behind the mandatory judicial approval of class settlements, the process by which it is sought and obtained, the currently relevant factors and indicia of settlement fairness which support all decisions to approve, and the roles of the principal settlement actors, particularly the settlement judge. It suggests hypotheses for reform applicable to these approval processes, roles of the actors and standard of settlement fairness. These hypotheses are tested, for their plausibility, against empirical data obtained from the qualitative interviews of seventeen judges conducted by the author in four target jurisdictions that have similar approaches to class action settlement approvals, and where class action litigation activity is heavy: Quebec, Ontario, British Columbia, and the United States federal courts. Ultimately, the thesis proposes final recommendations for reform of the class action settlement approval procedure.
Identifier : https://escholarship.mcgill.ca/concern/theses/n009w645z
Keywords: Class action; Class action settlement; Settlement parties

South African anti-dumping law and practice : a juridical and comparative analysis of procedural and substantive issues - Sibanda, Omphemetse Stephen (North-West University, 2011)
This thesis addresses issues of anti-dumping law and practice from a critical and juridical analysis position. In particular, the thesis seeks to determine whether the South African anti-dumping regime is compliant with the anti-dumping regime of the World Trade Organization (hereafter WTO), and to consider possible solutions for addressing instances where the South African law is not WTO compatible. The thesis departs from the hypothesis that the WTO merely requires functional equivalence of the implementation of national legislation on anti-dumping, and not the verbatim adoption of WTO jurisprudence and relevant provisions of the Agreement on the Implementation of Article VI of the General Agreement on Tariffs and Trade of 1994 (hereafter URAA), into the legislation of State Parties. Some of the provisions of the URAA are not completely clear, and are cast in convoluted and complicated technical jargon, leaving loopholes that may be justifiably exploited by State Parties. The study in this thesis was achieved through the critical analysis of legislation and relevant legal documents, case law and contemporary literature. The primary research paradigm used in this study is interpretive and analytical, which is the same as qualitative research methodology. The legal comparative research method, with a historical component, also played an important role in this study. The literature study undertaken and the critical analyses made of the South African anti-dumping regime show mixed findings. The South African antidumping regime was found to have both positive aspects and problematic aspects when compared with WTO regulations. Some of the critical areas of the South African anti-dumping regime are WTO compatible whilst others are not. In some areas the South African anti-dumping regime has adopted functionally equivalent provisions to the provisions of the WTO law. However, the practice of the International Trade Administration Commission (ITAC) is sometimes fraught with inconsistencies. The compatibility of the South African anti-dumping system with the WTO regime came close to being examined by the WTO on 1 April 1999 in the dispute of South Africa - Anti-dumping Duties on the Import of Certain Pharmaceutical Products from India based on allegations that the method for calculating normal value used by the ITAC was found to be inconsistent with the URAA. Similarly, the conformity of the procedures and findings of the International Trade and Administration Act (ITAA) in anti-dumping cases came under attack in the cases of Algorax v The International Trade Administration Commission and others, and Scaw v The International Trade Administration Commission and others, respectively. Finally, the thesis ends with recommendations in response to the challenges identified and key submissions made throughout the analysis. Key recommendations include the broadening of the concept of interested parties to include registered trade unions and trade union federations; introducing an explicit and mandatory "public Interests" provision to ensure that South Africa's anti-dumping administration is free from political trappings in the form of the involvement of the Minister of Trade and Industry; introducing the new section 31 bis of the ADR in order to allow the initiation of anti-dumping petitions by a registered trade union or trade union federation; providing procedural guidelines for self-initiation of anti-dumping petitions by the ITAC; increasing transparency in anti-dumping proceedings and enquires; setting realistic time-lines for all anti-dumping processes and ensuring compliance with the same; improving the institutional and functional capacity of the ITAC; amending section 18.3 of the ADR to allow search and seizure operations pursuant to the provisions of the Criminal Procedure Act 51 of 1977 and the Customs Act; having a clear provision on verification visits confidentiality and a clear provision on producer knowledge; introducing a clear provision in the ADR dealing explicitly with zeroing pursuant to Article 2.4.3 (ii) of URAA; and the introduction of duty refund procedures. It is hoped that the recommendations made in this thesis, which are in the form of suggested legislative interventions required to upgrade certain areas of South African anti-dumping law and practice to be fully WTO compliant, will influence the introduction of suitably crafted anti-dumping legislation in South Africa. It is further hoped that the thesis will become an invaluable source of information for practitioners and students, and a critical source on the best practice for the imposition and implementation of anti-dumping measures. Moreover, the thesis will add to the body of academic writing on South African anti-dumping law.
Keywords: Antidumping duties; Dumping (International trade); South Africa

Market access and sustainable development: a legal policy analysis of the market access regime of the least developed countries under the WTO - Tania, Sharmin Jahan (Macquarie University, 2011)
"The main objective of the thesis is to examine whether improved market access for the exports of the least developed countries (LDCs) is a significant means for achieving sustainable development through trade. Further, it aims to examine whether LDCs face challenges in achieving their sustainable development in the existing market access regime... Recognising the specific needs of LDCs, the Preamble to the 'WTO Agreement' calls for positive efforts designed to ensure that LDCs secure a share in the growth in international trade commensurate with the needs of their economic development."
Keywords: Commerce; Developing countries; Exports; Foreign trade regulation; Free Trade; Sustainable development; WTO; World Trade Organization

Essays on policy reforms in trade, investment and taxation - Wagle, Swarnim (Australian National University, 2011)
This thesis consists of three essays on trade, investment, and taxation that are unified by their policy relevance to developing countries. Following an introductory chapter on policy reform, the first essay revisits the institutional determinants of foreign direct investment (FDI) using a comprehensive new data set covering more than 80 countries. It exploits the presence of confirmed zero investment flows between countries to estimate productivity cut-offs of firms that invest abroad profitably. This approach corrects likely biases arising from firm heterogeneity and country selection in a theoretically derived gravity-type model. The analysis finds inward FDI to be highly responsive to cross-country variation in specific institutional provisions, such as arbitration of disputes and legal procedures to establish foreign subsidiaries. The importance of FDI-specific regulations stands out even after controlling for the general quality of institutions. Statutory openness to FDI, however, has no association with actual inflow of investment. The second essay examines cross-national differences in the survival of exports through the lenses of product, industry, and country characteristics. The estimates are derived from a new application of discrete-time models instead of the continuous-time (Cox) models that are standard in trade duration analysis. The examination of exports originating in more than 100 developing countries covering 4000 products over 12 years shows that export flows are much more fragile than suggested by trade theory. Using new measures of product sophistication and export diversification, the paper finds evidence of information and network externalities that aid export survival. Exports concentrated in a few industries or in a narrow range of destination markets exhibit higher rates of death, whereas export concentration within some industries is positively associated with survival, suggesting a synergistic network effect. The probability of export death decreases with proximity from the capital content of products to the national factor endowment, competitive real exchange rate, and bilateral trade preferences. Further, death rates for dynamic subsets of exports like manufactured components and processed food differ from other products, belying the notion that short durations are necessarily a result of poor exporter capabilities. The third essay assesses the revenue implications of coordinated tariff and tax reforms. It is shown for a sample of low-income countries over 25 years that they have had a mixed record of offsetting reductions in trade tax revenue, and that Value-Added Tax (VAT) has, at best, played a limited role. The paper then analyzes the specific case of Nepal, using a unique data set compiled from unpublished customs records of imports, tariffs, and all other taxes levied at the border. It estimates changes to revenue and domestic production associated with two sets of reforms: i) proportional tariff cuts coordinated with a strictly enforced VAT; and ii) proposed tariff cuts under a regional free trade agreement. It is shown that a revenue-neutral tax reform is conditional on the effectiveness with which domestic taxes are enforced. Furthermore, loss of revenue as a result of intra-regional free trade can be minimized through judicious use of Sensitive Lists that still cover "substantially all the trade" as required by Article XXIV of the General Agreement on Tariffs and Trade (GATT).
Keywords: Commercial policy; Fiscal policy; Free Trade; Investments; Taxation

INCOTERMS as a form of standardisation in international sales law : an analysis of the interplay between mercantile custom and substantive sales law with specific reference to the passing of risk - Coetzee, Juana (University of Stellenbosch, 2010)
International sales contracts have very specific needs that stem from the multiplicity of legal systems which apply to such contracts. In addition to harmonised law, mercantile custom is able to address many of these needs. Mercantile custom represents usages which are clear, certain and efficient and are expected to be known and applied by merchants in a particular trade or region. To this extent mercantile custom fulfils an automatic harmonisation function. However, where a custom does not enjoy uniform application across all branches of trade, the harmonisation function of mercantile custom is limited, as is the case with trade terms. Trade terms reflect mercantile customs and usages which developed over a long time in order to simplify the trade in goods that are transported from one place to the other. They regulate the delivery obligations of the seller and buyer as well as associated obligations such as the passing of risk. Trade terms negate the need for elaborate contract clauses and appear in abbreviated form in contracts of sale. Although they provide a uniform expression of mercantile custom in a particular location or trade, the understanding of trade terms tend to differ from country to country, region to region or from one branch of trade to the next. The ICC INCOTERMS is an effort to standardise trade term definitions at the hand of the most consistent mercantile customs and practices. The aim of this study is to investigate the efficiency of INCOTERMS as a form of standardisation in international sales law. For purposes of the investigation the focus is limited to the passing of risk. Although national laws usually have a default risk regime in place, merchants still prefer to regulate risk by means of trade terms. This study will investigate the legal position in the case of FOB, CIF and DDU terms. An analysis of the risk regimes of a few selected national systems will show that each has their own understanding of these trade terms. The United Nations Convention on Contracts for the International Sale of Goods (CISG) does not refer to trade terms, but many commentators have concluded that the CISG risk rule is consistent with INCOTERMS. The study will discuss this in more detail. To determine the efficiency of INCOTERMS as a form of standardisation in international sales law, the study examines their characteristics, legal nature as well as their limited scope of regulation. Specific emphasis is placed on the interplay between the CISG and INCOTERMS and the possibility of some form of interaction and collaboration between the two instruments. It is concluded that collaboration between INCOTERMS and the CISG adds value to the international law of sales by increasing the efficiency of an international business transaction and thereby facilitating international trade.
Keywords: CISG; INCOTERMS; Mercantile custom; Standardisation

A politico-legal framework for integration in Africa : exploring the attainability of a supranational African Union - Fagbayibo, Babatunde Olaitan (University of Pretoria, 2010)
The emergence of the African Union (AU) is seen as an effort to reposition Africa for the challenges of contemporary global realpolitik and, in particular, it provides a road map towards the attainment of a political union. The institutional architecture of the AU, modelled after the European Union (EU), indicates an intention on the part of the architects of the AU to endow the organisation with supranational attributes. However, none of its institutions has as yet started to exercise supranational powers. It is against this background that this thesis explores the feasibility of transforming the AU from a mere intergovernmental organisation into a supranational entity. In the course of the investigation, it was found that a major obstacle to realising this is the absence of shared democratic norms and standards, a consequence of the unconditional membership ideology of the AU. This thesis argues that the starting point of closer integration in Africa should be the cultivation and adoption of shared norms and values. To address this, the study proposes that the AU design an institutional mechanism for regulating its membership. Using the African Peer Review Mechanism (APRM) as a case study, this study shows that it is possible to establish a regulatory regime based on strict adherence to shared fundamental norms and values. A major recommendation is the transformation of the APRM into a legally binding instrument for setting continental democratic standards, assessing whether member states fulfil these standards and ultimately determining which member states are qualified, based on objective standards, to be part of a democratic AU.
https://repository.up.ac.za/handle/2263/28573
Keywords: African Union; African peer review mechanism; Regional economic communities (RECs); Regional integration

A reformatory approach to state regulation of insolvency law in South Africa - Calitz, Juanitta Christelle (University of Pretoria, 2010)
https://repository.up.ac.za/handle/2263/30839
Keywords: Insolvency; South Africa; State regulation

The suitability of the South African corporate tax regime for the use of South African resident intermediary holding companies - Legwaila, Thabo (University of Pretoria, 2010)
An Intermediary Holding Company (“IHC”) is a company that is interposed between an ultimate holding company and the operating subsidiaries of a group of companies. The IHC operates at an international level such that either its holding company or its subsidiaries or both are located in a country foreign to the IHC. Its main functions are to acquire, manage and dispose of the assets of the group of companies and to facilitate structural flexibility of a group of companies. Investors have tax and non-tax reasons for conducting business using an IHC, and, depending on the reasons, they determine the location of the IHC based on the characteristics of potential host countries. This thesis analyses the suitability of the South African corporate tax regime for the use of South African-resident Intermediary Holding Companies. The South African government has the objective of promoting South Africa as a gateway for investment in Africa and for this reason the present research is important. Such an objective could be adversely affected by a corporate tax regime that is not suitable for the operations of an IHC. Furthermore, the Katz Commission recommended in 1997 that South Africa should consider introducing a regime that is suitable for the location of holding companies. In discharging its functions the IHC attracts liability for corporate income tax, capital gains tax, controlled foreign company tax and dividends tax. It also exposes itself to anti-avoidance measures such as thin capitalisation and transfer pricing provisions. The existence of such taxes and anti-avoidance measures in the tax system of a country may deter investors from locating an IHC in such country. Exchange control regulations could also adversely affect the ability of the IHC to perform its functions effectively, as their purpose is to restrict the movement of capital out of the country. The South African legal system contains all these taxes and anti-avoidance measures as well as exchange control provisions. However, it also contains tax instruments that alleviate the tax burden on an investor using an IHC such as the participation exemption, advance tax rulings and a network of tax treaties. Against this background this thesis analyses the South African corporate tax system to determine whether it is suitable for locating an IHC. In the analysis, a comparative study is done of the tax systems of two of the most effective IHC host countries, namely the Netherlands and Mauritius. In addition, a brief discussion of the special features contained in the tax systems of Belgium, Ireland and the United Kingdom outlines why these jurisdictions are not necessarily successful in attracting IHCs. The thesis also discusses harmful tax practices and the attitude of the international community towards countries that engage in harmful tax competition in order to determine the limits to which a country should use the tax system to attract investment. Finally, the thesis makes recommendations as to what adjustments could be made in order to enhance the suitability of South Africa to host an IHC. The thesis recommends a special dispensation as regards corporate income tax and exchange control that would apply to wholly-owned South African companies that own foreign subsidiary shares and loans that consist of 80% of the gross asset total of these companies.
Keywords: Intermediary Holding Company; South Africa; Tax; Taxation

Some comparative aspects of corporate rescue in South African company law - Loubser, Anneli (University of South Africa, 2010)
South African company law has provided for the rescue of financially distressed companies since 1926 when the statutory procedure of judicial management was introduced by the Companies Act 46 of 1926. Unfortunately, judicial management has never been regarded as a successful corporate rescue procedure and for most of its existence it has been severely criticised on many grounds. The Companies Act 61 of 1973 that replaced the Companies Act 46 of 1926 did very little to improve this situation and judicial management remained underutilised. As a result, the Companies Act 71 of 2008 now introduces two newly-created corporate rescue procedures in the form of business rescue proceedings and the compromise with creditors. This study analyses judicial management and the new corporate rescue procedures to establish whether the identified weaknesses of judicial management have been adequately and effectively addressed in the new procedures. A comparative study with similar procedures in England and Germany is undertaken to determine whether the South African legislature has delivered on its promise to create a system of corporate rescue that will meet the needs of a modern South African economy. Several weaknesses in the new procedures are identified and a number of recommendations are made to improve the relevant provisions and to assist in providing South African company law with an efficient and acceptable corporate rescue regime.
https://uir.unisa.ac.za/handle/10500/3575
Keywords: Bankruptcy; Business failures; Business recovery; Business rescue; Corporate insolvency; Corporate reorganizations; Corporate rescue; Corporation law; Debtor and creditor; Financial distress; Insolvency; Insolvency practitioners

Impact of Macro and Micro Governance Structures on Earnings Management - Houqe, Muhammad Nurul (Victoria University of Wellington, 2010)
This study examines the macro and micro level determinants of the quality of reported earnings. The prior literature suggests that both micro and macro variables impact on discretionary accruals choice in managing earnings. However, most of the studies on earnings management have been single country studies that have focussed only on micro variables as all firms within the samples examined have been subject to the same interplay of macro economic, legal, cultural and institutional frameworks. This study addresses this gap in the literature by using a sample of 156,906 firm year observations from 63 countries over the period 1998-2007 to examine the role of thirteen micro and macro variables in determining earnings quality. The macro variables studied include legal enforcement, political system, and control of corruption, culture and adoption of IFRS. Earnings management is estimated using the modified Jones model (Dechow et al. 1995) in a cross section (DeFond and Jiambalvo 1994; Francis et al. 1998). The results of the study indicate that macro and micro level variables have a strong impact on earnings management behaviour and thus earnings quality. The limits imposed by a country's legal, cultural and institutional setting on managerial discretionary accruals choices, strongly impact the quality of reported earnings. Future research on earnings management should therefore control both micro and macro level variables.
Keywords: Earnings management; Macro governance; Micro governance

The participation of developing countries in the dispute settlement system of the WTO - Al. Shraideh, Saleh Adnan (Macquarie University, 2010)
International trade relations have become much more legalised under the World Trade Organization (WTO) than under the former international trade system created pursuant to the General Agreement on Tariffs and Trade (GATT). The Dispute Settlement Understanding (DSU) of the WTO clearly represents a shift toward a rule-oriented, legalistic and adjudicative approach, which is intended to enhance that status of, and confidence in, the WTO dispute settlement system. The approach is likely to ensure greater stability and predictability in the system by encouraging precise decisions on the merits of disputes and discouraging infractions. Its greater binding effect serves as a powerful disincentive to those Members who have a propensity to favour unilateral measures to solve international trade disputes. This is particularly beneficial for developing countries that sought a system which recognises their disadvantaged position compared to the greater bargaining and retaliatory power of developed countries. However, despite the positive assessment of the WTO dispute settlement system, the functioning of the system is working against the interest of developing countries in having an efficient dispute settlement system that considers their needs and deals fairly with their disputes. This thesis examines the participation of developing countries in the dispute settlement system of the WTO, and argues that they are in a disadvantageous position compared to their developed counterparts. The system's failure to effectively address or efficiently deal with this position is an evidence of its bias against and deficiency towards developing countries' participation. The thesis focuses on the problematic issues developing countries face throughout their use of the system. It also considers the role that the DSU has played in addressing these issues and the efficiency of that role in restraining and limiting their effect on developing countries' participation in the system. The thesis analyses some ideas on the reform of the DSU that have been proposed through WTO negotiations or literature, and discusses their applicability on the current dispute settlement system. Finally, the thesis employs these proposals along with its discussion on the subject to introduce a reformed model of the DSU which is more sensitive to developing countries' concerns in the system in order to help providing an understanding of how such modifications could be carried out in future reforms on the DSU.
Keywords: Conflict management; Developing countries; Foreign economic relations; GATT; General Agreement on Tariffs and Trade; International relations; Politics and government; WTO; World Trade Organization

Reforming corporate governance: Protecting minority shareholder rights through a strong corporate law system - Deniz, Ozden (American University, 2010)
Keywords: Association law; Corporate governance; Corporate law; Minority shareholder (protection)

A critical evaluation of the interaction between sport and law in South Africa - Louw, André Mouton (Stellenbosch University, 2010)
This dissertation contains an evaluation of the interaction between law and sport in South Africa. The evaluation includes description of the main areas where laws (in the form of the common law, legislation and the relevant provisions of the Constitution of the Republic of South Africa, 1996) apply to sport, in the contexts of both amateur sport and the fast-developing professional sports industry. Apart from such descriptive content, the dissertation will also critically evaluate the appropriateness of the relevant laws and their application in the often atypical context of sport, as well as the courts' treatment of the relevant legal issues. In the process of providing such critical evaluation, and where relevant, the author includes a comparative analysis of the treatment of relevant legal issues in other jurisdictions (most notably the United Kingdom and European Union, which are especially relevant in light of the application of the 'European model' of sports governance and regulation, which applies to the major sporting codes in South Africa). In particular, the author critically evaluates the following aspects of the South African jurisdiction's treatment of the application of law to sport: - The South African system of public regulation of sport by the State (and, specifically, the issue of the race-based transformation of sport, which involves an apparent government-driven agenda and is unique to the South African jurisdiction); - The courts' treatment to date of the susceptibility of the conduct of sports governing bodies to judicial scrutiny (and of the nature of such bodies as voluntary associations); - Various aspects related to the application of employment laws to the employment of professional athletes in team sports; - The application of common law remedies for breach of contract in the professional sports employment context; - The potential application of the restraint of trade doctrine (in, as the author suggests, an extended_ form) in the context of the freedom of movement of professional athletes; The apparently unsatisfactory state of current South African law in respect of legal protection against commercial misappropriation of aspects of the persona of famous athletes (i.e. in the context of 'image' -or-,'publicity' rights as recognized in certain other jurisdictions); and - An evaluation of the extensive protection (especially in the form of specific legislation in South Africa) against ambush marketing of major sporting events. The author includes some concluding observations regarding the state of South African sports law as compared to other jurisdictions, as well as some comment on expectations for the future development and potential importance of the South African domestic jurisdiction in the application of law to sport.
URI: http://hdl.handle.net/10019.1/49490 There are three other contributors to this work numbering 15 p. in total.
Keywords: Comparative law; European Union; South Africa; Sports; United Kingdom

Business law transplants and economic development: an empirical study of contract enforcement in Dakar, Senegal - Paquin, Julie (McGill University, 2010)
La création d'environnements attrayants pour les investisseurs est récemment devenu une priorité pour les spécialistes du développement, qui conseillent aux pays en voie de développement d'adopter les « meilleures pratiques » d'affaires utilisés dans les pays développés. Bien qu'on reconnaisse que le transfert de modèles juridiques d'un pays à un autre entraîne souvent des résultats décevants, la question du niveau de compatibilité requis entre les modèles transférés et le pays importateur est le plus souvent ignorée ou considérée comme une question technique relevant de la compétence des professionnels du droit locaux. Dans ce processus, pratiquement aucune place n'est faite au point de vue des utilisateurs finaux des nouvelles normes et institutions. La présente thèse se fonde sur une étude empirique de l'impact de la réforme du droit des affaires relativement en matière d'exécution des contrats. Dans une première partie, les hypothèses sur lesquelles les réformes actuelles se fondent sont examinées à la lumière de contributions provenant de divers champs disciplinaires. Divers facteurs considérés comme expliquant les effets limités des réformes entreprises jusqu'à présent sont présentés. La deuxième partie analyse le contenu de 30 entretiens en profondeur réalisés auprès de petites et moyennes entreprises de Dakar, Sénégal. Les entretiens révèlent que les PMEs dakaroises font preuve d'une grande flexibilité dans l'exécution de leurs contrats d'affaires, et que la qualité des institutions juridiques et judiciaires joue un rôle peu important dans les décisions qu'ils prennent à cet égard. L'environnement général dans lequel elles opèrent, qui se caractérise par la présence de contraintes financières importantes, un haut niveau d'inceritude et une grande interdépendance entre les entreprises, constitue le facteur le plus important pour expliquer le comportement des entreprises. La troisième part
https://escholarship.mcgill.ca/concern/theses/gm80hv75c
Keywords: Business law; Contract enforcement; Economic development; Senegal

A Critique of Trade Disputes Settlement Mechanism in Nigeria: 1968 to 2004 - Anyim, Francis Chukwudike (University of Lagos, 2009)
Full texts attached
https://ir.unilag.edu.ng/handle/123456789/4419
Keywords: Conflict Manifestation; Labour market research; Marxist Perspective; Process of Collective Bargaining; Strike and its effect

The relevance of prior use in trade mark conflicts - Alberts, Riaan Willem (University of South Africa, 2009)
This thesis investigates the role of prior use in common and statutory trade mark law. In the United States a pertinent requirement is priority of use. In the United Kingdom and South Africa, a reputation must be present. In the United Kingdom a plaintiff is required to have goodwill in the country, but in the United States and South Africa it is not required. The conception of a mark does not qualify for protection. It is not required that a business must have actually entered the market. In the United States the general approach is that a plaintiff will not receive protection in a remote area, but regard must be had to zones of natural expansion. British and South African law is the same, and protection may be obtained in areas where there is no trading. Where a dual reputation exists, neither party will be able to act against the other. The mere fact that the user of a mark was aware of the use thereof by another person, does not exclude protection. A trade mark application can be opposed on the basis of another application, combined with use of a mark, or on the ground of prior use. In some instances the fact that a mark has been filed will influence the burden of proof. In general, a registration can be expunged on the same grounds as would constitute grounds of opposition. The concurrent use of a mark can form the basis for the registration of a mark. In the United States, the use must have taken place prior to the filing date of the other party, but in the United Kingdom and South Africa, prior to the own filing date. In the latter two countries, knowledge of a mark is not necessarily exclusionary. Prior use is generally accepted as a defence to an infringement action. It is, however, noted that in various countries, it is only use prior to the relevant date that will be protected, and there is not necessarily a right to extend the scope of use concerned.
Keywords: Common law trade marks; Competencia; Competition law; Intellectual property; Trade marks; Unfair competition; Unlawful competition

Selective legal aspects of bank demand guarantees - Kelly-Louw, Michelle (University of South Africa, 2009)
Bank demand guarantees have become an established part of international trade. Demand guarantees, standby letters of credit and commercial letters of credit are all treated as autonomous contracts whose operation will not be interfered with by courts on grounds immaterial to the guarantee or credit itself. The idea in the documentary credit transaction/demand guarantee transaction is that if the documents (where applicable) presented are in line with the terms of the credit/guarantee the bank has to pay, and if the documents do not correspond to the requirements, the bank must not pay. However, over the years a limited number of exceptions to the autonomy principle of demand guarantees and letters of credit have come to be acknowledged and accepted in practice. In certain circumstances, the autonomy of demand guarantees and letters of credit may be ignored by the bank and regard may be had to the terms and conditions of the underlying contract. The main exceptions concern fraud and illegality in the underlying contract. In this thesis a great deal of consideration has been given to fraud and illegality as possible grounds on which payment under demand guarantees and letters of credit have been attacked (and sometimes even prevented) in the English, American and South African courts. It will be shown that the prospect of success depends on the law applicable to the demand guarantee and letter of credit, and the approach a court in a specific jurisdiction takes. At present, South Africa has limited literature on demand guarantees, and the case law regarding the grounds upon which payment under a demand guarantee might be prevented is scarce and often non-existent. In South Africa one finds guidance by looking at similar South African case law dealing with commercial and standby letters of credit and applying these similar principles to demand guarantees. The courts, furthermore, find guidance by looking at how other jurisdictions, in particular the English courts, deal with these issues. Therefore, how the South African courts currently deal/should be dealing/probably will be dealing with the unfair and fraudulent calling of demand guarantees/letters of credit is discussed in this thesis.
Keywords: Bank guarantee; Demand guarantee; Documentary credit; Fraud; Freezing injunction; Garantie bancaire; Letters of credit; Suretyship and guaranty

A critical analysis of problem areas in respect of assets of insolvent estates of individuals - Evans, Roger Graham (University of Pretoria, 2009)
The Law of Insolvency in South Africa is regulated by the provisions of the Insolvency Act 24 of 1936, with foundations in our common law, which has been influenced by different legal systems from Western Europe. But currently there is also other legislation affecting the insolvent debtor and the property in the insolvent estate. The courts too have had to formulate rules to govern aspects of insolvency law in South Africa. These variables created problem areas in insolvency law and in respect of the of the policies upon which the insolvency system hinges. The predominant policy in South African insolvency is the collection of the maximum assets of the debtor for the advantage of creditors in insolvent estates. This strict creditor orientated approach created further problem areas in respect of assets in the insolvent estates of individual debtors. If advantage to creditors cannot be shown in an application for the sequestration of a debtor’s estate, a court will refuse to grant that order. This strict policy overshadows policy concerns in respect of assets in insolvent estates, and regarding exemption law in respect of those assets. This has resulted in insolvency law reformers in South Africa missing the bigger picture, namely, that South Africa is a creditor driven developing society. It is conceivable that in the transformed South Africa, and in the present world economic chaos, there will be an escalation of sequestrations of the estates of individual debtors. Bearing this in mind, a reformed insolvency law system must become more debtor friendly. A change in the philosophy is needed in favour of an exemption policy for insolvent estates. Exemption policy must be based on the interest of the debtor and his dependants, his dignity, creditor and third party interests, social welfare, and human rights imperatives within the South African constitutional framework. Exemption policy must be linked to the policy of a “fresh start” for the debtor. The different policies in insolvency however create a conflict of interest among the different stakeholders, particularly regarding the assets in insolvent estates, thereby creating problem areas. In this thesis several problem areas are identified and critically analysed. The position of property included in, and excluded from, individuals’ insolvent estates is investigated from a brief historical perspective, and in a brief comparative survey of the insolvency systems of the United Kingdom and the United States of America. Acute problem areas are critically analysed in detail, and the constitutional impact on property in insolvent estates is considered in a separate chapter. The South African Law Reform Commission’s review of South African insolvency law is critically analysed in a chapter of this thesis, concluding that the Commission’s review is inadequate. This thesis concludes that there is a need to reform the insolvency system in South Africa and proposes a way forward in respect of property included in, and property excluded or exempt from insolvent estates. This thesis states the law to the end of October 2008.
Keywords: Advantage to creditors; Creditor; Debtor; Disposition of property

Labour law implications of the transfer of an undertaking - Smit, Nicola (University of Johannesburg, 2009)
This thesis provides a comprehensive analysis of the legal, social, and economic consequences of business transfers on employment contracts, focusing on South African law and its comparison with international standards. It critically evaluates the automatic transfer of employment contracts, the protection of employee rights, and the legal complexities surrounding insolvent undertakings.
Keywords: Labour law; Labour legislation; Transfer (Law)

Rethinking the world trade order: towards a better legal understanding of the role of regionalism in the multilateral trade regime - Abualethem Nsour, Mohammad Fahed (McGill University, 2009)
Regional Trade Agreements (RTAs) have proliferated at an unprecedented pace since the creation of the World Trade Organization (WTO). Although the WTO legally recognizes countries’ entitlement to form RTAs, neither the WTO nor parties to RTAs have an unequivocal understanding of the relationship between the WTO and RTAs. In other words, the legal controversies, the result of uncertainty regarding the application of the WTO/GATT laws, risk undermining the objectives of the multilateral trade system. This thesis tackles a phenomenon that is widely believed to be heavily economic and political. The thesis highlights the economic and political aspects of regionalism, but largely concentrates on the legal dimension of regionalism. The main argument of the thesis is that the first step to achieving harmony between multilateralism and regionalism is the identification of the legal uncertainties that regionalism produces when countries form RTAs without taking into account the substantive and procedural aspect of the applicable WTO/ GATT laws. The thesis calls for the creation of a legal instrument (i.e. agreement on RTAs) that combines all of the applicable law on RTAs, and simultaneously clarifies the legal language used therein. Likewise, the WTO should have a proactive role, not merely as a coordinator of RTAs, but as a watchdog for the multilateral system that has the power to prosecute violating RTAs. The author is aware that political concerns are top priorities for governments and policy makers when dealing with the regionalism problematic. Hence, legal solutions or proposals are not sufficient to create a better international trade system without the good will of the WTO Members who are, in fact, the players who are striving to craft more regional trade arrangements.
Identifier: https://escholarship.mcgill.ca/concern/theses/3r074w80k
Keywords: GATT; International Trade; Regional Trade Agreements (RTAs); WTO

Harmonisation of procedural law in international commercial arbitration - Chang, Mann-Long (University of Stirling, 2009)
The principle of party autonomy is widely accepted in the practice of international commercial arbitration. However, it still encounters certain limitations in its applications, especially for the fact that the demands of natural justice and the public good cannot be neglected by the parties. The various states in the international system have and operate peculiar systems of mandatory rules and public policies, which tend to impart significantly on the arbitral procedure, thereby creating a situation of discordance of outcomes of arbitration in different countries. For this reason, this writer intends to examine ways by which the various procedural laws can actually be harmonised. This thesis shall therefore focus on the discordances and confusion that often arise in the interacion of the various laws that may be applicable to the arbitral process in International commercial arbitration, as well as ways of achieving a harmonisation of these laws.
Keywords: Arbitrage commercial international; Arbitragem; Arbitraje; Arbitration; International commercial arbitration

Libyan Attitudes towards Islamic Methods of Finance: An Empirical Analysis of Retail Consumers, Business Firms and Banks - Gait, Alsadek Hesain Abdelsalam (Griffith University, 2009)
Libya is a predominately Muslim country where Islamic finance has not yet been established. However, given the current extensive program of financial reform in Libya and the rapid growth and appeal of Islamic finance in comparable economies, there is growing pressure for a system of Islamic finance to be provided. There is then a pressing need for research into the prospects for Islamic finance from a consumer and provider perceptive to inform this debate and thereby meet the needs of policymakers, financial service providers and prospective users. Accordingly, this study of Libyan attitudes towards Islamic methods of finance, the first study attempted in the Libyan context and one of few studies globally, applies a model derived from the Theory of Reasoned Action to analyse attitudes towards Islamic finance. The particular focus is to understand how the Theory of Reasoned Action can be used for predicting and understanding attitudes towards the potential use of Islamic methods of finance by Libyan retail consumers, business firms and banks. Four main research questions are posed to address this objective. First, does awareness of Islamic methods of finance influence attitudes towards the use of Islamic finance? Second, do socioeconomic, demographic and other factors influence attitudes towards Islamic finance? Third, what are the principal motivating factors towards the potential use of Islamic finance? Finally, is religion the major influence on the likelihood of engaging in Islamic finance? Three surveys of 385 retail consumers, 296 business firms and 134 bank managers in Libya are conducted in 2007/08 to achieve this objective. Descriptive analysis and multivariate statistical analysis (including factor analysis, discriminant analysis and binary logistic regressions) are used to analyse the data. The principal findings are that awareness of Islamic methods of finance and socioeconomic, demographic and business characteristics are key determinants of the likelihood of the use of Islamic finance. Further, religion plays a key, though not the only, role in influencing these attitudes. The thesis findings are of key importance in informing future financial industry practice and financial policy formation in Libya.
Accepted: 2018-01-23T02:48:08Z
Keywords: Finance; Financial policy; Financial reform; Islam; Islamic finance; Libya

Income splitting, settlements and avoidance: taxing the family on business profits - Loutzenhiser, Glen (Oxford University, 2009)
In a progressive income tax system with an individual tax unit, high-rate taxpayers have an incentive to split income with lower-rate family members to minimise the family’s total tax burden. This raises equity and neutrality concerns. Adopting a spousal tax unit limits the gains from income splitting, but the individual is the better choice on privacy, autonomy, equality, definitional, marriage neutrality and work incentive grounds. Once the individual is chosen as the income tax unit, the control model provides a strong policy basis for attributing both earned and unearned income to individuals. Income splitting, however, undermines this model as well as the individual tax unit. This thesis focuses on the UK’s approach to income-splitting in family businesses. The relevant UK income tax rules, particularly the settlements provisions, are inadequate for the task. Various possible reforms are examined. Incorporating a transfer pricing or ‘reasonableness’ test into the settlements provisions would strengthen these rules, but would make taxpayer compliance with an uncertain regime even more difficult. Another option is to expand the scope of employment tax by moving the borderline between employees and the self-employed or companies. Deeper structural reforms could be made to enhance the neutrality of taxation on different legal forms of economic activity. This would reduce the incentives to incorporate for tax savings, including from income splitting. Integration of income tax and NICs is one such option; a dual income tax is another. A TAAR or GAAR also could be pursued. Ultimately, some combination of these various reform options could provide a partial solution to this challenging issue.
Keywords: Family taxation; Husband and wife; Income splitting; Settlements; Taxation

A balancing act: a framework for participation of non-state actors in the World Trade Organization - Majlessi, Mohammad (McGill University, 2009)
This thesis focuses on the interaction of two categories of non-state actors, private sector corporate actors and non-governmental organizations, with states in the context of the World Trade Organization (WTO) through a lens of public international law. It builds on the premise that the notion of states as the only subjects of international law is not adequate for a modern system of global governance, as it does not reflect the realities of fast-paced globalization and increased co-operation in a world where the boundaries of the private and public are increasingly blurred. It does not necessarily provide solutions for participation of non-state actors in the WTO, but demonstrates that developments in international relations warrant more space for participation of non-state actors, and that the current system of the WTO fails to provide sufficient space for participation. The thesis argues that, for both historical and pragmatic reasons, developments in the areas of GATT and international trade law occurred outside their natural course, leading to the myth of a “self-contained” trade regime not part of public international law. The WTO, unlike its predecessor, enjoys a proper institutional framework and mandate; one can no longer use the excuse of institutional handicap for excluding it from the system of global governance. Liberalization of international trade has far-reaching consequences which are not limited to the trade arena and the WTO, its member states, and scholars of international trade law have to assume their role in the broader context of an international legal order. Non-state actors’ formal participation can contribute to striking a balance between different forces and interests at work in the area of trade liberalization and its interplay with other non-trade issues. After setting the framework for the study, the thesis outlines modes of participation of non-state actors in the creation and modification of WTO law as well as in its enfor
https://escholarship.mcgill.ca/concern/theses/nv9354568
Keywords: Balancing act; International Trade; WTO; World Trade Organization

Status Ambiguity and Conflict in the Market - Tan, David (Emory University, 2009)
My main theoretical contention is that status hierarchies provide a source of guidance to firms for resolving disputes. A status hierarchy implies a system of deference rules among firms. When disputes arise, deference rules can provide a basis for shared expectations and protocols of conduct about how technical ambiguities should be resolved. In many contexts, technical merit is difficult to assess. However, deference rules can operate as social conventions to which firms default, helping to align potentially incompatible expectations. Within this general framework, my dissertation examines how competitors in the semiconductor industry manage uncertain and frequently overlapping patent rights. In practice, patent rights are highly imperfect legal instruments when it comes to demarcating each firm's contributions to innovation in the industry. Patent disputes arise because of the ambiguity this creates about how much of the collective market returns to innovation each firm is entitled to receive. Despite the prolific patenting and propensity for disputes, the industry has remarkably not ground to a halt from runaway litigation. Litigation events, while significant, are rare. I suggest that this degree of order is, at least partly, attributable to status processes. Status can operate as a stabilizing force in the market, helping to generate orderly competition in the face of disputes. To examine whether this is the case in the semiconductor industry, I theorize that disputes are less easily resolved when the parties involved face greater status ambiguity, i.e. are less clearly differentiated from one another in status. Under status ambiguity, deference rules lose the rule-like, universal quality that makes them persuasive in resolving disputes. This has two consequences. First, firms facing low status ambiguity are less likely to be involved in patent litigation than are firms facing high status ambiguity. Patent litigation events represent failures to resolve patent disputes out of court. Second, firms facing low status ambiguity increase their product line sizes more than do firms facing high status ambiguity. The threat of difficult-to-resolve patent disputes represents a cost that can deter firms from bringing products to market.
Permanent URL: https://etd.library.emory.edu/concern/etds/9g54xj191?locale=en
Keywords: Litigation; Patent; Semiconductor; Status

Recognition of various stakeholder interests in company management - Esser, Irene-Marié (University of South Africa, 2008)
Good corporate governance should be the cornerstone of all company management. Directors ought to know in whose interests the company should be managed. This thesis attempts to answer the following question: whose interests must be granted primacy in the management of a company? In chapter 1 it is stated that shareholders' interests are traditionally granted primacy in the management of a company. There has, however, been a shift in public opinion towards recognition of a wider variety of interests that should be considered than only those of the shareholders. These interests include, inter alia, environmental interests and those of the investors, employees and consumers. This thesis thus focuses on the primary stakeholders, namely individual shareholders, creditors, employees, consumers and suppliers. In chapter 2 a theoretical foundation is provided on the nature of a company. The different theories on the nature of a company, emphasising either shareholder primacy or stakeholder protection, are discussed. A combined new theory is proposed. It is suggested that the confusion relating to the meaning of "the company" needs to be eliminated. Chapters 3, 4 and 5 provide an international comparison of the company law in Botswana, Australia, New Zealand and the United Kingdom. The focus falls, firstly, on directors' duties, secondly, on the question in whose interests directors should manage a company and, thirdly, on the codification of their duties. In chapter 6 the South African position is evaluated. First, the possible stakeholders are identified and the protection currently afforded them is explained. The reports of the King Committee on Corporate Governance, the Policy Document on company law reform as well as the Companies Bill of 2007 are discussed. Draft clauses are recommended to be incorporated in new company legislation to provide directors with clarity on what is expected of them. It is the aim of this thesis to provide clarity on whose interests should receive primacy when directors manage a company. The outcome of this research should provide a clear indication to South African directors of what is expected of them and who the beneficiaries of their fiduciary duties are.
Keywords: Codes of best practice; Consumers; Corporate governance; Corporation law; Creditors; Directors' Duties; Shareholder value; Shareholders; Social responsibility of business; Stakeholders

Crossing the Wires: the Interface between Law and Accounting and the Discourse Theory Potential of Telecommunications Regulation - Carter, David Bernard (Victoria University of Wellington, 2008)
Regulating telecommunications is complex: international experience indicates that there is no 'successful' regulatory framework due to the balancing of industry and regulatory interests (Laffont & Tirole, 2000, p. 13). The New Zealand 'light-handed' regulatory experiment failed and the 1999 General Election presented an opportunity for change in telecommunications. The Labour-led Government in implementing a policy of 'responsible re-regulation' enacted the Telecommunications Act 2001, signalling the passage of "landmark telecommunications legislation ..." (Swain, 2001d). Within the Telecommunications Act 2001, 'cost' assumed a central regulatory role. It is this move to cost that this thesis considers in identifying, developing, and critiquing the interface of law and accounting. The thesis examines the increasing call for accounting information in law and regulation by interrogating the use, presentation, and reception of accounting to examine the interface between law and cost in the regulation of telecommunications. The Telecommunications Act 2001 incorporates total service long run incremental costing as the 'costing technique' for interconnection access and annual net costing for the Telecommunications Service Obligation. Through interrogating 'cost' as an accounting technology, in contrast to the economic and legal conception of cost as a simple, objective concept, the thesis illustrates the role of cost at methodological, technical, and political levels, and the challenges that this poses for telecommunications regulation. The thesis articulates the relevance of discourse theory to the interface of law and accounting. Consequently, the thesis investigates the formation and discursive enunciation of standpoints of political identities characterised by antagonism and uncertainty. This includes identifying attempts by interested parties, including industry actors, stakeholders, and the Government and its agents, to articulate 'new' discourses centred on nodal points around 'cost'. The rhetorical analysis examines how actors articulate the metaphorical element of 'cost' in agitating for particular costing methods to be included in the legislation. The empirical analysis examines the process of rhetorical condensation as arguments for and against the incorporation of total service long run incremental costing and net costing came to signify the complete failure of the light-handed regulation. Then, by examining the politics following the enactment of legislation, this condensation is unpacked. The analysis of the contestation over interpreting and implementing the regulation illustrates displacement of the 'common' signifier resulting in confusion and disappointment in relation to the aims of the new regulatory regime.

The development of performance requirements in international law and their effect on BITs and FTAs as well as on the agreeing parties - Bless, Christopher Josef Manfred (Universität Wien, 2008)
Performance requirements are part of a system of policy measures implemented by states to advance their economic, social and political objectives. A universally agreed upon definition of performance requirements is not available. Rather they are defined by the applicable legal norms and their assessment is dependent upon their effect on the parties of each individual case. The scope of legal protection these regulations provide must be measured separately for each norm within the scope of the specific legal framework. This dissertation has two objectives: First, the implementation and legal effect of performance requirements in international investment and trade law are investigated. Secondly, a legal test will be developed, that allows for an assessment of performance requirements. In a first step, the legal treatment of performance requirements will be analyzed from a theoretical perspective. Subsequently, the legal practices relating performance requirements and the relevant provisions in international investment and trade law will be identified. The developed legal test does not only do justice to the economic, social and political framework within which each performance requirement must be looked at but is also adaptable in a way that it can be applied to a variety of situations and legal traditions. It satisfies both the demands of legal certainty and clarity as well as facilitating the finding of justice on an individual basis. Understanding the advantages of foreign direct investment, the analysis performed aims promote the usage of performance requirements in a way that foreign direct investment will push the global economy forward.
https://phaidra.univie.ac.at/detail/o:1258202
Keywords: FIRA; Foreign direct investment; Free trade agreements; International Trade; International investment; Investment treaties; NAFTA; Performance requirements

Directors’ duties to creditors - Lombard, Sulette (University of Pretoria, 2007)
Creditors of the corporate business form are in a vulnerable position. Recognition of the plight of corporate creditors led to the implementation of various legal measures aimed at protecting their financial interest in the company. These measures proved disappointingly inadequate in many instances. As a result the judiciary in some jurisdictions felt compelled to develop existing legal principles pertaining to directors’ duties in such a way that they could be used to facilitate protection of corporate creditors’ interests. This development did not meet with universal approval. Those opposed to the extension of directors’ duties to protect creditors’ interests have three main arguments against it. The first is related to conceptual issues and policy concerns. The second argument is that existing remedies are more than adequate to protect creditors’ interests. A last argument against a directorial duty to creditors pertains to the practical implementation of this extended duty. It is argued that the existing legal framework with regard to directors’ duties is not suitable to provide protection for creditors’ interests. However, it was shown in this study that the extension of directors’ duties to protect creditors’ interests is indeed justifiable on a sound conceptual basis and that policy concerns regarding such an extension are either unfounded, or should be addressed in some other way. An analysis of existing protective measures and remedies often referred to by opponents of an extension of directors’ duties, namely statutory personal liability of directors, traditional insolvency remedies, and the piercing of the veil doctrine furthermore showed that these measures are inadequate. This leads to the conclusion that there is a definite need for an alternative remedy, such as the extension of directors’ duties to include creditors’ interests. The existing legal framework in respect of directors’ duties furthermore proved to be capable of being successfully adapted to include creditors’ interests. Central issues in this respect, as was indicated by an analysis of case law, are the point in time when the duty to creditors is triggered, the beneficiary of the duty, in other words who would have locus standi in case of a breach of the duty, and the type of protection afforded to creditors’ interests by way of fiduciary duties and the duty of care and skill. The existing legal framework also provides measures in terms of which honest and diligent directors may be relieved from liability, such as indemnification, relief granted by the courts and director liability insurance. These measures, if formulated correctly, may achieve and maintain the essential balance between accountability and entrepreneurial freedom. The legislature appears to have adopted a cautious approach to the issue of directors’ duties to creditors. It thus seems to be up to the judiciary to develop directors’ duties to creditors in a meaningful way. Pioneering in this respect has already been done in Australia, New Zealand, England, Canada and the United States of America. It is to be hoped that the South African judiciary will follow suit when the opportunity to do so arises.
Keywords: Beneficiary of directors’ duties; Company law; Company’s interests; Corporate law

Legal aspects of corporate governance in the republic of South Africa: towards a possible model for improved stakeholder relations within the corporation - Spisto, Michael Paolo (University of the Witwatersrand, 2007)
Traditionally, company law assumes that the directors’ role is to run the company for the benefit of its shareholders alone and to maximise profits for them. It can be argued, however, that this view is too narrow and outdated; that is, company directors should have regard to the rights and interests of a broader range of corporate stakeholders. Hence, the question is whether we should change our perception of the company or corporation from one run by directors dedicated exclusively to serving the interests of shareholders to that of a corporation whose main purpose is to bring benefit not only to its owners and creditors, but also to its employees, the community and the environment. Given that reforms of directors’ duties in light of the above considerations have found their way into legislation across the globe, this thesis examines how and to what extent legal rules and policies should develop in South Africa to place directors under a positive duty to take account of the interests of bodies other than shareholders. Current South African company law does not contain clear rules regarding corporate governance issues and the duties and liabilities of directors. These matters have been left to the common law and Codes of Corporate Practice. Thus, there is no extensive statutory scheme in South Africa, which covers the duties, obligations and accountability of directors. The focus in this thesis is on the rights and interests of employees and the premise that is defended is that it is valuable to corporations to provide employees with an institutionalised voice at board level. It is argued that there is global evidence that where employees participate in the decision-making processes of the company, performance is generally enhanced. This, in turn, directly impacts upon and improves economic productivity, generating a ‘win-win’ situation. The question of the duties of company directors and managers is attracting much attention in South Africa. With rapidly developing and changing labour legislation in South Africa, it is essential to consider the extent to which the country should reassess its traditional principles of company law and corporate governance policies in order to encourage participatory roles for employees in the workplace. It is argued that if South Africa is to improve corporate productivity levels with its re-entry into international markets, management and labour must find improved ways of dealing with one another. The main purpose of this thesis, therefore, is to propose and formulate a workable corporate governance model for South Africa – one that would be advantageous to all stakeholders, especially the employees. This is achieved by comparing and contrasting international models of corporate governance and by applying the best features of each to the unique South African corporate system of values, structures and traditions. It is suggested that the current unitary board structure operating in South Africa has become outdated and does not provide employees with rights enabling them to engage in the decision-making processes of the corporation with their employees at an adequate level. In its place, a two-tier board system of corporate governance is proposed. The economic success of a company will bring about social benefits to many stakeholder constituencies. This will not happen if the company is a financial failure. The issue of obliging directors to act primarily for the benefit of shareholders alone is questioned. Corporate governance reforms were undertaken in many parts of the world in the late 1980’s and early 1990’s. This reform process questioned whether the interests of the company should be managed for the shareholders alone or for the other corporate stakeholders as well. There are many views that strongly support the idea that corporate governance should be seen as a system by which corporations are to be governed for the benefits of all stakeholders, including shareholders, employees, creditors, suppliers and the community. In this way, companies should be run as communities in partnerships with all their stakeholders. Thus, this thesis proposes that the success of a company is inextricably intertwined with a consideration of the rights and interests of its employees and other stakeholders.
URI: http://hdl.handle.net/10539/1969
Keywords: Bond/Debenture Holders; Community; Companies; Corporate governance; Corporations; Creditors; Employees; Environment; Interests; Models; Rights; Shareholders; South Africa; Stakeholder Relations

Alternative means to regulate the employment relationship in the changing world of work - Vettori, Maria-Stella (University of Pretoria, 2006)
Advancing technology has caused rapid and dramatic changes in the world of work. Labour law systems grounded in the industrial era, with their emphasis on collective bargaining, are not suitable in today’s world of work. Throughout the world, the ‘atypical employee’ is replacing the standard or typical employee whose terms and conditions of employment were generally regulated by collective agreements. Atypical employee’s terms and conditions of employment generally are not regulated by collective agreements. World– wide trends in the decentralisation of collective bargaining, decollectivisation and individualisation of the employment relationship have contributed to a decline in trade union power and influence. Consequently the number of workers covered by collective agreements has decreased. Collective bargaining has been rendered less effective because of the changing the world of work. The South African labour law system places a huge emphasis on collective bargaining, particularly at industry level, for the protection of employee interests. Given these trends in the changing world of work, the appropriateness of this emphasis on industry or central level collective bargaining is questioned. The vacuum left by the inadequacy and inability of trade unions to protect employee interests in a comprehensive manner by means of collective bargaining, needs to be addressed. The following alternative means of protecting employee interests are considered: (i) The socialisation of the law of contract; (ii) the interpretation given to the constitutional right to fair labour practices; and (iii) the role of good corporate governance and corporate social responsibility. These alternative means of addressing legitimate employee interests could play a role in filling the vacuum created by trade union decline. The South African law of contract is capable of bridging the gap between law and justice by the application of the concepts of good faith and public policy, so that employment contracts may take cognisance of employee interests despite the imbalance of power between employer and employee. The protection of worker interests by means of the constitutional right to fair labour practices depends on the judge’s interpretation of what is fair. Implementation of good corporate governance codes can be influential in protecting and promoting employee interests.
Keywords: Atypical employee; CSR; Collective bargaining; Corporate Social Responsibility; Corporate governance; Decentralization; Decollectivisation; Fordism; Individualization

Search and seizure, production and preservation of electronic evidence - Nieman, Annamart (North-West University, 2006)
Criminals are becoming increasingly involved in computing activity and connectivity, but practitioners in the criminal justice field do not seem to be keeping pace with crime in a computing context. Being comfortable with the technology that underpins the Information Age is a non-negotiable skill for those who have to unravel and bring twenty-first century crimes to book. Chapter two of this study therefore sought to serve two purposes. The first aim was to acquaint the reader with the exceedingly complex technologies involved in computers and networks. The second aim was to clarify the technical context and terminology typical of the collection of electronic evidence. South Africa signed the Cybercrime Convention in November 2001. At present, the Cybercrime Convention is the only existing internationally accepted benchmark, inter alia, for the procedural powers aimed at the collection of electronic evidence. The main objective of this study was to consider whether the South African search and seizure, production and preservation devices need to be augmented and/or aligned so as to be on par with the devices proposed in the Cybercrime Convention. This objective was served in two ways. Firstly, an exposition of the requirements, scope, conditions and safeguards of the domestic and transborder search and seizure, production and preservation mechanisms proposed by the Cybercrime Convention was provided in chapter three of this study. Secondly, an exposition of the domestic and transborder international search and seizure, production and preservation devices available in the current South African legislative framework was given in chapter four of this study. A comparative analysis was done between the South African catalogue of criminal procedural search and seizure, production and preservation devices compared to those set out in the Cybercrime Convention. Where any alignment or augmentation of the South African devices was found to be necessary, this study identified these intervention areas. The findings and recommendations based on this comparative analysis were set out in chapter seven of this study. In considering any alignments and/or augmentations required in respect of the South African domestic search and seizure, production and preservation mechanisms, the application of the equivalent mechanisms directed at electronic evidence used in the United States of America and England were investigated in chapters five and six respectively. The lessons learned were also referred to in chapter seven of this study.

A comparative legal study of the dilution of registered trade marks in selected jurisdictions to further the development of the remedy in South African law - Van der Walt, Elizabeth Margaretha (Stellenbosch University, 2005)
Trade marks are among the most valuable commodities of the modern business world. Adequate protection for trade marks to prevent the misappropriation of their incredible marketing power is therefore important. The aim of this dissertation is to make recommendations regarding the further development of existing South African law regarding the protection of registered trade marks against dilution, particularly by the courts. Current statutory protection is examined and compared with trade-mark law in the United States and the European Union. Although the concept of dilution originated in Germany, most of its development took place in the United States, starting in 1927 with an article by Frank Schechter. Dilution occurs when the awareness that a specific mark signifies a single product from a single source changes to an unmistakable awareness that the same mark signifies various things from various sources. The primary theories as to how dilution occurs are blurring and tarnishment. Although the dilution concept is widely recognised, there is still a debate amongst legal scholars on whether trade marks deserve protection against dilution. The extent of protection that the law gives to trade marks largely depends on the socioeconomic functions that a trade mark is perceived to fulfil. The original source or origin function is protected by the traditional infringement provisions. The identification or distinguishing function, quality function and advertising function subsequently gained recognition. The advertising function is statutorily recognised in various jurisdictions, which prevents trade-mark dilution. Statutory recognition of dilution in the United States first occurred in State law from 1947 onwards. Protection is generally given to distinctive or strong trade marks where a similar mark is used on dissimilar goods in the absence of confusion in such a way that there is a likelihood that the reputation of the senior mark will be injured. The parameters of the concept were developed and refined mainly through case law. Federal protection against dilution was only introduced in 1995. The new Act, although widely welcomed, also brought some unpredictability and interpretation problems. The first statutory dilution protection for trade marks in Europe is found in the Uniform Benelux Trade Marks Act. In 1989 the European Union adopted the Trademark Directive, with the aim of harmonising the legal protection afforded to trade marks. Its "dilution" provisions were incorporated into the United Kingdom's Trade Marks Act of 1994. The sometimes conflicting interpretations of these provisions by the English courts and the Court of Justice of the European Communities are discussed. The South African Act shows a substantial degree of harmony with legislation in the United Kingdom and other European countries. Aspects of the wording of the dilution provisions are however open to interpretation by the courts. Until the end of 2003 there was only one major trade-mark dilution case decided by a South African court, namely SAR v Laugh It OjJPromotions, which is discussed in detail. The dissertation concludes with recommendations to aid South African courts in the future interpretation and application of the dilution provisions. Amendments to the legislation are also proposed to promote greater clarity.
URI: http://hdl.handle.net/10019.1/50239
Keywords: Brand name products; Comparative law; European Union countries; Intellectual property; South Africa; Trademarks; United States

The cultural industries as a regulatory challenge for international trade law : insights from the NAFTA, the WTO and the EU - Neuwirth, Rostam Josef (European University Institute, 2005)
In the universal history of mankind, the concepts “culture” and “trade” have long denominated two important trains of human aspirations and activities. Notwithstanding their great significance for human life in its entirety, they have been widely regarded as belonging to distinct spheres, which were deemed to be difficult, if not impossible, to reconcile. This perception was also widely reflected in the sphere of law, where their respective fields have been subject to separate regimes based on the logic of their mutual exclusivity and expressed in the concept of res extra commercium. By contrast, the concept of “cultural industries”, which was originally derived from the term Kulturindustrie coined by protagonists of the Frankfurt School introduced a new category of cultural goods and services, which began to strongly challenge the traditional legal separation of cultural from economic considerations. Their novelty as well as their more subtle conceptual implications led to the controversy over the treatment of the dual, i.e. both cultural and economic, nature of such goods and services, which surfaced first during the bilateral trade negotiations between Canada and the United States and soon afterwards during the multilateral Uruguay Round negotiations. In the latter, it was the controversy over the exception culturelle that almost derailed the successful establishment of the World Trade Organization (WTO). Since then the problem remains unsolved, and reinforced by the decision of the WTO Panel in the Canada Periodicals Case, the quest for an appropriate conceptual approach allowing for the correct legal answer to the conundrum of culture and trade continues up to this day. In this quest, the present thesis forms an attempt to cast some light on the culture and trade conundrum with a view to isolating options for an appropriate legal response of the multilateral trading system under the WTO. It follows the evolution of the concept of cultural industries, from its birth in the context of critical social theory across the field of political economy to its first appearance in the legal context with the 1988 Canada-United States Free Trade Agreement. After a short analysis of the cultural industries exemption in the North American context, its focus shifts to the GATT/WTO system of which the basic provisions are discussed in connection with the category of cultural goods and services known as the cultural industries. Their critical analysis yields the present imperfections inherent in the WTO system as a corollary of the fragmentation of the international legal order. Before some final conclusions are drawn, these imperfections are contrasted with the relevant experiences within the context of the process of European integration from the European Economic Community to the European Union.
Artwork Medium: Paper Interview Medium: Paper
Keywords: Cultural property; Foreign trade regulation; Property protection

Theories of the company, employees and takeover regulation - Johnston, Andrew (European University Institute, 2004)
Keywords: Consolidation of corporations; European Union countries; Labor laws and legislation; Merger of corporations; Social policy

Corporate governance: a practical and effective response to the challenges raised - Fridman, Josef J. (McGill University, 2004)
This thesis seeks to address corporate governance from both a practical as well as an academic perspective. It searches for solutions to self-interest and agency costs, problems that it is posited are innate to the anthropomorphism of the corporation and to the separation of management and ownership of widely held, publicly traded, corporations. Practically, this dissertation is anchored in experience, garnered from empirical research, based on in depth and general surveys, as well as detailed interviews. It examines the workings of corporations, including their boards of directors, of gatekeepers, of checks and balances and of shareholders and the relative importance and rationale for the roles that they play. Based on the academic and empirical efforts it is posited that self-interest and the funneling syndrome, (a process whereby information required for decision making is constrained and managed by those in control), almost always predetermines the outcome of the corporate formal decision making process involving the board of directors. This facilitates abuse. When it occurs and there appears to be no accountability, confidence essential to the capital markets, quite understandably, suffers. A hypothesis is advanced to explain the complexity of a potential failure of corporate governance through a relatively simple formula. It draws conclusions as to what is required to help address the challenges raised by the breakdown in effective corporate governance and to help instill greater investor confidence. A self-assessment mechanism to help quantify how effectively a corporation is dealing with corporate governance, both on an absolute basis (comparing itself year over year) and on a relative basis (compared to one's peers) is proffered. This tool of more effective corporate governance, seeks to identify the causes for breakdowns in corporate governance and to assist a board of directors in dealing more proactively with this challenge.
https://escholarship.mcgill.ca/concern/theses/nz8060241
Keywords: Corporate governance

Self-employment and the personal scope of labour law : comparative lessons from France, Italy, Sweden, the United Kingdom and the United States - Engblom, Samuel (European University Institute, 2003)
The past two decades has seen a growing interest, from both policy makers and scholars, in the legal regulation of work performed by self-employed workers. Increases in non-agricultural selfemployment in industrialised countries, together with political and ideological shifts, have fuelled interest in self-employment as a means of increasing employment. The attractions of selfemployment are manifold. To firms, self-employment is part of a two-fold change in the way firms operate: the move towards more flexibility as to the size and composition of the workforce, marked by an increased use of atypical workers and the disintegration of firms by arranging production through outsourcing, subcontracting and franchising. To workers, self-employment offers the greater autonomy connected with being their own boss, a chance of higher returns, or, at least, opportunities of gainful employment in times of high unemployment. To governments, self-employment has been seen as a means of increasing the number of small businesses, supposedly beneficial to the creation of new employment. Encouraging and removing barriers to self-employment is, therefore, a priority for many governments.
Keywords: Labor laws and legislation

Essays on Bargaining with Outside Options - Adamuz Peña, Mercedes (Universitat Autònoma de Barcelona, 2002)
Los modelos de negociación con opciones exteriores normalmente suponen que los pagos de estas opciones son independientes de las acciones que los negociadores toman durante el proceso negociador. Sin embargo, en muchos contextos, la opción exterior depende de lo que las partes hagan durante la fase negociadora. Uno de estos contextos es el de aquellas negociaciones que se llevan a cabo en presencia de un árbitro. Esta tesis realiza algunas contribuciones a la teoría de la negociación con opciones exteriores, enfatizando aquellas situaciones donde las opciones exteriores aparecen por la intervención de árbitros. En el capítulo 2 analizo los efectos del arbitraje en las negociaciones cuando su uso es voluntario. Considero un modelo de negociación por concesiones donde las partes tienen la posibilidad de llamar a un árbitro con el consentimiento del oponente. Demuestro que la introducción del arbitraje distorsiona el resultado de la negociación. Esta distorsión depende de los costes relativos de implementar una partición mediante un proceso negociador versus un proceso arbitral. Si los costes del arbitraje son pequeños en relación a los costes de la negociación, entonces la partición negociada se aproxima a la propuesta por el árbitro, y en casos extremos el arbitraje es utilizado en equilibrio. Sin embargo, los jugadores no eligen siempre el método más eficiente de resolver su disputa: a veces negocian cuando es más eficiente acudir al arbitraje. En el capítulo 3 estudio los efectos de diferentes procedimientos arbitrales en el resultado de una negociación, en un modelo donde los jugadores realizan demandas no crecientes y el árbitro es llamado solo cuando las negociaciones se declaran rotas. Dos procedimientos arbitrales son analizados: el arbitraje convencional, donde el árbitro es libre de elegir su acuerdo y el arbitraje de oferta final, donde el árbitro está obligado a elegir una de las últimas ofertas de los jugadores. Demuestro que si los jugadores son suficientemente pacientes y el árbitro sigue un procedimiento de oferta final, en equilibrio, los jugadores negocian una partición pero toma algún tiempo llegar a ella. Sin embargo, si el árbitro sigue un procedimiento convencional, en equilibrio los jugadores utilizarán esta institución para resolver su disputa. Finalmente, en el capítulo 4 discuto el papel que juegan las opciones exteriores inciertas en las negociaciones cuando existe información incompleta acerca de su existencia. Examino una guerra de desgaste donde los jugadores disfrutan de información privada acerca de sus posibilidades de dejar la mesa de negociación para tomar una opción exterior. Hay dos tipos de jugadores: los tipos débiles, que no tienen opciones exteriores y prefieren conceder que salirse del juego, y los tipos fuertes que tienen opciones exteriores tales que prefieren salirse que conceder. El principal mensaje que surge del análisis de este juego es que la incertidumbre acerca de la posibilidad de que el oponente se vaya, mejora la eficiencia porque incrementa la probabilidad de concesión. Más precisamente, si la probabilidad de que el oponente sea fuerte es relativamente alta, la negociación acaba con una concesión segura. En el otro extremo, si la probabilidad de que el oponente sea débil es alta, los tipos fuertes dejarán en algún momento el juego con probabilidad igual a 1, dejando a los débiles jugando, desde ese momente en adelante el ineficiente equilibrio de la guerra de desgaste clásica. Incluso en este caso, la probabilidad de concesión a lo largo de la fase de incertidumbre del juego se incrementa.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Ciències Socials; Conventional arbitration; Final-offer arbitration; Negociación; Opciones exteriores

Law of money, value and payment - Eitelberg, Eduard (University of Durban-Westville, 2002)
Societies have, since time immemorial, traded real goods and services for expectations of goods and services in some future. These expectations have been associated with tangible and, lately, intangible property - which is generally called money. From the crude quantity theory of money, the purchasing power of a monetary unit is given as 1/ P = T/(Mv). P is the price of the traded goods and services T, M is the total money supply and its turnover rate is v. The total money supply M is dominated by bank credit. In the South African law (and elsewhere) the judicial recognition given to bank credit (1) as money seems to have happened as an unintended side-effect to accepting cheques as delivery vehicles in a cash transfer without any tangible money moving from the transferor to the transferee. In payment of money, the law of property and the law of contract overlap and become inseparable. Both the English and South African laws define payment as performance of a preceding duty. The Supreme Court of Appeal, in the Vereins- und Westbank case seems to have declared an abstract transfer of ownership of money to be payment even though no preceding duty to pay was found. The profit of a financial investment is called interest and is calculated from a simple or compound interest formula. Despite medieval legal, theological and ethical objections, neither is illegal in the South African positive law. The last remnant of the medieval protection of a guilty debtor (often the ruler) at the expense of an innocent creditor is the in duplum rule. This is particularly obnoxious during modern rampant inflation that was unknown and could not be predicted when only metallistic money was in use. The influence of the in duplum rule is being limited by recent restrictive judgments in South Africa and in Zimbabwe. In South Africa, the Government has a constitutional duty to ensure that its subjects are not deprived of property. Specifically, the Constitution prescribes in Section 224(1) that the South African Reserve Bank must 'protect the value of the currency'. It is shown that the recent Reserve Bank policies, unless urgently modified, are in conflict with the publicly promised inflation rate of no greater than 6%. The exchange rates depend fundamentally on the price levels of the traded or tradable goods and services in the respective economies. This leads to the concept of purchasing power parity, which is most accurately reflected in the relationship between interest rates in different states and their relative foreign exchange depreciation rates. It is submitted that the South African Exchange Control Regulations have outlived their usefulness (if ever they had any) and are unconstitutional - at least in so far as they interfere with the South African Reserve Bank's obligation to pursue its primary object 'independently and without fear'. In the main, the South African Courts have applied restrictive interpretation to the Exchange Control Regulations and they have justifiably ignored the public international law obligation of the Republic to recognise the Exchange Control Regulations of fellow IMF members extraterritorially. (1) To money related claims on banks - see the body of the thesis for the two-creditor-two-debtor legal aspects in the 'bank credit'.

Community competence to control mergers : the jurisdictional divide - Burnley, Richard (European University Institute, 2002)
Keywords: Antitrust law; European Union countries; Unfair Competition

Globalization and the limits of National merger control laws: gaps in global governance and the need for an international merger control regime - Wilson, Joseph (McGill University, 2002)
From an economic perspective, globalization is dismantling national barriers to entry and is transforming domestic markets into a global market. To meet the challenges posed by the integration of markets, corporations are joining forces with their former competitors to expand their presence in the global market. Rapid growth in transnational mergers to create global corporations is one of the key features of globalization. As multinational corporations are uniting, so should antitrust agencies that regulate them. Antitrust agencies around the world are realizing that the consumers whom they are mandated to protect are being adversely affected by decisions made beyond their national borders. By using the "effects" test, countries bring within their jurisdiction review of any merger or acquisition involving foreign companies with significant revenue or assets within their jurisdiction. The proliferation of merger control laws, in the absence of a mechanism to coordinate the transnational merger review, places an unnecessary burden on merging parties, and runs the risk of divergent outcomes, which at times cause friction among nation-states. Both to alleviate unnecessary burdens imposed on corporations and to reduce inefficiencies produced by the disparate review of a single transnational merger by several countries, this thesis proposes an International Merger Control Regime integrated into the WTO. The proposal focuses on ways to operationalize a "Lead Jurisdiction" model of oversight rather than on the creation of a new supranational decision-making agency. WTO dispute settlement and arbitration would be used to resolve conflicts arising out of the inability of a Lead Jurisdiction to arrive at an outcome satisfactory to other significantly affected jurisdictions.
Identifier: https://escholarship.mcgill.ca/concern/theses/2z10wr888
Keywords: International merger control; Merger; Merger control

Procedural detachment in international commercial arbitration : the law applicable to arbitral procedure - Petrochilos, Georgios (University of Oxford, 2000)
This thesis seeks to ascertain the rules of private international law determining the procedural law of international commercial arbitral proceedings. In an Introduction, the author outlines the fundamental notions, introduces the topic and the major doctrines and issues, and sets out his methodology and structure of the work. The thesis examine first, as a preliminary issue, the considerations influencing the assumption of jurisdiction over arbitral proceedings. Chapter 1 discusses the various theories on the lex arbitri (the law supplying the general legal framework of an arbitration) as relevant to the procedural law, and concludes that they are deductive and therefore unable to satisfactorily to determine the applicable procedural law. Chapter 2 analyses major national laws as case-studies of the technique and scope of application of international arbitration law, and suggests a model of legislative and court jurisdiction based on the legal concept of 'seat of the arbitration' and on considerations based on the most appropriate court to control an arbitration. Chapter 3 discusses the obligations of the state of the seat under the European Convention on Human Rights and confirms the findings in Chapter 2. In a second part, the thesis elaborates on the title and extent of permissible municipal law interference. Chapter 4 tests the validity of the propositions derived from Chapters 2 and 3 against arbitral practice and concludes that seldom will arbitrators derogate from the law of the seat. Chapter 5 examines the particular case of arbitrations with states and similar entities. The third part discusses the relevance of compliance with the law of the seat at the stage of enforcement of an award. Chapter 6 deals with the technical issue of whether annulment at the place of making precludes enforcement in other fora. That chapter gives the opportunity to discuss models of separation of international jurisdiction and co-operation between different jurisdictions from a practical perspective. It thus serves as a convenient introduction to Chapter 7, which discusses the more abstract question of the nexus required between an arbitral award and the municipal law of the state of rendition in order for the award to enter, in limine, the scope of application of the international instruments in the field. The thesis ends with Conclusions in the form of model provisions for municipal law and arbitration rules.
https://ora.ox.ac.uk/objects/uuid:41c82c4d-d708-4cfe-b853-d50e41ea0773
Keywords: Arbitrage; Arbitragem; Arbitration; International commercial arbitration; Procédure arbitrale